Overcoming neoliberal globalization: social-ecological transformation from a Polanyian perspective and beyond - Brand, Ulrich; Görg, Christoph; Wissen, Markus (Globalizations, 2020)
The ecological crisis has intensified in many respects. Prominent proposals to deal with the crisis are discussed under the header 'sustainability transformations' or even 'Great Transformation'. We argue that most contributions suffer from a narrow analytical approach to transformation ignoring the largely unsustainable dynamics of global capitalism and the power relations involved in it. Thus, a 'new critical orthodoxy' of knowledge about transformation is emerging which runs the danger to contribute to a spatially and socially highly uneven green capitalism. This article claims that the current debate on social-ecological transformation can be enriched by a Polanyian understanding but also based on regulation theory. We distinguish between three types of transformation: incremental adaptation of the current institutional systems, institutional change in favour of a new 'green' phase of capitalism, and a post-capitalist great transformation that implies a profound structural change of the mode of production and living.
Political Science; Economics
Keywords: POLANYI; Karl; 1886-1964; capitalism; crises; debates & debating; ecological crisis; globalization; imperial mode of living; nature as fictitious commodity; regulation theory; social ecology; social-ecological transformation; sustainability

Tim Rogan. The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. - Dale, Gareth (The American Historical Review, 2019)
When the capitalist system hits the rocks and neoclassical economics loses its aura, alternative traditions invite attention. Tim Rogan’s The Moral Economists i
History
Keywords: The Moral Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson; and the Critique of Capitalism (book); book review; capitalism

The political economy of family policy expansion: Fostering neoliberal capitalism or promoting gender equality supporting social reproduction? - Ferragina, Emanuele (Review of International Political Economy, 2019)
This article presents a new theoretical and empirical approach to understand family policy expansion in relation to the political economy of welfare state retrenchment and social reproduction in 23 OECD countries. From a Polanyian perspective, this expansion can be interpreted as a movement toward commodification and liberalization, and a countermovement of gender liberation. The first movement seems to characterize family policy expansion as a tool to foster neoliberal capitalism and the advent of a Schumpeterian Workfare State, conspiring with welfare state retrenchment to encourage employment within an environment of growing precarization. The second movement appears to assuage the social reproduction crisis. This countermovement seems to act as a cushion to soften the shift from a male income earner toward a dual earner model, supporting working parents in meeting escalating childare costs. Looking at the expansion of childcare spending and the retrenchment of minimum income guarantees for couples with children, an empirical illustration of this concomitant 'double movement' reveals that the first holds sway over the second in most countries. Furthermore, household income and maternal levels of education impact on childcare usage, magnifying the negative distributional consequences of cutting minimum income guarantees in favor of childcare.
Political Science
Keywords: Schumpeterian workfare state; childcare; commodification; countermovement; family policy; gender equality; neoliberalism; social reproduction; welfare state retrenchment

On Misunderstanding the Second Contradiction Thesis - Rudy, Alan P. (Capitalism, Nature, Socialism, 2019)
James O'Connor's "second contradiction" thesis is widely misunderstood as an ecological crisis theory. Most of the criticisms of the theory derive from this misreading, including those which ignore relations between ecological, personal and communal conditions and those which see the "first" and "second" contradictions as materially distinct. O'Connor himself is partially responsible for the misreading, however. His writings tended to put the ecological out front, and his use of Polanyi's romantic idea of "fictitious commodities" reinforced that tendency. The defense developed here rejects ecologistic readings, ties the second contradiction thesis backwards and forwards in O'Connor's work, unpacks the meaning of "conditions" for Marx and O'Connor, and suggests that Neil Smith's argument that capitalist second natural relations generate qualitatively new processes by which nature, human nature and space are produced would have served O'Connor better.
Sociology
Keywords: MARX; Karl; 1818-1883; O'CONNOR; James; POLANYI; Karl; 1886-1964; SMITH; Neil; conditions of production; contradiction; ecological Marxism; ecologism; environmental marxism; human behavior; second contradiction

SEE Beyond Substantive Economics: Avoiding False Dichotomies - Spash, Clive L. (Ecological Economics, 2019)
The proposal has been put forward that ecological economics seek to become substantive economics (Gerber and Scheidel 2018). This raises important issues about the content and direction of ecological economics. The division of economics into either substantive or formal derives from the work of Karl Polanyi. In developing his ideas Polanyi employed a definition from Menger and combined this with Tönnies theory of historical evolution. In this paper I explore why the resulting substantive vs. formal dichotomy is problematic. In particular the article exposes the way in which trying to impose this dichotomy on history of economic thought and epistemology leads to further false dichotomies. Besides Polanyi, the positions of other important thinkers informing social ecological economics (SEE) are discussed including Neurath, Kapp and Georgescu-Roegen. The aim is to clarify the future direction of ecological economics and the role in that future of ideas raised under the topic of substantive economics.
Economics; Political Science
Keywords: economic anthropology; epistemology; formal economics; history of thought; social ecological economics; substantive economics

Karl Polanyi, the "always-embedded market economy," and the re-writing of The Great Transformation - Lacher, Hannes (Theory & Society, 2019)
This article seeks to subject Fred Block and Margaret Somers' influential reconstruction of Karl Polanyi's The Great Transformation to a systematic review. I show that Block & Somers's central claim—that Polanyi's thinking underwent a "theoretical shift" as he wrote his seminal book—is not supported by archival evidence. I demonstrate that all the narrative keys that Block & Somers advance to lend plausibility to their discovery of a "theory of the always-embedded market economy" in The Great Transformation, wither under critical probing. While this article does not advance a comprehensive alternative reconstruction of Polanyi's main work, the essential continuities it uncovers in his social thought suggest that Polanyi's book is best understood as the culmination of his long-standing efforts to rebuild a radically transformative socialism on non-Marxist foundations. The recognition that Polanyi's political purposes extend far beyond regulated capitalism or social-democracy, I conclude, makes it possible—and indeed necessary—to read The Great Transformation as an internally coherent work of social theory.
Political Science; Sociology
Keywords: BLOCK; Fred L.; SOMERS; Margaret R.; capitalism and socialism; critical institutionalism; economic sociology; fascism; neo-Polanyian social theory; political economy

De-privatisation and remunicipalisation of urban services through the pendulum swing: Evidence from Germany - Weber, Gabriel; Cabras, Ignazio; Frahm, Lars-Gunnar (Journal of Cleaner Production, 2019)
This paper explores and examines the distribution of environmental conflicts in Germany between 1985 and 2015, analysing the main causes for environmental conflicts related to privatisation and de-privatisation processes of urban services in 80 German cities. Using information collected via means of a Delphi Method based on focus groups with experts, we identify 90 cases of large-scale privatisation initiatives involving urban services occurred in different fields within the period considered. In 38 cases, privatisation was reversed due to initiatives undertaken by environmental justice organisations and other local grassroots groups promoting de-privatisation and re-municipalisation. In another 30 cases, privatisation was prevented as a result of these initiatives. Findings from our analysis indicate that de-privatisation initiatives and potential conflicts related to them are frequently driven by grassroots organisations promoting the provision of commons-based urban services. Our findings also suggest that privatising services in the energy, water supply and waste management sectors is likely to negatively affect the quality of service supply and increasing prices for urban residents. Image 1 • This paper explores ecological conflicts in Germany by using comparative analysis, statistics, and political ecology. • It investigates the main causes for conflicts related to privatisation and de-privatisation of urban services. • With a Delphi Method and focus groups with experts, we identify 90 cases of large-scale privatisation. • 38 initiatives of de-privatisation are identified, many driven by grassroots organizations reclaiming the concept of commons. • De-privatisation initiatives indicate a pendulum swing towards more socially controlled production.
Business; Management Studies
Keywords: Delphi method; Germany; Polanyi's pendulum; city dwellers; environmental justice; pendulums; political ecology; privatisation and de-privatisation; remunicipalisation; services and utilities; sustainable cities; urban areas; water supply management

Global Cities as Market Civilisation - Curtis, Simon (Global Society: Journal of Interdisciplinary International Relations, 2019)
Building upon interdisciplinary efforts to understand the origins, logic and significance of global cities, this article argues that global cities should be seen as a critical component and outcome of a political project to generate a global market society. Global cities should be seen as the successful implementation of free-market political philosophy, constructed and defended by a particular historical configuration of international society. The historical transformation of urban form signalled by the "global city" concept is tightly bound to the neoliberal restructuring of the world economy in the 1970s, underpinned by US hegemonic power. The first part of this article argues that the distinctive historical origin of global cities has shaped their current trajectories and draws the horizon of their future prospects. Having established the connection between liberal world order and global cities, the second part of the article argues that the contemporary form of the global city is under threat from two sources. The first threat is internal to the global city form itself. Global cities have internalised the contradictory forces of market liberalism. They have registered astonishing economic growth over the last four decades, and generated vast material and intellectual resources. But, at the same time, they have become deeply divided and polarised in ways that threaten the urban fabric. The second source of threat comes from the possible weakening or collapse of liberal world order, with the accelerating decline of US hegemony. Drawing on aspects of Karl Polanyi's analysis of the nineteenth-century "great transformation", the article argues that a number of future trajectories for the global city can be identified in the contemporary moment.
Political Science; International Relations
Keywords: global city; market liberalism

Networked but Commodified: The (Dis)Embeddedness of Digital Labour in the Gig Economy - Wood, Alex J; Graham, Mark; Lehdonvirta, Vili; Hjorth, Isis (Sociology, 2019)
This article investigates the (dis)embeddedness of digital labour within the remote gig economy. We use interview and survey data to highlight how platform workers in Southeast Asia and Sub-Saharan Africa are normatively disembedded from social protections through a process of commodification. Normative disembeddedness leaves workers exposed to the vagaries of the external labour market due to an absence of labour regulations and rights. It also endangers social reproduction by limiting access to healthcare and requiring workers to engage in significant unpaid 'work-for-labour'. However, we show that these workers are also simultaneously embedded within interpersonal networks of trust, which enable the work to be completed despite the low-trust nature of the gig economy. In bringing together the concepts of normative and network embeddedness, we reconnect the two sides of Polanyi's thinking and demonstrate the value of an integrated understanding of Polanyi's approach to embeddedness for understanding contemporary economic transformations.
Sociology
Keywords: commodification; digital labour; disembeddedness; embeddedness; freelancing; gig economy; outsourcing

Contesting household debt in Croatia: the double movement of financialization and the fetishism of money in Eastern European peripheries - Mikuš, Marek (Dialectical Anthropology, 2019)
Croatia has experienced a marked boom in household debt in the 2000s. Much of this lending took high-risk and predatory forms that transferred significant risks to debtors, which in turn became the target of contestation by debt activists. This paper uses the Polanyian idea of "double movement" to show how the Croatian debt contestations responded to the distinctively peripheral form of financialization in Eastern Europe, characterized by unequal geoeconomic relationships and an intensified expropriation of debtors. This framework further highlights the importance of money in contemporary credit/debt relationships and their contestation, which has so far received insufficient attention in relevant anthropological scholarship. Instead of the currently fashionable credit theories of money, the paper uses the Marxian concept of the fetishism of money to unpack the roles of money in these processes. The analysis of discourses and practices of two groups of debtors and activists reveals how they used nationalist ideological frameworks and institutional channels such as litigation, again largely ignored by existing anthropological literature, to challenge the particular inequalities of peripheral financialization and the expropriation of debtors through the lenders' predatory manipulations of the money fetish.
Anthropology
Keywords: Croatia; Eastern Europe; consumer credit; contestation; debtor & creditor; financialization; household debt; money

Islam, entrepreneurship, and embeddedness - Tok, M. Evren; Kaminski, Joseph Jon (Thunderbird International Business Review, 2019)
This study centers on the premise that entrepreneurship is an embedded process. Although "the entrepreneur" is inherently an "individual," entrepreneurship can never be fully disembedded from the more general social settings within which any business venture is situated. An Islamic‐based economic discursive framework should be cognizant of the different forms of sociality, spatiality, and community as well as the various norms, codes, and symbols that define society more generally. The work of Karl Polanyi on embeddedness is engaged and juxtaposed with Islam's understanding of the ideal mode of economic discursive practices. Islamic economic models and Polanyi are both critical of the corrosive effects of unbridled capitalism and individualism that ultimately lead to reification and exploitation. The conclusion recommends more small‐N case studies by researchers and entrepreneurial educational materials that emphasize the importance of networks and local embeddedness.
Business; Islamic Studies
Keywords: Islam; POLANYI; Karl; 1886-1964; discursive practices; economic models; entrepreneurship; teacher researchers

Problematizing capitalism(s): Big difference? - Peck, Jamie (Environment & Planning A, 2019)
In the article, the author examines the social science theories of Fred Block, particularly on such topics as capitalism, finance, markets, and government. Other topics include Block's opinions on Polanyian socioeconomics, his thoughts on economic diversity and capitalist transformation, as well as the universalist model of capitalism as free-market globalism.
Geography
Keywords: BLOCK; Fred L.; capitalism; finance; free enterprise; markets; social sciences; the state

Economic Liberalism and the State: Dismantling the Myth of Naïve Laissez-Faire - Stahl, Rune Møller (New Political Economy, 2019)
The article offers a critique of the prevailing understanding of the relationship between neoliberalism and classic nineteenth-century liberalism in contemporary international political economy (IPE) and offers a redefinition inspired by Polanyi and Gramsci. Within critical IPE studies, a consensus has emerged that neoliberalism cannot be reduced to a simple attempt to roll back the economy and let loose free-market forces. However, this insight relies on contrasting neoliberalism with a classic liberalism, that is, a simple attempt to implement just this naïve laissez-faire ideology. In contrast, this article argues that nineteenth-century liberalism is also characterised by an active use of state and legislative power. Through a historical study of two cases from nineteenth-century Britain, Poor Law reform and the Gold Standard, the paper will argue that state action played a central role even during the heyday of laissez-faire liberalism. With a starting point in Polanyi's dictum that 'laissez-faire was planned', this reinvestigation will point towards a need to develop a more nuanced understanding of the distinctions between economic theory, ideology, and practical policy, as well as pointing towards a general reinterpretation of the role of the state in liberal economic ideology.
Political Science
Keywords: classical liberalism; critical political economy; economic governance; history of economic thought; international political economy; liberalism; liberty; neoconservatism; neoliberalism; ordoliberalism; state theory

Knowledge and social freedom - Rief, Silvia (Journal of Cultural Economy, 2019)
Sociology
Keywords: Karl Polanyi's Vision of a Socialist Transformation (Book); book review; commentary; freedom

Ethnoracial Populism: An Alternative to Neoliberal Globalization? - Antonio, Robert J. (Social Epistemology, 2019)
Worldwide emergence of strongmen leaderships and eroded or failed democracies suggest that the era of unchallenged neoliberal hegemony may be winding down and that alternatives are rising. The presidential election of Donald Trump has inspired rightwing populists at home and abroad. This paper will analyze the Trumpist fusion of authoritarian ethnoracial nationalism with neoliberal adventure capitalism and the broader matter of how neoliberal de-democratization opens way for right-wing populism and illiberal capitalism. The topics will be explored in part through discussions of earlier theories of Friedrich Hayek, Carl Schmitt, John Dewey, and Karl Polanyi that have been revived and deployed in the current debates over neoliberalism, populism, and democracy.
Sociology
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; Presidential elections; SCHMITT; Carl; 1888-1985; Trumpism; de-democratization; ethnoracial populism; globalization; nationalism; neoliberalism; populism; right-wing populism

Karl Polanyi and the Law of Market Society - Frerichs, Sabine (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi started his career as a doctor of law and practiced law for a while; but he did not become a legal scholar. As an economic historian, anthropologist, or sociologist, he was concerned with the relation of economy and society. But even though law is an important factor in mediating this relationship, Polanyi gave little attention to the law as such. As part of an endeavour to advance a ‘Polanyian’ economic sociology of law, this article develops the ‘law of market society’ as an analytical category. For this purpose, three argumentative strategies are combined. First, the article draws on The Great Transformation to reconstruct the role of law in the processes of commodification and decommodification. Second, it turns to Marxist scholarship to explore the conceptual link between law and economics and to ponder to what extent law itself can become a commodity. Third, it links Polanyi’s approach with American institutionalism, and Commons’ work in particular, to show how the evolution of the ‘law of market society’ can also be understood as a collective enterprise which continuously evolves. It is argued that these perspectives complement each other and help to bring the law back in where it is missing.
Sociology; Law
Keywords: law of market society; sociology of law

Historicizing Karl Polanyi - Gräser, Marcus (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi’s book The Great Transformation has found great resonance in the social sciences in recent years—especially in sociology, political economy and political science. The interest in Polanyi among historians is still modest in comparison. There are not enough studies that treat Polanyi as an object of intellectual history/history of science, nor has Polanyi been used hitherto as an idea-giver for the growing field of global history—despite the fact that his book can be understood as global history. It is high time to “historicize” Polanyi in several ways.
Sociology
Keywords: history of science; intellectual history

Commodity Studies with Polanyi: Disembedding and Re-Embedding Labour and Land in Contemporary Capitalism - Langthaler, Ernst; Schüßler, Elke (Österreichische Zeitschrift für Soziologie, 2019)
This article aims to inform current debates in the field of transnational commodity studies through a Polanyian lens. Polanyi reminds us of the need to pay attention to the “double movements” in which fictitious commodities are disembedded from and re-embedded in society. We focus on two fictitious commodities, labour and land, which are conventionally treated as mere inputs for the production of genuine commodities. Through investigating the disembedding and re-embedding of labour in the garment industry, and of land in the agro-food sector since the 1970s, we gain insights regarding the commodification of fictitious commodities in the context of transnational commodity chains. The developments in both fields imply not just simple double movements, but complex entanglements of disembedding and re-embedding dynamics at the interface of state, business and civil society actors.
Sociology
Keywords: commodity studies; double movement

The Rise of Populist Movements in Europe: A Response to European Ordoliberalism? - Cayla, David (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
This article aims to explain the contemporary emergence of populism in the European Union. According to Polanyi's double movement framework, the emergence of these political forces can be understood as the result of protective responses from societies weakened by difficult market adjustments. Since the Single Act treaty (1986), the European economy took a path that intended to create a supranational self-adjusting markets economy based on the ordoliberal philosophy. However, by detaching the economic sphere from the reach of politics, the European Single Market has injured some important social institutions. The rise and the diversity of populisms in the European Union can therefore be explained by an attempt to preserve some national institutions that were diversely impacted by the market forces.
Economics; Political Science
Keywords: European Single Market; free enterprise; institutional economics; international relations; neoliberalism; ordoliberalism; populism; social functions; social institutions

Doing justice to Karl Polanyi - Devine, Pat (Capitalism, Nature, Socialism, 2019)
Political Science; Sociology
Keywords: POLANYI; Karl; 1886-1964; book review; economic activity; economics; social control; social forces

State Capitalism Revisited: A Review of Emergent Forms and Developments - Dolfsma, Wilfred; Grosman, Anna (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Even when the neoliberal ideology of the free market was more dominant than it now is, the state was involved in economic activities that could be undertaken by private firms. State capitalism takes increasingly diverse forms, including beyond direct, partial or even indirect ownership. This paper briefly reviews some of these forms without claiming to be exhaustive as the shape state capitalism takes differs widely across the institutionalized contexts of countries. We assess state capitalism using Polanyi's double movement framework and argue that this framework needs adaptation to novel forms of state capitalism that include, e.g., state-owned multinationals and sovereign wealth funds.
Business; Management Studies
Keywords: SOMNCs; capitalism; double movement; economic development; economic systems; international relations; investments; profit; sovereign wealth funds; state capitalism; state-owned enterprises

Remittances and Households in the Age of Neoliberal Uncertainty - Khanal, Kalpana; Todorova, Zdravka (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
International migration and remittance flows have been reframed as catalysts for poverty reduction and development through marketization. Growth, measurement, and promotion of global remittances have emerged against the backdrop of neoliberal structural adjustment programs and financialization. Those processes have paralleled the emergence of the transnational household as a global institution. The article suggests that transnational households characterize a new stage of neoliberal capitalist development. The article revisits Karl Polanyi's The Great Transformation and discusses how active governance and neoliberal discourse regulate and frame labor and remittances as "fictitious commodities." Further, it is argued that transnational households take active roles in Polanyi's "double movement," by providing social protection amidst narrow public responsibility for provisioning. The article identifies this as a new element of "the great transformation," and referring to J. K. Galbraith, as a new age of neoliberal uncertainty.
Economics
Keywords: double movement; economic development; fictitious commodities; income; neoconservatism; neoliberalism; remittances; transnational households

The Double Movement Ten Years After the Fall of Lehman Brothers - Vidal, Gregorio; Marshall, Wesley C. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Ten years after the collapse of Lehman Brothers and the sharpest moments of panic within the global—and particularly the United States banking system—a somewhat strange dynamic has appeared. While the principal agents behind the crisis have collapsed their own institutions, the markets that they dominated, and even provoked what has been called the third crisis of economic theory, their political power has not waned. This theme has been well addressed by some academics such as Philip Mirowski (2013), while it has flummoxed others. In this article, we will argue that Karl Polanyi's theory of the "double movement" offers a coherent framework that is able to account for the history of the last ten years. Polanyi argues that different groups and members of society seek protection from the market, and that this search for protection has been the driving force between historical change. Polanyi does not ignore class; rather, he argues that different social classes can protect themselves in more or less effective ways. We argue that during the last ten years, the interests of globalized financial capital have been able to protect themselves with utmost effectiveness, while all other classes have been trammeled, often not even recognizing how or why actions are taken against the general interest.
Economics; History
Keywords: Lehman Brothers; capital market; double movement; financial crisis; financial markets; securities; stock exchanges; stocks (finance)

Populism in Times of Attempted Unity of Heterogeneous Social Demands - Wagner, Paulus (International Spectator, 2019)
N/A
Keywords: HOLMES; Christopher; POLANYI; Karl; 1886-1964; Polanyi in Times of Populism: Vision & Contradiction in the History of Economic Ideas (Book); book review; economic policy; nonfiction; populism

The Last Gasp of Neoliberalism - Watkins, John P.; Seidelman, James E. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
The ideas of both Thorstein Veblen and Karl Polanyi shed light on understanding the last gasp of neoliberalism. The last gasp refers to Donald Trump's abandonment of free trade, long considered a cornerstone of the neoliberal agenda, and his overt attacks on democratic institutions. In Trump, neoliberalism's attempt to overcome the gridlock of liberal democracy has revealed its fascist leanings. Both Polanyi and Veblen warned about the trend towards fascism. Trump was elected, in part, by filling the void left by the factioning of neoliberalism, in part by the injustice felt by people in rural areas, those with stagnant incomes, white males, and others. Trump has transcended the neoliberal agenda, approaching market relations from the point-of-view of the fight. The emergence of a predatory culture, in both the domestic and international realms, resembles the culture outlined in Veblen's The Theory of Business Enterprise. Trump's actions reveal the need to extend Polanyi's idea of social protection given the negative effects of modern technology and Trump's efforts to dismantle or reduce some regulatory agencies. Changing demographics and the adverse reaction to Trump's fascist leanings may yet see the emergence of a new progressive era, suggesting, at least, that Trump represents the last gasp of neoliberalism.
Economics
Keywords: POLANYI; Karl; 1886-1964; VEBLEN; Thorstein; 1857-1929; capitalism; democracy; double movement; fascism; international relations; neoliberalism

Financialization, Class Interests, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Many observers expected a stronger countermovement against neoliberalism following the Great Recession. This article argues that such a protective response failed to materialize because the financialization process has aligned the preferences of labor and rentier classes. The result has been weaker support in democracies for expansionary monetary and fiscal policies during the early stages of recessions, which further lowers aggregate spending by increasing uncertainty. Thus, reversing the culture of financialization may be a necessary condition for preventing and responding to financial crises.
Business; Economics
Keywords: Polanyi; Karl; 1886-1964; business development; double movement; economic development; economic policy; financial crises; financialization; macroeconomic policy; monetary policy

Absolute Capitalism - Foster, John Bellamy (Monthly Review: An Independent Socialist Magazine, 2019)
The article deals with the emergence of absolute capitalism due to the efforts of states to promote social reproduction. It explores the association between absolute capitalism and neoliberalism, a ruling-class political-ideological project that is connected to the rise of monopoly-finance capital. Some 20th century thinkers had their own ideas about absolute capitalism, including Karl Polanyi and John Maynard Keynes.
Sociology
Keywords: KEYNES; John Maynard; 1883-1946; POLANYI; Karl; 1886-1964; capitalism; finance capitalism; neoliberalism; social reproduction

The New Alchemy: Economic liberalism, neoliberalism, and Thomas Pynchon's Against the Day - Carswell, Sean (Textual Practice, 2019)
This article utilises Karl Polanyi's landmark 1944 text The Great Transformation to explicate economic liberalism as it is represented in Thomas Pynchon's Against the Day. Polanyi argues that a fundamental flaw of economic liberalism is its treatment of labour and land as commodities. This commodification leads to economic and ecological disasters. Pynchon demonstrates these disasters throughout his encyclopaedic novel. Further, using Pynchon's metaphor of bilocation – literally being in two places at the same time – this article 'bilocates' the economic liberalism represented in the novel with contemporary neoliberalism, specifically as neoliberalism is characterised by David Harvey and Wendy Brown. Ultimately, this exploration leads to a discussion of freedom within a neoliberal society, particularly as it is envisioned in Pynchon's novel.
English; Literary Studies
Keywords: Against the Day (book); BROWN; Wendy; HARVEY; David; PYNCHON; Thomas; 1937-; economic liberalism; economics; fictitious commodities; globalization; neoliberalism

Can Karl Polanyi Explain the Anthropocene? The Commodification of Nature and the Great Acceleration - Steinberg, Ted (Geographical Review, 2019)
The most important historical work on the Anthropocene to date is J. R. McNeill and Peter Engelke’s The Great Acceleration: An Environmental History of the Anthropocene since 1945 (2016). The authors argue that the Anthropocene began in 1945, not in the eighteenth century, as some scientists have proposed. They single out unintentional “human actions” as the driving force behind the significant changes in biogeochemical processes unfolding since the middle of the twentieth century (McNeill and Engelke 2016, 4, 208). The main title of their book mimics a phrase first used at a 2005 conference on the future of the planet and refers to the escalating human threats to the so-called Earth System. The title was meant to parallel Karl Polanyi’s The Great Transformation: The Political and Economic Origins of Our Time (1944). Born in 1886 in Hungary, Polanyi became one of the world’s greatest economic historians. In an endnote to their book, McNeill and Engelke explain that Polanyi saw the “market economy” as a recent invention that “must be understood as embedded in social traditions, customs, and habits of the mind.” Likewise, they continue, human impacts on global ecology “are embedded in societies and their traditions” (McNeill and Engelke 2016, 213).
Geography
Keywords: ENGELKE; Peter; Great Acceleration: An Environmental History of the Anthropocene Since 1945; The (Book); MCNEILL; J. R.; anthropocene epoch; capitalism; globalization; nonfiction; urban development

Neoliberal Legality as Dual Process: Embeddedness, Courts and Crime Prevention in the United States - Campeau, Holly; Levi, Ron (British Journal of Criminology, 2019)
This article advances research on 'neoliberal legality' to focus on the role of courts in response to neoliberal crime prevention approaches. Drawing on Karl Polanyi's analysis of embeddedness in market capitalism, along with criminological research on the penal state, we analyse three case studies reflecting central crime prevention approaches of the neoliberal era in the United States. We find that neoliberal legality is more complex than simply legitimating or resisting neoliberal policies. We highlight how courts did both at once—they moderated the harshest edges of neoliberal policies through alternative symbolic frames, yet in so doing also legitimated the core of neoliberal crime prevention efforts. We argue that neoliberal legality operates through this dual process, in which the basic thrust of neoliberalism is legitimated by also having policies moderated, recast and embedded within other social and juridical expectations.
Criminology; Sociolegal Studies
Keywords: POLANYI; Karl; 1886-1964; United States; capitalism; courts; crime prevention; embeddedness (socioeconomic theory); law; neoliberal legality; neoliberalism; penal state

The future of capitalism: Trends, scenarios and prospects for the future - Delanty, Gerard (Journal of Classical Sociology, 2019)
The article provides a framework for thinking about how the question of the future of capitalism might be addressed. One of the problems resides in the very definition of capitalism and of what its defining features consist of and whether we should be talking about 'capitalist society' or the 'capitalist economy' or some kind of post-capitalist condition. Following Polanyi, Castoriadis and Habermas, it is argued that capitalism and democracy together constitute the defining dynamics of modernity and that the resulting tensions will provide momentum for the main circuits of potential change. Five scenarios for looking at the future are discussed. These will form the main substance of the article: varieties of capitalism, systemic crises of capitalism, catastrophic collapse, low growth capitalism and post-capitalism. In conclusion, it is argued that there are various possibilities that can be understood in terms of transitions, breakdown or transformation, but a likely future trend will be less the end of capitalism than the harnessing of 'super-capitalism' and that there are limits to the accumulation of capital.
Sociology
Keywords: MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; SCHUMPETER; Joseph Alois; 1883-1950; WEBER; Max; 1864-1920; capital; capitalism; democracy; future of capitalism; modernity; neoliberalism; varieties of capitalism

Climate Change and the Polanyian Counter-movement: Carbon Markets or Degrowth? - Stuart, Diana; Gunderson, Ryan; Petersen, Brian (New Political Economy, 2019)
In the midst of a wave of market expansion, carbon markets have been proposed as the best way to address global climate change. While some argue that carbon markets represent a modern example of a Polanyian counter-movement to the environmental crisis, we adopt a structural interpretation of Polanyi to refute this claim. Carbon markets represent a further expansion of markets that fails to address the underlying contradictions related to the commodification of nature. In addition, they increase risks to society and the domination of economic elites. While carbon markets further subject social and ecological relations to market mechanisms, we examine degrowth as a possible response to climate change that prioritises social and environmental goals over economic growth. While degrowth continues to be dismissed as impractical or impossible, a growing number of scholars, scientists and activists argue it is the only way to address global climate change. In contrast to carbon markets, we argue degrowth could represent a genuine Polanyian counter-movement in response to climate change. In addition, degrowth could help all those disenfranchised by market fundamentalism by addressing the triple crises related to the commodification of land, labour and money.
Political Science; Sociology
Keywords: carbon markets; carbon offsetting; climate; climate change; degrowth; economic development; economic elites; emissions (air pollution); environment; environmental studies

Postneoliberalism as institutional recalibration: Reading Polanyi through Argentina’s soy boom - Berndt, Christian; Werner, Marion; Fernández, Víctor Ramiro (Environment and Planning A: Economy and Space, 2019)
While postneoliberalism is often interpreted as a societal reaction against the deleterious effects of marketization in Latin America, this paper develops a finer-grained Polanyian institutional analysis to gain better analytical purchase on the ambivalent outcomes of postneoliberal reforms. Drawing on recent insights in economic geography, and in dialogue with the Latin American structuralist tradition, we elaborate our framework through a case study of the Argentinian soy boom of the 2000s, identifying forms of market extension, redistribution, reciprocity and householding that facilitated this process. We argue for a multi-scalar approach that balances attention to national and extra-local dynamics shaping the combination of these forms, identified through the lens of the “fictitious commodities” of the soy boom: money (credit, currency and cross-border capital flows), land (in the agricultural heartland and frontier regions), labor (transformed and excluded in a “farming without farmers” model) and, we add, knowledge (biotech). Our analysis identifies internal tensions as well as overt resistance and “overflow” that ultimately led to the collapse of postneoliberal regulation of the soy complex, ushering in a wider, market-radical counter-movement. Refracting double-movement-type dynamics through the prism of heterodox institutional forms, we argue, allows for a better grasp of processes that underlie institutional recalibrations of progressive and regressive kinds.
Geography
Keywords: Argentina; Polanyi; institutions; marketization; post-neoliberalism; soy; uneven development

Who Plans Our Political Economy? A Solidarity Economy Vision for Democratic Political Economy Planning - Gilbert, Geoff (Harvard Unbound, 2019)
The Democratic Party's current left-wing resurgence shows that significant popular support exists for an expanded vision of fundamental rights for all people: rights to public health care and higher education; affordable housing; living-wage jobs; and a Green New Deal that transitions human society to ecological sustainability while also reducing inequality. But what are the best institutional means to provide this expanded vision of fundamental rights? This paper argues that we must stop expecting or hoping that highly centralized state and corporate institutions, which reserve rights to ownership and control for the few, will produce any results other than those that benefit the few. I argue that in order to provide an expanded vision of fundamental rights we must create a democratic political economy comprised of institutions that are themselves democratic and controlled by the people they are meant to serve. Guided by Karl Polanyi's insight that the fictitious commodification of labor, land, and money has made human society an accessory of the economic system, I propose a vision for creating, starting at the city level, democratic systems for controlling land, labor, and money. The vision–inspired by global movements including the Zapatistas in Mexico, the Movement of Landless Workers in Brazil, the Kurds in Rojava in Northern Syria, and the municipalist movement in Spain–calls for democracy in the workplace through worker cooperatives, local democratic ownership and control of land through land banks, community land trusts, and a land value sales tax, and democratic banking through public banks at the city level. By demonstrating the viability of democratic political economy institutions at the local level, organizers can amass resources to build toward broader systemic transformation.
Law
Keywords: fictitious commodification; fundamental rights; green new deal

Regulating labour dispatch in China: A cat-and-mouse game - Xiaojun, Feng (China Information, 2019)
This article suggests cautious optimism toward the prevailing Polanyian countermovement discourse by providing a timely and comprehensive examination of the enforcement of the labour dispatch regulation in China. Since the enactment of the regulation, some enterprises have narrowed the remuneration gap between agency workers and formal employees, while others have retained a large gap in overtime pay, bonuses, and welfare benefits between these two groups of workers. The regulation has reduced the number of agency workers, but has invoked the abuse of the more precarious 'outsourced' workers as well. The regulation has had little effect on limiting the use of agency labour to temporary, auxiliary, or substitute positions, raising the requirements of engaging in the labour dispatch business, or stabilizing the employment of agency workers. This article contributes to the extant literature on regulatory enforcement by examining the effects of non-standard employment regulation, highlighting the variance of labour law compliance among enterprises with different types of ownership, and demonstrating how China's ongoing transformation from a planned to a market economy since the 1980s and from high growth to a new normal since 2010 has fundamentally constrained the full implementation of its labour protection regulation.
Development Studies; Oriental Studies
Keywords: China; agency workers; countermovement; employment; labor market; labour dispatch; labour market; labour market regulation; law enforcement; new normal; outsourced workers; precarity

Changing Approaches to Development since 1950: Drawing on Polanyi - Stewart, Frances (History of Political Economy, 2018)
The article focuses on analysis of Karl Polanyi in the book "The Great Transformation" which explained the changes in Great Britain from eighteenth-century mercantilism to nineteenth-century free markets to the state-centered interventionism of the mid-twentieth century evident when he was writing. It mentions additional features needed for understanding the evolution of development thought and repeal of the Corn Laws in 1846, leading to free trade in agricultural products.
Development Studies; Political Science
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; economic development; free enterprise; free trade; mercantile system

Tensions in the Triangle: Monetary Plurality between Institutional Integration, Competition and Complementarity - Blanc, Jerome (Evolutionary and Institutional Economics Review, 2018)
This text aims at accounting for the plurality of money by emphasizing the delicate and evolving balance of the legal monetary systems and the continued existence of moneys that stay outside, though their continuation is subjected to chronic difficulties. It uses Polanyian concepts to take the wide and increasing variety of money into account and mobilizes criteria able to analyse the variety of links between them. It proposes a framework based on the representation of a "plurality triangle" with institutional integration, complementarity and competition, and it analyses the positioning of moneys in this framework as well as tensions that may generate shifts in their positioning.
Economics; Sociology
Keywords: current heterodox approaches: historical; evolutionary; institutional; monetary systems; money

Terrains of Civil and Uncivil Society in Post-Apartheid Durban - Bond, Patrick; Mottiar, Shauna (Urban Forum, 2018)
Post-apartheid Durban civil society politics reflects not only durable anti-racist activism, but primarily, Karl Polanyi's pendulum of a 'double movement' of the market against people and environment on the one hand, and social backlashes against neoliberalism on the other. The most important movements and campaigns of a socioeconomic nature can be summarised as follows: local resistance to economic disempowerment and lack of service delivery in various trade union strikes (1994-present), South Durban's fight against polluters and the port's expansion (1996-present), Chatsworth's water and electricity battles (1999-2012), the Treatment Action Campaign's access to AIDS medicines (early 2000s), Abahlali baseMjondolo's anti-eviction campaigns (2005-present), the defence of the Early Morning Market (2009-10), the Umlazi Occupy (2012), and sporadic community protests throughout. Resistance has occurred in urban poor neighbourhoods and townships and also penetrated the Durban inner city and university campuses. Durban activists' tactics range from militant protests to 'occupation' of space ranging from townships to the Speaker's Corner next to the Convention Centre, innovative door-to-door campaigning and court action. While the limits of single-issue and often assimilationist civil society politics are becoming obvious in one of the world's most unequal cities, there still has not yet been a successful 'united front' project to fuse interests, in part due to ideological division and the geographical diffusion of dissent.
Political Science
Keywords: Durban; HIV/AIDS; South Africa; Treatment Action Campaign; anti-racism; apartheid; civil society; demonstrations (collective behavior); double movement; environmental justice; protest; social movements; socioeconomics; trade unions

Polanyi, Hayek and embedded neoliberalism - Cahill, Damien (Globalizations, 2018)
Written originally on the seventieth anniversary of the publication of Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation, this article critically analyses how the ideas of Hayek and Polanyi have been deployed to understand neoliberalism. It argues that dominant scholarly interpretations tend to miss the significance of each thinker to an understanding of neoliberalism, as well as some of the key dynamics of neoliberal forms of capitalist regulation. Drawing upon the work of Polanyi, the article advances the concept of embedded neoliberalism. From the 1970s neoliberal regulations became deeply embedded in a series of institutions, class relations and ideological norms. This helps to explain both the durability of neoliberalism, and the onset of crisis in 2008. In this context, Hayek’s ideas are best understood as providing a malleable set of concepts underpinning neoliberal ideology, rather than the chief causal agent in the neoliberal transformation of states and economies.
Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalism; embeddedness; liberalism; neoliberalism

Between perfection and damnation: The emerging geography of markets - Cohen, Dan (Progress in Human Geography, 2018)
Economic geographers have recently taken up the study of markets after a long period of inattention. This growing literature has highlighted the diverse spaces, scales, and fields where markets are present, as well as the ways in which markets vary in form. However, the study of markets in economic geography still exists in tension between neoclassical and Marxist conceptions of markets as predictable and approaches like the social studies of economization/marketization which emphasize their contingency. This paper argues that work of Polyani and Gramsci can provide a way forward for the subfield through conceptualizing markets as sites of social struggle.
Geography
Keywords: capitalism; counterhegemony; earth scientists; economic geography; economic systems; geographers; human geography; marketization; markets; neoliberalism

‘Our world was made by nature’: constructions of spontaneous order - Dale, Gareth (Globalizations, 2018)
This article explores the concepts of spontaneity and spontaneous order, in particular their deployment by Friedrich Hayek and Karl Polanyi. Although in many respects these thinkers were poles apart, the article identifies a point of convergence. They both mobilize the concept of spontaneity in a manner that naturalizes a particular social process: for Hayek, the market economy, for Polanyi, society’s protective movement that arises in reaction against the market economy. To contextualize the uses of spontaneity by Hayek and Polanyi, I trace its evolution, with reference to Leibniz, Mandeville, and the thinkers of the Scottish Enlightenment. Having sketched the ways in which earlier thinkers understood spontaneity, I turn finally to Hayek and Polanyi. I argue that their invocations of spontaneity and spontaneous order contribute to a downplaying of relations of domination and exploitation. While Hayek sees the market system as the exemplar of spontaneous order, for Polanyi, the concept of spontaneity underpins his belief that the protective countermovement is a ‘natural’ reaction to the evils of market society; as such, power relations pass beneath the radar.
Political Science; Sociology
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; HAYEK; Salma; 1968-; POLANYI; Michael; 1891-1976; social order; socialism; spontaneity; spontaneity (philosophy); spontaneous order

Democracy disembedded - Dimitrijevic, Nenad (Philosophy & Social Criticism, 2018)
Democracy is in serious difficulties. Three features of the crisis stand out. First is the dominant culture of disillusionment in democracy, which transpires as the mistrust in constitutionalist institutions and values. Second, political authority, both at domestic and international levels, is largely substituted by the rule of non-transparent and unpredictable social powers. Third, democratic states are deprived of much of their capacity to govern, but they retain a non-negligible capacity to coerce.The article is structured as follows. Section I introduces Karl Polanyi’s concept of embeddedness and juxtaposes it to the theoretical defense of market disembeddedness advanced by the classical political economy. It then points to the challenge that the complexity of the contemporary society poses to the idea of embeddedness and identifies the need for further analytical clarification of the idea. Section II tries to explain why the idea of embeddedness is intuitively suspect. One reason is found in the dominant understanding of liberalism as a regime that rests on the separation between private and public realms. The section closes with a reference to internal tensions of this reading of liberalism. Section III provides a diagnosis of the contemporary condition of disembeddedness. The core claim is that the combination of neoliberalism and globalization has created a condition of multiple—normative, social, political and legal—disintegration, which questions the very survival of democracy. Section IV addresses the question of transformation, focusing on the need for the reconceptualization of liberal equality.
Political Science
Keywords: POLANYI; Karl; 1886-1964; democracy; disembeddedness; embeddedness (socioeconomic theory); equality; globalization; liberalism

Polanyi’s two transformations revisited: a ‘bottom up’ perspective - Halperin, Sandra (Globalizations, 2018)
In The Great Transformation, Karl Polanyi offers a ‘top-down’ analysis of the rise and demise of Europe’s unregulated market system. He assumes that changes in the organization of the international economy provide particular kinds of opportunities for states to act which, in turn, shapes the extent to which social forces will be able to influence state policy. Consequently, his analysis focuses, first, on the international institutions created by the self-regulating market system; then on the ‘liberal state’ which these made possible; and finally on how the system impacts ‘society as a whole’. The account which this analysis produces systematically underplays the social struggles which propelled and emerged from the rise of Europe’s nineteenth century system and which ultimately led to its demise. In revisiting the two periods that are the focus of Polanyi’s analysis, this article assumes that states and interstate systems reflect the interests of powerful social forces. Thus, working from the ‘bottom up’, it focuses on the class interests that produced Europe’s market system, the state and international structures which reflected and supported them, and the social struggles that ultimately brought about the collapse of the system. What this ‘bottom up’ account reveals is the centrality of a ‘double movement’, not of market expansion and a protective countermove on the part of ‘society as a whole’, but of dominant classes monopolizing economic opportunities from global expansion, and a rising ‘red tide’ of disaffected workers. This double movement, it argues, better explains the demise of the system and the changes that ensued from it.
Political Science
Keywords: class conflict; double movement; economic development; industrial capitalism; international relations; markets

Against exceptionalism: the legitimacy of the neoliberal age - Konings, Martijn (Globalizations, 2018)
After the financial crisis of 2007-08, many commentators, adopting a broadly Polanyian logic of reasoning, expected a departure from neoliberalism. The failure of this shift to materialize has typically been accounted for in ‘exceptionalist’ terms: the persistence of neoliberalism is understood not as a function of a specific legitimacy it has itself engendered, but in terms of external interventions by elites who manage to ‘capture’ executive and regulatory institutions and so to bypass democratic pressures. This paper argues that such an approach underestimates the endogenous sources of legitimacy and resilience that neoliberal governance commands. It criticizes the idea that neoliberalism is at its core dependent on a Schmittian exceptionalism and suggests a perspective on Hayek's articulation of neoliberalism that dissociates it from such an exceptionalist approach. The article proceeds to interrogate the rationality of neoliberalism by examining its distinctively secular temporal logic, rooted in speculation, preemption and reaction.
Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalism; exceptionalism; legitimacy; neoliberalism; preemption

Polanyi vs Hayek? - Mirowski, Philip (Globalizations, 2018)
Karl Polanyi and Friedrich Hayek are often portrayed as implacable intellectual opponents but their respective historical trajectories suggest some telling similarities. Here we describe some key similarities in their approach to markets, as a prelude to evaluating the political consequences of relying upon their Austrian conceptions of nature-based and constructivist framing of markets. Perhaps it is time to transcend their dichotomy.
Economics; Science and Technology Studies
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; POLANYI; Michael; 1891-1976; constructivism; markets; science and technology; spontaneous order

The great trasformismo - Morton, Adam David (Globalizations, 2018)
The purpose of this article is to explore the commonalities and differences between Karl Polanyi and Antonio Gramsci in their assessment of the origins of fascism as located within the rise of capitalism in the nineteenth century and its structural impasse in the twentieth century. Specifically, the aim is to trace a set of associations between Polanyi and Gramsci on the transformations wrought across the states-system of Europe prior to the crises that engulfed capitalism leading to the rise of fascism in the twentieth century. Focusing on the class structures that emerged out of the expansion of capitalism across Europe in the nineteenth century reveals that there was less a ‘great transformation’ in terms of a rupture with the past through the rise of liberal capitalism. Rather, there was more a slow and protracted process of class restoration known as passive revolution, or a ‘Great Trasformismo’, referring to the molecular absorption of class contradictions marking the consolidation and expansion of capitalist social relations. In sum, it is argued that The Great Transformation is understood better if read through the epoch of passive revolution, or The Great Trasformismo, which entailed the restoration and maintenance of class dominance through state power. This approach therefore opens up questions, rather than forecloses answers, about the historical geographies constituting the spaces and places of the political economy of modern capitalism.
Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; POLANYI; Karl; 1886-1964; capitalism; fascism; passive revolution

Karl Polanyi as a spatial theorist - Roberts, Philip (Globalizations, 2018)
The ‘spatial’ turn in political economy has re-invigorated Marxian analysis, allowing for new research programmes into urbanization, geopolitics, and social movement activity amongst other topics. This tendency emerged through a critical re-reading of Marx and Gramsci, amongst others, uncovering spatial analyses embedded in the logic of their arguments. Conversely, Karl Polanyi’s interlocutors have tended to add geographical analysis as an additional layer of theory, reading space ‘in’ to the text. However, a close reading reveals that a concern with space permeates Polanyi’s analysis. As such, it is possible to read space ‘out’ of Polanyi, adding a level of theoretical rigour and logical consistency when applying his insights to geographic topics. This article carries out an exegesis of Karl Polanyi’s work, uncovering a theoretical framework that deals with space, place, scale, fixity, and motion. From this vantage point, the article considers the potential implications of this new geographical reading of Polanyi.
Geography
Keywords: Marxist philosophy; POLANYI; Karl; 1886-1964; capitalism; geography; international political economy; neoliberalism; scale; social sciences; space; spatial turn

Neoliberalism as a real utopia? Karl Polanyi and the theoretical practice of F. A. Hayek - Rodrigues, João (Globalizations, 2018)
This article interprets Hayek’s theoretical practice with the help of Polanyi’s framework. Hayek aimed at renewing liberalism after the interwar period, thus helping transforming it into neoliberalism, a real utopia instrumentally concerned with the political and moral economies underpinning markets. The distance between neoliberal theory and practice is less pronounced than it is sometimes assumed. The strength of neoliberalism partially stems from a capacity to articulate an effort to think about real-world mechanisms with an effort to demolish, reconfigure or transform existing structures. Despite his failure to anticipate neoliberalism, Polanyi gives ample intellectual resources to critically interpret the tasks that neoliberals would collectively have to face at the theoretical level, in an epoch of ideological marginality, before their triumphal political deployment at the global level.
Economics; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; market; neoliberalism; utopia

Market/society: mapping conceptions of power, ideology and subjectivity in Polanyi, Hayek, Foucault, Lukács - Short, Nicola (Globalizations, 2018)
In light of discussions around the common anniversary of the publication of Karl Polanyi’s The Great Transformation and F.A. Hayek’s The Road to Serfdom, this article puts these texts - iconic representations of social democratic and neoliberal political theory - into conversation with Michel Foucault’s subsequent, influential critique of neoliberalism, The Birth of Biopolitics. There are interesting points of contact in the way each text constructs its argument, even as they arrive at distinct positions vis-à-vis the material and subjective nature of market society, while nevertheless sharing an opposition to Marxian approaches. Yet the work of Polanyi and Hayek’s Marxian contemporary, Lukács’ History and Class Consciousness, offers precisely a critical framework for understanding the relationship between markets, liberty and society in which the material and the subjective need not be read as antagonistic. It is thus also examined here, in an effort to shed light on how discussions of contemporary neoliberalism are framed.
Political Science
Keywords: Canada; FOUCAULT; Michel; 1926-1984; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; LUKACS; Georg; MARX; Karl; 1818-1883; Marxism; Road to Serfdom (book); commodity; homo economicus; market society; neoliberalism; power

Reading Polanyi in Erbil: understanding socio-political factors in the development of Iraqi Kurdistan - Smith, Robert (Globalizations, 2018)
The Kurdistan Regional Government emerges out of the chaos of post-Saddam Iraq as a rare positive, providing both political stability and economic growth. However, the outward display masks a more complex domestic settlement where the trappings of the free market coexist with political parties who are significant economic actors. How can this model of development in Iraqi Kurdistan be explained? Turning to the writings of political economist Karl Polanyi, does his thinking on relations between society and economy offer a way to unpack the development? And what does this analysis tell us of prospects for Iraqi Kurdistan?
Political Science
Keywords: Iraq; Iraqi Kurdistan; Kurdistan; Kurdistan Regional Government; POLANYI; Karl; 1886-1964; international studies

A moral householding perspective on the sharing economy - Laamanen, Mikko; Wahlen, Stefan; Lorek, Sylvia (Journal of Cleaner Production, 2018)
Abstract In this paper, we scrutinise the sharing economy from a moral householding perspective and evaluate the moral justifications for a sustainable form of the sharing economy. We consider the emergence of normative moral justifications through householding practices that rest on local mobilisation of people in defence of communities and commitments against the adverse impacts of neoliberal market capitalism. Our perspective draws on Karl Polanyi's conceptualisation of householding, that is, autarchic, communistic provision in a closed community. Using timebanking as an example, we illustrate how a moral sharing economy can be mobilised in collective battles against the current neoliberal system of economic crisis. We contribute to the amassing sharing economy literature emphasising a central, yet missing element of the current discourse: householding as practices creating self-sufficiency and autonomy as well as combining both kin and stranger.
Political Science; Management Studies
Keywords: financial crises; householding; households; market capitalization; mobilisation; moral economy; sharing economy; sustainable development; timebanking

The Truncated Commercialization of Microinsurance and the Limits of Neoliberalism - Bernards, Nick (Development & Change, 2018)
Microinsurance — defined as low‐cost insurance products targeting low‐income populations — exemplifies key themes in contemporary neoliberalism, and has figured prominently in neoliberalism's turn to discourses such as 'risk management' and 'financial inclusion'. The development of commercial markets for microinsurance, however, has in practice been highly variable and often very limited. This article considers the implications of this process of 'truncated commercialization'. It draws on a Polanyian analytical framework that emphasizes the contradictory regulatory dynamics involved in the commodification of labour. The article applies this approach by tracing multiscalar efforts to promote microinsurance, examining the emergence of the concept in the efforts of the International Labour Organization to promote social security for informal workers in the 1980s and 1990s, looking at the adoption of explicitly commercializing imperatives in the work of the International Association of Insurance Supervisors in the 2000s, and, finally, considering a case study of South Africa. The truncated commercialization of microinsurance, it is argued, provides a useful lens through which to see the practical impossibility of neoliberal development strategies.
Political Science; Development Studies
Keywords: International Association of Insurance Supervisors; International Labour Organisation; commercialization; microinsurance; neoliberalism; social security

A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
History; Religious Studies
Keywords: Great Transformation; The (Book); KING; Martin Luther; Poor People's Campaign; TRUMP; Donald; embeddedness

Ritual Matters: Changing Ontologies, Values, and Ecological Conscience Formation - Davy, Barbara Jane; Quilley, Stephen (Journal for the Study of Religion, Nature & Culture, 2018)
Karl Polanyi (1944, 1968) argued that the 'disembedding' of the economy from society entailed a curtailment of social constraints on economic transactions. This disembedding coincided with what Max Weber (1946) called disenchantment, and the erosion of cognitive-experiential reciprocity between humans and nature. Following Lynn White Jr. (1967), many scholars of religion and ecology have argued that losing the sense of divinity immanent in the world caused the modern devaluation of nature. But the loss of ritual practices is key to this. Integrating Roy Rappaport's (1968, 1979, 1999) understanding of the regulative ecological functions of ritual with a processual understanding of ontology following Norbert Elias (1939, 1978, 1989) suggests that reviving ritual gifting practices may be a vehicle for ecological conscience formation and the social-ecological transformation of modern society. Removing the rituals surrounding the giving of gifts removed crucial informal governance structures from pre-modern cultures, resulting in a general collapse of meaning structures in modern market societies, producing a pervasive individualized ontology and what Elias (1991) called 'the society of individuals'. A revival of ritual gifting practices that re-enchant human relations with other than human persons, such as found in what Graham Harvey (2006, 2016) has called 'the new animism', may revive relational ontology and shift modern society toward a more sustainable path by re-embedding the economy in society.
Environmental Studies; Religion Studies
Keywords: POLANYI; Karl; 1886-1964; animism; ecological conscience formation; ecology - religious aspects; environmental behaviour; gift economy; informal governance; new animism; ontology; relational ontology; religion and ecology; ritual; systems theory; systems thinking

Ritual and Economy: From Mutual Embedding to Non-Profit Festivalisation in Provincial Hungary - Hann, Chris (Ritualas ir ekonomika: nuo abipusės nesuprekintos ekonomikos iki nevyriausybinės festivalizacijos provincinėje Vengrijoje., 2018)
'No human beings, at whatever stage of culture, completely eliminate spiritual preoccupations from their economic concerns' (Malinowski 1935: xx). Drawing on the history and theory of economic anthropology from the pioneering investigations of Bronislaw Malinowski to the work of a postdoctoral research team at the Max Planck Institute for Social Anthropology (Halle/S) between 2009 and 2012, this paper* explores the interface between ritual and the economy in socialist and post-socialist Eastern Europe. The ruptures of early socialism gave way to a re-embedding of the economy that was especially dynamic in the sphere of the household. By contrast, postsocialist disembedding is proving harder to modify. (English)
Anthropology
Keywords: (at)kerėjimas; (dis)enchantment; (po-)socializmas; (post-)socialism; Eastern Europe; Karlas Polanyi; MALINOWSKI; Bronislaw; 1884-1942; POLANYI; Karl; 1886-1964; economic anthropology; ekonomikos nesuprekinimas; ekonominė antropologija; embeddedness; ritual; ritualas; social anthropology; socialism

China's Middle East investment policy - Kenderdine, Tristan; Lan, Peiyuan (Eurasian Geography & Economics, 2018)
China's greater Middle East geoeconomic strategy is centered on an external trade and industry policy. This trade and industry policy combines geopolicy and geoeconomic policy to export industrial capacity bases in what amounts to a geoindustrial policy and a parallel trade strategy. Practical coordination is under the umbrella of the central International Capacity Cooperation macro-policy. China's provincial governments are then tasked with offshoring China's industrial capacity to Middle East economies through specialized International Capacity Cooperation funds, which are then coordinated by sectoral industry associations: International Capacity Cooperation Industry Enterprise Alliances. The final industrial policy is then deployed by matching China's provinces and prefectures to external geographies. This amounts to a State Outward Direct Investment Strategy. This paper uses primary sourced Chinese policy documents from central and provincial state administrative agencies to build a historical institutional record. We then employ a Polanyian analysis of the embeddedness of State functions in China's external investment activities and industrial transfers, analyzing China's external trade and industry policy in the Middle East in terms of state–market institutional interrelationality.
Political Science; International Studies
Keywords: China; China policy; Middle East; Middle East policy; foreign investments; foreign relations; geoeconomics; geoindustrial policy; geopolicy; institutional economics; investment policy

Rethinking the Double Movement: Expanding the Frontiers of Polanyian Analysis in the Global South - Goodwin, Geoff (Development & Change, 2018)
Over the last two decades a rich and diverse body of literature has emerged which uses the ‘double movement’ to analyse social, political and economic change in the global South. The main aims of this article are to expand the boundaries of this scholarship and improve our understanding of how to use the concept to analyse capitalist development in the region. It seeks to achieve this by explaining and extending the original formulation of the double movement, creating a dialogue between scholars who follow alternative readings of the concept, and proposing a revised formulation which builds on the existing literature while moving in new directions. The article concludes by signposting potentially fruitful areas of Polanyian analysis.
Political Science; Development Studies
Keywords: capitalism; commodification; developing countries; development studies; double movement; economic reform; liberalism; political change; social change; social movements

Review of The Hungarian Writings by Karl Polanyi - Moussaly, Omer (International Critical Thought, 2018)
In the current times of political crisis, a giant thinker such as Karl Polanyi will return to the forefront of intellectual debate. Many of his important early articles have only been available in Hungarian or in German. With the publication of The Hungarian Writings (2016), edited by Gareth Dale (Senior Lecturer in Politics and International Relations at Brunel University London), a major gap in Polanyi studies has been filled. These essays, published for the first time in English, provide a key to understanding Karl Polanyi’s later works. The range of issues that are reviewed in these writings is astounding. Everything from Marxism to politics, economics and sociology is examined by the extraordinary mind of the author. Events such as the Russian revolution and the significance of Bolshevism are also explored. Lastly, a section of correspondence to such eminent intellectuals as Georg Lukaćs and Istvan Meszaros gives the reader an inside look into the socialist worldview of Karl Polanyi. This book truly shines a new light on many aspects of Polanyi’s critique of capitalism developed in his magnum opus, The Great Transformation (1944). Various aspects of The Hungarian Writings will be explored in depth in this critical review.
Political Science
Keywords: Bolshevism; Canada; Great Transformation; The (Book); Hungarian Writings; The (Book); Marxism; POLANYI; Karl; 1886-1964; Quebec; Russian Revolution; 1917-1921; economics; nonfiction; socialism

"Race" and the upsurge of antagonistic popular movements in Sweden - Schierup, Carl-Ulrik; Ålund, Aleksandra; Neergaard, Anders (Ethnic & Racial Studies, 2018)
Across a crisis-stricken Europe battles rage for post-neoliberal hegemony, with "race" and "austerity" as central signifiers. One of the places where the frontlines are most pregnant is Sweden; long perceived as a role model for its welfare state, cultural equity and social equality. Sweden is, however, facing social conflicts following in the tracks of a deep transformation in terms of welfare cuts, racialization and growing social polarization, targeting in particular a disadvantaged migrant and post-migrant population. On that background, the paper focuses on the upsurge of mutually antagonistic popular movements - "racist" and "anti-racist". We use Sweden as an exemplary case of Europe's present Polanyian moment, reminiscent of the 1930s. Yet, current upheavals expound, the authors claim, a different configuration of crisis and racism as well as a dissimilar utopia for the imagineering of nation and community.
Sociology; Ethnic Studies
Keywords: Europe; Sweden; ethnic studies; hostility; immigration opponents; migration; neoliberalism; new right (politics); populism; race; racism; social class; social movements; sociology

Globalization and Business Regulation - Djelic, Marie-Laure; Quack, Sigrid (Annual Review of Sociology, 2018)
In the twenty-first century, global business regulation has come of age. In this article, we review the literature on globalization and business regulation from the angle of transnational governance, a recently evolving interdisciplinary field of research. Despite the multiplicity and plurality of regulatory platforms and products that have emerged over time, we identify common patterns of field structuration and parallel trajectories. We argue that a major trend, both in practice and in scholarly work, is a move away from an idealized convergence around a set of unified global rules; instead, our conceptualizations and our practices of transnational business regulation increasingly demonstrate a concern for the adaptability of transnational rules to resilient and resistant contextual specificities. Another important trend, both in practice and in scholarly fields, is a growing focus on the complex dynamics between rule making on the one hand and rule implementation and monitoring on the other.
Sociology
Keywords: POLANYI; Karl; 1886-1964; business regulation; globalization; governance; market ideology; neoliberalism; soft law; transnational; value chains

Information Policy and the Spatial Constitution of Digital Geographic Information Markets - Alvarez León, Luis F. (Economic Geography, 2018)
Information policy has become one of the key instruments for the commodification and marketization of goods in contemporary capitalism. However, the spatializing role of this and other legal regimes has not been explored in depth. Among the categories of goods whose production and circulation is shaped by information policy, geographic information is increasingly salient in the digital economy due to the strategic and economic value derived from its integration of location and context. This article explores the role of information policy regimes in spatially bounding, structuring, and regulating digital geographic information markets. This is conducted through a Polanyian economic geographic approach that contextualizes, integrates, and synthesizes two types of geographic information market formations, and focuses on the institutional dimension of information policy regimes. In developing this approach, the article argues that legal regimes (in this case information policy) are capable of spatializing markets by structuring, integrating, and delimiting the actions of states and other actors, such as private corporations and consumers, within particular jurisdictions. The empirical section of the article illustrates this argument by showing how three aspects of information policy—(1) intellectual property, (2) infrastructure, and (3) commercialization—shape specific configurations of digital geographic information markets within the various administrative scales in the European Union, a globally influential jurisdiction for information policy, and where a regional digital market is in the process of construction. The article concludes by arguing that a Polanyian economic geographic approach provides a solid basis with ample versatility to account for the necessary integration of a legal perspective into the analysis of new kinds of goods (such as digital geographic information) and the spatialities of their emerging market configurations.
Geography
Keywords: United States; capitalism; digital economy; geographic information; geographic information systems; information markets; information policy; intellectual property; legal frameworks; prediction markets

The economic shift and beyond: Care as a contested terrain in contemporary capitalism - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Current Sociology, 2018)
This article argues that we are witnessing a fundamental transformation of capitalism. Under the auspices of an economic shift, social reproduction and constituent care and care work are undergoing a process of reorganization. The first part draws on Karl Polanyi’s analysis of the relation between market and society and on contemporary revisions of his approach. Referring to core arguments from his perspective on the market society it identifies processes of commodification, marketization and quasi-marketization, which we can understand as an economic shift driving the development in the field of care and care work. The second part refers to empirical studies in Austria and Germany and reflects in terms of a Polanyian double movement on how far care and care work – in the case of elder and child care and, more precisely, home care agencies, residential care communities and the social investment state – have become a contested terrain. The third part, the conclusion, points out how tendencies like the economic shift touch care and care work.
Sociology
Keywords: Giro económico; Virage économique; agence de soins à domicile; agencias de atención a domicilio; atención a los mayores y la infancia; capitalism; care work; communautés de soin; comunidades de atención; corporate reorganizations; doble movimiento; double movement; doublé mouvement; economic shift; elder and child care; home care agencies; inversión social; investissement social; reproducción social; reproduction sociale; residential care communities and social investment; social reproduction; social services; socioeconomics; soin aux personnes âgées et à l’enfance

Political economy and the need for a moral critique of capitalism - Cruddas, Jon (Renewal (0968252X), 2018)
N/A
Keywords: Moral Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); POLANYI; Karl; 1886-1964; ROGAN; Tim; book review; capitalism; nonfiction

Labour Protest and Industrial Peace: Russian Steelworkers' Encounters with Economic Reforms and Unravelling Social Protections - Evans, Allison D. (Economy and Society, 2018)
The collapse of the Soviet Union brought a series of economic reforms: privatization, increased foreign direct investment and weakened benefits. Correspondingly, some scholars expected trade unions to serve as a major contribution to the development of a democratic civil society that would serve as a Polanyian double movement to these disruptive reforms. However, Russia's steelworkers have stood out as particularly weak and unwilling to strike due to their dependence on their employer for almost all aspects of their livelihoods. But is this lack of large, legally sanctioned and disruptive strikes truly evidence of worker quiescence and weak trade unions? Using an analysis of local newspaper accounts and archival documents to process-trace the interactions of workers, trade unions and management, this paper offers a counter-argument to the generalizations of past studies. Specifically, protests tend to be more frequent and extreme when there is union competition within a company and when foreign owners violate labour laws. Unions tend to engage in non-protest bargaining strategies when companies face bankruptcy or closure under domestic ownership. Because Russia was an early case of the rapid liberalization reforms that have been broadly recommended to developing and post-communist countries, a closer reading of on-the-ground conditions and protest aids in a broader understanding of the variation in backlash to global capitalism.
Political Science
Keywords: Russia; cement; ceramics; collective bargaining; dispute resolution: strikes; arbitration; and mediation; double movement; glass; industry studies; metals and metal products; population; property rights; socialist systems and transitional economies: factor and product markets; socialist systems and transitional economies: political economy; trade unions: objectives; structure; and effects

The Moral Economists. R.H. Tawney, Karl Polanyi, E.P. Thompson, and the Critique of Capitalism - Gruber, Stephan (Economía (02544415), 2018)
Economics
Keywords: book review

Reconstructing Polanyi? - Levien, Michael (Development & Change, 2018)
Most people read Karl Polanyi today because his critique of laissez faire capitalism seems remarkably applicable to our neoliberal times. Although his late work on ancient and ‘archaic’ economies has enjoyed a consistent specialist readership, Polanyi is best known today for his 1944 magnum opus, The Great Transformation (henceforth GT). Covering a large sweep of mostly European history, the GT seeks to show that the attempt to create a ‘self-regulating market’ was a radical and recent departure from all preexisting economies; that this effort to ‘disembed’ the market from society required a great deal of state planning and force; and that the commodification of the ‘fictitious commodities’ land, labour and money was so socially destructive that it generated countermovements that demanded, and in some measure achieved, social protection. Polanyi termed this whole cycle of disembedding and re-embedding the market the ‘double movement’, and tried to show that it was the underlying cause of the great depression, fascism and two world wars. Given the relentless march of commodification in the neoliberal period and the variety of political responses this has generated (from both the left and far right), many people have been drawn to the idea that we are living through another double movement.
Sociology; Development Studies
Keywords: DALE; Gareth; POLANYI; Karl; 1886-1964; Reconstructing Polanyi: Excavation & Critique (Book); book review; double movement; nonfiction

European Politics and the Neoliberal Paradigm - Sliwinski, Krzysztof (Australian & New Zealand Journal of European Studies, 2018)
This paper looks at the European integration project in its current iteration drawing on Karl Polanyi's assertion that markets are inseparable from the socio-cultural context. In this regard, all attempts to liberalise the economy (not excluding European integration, which is based on the principle of the single market) have practical and indeed tangible political ramifications. The main hypothesis of the paper lies in the recognition of the fact that the neoliberal agenda is one of the defining features of European integration. It is after all, the project of the single market, with its free movement of goods, services, capital, and labour that underpins European Union integrative practice. Secondly, it is the presupposition of this paper, that there is a certain degree of congruence between the economic elites, operating within the neoliberal framework, and the centre-left political elites. The argument here is that the logic of neoliberalism has been fundamentally accepted across the mainstream of the political spectrum. This consequently means that even left-wing parties have had to reposition themselves both ideologically and practically, which brings the conclusion that the market has lost its role as the basic ideological differentiator between the traditional right and left. The axis of political debate has consequently shifted to moral issues such as the relationship between the state and the church, immigration, and gender.
Political Science; European Studies
Keywords: EU; European Union; European integration; democracy deficit; international studies; neoliberalism; political ideologies

Capitalism goes care: Elder and child care between market, state, profession, and family and questions of justice and inequality - Aulenbacher, Brigitte; Décieux, Fabienne; Riegraf, Birgit (Equality, Diversity & Inclusion, 2018)
The starting point of the paper is the meteoric rise of care and care work upon the societal and sociological agenda. Referring to Polanyi, the authors argue that this is the manifestation of a new phase of capitalist societalisation (Vergesellschaftung) of social reproduction in the form of an economic shift. The purpose of this paper is to discuss the societal organisation of care and care work and questions of inequality and justice.Design/methodology/approach The first part of the paper illustrates some facets of the economic shift in the field of care and care work. The second part reconstructs the societal organisation of care and care work in the private sector, state, third sector and private households from the mid-twentieth century in the context of questions of inequality and justice. The third part draws on the institutional logics perspective and French pragmatic sociology and the own case studies on home care agencies (HCA), residential care communities (RCC) and early child care (ECC) in Austria and Germany and shows how conflicting demands give rise to new questions of justice. The paper ends with a short conclusion.Findings The paper shows how the commodification and de-commodification of care and care work have changed over time and how the economic shift – illustrated in the case of HCA, RCC and ECC – is accompanied by conflicting demands and questions of justice.Originality/value A Polanyian perspective on the relation between market and society is combined with the neo-institutionalist and pragmatic idea that orientations rooted in the “logics” of the market, the state, the family and the profession influence how conflicting demands in elder and child care are dealt with and how questions of inequality and justice arise.
Sociology
Keywords: capitalism; care work; caring communities and social investment; community health services; countermovement; decommodification; economic systems; elder and child care; home care agencies; home care services; social justice; social reproduction

A hands-on hands-off approach: governance of managed long-term care services in a context of rapid policy change - Nisbet, Elizabeth (Public Management Review, 2018)
Amidst state-level budgetary pressures and growing elderly populations, many US states have adopted managed care for home-based services funded through the Medicaid program. New York State’s managed care mandate is part of a Medicaid ‘Redesign’ targeting health outcomes, cost control, and administrative efficiency, reflecting features emphasized by both governance and New Public Management frameworks, but neither adequately captures this case. Incorporating a Polanyian perspective can elucidate this market expansion and related reactions and re-regulation. Drawing from interviews with staff of service-providing agencies, this case study reveals outcomes contrary to goals: administrative complexity, containment of care, and unexpected costs.
Political Science
Keywords: United States; United States federal budget; cost control; governance; health care reform; home care services; long-term care; medicaid; medical care costs; public management

Rethinking Money as an Institution of Capitalism and the Theory of Monetary Circulation: What Can Modern Heterodox Economists/Institutionalists Learn from Karl Polanyi? - Seccareccia, Mario; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2018)
Modern heterodox theories of money reject the neoclassical conception of money as primarily a medium to facilitate exchange. These heterodox theories of money all have as common starting point an analysis of credit-debt relations in which production is a central feature, with these economies organized along capitalistic design. The Keynesian-Marxian framework describing the process of monetary circulation, traditionally referred to as the theory of the monetary circuit (TMC), perhaps best represents this comprehensive vision. This broad TMC analytical framework is compatible with institutionalist theories of money that also point to the importance of credit-debt relations. The question, however, is whether this more unified heterodox theory of money, which describes sequentially monetary relations under capitalism, can be used to understand pre-capitalistic monetary institutions. By conceptualizing money as a means of payment rather than medium of exchange, Karl Polanyi’s analysis offers social scientists crucial insights to understanding monetary relations in all types of societies in which credit-debt relations have emerged historically.
Economics
Keywords: POLANYI; Karl; 1886-1964; credit; credit-debt relations; debt; heterodox economics; monetary circuit; money; money as a means of payment; neoclassical school of economics

In the market for humane rights - Inglis, Fred (Times Higher Education, 2018)
History; Education
Keywords: Human rights; Moral Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); Rogan; Tim; austerity (economics); book review; cultural history; nonfiction

The Double Movement in Polanyi and Hayek: Towards the Continuation of Life - Faria, Filipe Nobre (Ethics, Politics & Society, 2018)
Karl Polanyi’s double movement is a dialectical process characterized by a continuous tension between a movement towards social marketization and a movement towards social protectionism. Notably, Polanyi condemns the former movement while defending the latter. Without using the term “double movement”, F.A Hayek’s theory of social evolution acknowledges the same phenomenon but reaches different normative conclusions. While for Polanyi the marketization of society is a utopia with dystopian consequences, Hayek’s evolutionary explanation of this dialectical process asserts that there is no alternative to a market oriented society. Both authors defend that their favoured movement is the one that truly supports the continuity of life. This article compares the authors’ normative readings of the double movement and concludes that, from an evolutionary perspective, Polanyi’s conclusion possesses a robustness that Hayek’s postulate lacks.
Philosophy
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; double movement

The Significance of Polanyi's Contribution: An Interpretation of the Neoliberalization and Commodification of Nature - Iannuzzi, Giulia (Janus.Net: e-Journal of International Relations, 2018)
Polanyi's analysis and contributions have been brought back into discussion due to the rapid emergence of market-based instruments designed to tackle environmental degradation. Polanyi is a crucial reference in current debates on globalization and international political economy. This article seeks to explore and discuss how his perspective, and the founding concepts of his work, can help us to interpret the current process of the neoliberalization and commodification of nature.
Political Science; Environmental Studies
Keywords: commodification; commodification of nature; environment; globalization; international relations; neoliberalism

Karl Polanyi's Genealogy of Utopian Liberalism - England, Christopher (Theory & Event, 2018)
Despite its centrality to current debates about globalization and neoliberalism, aspects of Karl Polanyi's The Great Transformation remain poorly understood. This article places Polanyi in conversation with Weber, Nietzsche, and Foucault in order to explicate his genealogy of utopian liberalism. This mode of thought emerged in the late 18[sup th] century as a response to the mass pauperism of the Industrial Revolution in England. It substituted a mechanistic naturalism for the political and ethical concerns of earlier economists. Polanyi shows that the allure of utopian liberalism is sustained because it functions as the public theodicy of a market society.
Political Science
Keywords: FOUCAULT; Michel; 1926-1984; NIETZSCHE; Friedrich; POLANYI; Karl; 1886-1964; genealogy; globalization; liberalism; neoliberalism; utopian liberalism

Uncertainty, Control, and Karl Polanyi's Protective Response - Zalewski, David A. (Journal of Economic Issues, 2018)
Post-Keynesian institutionalist economists like Wallace Peterson and John Kenneth Galbraith recognized that the impact of uncertainty on economic wellbeing depends in part on the degree of control people have over the sources and consequences of it. Given the inability of government and other large institutions to reduce uncertainty or to provide citizens with the ability to manage it, mediating structures are considered as an alternative means of promoting economic security. The article concludes by describing and evaluating several of these alternatives.
Economics
Keywords: Austrian; Stockholm School; criteria for decision-making under risk and uncertainty; current heterodox approaches: historical; evolutionary; general welfare; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; well-being

The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism - Crook, Paul (Australian Journal of Politics & History, 2018)
The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. By Tim Rogan (Princeton and Oxford, Princeton University Press, 2017), pp.263 + viii. AU$48.82 (hb). Available in Australia through Footprint Books.
Political Science; History
Keywords: MORAL Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson & the Critique of Capitalism; The (Book); POLANYI; Karl; 1886-1964 - political & social views; ROGAN; Tim; TAWNEY; R. H. (Richard Henry); 1880-1962; THOMPSON; E. P. (Edward Palmer); 1924-1993; book review; nonfiction; political attitudes

Beyond Double Movement and Re-regulation: Polanyi, the Organized Denial of Money Politics, and the Promise of Democratization - Feinig, Jakob (Sociological Theory, 2018)
Although Karl Polanyi is best known for his theorization of market regulation and the double movement, democratizing the economic was one of his core concerns. He believed societies need to bring labor, land, and money under collective oversight to displace the logic of market fundamentalism with the logic of human needs. In this article, the author draws on Polanyi’s vocabulary to shed light on the denial of money politics and the possibility of democratization. The author illustrates these dynamics through an analysis of long-term dynamics of (de)politicization in British colonial America and the United States through the 1930s. The author developed this approach hoping that it can contribute to nudging public debates beyond regulation and monetary policy techniques and toward popular involvement and knowledge.
Sociology
Keywords: Polanyi; democratization; depoliticization; double movement; gold standard; money; social theory; sociology

Situated responses to the post‐political city: An introduction - Richter, Anna; Fitzpatrick, Susan (Area, 2018)
It seems with the ever more complex instituting of aggressive neoliberal renewal policies comes an intensified effort to use the language of consensus and civic unity. The post‐political debate frames this discussion, and it is from this perspective that we propose a fuller consideration of urban renewal policy, and how these forces are embedded within the narrowing of what has been called the “properly political”. In bringing together accounts of the dynamic political life of communities and groups of interest who are confronting urban renewal policy in Glasgow, we make a case for recognising an intensification of political articulation, position‐taking and action. This recognition comes in response to the argument that we are currently experiencing a post‐political consensus and that democracy has been annulled in the process. We see evidence of a Polanyian “double movement” in which the construction of consensual publics is such a marked characteristic across different accounts, and how this appears to have opened up new critical spaces of debate and action within the various communities of interest. We therefore openly question the post‐political as a condition, or a process, which seemingly unfolds unimpeded. We fear that “post‐political” runs the risk of becoming a citational practice, that through repetition of the term, a narrowing of political articulation and action within the debate starts to occur. Our case studies aim to highlight the blind spots of the post‐political debate by focusing on the actually existing spaces of political articulation and position‐taking apparent in Glasgow.
Geography
Keywords: Glasgow; articulation (speech); consensus (social sciences); debates & debating; political; urban policy; urban renewal

A Theoretical Note on Commodification of Labour Power in China and the Global Putting-Out System - Westra, Richard (Journal of Contemporary Asia, 2018)
This article captures China's role in global manufacturing through the prism of conceptualisation of the commodification of labour power in Marxist theory. It argues that modalities of China's labour force co-optation in assembly and lower value added production for export of consumer goods to advanced economies carries more of a family resemblance with putting-out systems of the pre- capitalist era than with the commodification of labour power sensu stricto marking the capitalist era from the mid-nineteenth century.
Law
Keywords: China; MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; capitalism; commodification; commodification of labour power; consumer goods; global value chains; globalization; international trade; labour supply; manufacturing industries; putting-out system; value chains

Discursive Synergies for a ‘Great Transformation’ Towards Sustainability: Pragmatic Contributions to a Necessary Dialogue Between Human Development, Degrowth, and Buen Vivir - Beling, Adrián E.; Vanhulst, Julien; Demaria, Federico; Rabi, Violeta; Carballo, Ana E.; Pelenc, Jérôme (Ecological Economics, 2018)
There is a growing awareness that a whole-societal “Great Transformation” of Polanyian scale is needed to bring global developmental trajectories in line with ecological imperatives. The mainstream Sustainable Development discourse, however, insists in upholding the myth of compatibility of current growth-based trajectories with biophysical planetary boundaries. This article explores potentially fertile complementarities among trendy discourses challenging conventional notions of (un)sustainable development – Human Development, Degrowth, and Buen Vivir – and outlines pathways for their realization. Human Development presents relative transformative strengths in political terms, while Degrowth holds keys to unlocking unsustainable material-structural entrenchments of contemporary socio-economic arrangements, and Buen Vivir offers a space of cultural alterity and critique of the Euro-Atlantic cultural constellation. The weaknesses or blind spots (‘Achilles heels’) of each discourse can be compensated through the strengths of the other ones, creating a dialogical virtuous circle that would open pathways towards a global new “Great Transformation”. As one of the main existing platforms for pluralist and strong-sustainability discussions, Ecological Economics is in a privileged position to deliberately foster such strategic discursive dialogue. A pathway towards such dialogue is illuminated through a model identifying and articulating key discursive docking points.
Political Science; Sociology; Economics
Keywords: biophysics; degrowth; ecosystem services; environemntal economics; post-development; pragmatics; socio-ecological transition; strategic dialogue; sustainable development; transformation discourses

In Search of Substantive Economics: Comparing Today's Two Major Socio-metabolic Approaches to the Economy – MEFA and MuSIASEM - Gerber, Julien-François; Scheidel, Arnim (Ecological Economics, 2018)
Ecological economics is largely about the ‘substantive’ (in ‘kind’) study of the economy, as opposed to a purely ‘formal’ economic analysis (in ‘money’). Following Kapp, Polanyi and others, this article argues that ‘substantive economics’ is interested in the biophysical and politico-institutional structure of the economy rather than in correct prices within a particular axiomatic conformity, as in ‘formal economics’. After outlining the history of the substantive vs. formal dichotomy, we point out that socio-metabolic analyses are ecological economics' most significant contribution towards substantive economics. The core of this article then compares what could be today's two best candidates for offering a distinctive foundation to ecological economics as substantive economics: Material and Energy Flows Analyses (MEFA) and Multi-Scale Integrated Analyses of Societal and Ecosystem Metabolism (MuSIASEM). While MEFA is more easily comparative and historical, MuSIASEM is more integrative and comprehensive. Yet we also argue that socio-metabolic analyses represent one of the three pillars of substantive economics and that both MEFA and MuSIASEM are still weak in integrating the politico-institutional structure (second pillar) and a theory of needs (third pillar). If such an integration was done, ecological economics would be in a position to offer a full-fledge, alternative ‘substantive economic theory’.
Economics
Keywords: MEFA; MuSIASEM; biophysics; comparative studies; ecological economics; economic impact; environmental economics; social metabolism; substantive economics

Reconstructing Karl Polanyi: Excavation and Critique - Neelakandan, Sanil M. (Capital & Class, 2018)
Law
Keywords: DALE; Gareth; POLANYI; Karl; 1886-1964; Reconstructing Karl Polanyi: Excavation & Critique (Book); economists; nonfiction

Latin American Structuralism and Current Financialization - Déniz, José; Marshall, Wesley C. (International Journal of Political Economy, 2018)
In this article, we attempt to update the understanding of the external constraint in Latin America by examining the recent history of the region through the analytical framework of Karl Polanyi in The Great Transformation. As we argue, the greatest force behind today’s external restriction is the financial sector, much as it was a century ago. To reinforce this hypothesis, we provide the reader with relatively new historical material and with arguments made by scholars from diverse backgrounds. Taking into consideration the political and economic structures of Latin America, we argue that the international connections between the elite of the center and the periphery remain the key aspect in understanding today’s complex reality.
Development Studies; Economics
Keywords: Great Transformation; The (Book); Latin America; POLANYI; Karl; 1886-1964; external restriction; financialization; structuralism

The agrifood question and rural development dynamics in Brazil and China: towards a protective ‘countermovement’ - Escher, Fabiano; Schneider, Sergio; Ye, Jingzhong (Globalizations, 2018)
This paper explores some features of the development paths taken by Brazil and China (two member countries of the BRICS grouping) in the current context of the crisis of neoliberal globalization and transformation of the political and economic world order. The authors use Polanyi’s ‘double movement’ thesis to argue that newly emerging rural development (RD) dynamics in China and Brazil are part of a protective ‘countermovement’, driven by actors and institutions responding to the contradictions of the concentration and internationalization of agrifood systems. However, thedirectionand scope of these countermovements are still open; their transformative potential should be viewed in Gramsci’s terms as a struggle for hegemony the outcome of which depends on the concrete ‘balance of social forces’. First, the paper characterizes the impacts of China’s rise on Brazil’s development, which subsequently found its economy under threat of reprimarization and deindustrialization. The paper then sketches some stylized facts of production and consumption within the Brazil–China soy–meat complex, a key element of the current global food regime, with a focus on corporate control of the soy–meat value chain, and its negative consequences. Finally, the paper identifies the key roles that actors and institutions linked to peasants and family farmers are playing in the RD dynamics of each country. Although China and Brazil represent two very different realities, the comparison shows that critical rural and agrifood issues are indeed moving onto the centre stage of the contemporary ‘double movement’.
Sociology; Rural Studies
Keywords: Brazil; Brazil–China soy–meat complex; China; deindustrialization; double movement; farming practices; food industry; globalization; production–consumption relations; rural development; rural policies

The Double Movement of the Landlord Class in Prewar Japan - Cohen, Mark (Journal of Japanese Studies, 2018)
The role of the landlord class in Japan's prewar economic and political development has been widely debated. Moving beyond conflicting arguments of landlords as semifeudal exploiters or as the linchpins of rural market development, more recent research has emphasized the nonmarket institutions, often inherited from the Tokugawa era, in which the contractual relations between landlords and tenants were embedded. However, this research has overemphasized the continuity of the rural economy. Rather than a smooth development, the historical trajectory of rural economic growth followed the "double movement" of capitalist development identified by the historian and economic anthropologist Karl Polanyi.
History; Japanese Studies
Keywords: Japan; Tokugawa Period; Japan; 1600-1868; capitalism; double movement; history; landlord-tenant relations

Reconstructing Globalization in an Illiberal Era - DeMartino, George F. (Ethics & International Affairs, 2018)
In their new indictments of global neoliberalism and the economic profession's culpability in its harms, Dani Rodrik and Joseph Stiglitz press the case for reconstructed globalization that generates benefits for all and not just for corporate and financial elites. Both books are deeply consistent with the insights of Karl Polanyi, who had identified the inherent contradictions of the project to create what he called a self-regulating economy. Like Polanyi, Rodrik and Stiglitz are attentive to the inadequacies of neoliberalism, and both emphasize the capture of the state and international economic policy by elites, who have turned their backs on those left behind. While Stiglitz emphasizes that the profession knows how to fix the problem by applying modern Keynesian insights, Rodrik emphasizes the inherent epistemic limitations facing economists. Indeed, his arguments about development policy reflect the insights of Friedrich Hayek into the limits of economic expertise.
Economics; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; RODRIK; Dani; STIGLITZ; Joseph; globalization; international relations; nationalism; neoliberalism; policy autonomy; trade; uncertainty

Capabilities Accumulation and Development: What History Tells the Theory - Dosi, Giovanni; Yu, Xiaodan (2018)
In this contribution we offer a broad overview of the technological, institutional and policy dynamics associated with the great transformation–borrowing Karl Polanyi (1944) expression–leading from traditional, mostly rural, economies to economies driven by industrial activities (and nowadays also advanced services), able to systematically learn how to implement and eventually how to generate new ways of producing and new products under conditions of dynamic increasing returns. Such a 'great transformation' entails a major process of accumulation of knowledge and capabilities, both at the levels of individuals and organizations. Certainly, part of such capabilities builds on education and formally acquired skills (what in the economists' jargon often goes under the heading of 'human capital'). However, at least equally important, capabilities have to do with the problem-solving knowledge embodied in organizations–concerning e.g. production technologies, the technical and social division of labor, labor relations as well as 'dynamic capabilities' of search and learning. In turn, the rates and directions of knowledge accumulation during the catch-up process and the ensuing effects upon the patterns of production and trade are shaped by the economic and institutional framework in which such processes are embedded.
Economics; Management Studies
Keywords: Great Transformation; The (Book); capability accumulation; catching-up; development; innovation

Polanyi's Economic Embeddedness, Countermovement, and Republican Political Economy - Escandell, Bru Laín (Ethics, Politics & Society, 2018)
The aim of this article is to contend that Karl Polanyi's work bears significant coincidences with the republican tradition of thought. The first of them is one of a methodological or epistemological kind, and it consists of the use of a very
Sociology
Keywords: countermovement; embeddedness; political economy; political economy and history; political philosophy; republicanism

The social aftermath of economic disaster: Karl Polanyi, counter-movements in action, and the Greek crisis - Kentikelenis, Alexander E. (Socio-Economic Review, 2018)
The economic crisis in Greece resulted in high unemployment and the dismantlement of social protection policies. How does society respond to the collapse of both welfare-state and market mechanisms? I examine these issues through the study of one working class community in Athens over 2012-13. Since the onset of the crisis, my informants experienced a simultaneous drop in living standards, loss of social status, and debasement of their symbolic construction of reality. To respond to these pressures, they relied on a combination of material survival strategies, the reconfiguration of social resources, and the reconstruction of cultural imaginaries. To explain these findings, the article draws on Karl Polanyi's analysis of countermovements to marketization and commodification. I argue in favour of augmenting the definition of countermovements to capture local-level responses, emphasising cultural aspects of social protection, and tracing the micro-foundations of countermovements that are nonetheless shaped by the macro-institutional context shaping action. This reading of Polanyi's work seeks to integrate many moving–and potentially contradictory–parts into a holistic analysis of societal responses to rapid and radical socioeconomic change.
Political Science; Sociology
Keywords: Greece; capitalist systems: political economy; countermovement; economic crisis (2008); financial crises; history of economic thought: individuals; national government expenditures and welfare programs

Karl Polanyi and the formation of this generation's new Left - Sandbrook, Richard (IPPR Progressive Review, 2018)
The article discusses whether the visionary thinking of economic historian Karl Polanyi provide a feasible fix in the 21st Century for forces of populism and neoliberalism. Topics include Polanyi's work is stated to offer three potential contributions to the formation of this generation's new Left which include analysis of fascism, post-Vienna approach to socialism.
Political Science
Keywords: POLANYI; Karl; 1886-1964; fascism; neoliberalism; populism; socialism

The Man from Red Vienna - Kuttner, Robert (New York Review of Books, 2017)
A review of the book "Karl Polanyi: A Life on the Left," by Gareth Dale, is presented.
N/A
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); book review; great powers (international relations); nonfiction

Pop-up Polanyi: Cultural entrepreneurs and the ‘vacancy fix’ - Scott, Michael; Szili, Gerti (City, Culture and Society, 2017)
Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – ‘pop-up shops’ – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how ‘pop-up’ programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how ‘vacancy fixes’ are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification.
Sociology; Geography
Keywords: creative cities; cultural entrepreneurs; gentrification; modes of economic integration; pop-up; rent gap

Market fundamentalism in the age of 'haute finance': The enclosing of policy space in 'emerging' India - Lakshminarayan, Srivatsan (Ephemera: Theory & Politics in Organization, 2017)
The rise of the Emerging Market is a remarkable exemplar of an idea that originated and was socialized in Western financial markets during the 1980s. It has since gained rapid, wider normative status with respect to a particular set of beliefs that motivate policy choices on macroeconomic management, economic development and financial sector reforms in developing and less developed countries. I draw on the Polanyian notion of commodification and recent extensions to his scholarship in the realm of ideas that seek to explicate processes through which the dominant ideal of the self-regulating market is justified as fundamental to the organization of society. Against the backdrop of globally mobile capital, I critique the prevalence of a particular ideology of emergence in which commodified geography and commodified finance interact to shape policy. In this process, evaluative talk plays a key role in legitimizing the expectations of global capital and overcoming inherent contradictions through the rhetoric of non-crises. I thus highlight the ascendance of a narrow and instrumentally economic understanding of emergence in contemporary, post reform India as is asserted in conventional policy discourse. I conclude by remarking on the significant constriction of ideational space for the consideration of alternative, historically informed approaches to social and economic development. The legacy of Karl Polanyi serves as a prophetic reminder for the consequences of such constriction.
Management Studies
Keywords: India; commodification; economic development; emerging markets; haute finance; macroeconomics

Family as a Socio-economic Actor in the Political Economies of East and South East Asian Welfare Capitalisms - Papadopoulos, Theodoros; Roumpakis, Antonios (Social Policy & Administration, 2017)
In this article, we revisit Karl Polanyi's concept of 'oikos' in order to reconceptualize the role of the family as both a welfare provider and an economic actor in the social reproduction of East and South East Asian welfare capitalisms. Our article is structured in four parts. First, we critically review existing approaches on the characteristics of welfare capitalism in East and South East Asia. We argue that existing approaches tend to isolate family as a welfare provider and neglect how the role of the family is institutionalized as a collective actor. The second part focuses on the role of the family in the social reproduction of welfare capitalism, and explores how, in East and South East Asia, the specific conditions for family's role as an economic actor were institutionalized historically. The third part revisits Polanyi's concept of 'oikos' and how 'householding' constitutes one of the most important forms of economic action allowing us to examine the family as a socio-economic actor. In the fourth section, we provide an analysis of families' available strategies and discuss evidence related to private education expenditure, household debt and labour market income share. We conclude by highlighting the need to re-articulate the importance of family as a collective socio-economic actor that, despite recent reforms and path departures, remains at the epicentre of East and South East Asian welfare capitalisms.
Political Science; Public Administration
Keywords: East and South East Asia; OIKOS (The Greek word); debt; economic conditions in Asia; families & economics; family; households and economics; social reproduction; welfare capitalism; welfare state

'Playing on the break': Karl Polanyi and the double-movement 'Against Modern Football' - Webber, David M (International Review for the Sociology of Sport, 2017)
While the popularity of English football increases worldwide, there has been a marked rise in the discontent expressed by a small but growing group of domestic fans. This dissent has led to the emergence of a movement broadly defined as being 'Against Modern Football' (AMF), a banner under which fans of rival clubs have gathered in an attempt to challenge the poor governance, commercialism and greed that has come to dominate the English game. This article offers a conceptualisation of what it means to be 'against modern football' based upon Karl Polanyi's analysis of the market society. Developing the dialectic of the 'double-movement' that appears in Polanyi's most famous work, The Great Transformation, this article demonstrates how these governing principles might be useful in explaining both the complex cultural political economy of English football and the possibilities that exist for the AMF movement to socially re-embed the modern game.
Sociology
Keywords: English football; athletic clubs; cultural political economy; soccer; sociology of sport; sports - social aspects; sports spectators; supporters

"Social Freedom" in the Twenty-First Century: Rereading Polanyi - Cangiani, Michele (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Karl Polanyi's analysis of the genesis, crises, and institutional transformations of contemporary society is grounded on a theory of the basic features and dynamics of capitalism as a peculiar form of society. This article intends to develop this thesis on the basis of a reading of Polanyi's The Great Transformation, with references to Polanyi's preceding and later research. Polanyi's theoretical and methodological achievements suggest a wide comparative outlook and offer a critique of economics, in addition to being deeply connected with his political philosophy. Polanyi's approach seems to be nearer to the original institutional thought – from Karl Marx to Thorstein Veblen, from Max Weber to Adolf Löwe and Karl William Kapp – than to current neo-institutional tendencies in economics, sociology, and historiography. The hard problems society presently faces suggest the need to adhere to Polanyi's radical point of view – that is, to a radical approach to Polanyi's thought.
History; Economics
Keywords: Poor Law; WEBER; Max; 1864-1920; capitalism; comparative analysis; economic policy; economic systems; freedom in a complex society; institutional method; market society

Why TTIP is an unprecedented geopolitical game-changer, but not a Polanyian moment - Eliasson, Leif Johan; García-Duran, Patricia (Journal of European Public Policy, 2017)
This contribution argues that the Transatlantic Trade and Investment Partnership (TTIP) is unprecedented, not because it constitutes a Polanyian moment, but rather because it offers an alternative to multilateralism through the World Trade Organization (WTO). Never before has bilateralism offered such a 'best alternative to no agreement' (BATNA) to members of the core decision-making body of the WTO negotiating arm, making TTIP an unprecedented geopolitical game-changer. The anti-TTIP campaign, however, has not been driven by concerns with either geopolitics or trade liberalization, but rather fears about the European Union's (EU's) bargaining power. By strategically focusing on the potential impact on public policy and safety standards, normative arguments promulgated by opponents reflect concerns with perceived threats to the status quo and a willingness to preserve the same. The United States is presented (implicitly) as more powerful than the EU, and therefore perceived as able to impose its preferences, which are considered too neoliberal.
Political Science
Keywords: European Union; TTIP; Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); bilateralism; free trade; geopolitics; trade

Markets, Knowledge and Human Nature: Friedrich Hayek, Karl Polanyi and Twentieth-century Debates on Modern Social Order - Innset, Ola (European History Quarterly, 2017)
The article reads the works of Friedrich Hayek (1899-1992) and Karl Polanyi (1886-1964) in the light of their political commitments to neoliberalism and socialism respectively. It argues that both thinkers were inspired to explain history and recent events in line with these commitments in their 1944 publications, The Road to Serfdom and The Great Transformation. Furthermore, they both developed their most significant insights by attempting to counter perceived challenges from political projects to which they were opposed. Polanyi spent much of his life trying to disprove a liberal attack on socialism as out of touch with the realities of human nature, whereas it was in debates with socialists that Hayek developed a new theory of the epistemological functioning of markets, which then became foundational for the neoliberal project. Taking into account the high-stakes politics of Vienna in the interwar years is crucial for fully understanding the social theory of these two thinkers.
History
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; human behavior; knowledge; markets; neoliberalism; social order; socialist accounting; socialist calculation debate; totalitarianism

Fictitious Freedom: A Polanyian Critique of the Republican Revival - Klein, Steven (American Journal of Political Science, 2017)
Prominent republican theorists invoke anonymous orders such as the market as mechanisms that secure freedom as non-domination. Drawing on Karl Polanyi's account of fictitious commodities and demonstration of the impossibility of a just and rational market society, this article critically scrutinizes neo-republican assumptions regarding the market, develops an alternate social theory within which to situate the ideal of non-domination, and illustrates the importance of this reconfiguration for the kind of collective agents and political strategies that can be expected to advance republican freedom in the economy.
Political Science
Keywords: Polanyi - political & social views; economic liberty; markets; republicanism; social theory

Unpacking the objectives and assumptions underpinning European aquaculture - Ertör, Irmak; Ortega-Cerdà, Miquel (Environmental Politics, 2017)
Increasing demand for seafood and the lack of growth of capture fisheries have boosted aquaculture growth worldwide. However, European aquaculture has been stagnating over the past decade, and European public authorities have been developing policies and strategies in efforts to reverse this. Aquaculture discourses in the European Union, based on 34 policy, planning, and strategy documents, are examined and a discourse analysis conducted following Bacchi's WPR (What is the Problem Represented to be?) approach. How the problems in these discourses are represented, the tensions among main objectives, and the implicit assumptions are unveiled, and discussed employing a Polanyian theoretical framework. Taking these assumptions for granted leads to a disembedded understanding of aquaculture, and facilitates the privatization of aquatic space and resources. The analysis contributes to the literature establishing the link between the expansion of aquaculture and the enclosure of aquatic resources and enriches environmental and political debates on European aquaculture.
Environmental Science
Keywords: Europe; European Union law; aquaculture; aquatic resources; discourse analysis; enclosures; environmental politics; fisheries; fishery policy; government policy; privatization

Polanyi for the Age of Trump - Krippner, Greta R. (Critical Historical Studies, 2017)
It is no exaggeration to say that Fred Block and Margaret Somers are almost singlehandedly responsible for reviving interest in Karl Polanyi’s intellectual and political legacy in American sociology. Their contribution has consisted not only in reminding sociologists of the power of Polanyi’s analysis of the rise of market society to make sense of our troubled times but even more importantly in resolving many of the difficult theoretical tangles that Polanyi gets himself into in the course of developing this analysis. Now their various essays, written over three decades, have been revised for publication in a single volume, supplemented with several new essays that introduce novel themes and also attempt to apply Polanyi’s conceptual apparatus to current social and political problems. 1 As a compilation of essays, the resulting volume defies easy summary—and I won’t attempt to offer a full treatment of the many important …
History; Sociology
Keywords: United States; capitalism; economic policy; free enterprise; historical sociology; market ideology

Commodifying art, Chinese style: The making of China’s visual art market - Zhang, Jun (Environment & Planning A, 2017)
The economic value of art to cities and regions has recently been vigorously pursued and actively studied. The rapid ascendance of China as a superpower in the global art market and associated transformation of China’s art space, however, are yet poorly understood. This paper develops a Polanyian framework to interpret the spatial and institutional evolution of China’s art market, seeing the (de)commodification of art as a cumulative process embedded in geo-historical interplays of triple logics—cultural, capital, and political, unfolding within, and reshaping in turn, historically inherited spatial structures.
Geogrpahy
Keywords: China; Chinese art; art - economic aspects; art industry; art market; commodification; cultural and creative industries; public art spaces

Re-reading Friedrich Hayek and Karl Polanyi in the Late-Modern Condition of Fragility - Cha, Taesuh (Political Studies Review, 2017)
The cardinal role of complexity in Friedrich Hayek’s theory of the market has hardly gone unnoticed. Indeed, there is now a considerable corpus of literature that has established the importance of spontaneity as a central concept around which neoliberal economic theory revolves. However, as William Connolly analyzes, its closed conception of economic processes simplifies real economic volatilities and ignores both modes of self-organization and creativity found in democracy and social movements that periodically irrupt into market processes. This article builds upon this critique of neoliberalism and employs Karl Polanyi’s genealogy of modern capitalism to understand historical imbrications between the market and the social and their contribution to the fragility of capitalism. Polanyi’s notions of “(dis-)embeddedness” and the “double movement” not only show us a more “complex” view of modern political economy but also provide us with important lessons for political responses to the recent crisis of neoliberal capitalism.
Political Science
Keywords: CONNOLLY; William; Friedrich Hayek; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; capitalism; complexity (philosophy); complexity theory; fragility; genealogy

When Polanyi met Farage: Market fundamentalism, economic nationalism, and Britain's exit from the European Union - Hopkin, Jonathan (British Journal of Politics & International Relations, 2017)
The vote for Brexit is not an isolated event, but part of a wave of populist, anti-elite revolts: a new 'anti-system' politics Western democracies are experiencing, shaking the existing consensus around economic integration, free markets and liberal values. This wave takes a variety of forms, but has in common a robust, even violent, rejection of the mainstream political elites and their values, and a demand for governments to act on the sources of social and economic distress and inequality. This article views Brexit as a part of this new anti-system politics, a reaction to the decline in ideological competition in democracies and the increasing impotence of politicians to address the upheavals wrought by global free market capitalism. This reaction has become particularly acute after the financial crisis of the late 2000s, which affected Britain disproportionately, and the failure of austerity policies to revive growth, crystallising the ineffectiveness of existing policies to deal with economic stagnation and cultural change. This policy failure is compounded by a perceived refusal of politicians to engage with the broader public and a lack of real choice between the mainstream political parties. The article will present evidence that a failed policy consensus, a rise in inequality and a decline in the representativeness of political elites, rather than a resurgence of intolerance or xenophobia, are the principal causes of the Brexit vote.
Political Science
Keywords: Brexit; British economic policy - 2010-; British withdrawal from the European Union; 2016-; Europe - Foreign relations - Great Britain; European Union; Great Britain - politics & government - 2007-; economic nationalism; economics; markets; membership; nationalism; protectionism

Karl Polanyi in an Age of Uncertainty - Block, Fred; Somers, Margaret R. (Contemporary Sociology, 2017)
Sociology
Keywords: DALE; Gareth; For a New West: Essays 1919-1958 (Book); Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; book review; nonfiction; socialism

The Great Recurrence: Karl Polanyi and the crises of the European Union - Goldmann, Matthias (European Law Journal, 2017)
In his seminal 1944 book The Great Transformation, Polanyi describes the rise and fall of liberal capitalism during the long nineteenth century. Many have realised that Polanyi has a lot to tell about the European Union in the aftermath of the financial crisis. The paper begins with an overview of Polanyi's historiography of the failure of nineteenth-century liberal capitalism and his account of the four elements that helped liberal capitalism thrive, while precipitating its collapse-the idea of the self-regulating market, the gold standard, international peace and liberal constitutionalism. Thereafter, the paper describes the particular transformations that these four elements underwent in the course of European integration and after the financial crisis, with a particular focus on the case law of the Court of Justice. The paper argues that their current constellation has a destructive potential that exceeds the economic dimension of the Union and might pave the way for a much greater failure, one that might defeat Europe's greatest success: the establishment of peace. Ultimately, the paper assesses current reform proposals in light of these insights and makes a number of proposals for re-embedding the economy in society.
Law
Keywords: European Union - politics & government; European Union countries; Great Transformation; The (Book); capitalism; embeddedness

The Quest to Bring Land under Social and Political Control: Land Reform Struggles of the Past and Present in Ecuador - Goodwin, Geoff (Journal of Agrarian Change, 2017)
Land reform was one of the most important policies introduced in Latin America in the twentieth century and remains high on the political agenda due to sustained pressure from rural social movements. Improving our understanding of the issue therefore remains a pressing concern. This paper responds to this need by proposing a new theoretical framework to explore land reform and providing a fresh analysis of historical and contemporary land struggles in Ecuador. Drawing on the pioneering work of Karl Polanyi, the paper characterizes these struggles as the attempt to increase the social and political control of land in the face of mounting commodification. The movement started in the 1960s and remains evident in Ecuador today. Exploring land reform in Ecuador from this theoretical perspective provides new insight into land struggles in the country and contributes to debates over land reforms of the past and present elsewhere in the Global South.
Political Sciences; Development Studies
Keywords: Ecuador; commodification; land markets; land reform; reforms; social movements

The Second Time Around? Polanyi and Today's Fascist Tendency - Sandbrook, Richard (Peace Magazine, 2017)
Discusses the relevance of Polanyi’s double movement in light of increasing support for far-right, authoritarian and neo-fascist movements in Europe and North America. The author quotes The Great Transformation on how fascism “was rooted in a market system that refused to function” (21), however, he chooses to center his analysis on an unpublished essay of Polanyi’s entitled “The Fascist Virus”. From this, he extrapolates that fascism operates like a disease within liberal capitalism, becoming lethal when tensions between capitalism and democracy hit crisis levels and unleashing itself into the body politic (20).
Peace Studies
Keywords: fascism; right-wing populism

Producers' cooperation within or against cooperative agricultural institutions? The case of reindeer husbandry in Post-Soviet Russia - Vladimirova, Vladislava (Journal of Rural Studies, 2017)
With the advance of economic neoliberalization along with the green economy paradigm that aims to alleviate rapid climate change, discussions of the rationale of cooperative organization of food production have come to the fore. This paper contributes to the scholarly understanding of motivations for cooperative organization of production by taking up empirical illustrations from the European North of Russia, where despite expectations of privatization after the dissolution of the Soviet Union, the cooperative organization of reindeer husbandry often persists, as a heritage of the Soviet state enterprises ( sovkhozes ). The paper aims at advancing the analysis of cooperative reindeer husbandry and its rationales employing ideas within the field of substantivist economic anthropology of postsocialism that started with Karl Polanyi's vision of the embedded economy (Polanyi, 1944). Further, I have employed the ideas of the renowned study by Caroline Humphrey of Soviet state farms as total social institutions (Humphrey, 1998) as well as Stephen Gudeman's dialectical approach to the economy (Gudeman, 2001). The analysis shows that the cooperative organization of reindeer husbandry reproduces the economic and social patterns that were developed in the Soviet period, perhaps also adapting and incorporating elements of traditional indigenous social orders. Such social arrangements and the accompanying moral values are embedded in the reindeer herding economy, and it is their persistence that indigenous people achieve through adhering to cooperative values.
Anthropology; Rural Studies
Keywords: Eurasian studies; agricultural societies; agriculture - Russia; cooperative organization; embedded economy; farmers & the environment; food production - environmental aspects; reindeer farming; substantivism

Earth Incorporated: Centralization and Variegation in the Global Company Network - Haberly, Daniel; Wójcik, Dariusz (Economic Geography, 2017)
Over the past twenty years, a widening gulf has appeared between the increasingly internationalized financing arrangements of the world’s leading corporations and the persistence of nationally compartmentalized approaches to the study of corporate control. In lieu of direct empirical evidence on corporate control at the global level, the most widespread assumption is that the globalization of ownership has taken the form of an expansion of arm’s-length, market-based arrangements traditionally prevailing in the Anglo-American economies. Here, however, we challenge this assumption, both empirically and conceptually. Empirically, we show that three-quarters of the world’s 205 largest firms by sales are linked to a single global company network of concentrated (5 percent) ownership ties. This network has a hierarchically centralized organization, with a dominantglobal network coreof US fund managers ringed by a more geographically diversestate capitalist periphery. Conceptually, we argue that the this architecture can be broadly explained through a Polanyianvariegated capitalistmodel of contradictory market institutionalization, with the formation of the global company network actually a counterintuitive product of global financial marketization. In order to understand this process of network formation, however, it is necessary to extend Polanyi’s model of a double movement, mediated through political interventions in the market, to incorporate Veblenian processes of evolutionary institutional change, mediated through the market.
Geography
Keywords: asset management; asset management concentration; corporate ownership internationalization; evolutionary economic geography; evolutionary economics; financialization; global company network; globalization; sovereign wealth funds; state capitalism; stock ownership; variegated capitalism

Institutional Matrices Theory, or X- and Y-Theory: A Response to F. Gregory Hayden - Kirdina-Chandler, Svetlana (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article draws attention to issues about the institutional matrices theory (IMT) as perceived by and raised in the article by F. Gregory Hayden. To clarify the “controversial” points, I structure my response narrative along two lines. First, I present the prehistory of IMT, or X- and Y- theory, including earlier work by scientists related to the concept of institutional matrix. I connect the development of the actual IMT with the period of “perestroika” and the associated market experiments and reforms in Russia and Eastern European countries. One could see that the effects of market reforms in Russia were different in comparison with other countries in economic transition. I show that the institutional approach was accepted as more relevant to understanding the unexpected results in Russian society. I present IMT as a development of the ideas of Karl Polanyi and Douglas North to answer the challenges of explaining the real social and economic processes in Russia, as well as its wider application to a broader range of economic and social situations in different countries. Second, I then present the main IMT theses, giving special attention to the issues as perceived and raised by Hayden. In conclusion, I suggest the possibility of a joint project that combines IMT consideration and the social fabric matrix (SFM) concept of F. Gregory Hayden.
Economics
Keywords: HAYDEN; F. Gregory; Perestroika; Russia; economic policy; economics; institutional matrices theory; reciprocity

Karl Polanyi: A Life on the Left - Kurtz, Geoffrey (New Political Science, 2017)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); book review

An anthropological reading of the policies of international development: export competitiveness as a conjunctural case study - Shakya, Mallika (Dialectical Anthropology, 2017)
Drawing on ethnography of the World Bank's private sector development program, this paper explores the ways in which discussions of export competitiveness emerged in the past decade or so and how they interacted with larger discourses on solidarity and development. The immediate context within which this idea emerged was that of the structural adjustment programs (SAPs) which had maintained that the public regulation of the private economy compromises on industrial productivity (and by extension distributive social justice). But it would be naïve to think that alternative ideologies have not tried to insert themselves within the Bank's neoliberal discourse on development. If anything, discursive narratives suggest that the very notion of export competitiveness initially worked to justify the role of the state in regulating and incubating the private sector in developing countries even if these attempts became disembedded from their local contexts in the long run. This paper contextualizes this specific encounter on export competitiveness within the broader discourse of development and economic anthropology to examine the discursive politics of policy and knowledge in the global aid industry.
Anthropology
Keywords: IFIs; World Bank; anthropology; competition (economics); competitiveness; development; disembeddedness; economic liberalization; embeddedness; ethnology; human economy; structural adjustment program (SAP)

Food industry structure in Norway and Denmark since the 1990s: Path dependency and institutional trajectories in Nordic food markets - Klimek, Bjørn; Hansen, Henning Otte (Food Policy, 2017)
Structural changes in Norwegian and Danish food industry since the 1990s is analysed as a path dependent response to the neo-liberal turn. Norway entered the 1990s as a protected market and Denmark as case of an export oriented industry. These developmental strategies are rooted in early 20th century industrialisation and influenced by institutional transformations in the 1990s, such as EU and WTO. Mergers and acquisitions (M&A) are studied in the context of changing political environments. Explaining two different trajectories, we combine path dependency theories and a Polanyi inspired ‘varieties of capitalism’ framework with corporate strategy theories on food industry M&As. We identify two different types of path dependent development, a self-reinforcing in Denmark and a transformative ‘breaking point’ in Norway.
Economics
Keywords: Nordic food markets; World Trade Organization (WTO); agri-food chain; business planning; food economics; food industry - economic aspects; food industry structure; food marketing; food mergers and acquisitions (M&A); food policy; food supply management; institutional change; path dependency

Free market ideology and deregulation in Colorado’s oil fields: Evidence for triple movement activism? - Malin, Stephanie A.; Mayer, Adam; Shreeve, Kelly; Olson-Hazboun, Shawn K.; Adgate, John (Environmental Politics, 2017)
Unconventional oil and gas extraction (UOGE) has spurred an unprecedented boom in onshore production in the US. Despite a surge in related research, a void exists regarding inquiries into policy outcomes and perceptions. To address this, support for federal regulatory exemptions for UOGE is examined using survey data collected in 2015 from two Northern Colorado communities. Current regulatory exemptions for UOGE can be understood as components of broader societal processes of neoliberalization. Free market ideology increases public support for federal regulatory exemptions for UOGE. Perceived negative impacts do not necessarily drive people to support increased federal regulation. Utilizing neo-Polanyian theory, interaction between free market ideology and perceived negative impacts is explored. Free market ideology appears to moderate people’s views of regulation:increasingthe effect of perceived negative impacts while simultaneously increasing support forderegulation. To conclude, the ways in which free market ideology might normalize the impacts of UOGE activity are discussed.
Sociology
Keywords: Colorado; deregulation - government policy; double movement; environmental sociology; fracking; free enterprise; free markets; gas extraction; hydraulic fracturing; market ideology; neoliberalism; oil fields; public support; triple movement; unconventional oil and gas production

CSR as a legitimatizing tool in carbon market: Evidence from Latin America’s Clean Development Mechanism - Benites-Lazaro, L.l.; Mello-Théry, N.A. (Journal of Cleaner Production, 2017)
Clean Development Mechanism (CDM) has incorporated sustainable development as one of their objectives. This objective gives companies an increasing motivation to contribute to sustainable development through their corporate social responsibility (CSR). However, perceived profitability of companies with carbon commodification were negatively associated with CDM projects. This paper aims to identify CSR activities in CDM in three Latin American countries, namely, Brazil, Mexico, and Peru and understand the drivers behind of these CSR initiatives. The study is based on the evaluation of 593 projects registered and Polanyi’s theory. We identified some CSR activities corresponding to the social, environmental and economic indicators in the three countries. This is not to say that all CDM developers are acting in a socially responsible manner. Certain CSR activities in most of the cases were implemented as a way to legitimize and as a means to achieve social acceptance.
Environmental Studies; Sustainability Studies
Keywords: CSR; Latin America; carbon dioxide mitigation; clean development mechanism; corporate legitimacy; corporate social responsibility; double movement; double-movement; economic aspects; embeddedness; emission control; social acceptance; social responsibility of business

Fixing network failures? The contested case of the American Manufacturing Extension Partnership - Brandt, Philipp; Whitford, Josh (Socio-Economic Review, 2017)
The article uses a case study of the American Manufacturing Extension Partnership to explore economic and industrial policy in the contemporary USA. Extensive quantitative and qualitative data are mobilized to show that: (a) the agency is pressured politically to limit its activities to 'blunt' remedies for identifiable 'market failures'; even as (b) regional centers in fact often orient also, and sometimes instead, toward 'coordination-oriented' policies to mitigate 'network failures'; and (c) these latter generate better results, on average, for client manufacturers. The findings challenge neo-institutional claims that economic policies are most effective only when complementary to the dominant institutional coordinating capacities embedded in the existing American political economy, or when they have the exceptional support of the American security establishment. They are, however, consistent with an alternative neo-Polanyian approach that explains when and how streetlevel policymakers dispersed across American federalism sometimes sidestep the ideological hegemony of 'market fundamentalism'.
Sociology
Keywords: United States; economic policy; embeddedness; industrial organization; industrial policy; institutional complementarity; manufactures; market failure; market fundamentalism; partnership (business); public policy; regional economies

Karl Polanyi: A Life on the Left - Innset, Ola (European History Quarterly, 2017)
History
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); nonfiction

It's not the Cases, It's the System - Koskenniemi, Martti (Journal of World Investment & Trade, 2017)
M. Sornarajah's recent analysis of investment arbitration as an offshoot of 'neoliberalism' is basically correct. But it attaches too much importance to the bias of the arbitrators and the procedural problems in arbitral practice. The controversy over the Trans-Pacific Partnership (TPP), the Transatlantic Trade and Investment Partnership (TTIP) and investment arbitration generally is not about the niceties of arbitral procedure, the discretion of arbitrators or the pros and cons of the European Union proposed 'investment court'. The significance of investment arbitration has to do with the many ways in which already the very presence of a 'dis-embedded' and one-sided system of claims automatically skews public policies in favour of foreign investors. The juristic debate is but the surface of struggle over the role of public power and democratic governance of domestic and global economy.
Law
Keywords: General Agreement on Tariffs and Trade (GATT); Sornarajah; Trans-Pacific Partnership (TPP); Transatlantic Trade and Investment Partnership (TTIP); World Trade Organization (WTO); arbitration & award lawsuits; fair and equitable treatment; investment arbitration; investments - lawsuits & claims; neoliberalism

Reproducing spaces of embeddedness through Islamic NGOs in Sub-Saharan Africa: reflections on the post-2015 development agenda - Tok, M. Evren; O’Bright, Ben (African Geographical Review, 2017)
This paper explores the nexus of religion, space, and development. It sheds light on the role of faith-based organizations (FBOs) as partners in sustainable development and key actors for achieving the Sustainable Development Goals in sub-Saharan Africa (SSA). Applying and building on the theoretical framework of Polanyi’sThe Great Transformationindicates that FBOs with value-laden agendas have formed new state spaces during the age of globalization, where state capacities are transferred to non-state actors at other levels. The case study of Qatari organizations in SSA demonstrates how their uptake of state capacities can lead to development efforts that are driven by faith apart from politics and economics, which help balance market liberalism and social protectionism to create the conditions for sustainable development. Among other things, FBOs offer alternative financing options and new opportunities for financial inclusion that are relevant to the implementation of the post-2015 development agenda.
Geography; African Studies
Keywords: Africa; Qatar; development; economic development; embeddedness; faith based NGOs; faith based human services; state spaces; sustainable development

Finance proud and industry vulnerable: When governments fail to defend the economic realm, citizens revolt - Pettifor, Ann (Juncture, 2017)
The subordination of society to self-regulating international markets is the reason why British workers and industries so often fall prey to predatory financiers, writes Ann Pettifor. It is also a fundamental cause of current political crises throughout the west – just as Karl Polanyi described almost 80 years ago.
Economics
Keywords: private equity firms; self-regulating market

Re-dynamising Local Economies in the Age of Trumpism - Bauwens, Michel; Niaros, Vasilis (Journal of Futures Studies, 2017)
The article presents the authors' arguments on the political and policy response behind the rise of Trumpism according from the analysis of authors Kojin Karatani, Karl Polanyi and Mark Blyth. Topics discussed include Karatani's book "The Structure of World History" on the integration of modalities for political and economic system, Polanyi's analysis in the book "The Great Transformation" on the systemic balance and the transition in regimes of value for re-alignment of modalities.
Futures Studies
Keywords: BLYTH; Mark; Futures studies; Great Transformation; The (Book); KARATANI; Kojin; Structure of World History: From Modes of Production to Modes of Exchange; The (Book); TRUMP; Donald; Trumpism; disembeddedness; local economies; technology

Polanyi and Foucault on the Issue of Market in Classical Political Economy: Complementary Approaches to the Radical Theory of Social Control - Guizzo, Danielle; de Lima, Iara Vigo (Review of Radical Political Economics, 2017)
Studies have pointed out that the value of markets is related to their impact on the character of a society. Karl Polanyi's thesis about social disembeddedness attributed to 19th century economic liberalism the responsibility for consolidating the process of separating markets from society, which changed the dynamics between the state and population when economic rationality began dictating their connections. However, Polanyi only suggested analyses regarding power relations between these three elements and their effects on the social context. This paper argues that Michel Foucault's writings concerning technologies of power and biopolitics complement Polanyi's considerations insofar as they provide an understanding about how biopolitics emerged and how this led to a new posture of the state regarding population care and economic environment regulation.
Economics
Keywords: FOUCAULT; Michel; 1926-1984; biopolitics; classical economic liberalism; embeddedness; liberalism; political science; sociobiology; socioeconomic theory; socioeconomics

Lawyers’ Empire and The Great Transformation - Harris, Douglas C. (International Journal of the Legal Profession, 2017)
A literary criticism of the book "Lawyers' Empire: Legal Professions and Cultural Authority" by Canadian lawyer W. Wesley Pue is presented. It outlines economic historian Karl Polanyi's assumption of Great Transformation in Western Europe that made the period of Pue's book long. It examines lawyers being innovators in Canada.
Law
Keywords: Canada; Lawyers' Empire: Legal Professions & Cultural Authority (Book); PUE; W. Wesley; Western Europe; lawyers

Karl Polanyi on economy and society: a critical analysis of core concepts - Hodgson, Geoffrey M. (Review of Social Economy, 2017)
The article presents the views of economic historian Karl Polanyi on the nature of economic and social embeddedness. Topics discussed include relationship between the economic and social embeddedness, the impact of the market economy, the transformation of society and production of material goods. Particular focus on limits of privatization, commodification, and marketization.
Economics
Keywords: business; capitalism; commodification; economic; economic activity; embeddedness; markets; social

The four modes of coexistence in social systems - Nechansky, Helmut (Kybernetes, 2017)
Purpose The paper aims to relate the four modes of coexistence of goal-orientated systems – conflict, hierarchy, the niche and cooperation – to static behavioral descriptions of social systems.Design/methodology/approach Analyzing the options for interactions of goal-orientated systems leads the four modes of coexistence. These show certain behavioral characteristics. Searching for these characteristics in selected behavioral descriptions in organizational theory, sociology, political science and system science allows relating them to certain modes.Findings In organizations, the four modes of coexistence show in general (Cameron and Quinn) and dyadic interaction patterns (Argyris). In sociology, they show in educational schemes preparing for specific modes (Bernstein) and in different exchange patterns (Polanyi). In political theory, the four modes of coexistence show in preferred policies of parties, in institutional development, in oligarch power politics (Winters) and in external policy. In system science, they show in problem solving strategies (Jackson) and “mindscapes” (Murayama).Research limitations/implications The analysis is restricted to static patterns leaving out dynamic developments, for example, in networks.Practical implications Together with previous investigations, the paper shows how behavioral descriptions ranging from psychology to politics correspond to the four modes of coexistence, and it suggests interrelations and alignments of the modes via various levels of societal organization.Originality/value The four modes of coexistence provide an unequivocal theoretical framework that allows finding parallels in behavioral descriptions ranging from psychology via sociology to politics.
Sociology
Keywords: business planning; cybernetics; decision making; decision-making; forms of integration; industrial organization (economic theory); interaction; politics; redistribution; sociology; systems theory

Urban Governance in Africa Today: Reframing, Experiences, and Lessons - Obeng-Odoom, Franklin (Growth & Change, 2017)
Progress in analysing the instrumental view of governance as an engine for growth, poverty reduction, and inclusive development has been held back by the difficulty in framing governance. This essay seeks to address this problem by 1) reframing urban governance 2) evaluating its aims, processes, and outcomes, and 3) explaining those outcomes on the basis of which some lessons are teased out. Using examples from Africa and an institutional political economy approach (based on institutional economics, Marxist political economics, Georgist political economics, and Polanyian political economy), I show that, overall, while urban economies are growing; both urban poverty and inequality levels have risen substantially. Urban governance has paved the way for new forms of urban development that only benefit the few. Not only are there differences in how urban services and resources are experienced, accessed, and controlled but the varieties are also socially differentiated. I argue that the underlying reasons for this disjuncture between 'urban governance' in theory and 'actually existing urban governance' are 1) difficulties in implementing urban governance theory consistently in practice, 2) problems arising because urban governance theory has been implemented in practice, 3) tensions that would entangle most policies which do not address historical and structural economic issues, 4) restrictive assumptions, and 5) incoherence among the different dimensions of urban governance. To resolve these contradictions, I put the case for major structural and institutional change involving: 1) the re-ordering of the roles of the state, market, and society as institutions of change; 2) re-working the relationships that bind together land, labour, capital, and the state, and 3) re-organising the channels for keeping the attainment of the ends of urban governance in check.
Development Studies
Keywords: Africa; economic development; economic policy; labor; labour; poverty reduction; public administration

Karl Polanyi: a life on the left - Payne, Anthony (International Affairs, 2017)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); POLANYI; Karl; 1886-1964; biography; book review; economists; nonfiction

Market Liberalism, Marginalised Citizens and Countermovements in India - Sahoo, Sarbeswar (Asian Studies Review, 2017)
How has neo-liberalism transformed the economic structure and policies of India? And what are the politico-economic implications of such policies for marginalised populations? Following Karl Polanyi’s theory of “double movement”, this paper argues that while market liberalism has helped India overcome the slow so-called “Hindu rate of growth”, it has adversely affected the economic interests of the poor. It further argues that the expansion of the market (first movement) has led to various social dislocations in the lives of the poor. Such dislocations have generated several countermovements (second movement), which have found expressions not just in electoral politics but also in various grassroots movements. While it may be true that such countermovements have not always been successful in overturning the tide of neo-liberalism, they have certainly influenced the policy priorities of the state in favour of the poor and the marginalised in India.
Area Studies; Asian Studies
Keywords: India; countermovement; double movement; economic policy; grassroots movements; neoliberalism; political mobilisation; social dislocation; social marginality; social welfare

‘Hipster Capitalism’ in the Age of Austerity? Polanyi Meets Bourdieu’s New Petite Bourgeoisie - Scott, Michael (Cultural Sociology, 2017)
This article dialogues Polanyi and Bourdieu to propose a new research agenda within the sociology of cultural production. Extending recent literature on hipsters, this iconic figure is shifted from the world of consumption to the world of production via Bourdieu’s conceptualisation of the new petite bourgeoisie. Using secondary empirical material of cultural micro-enterprises, two ideal-typical career strategies are sketched: cultural-capital oriented seeking to secure positions within established creative industries, and economic-capital orientated stylising ‘old’ petite bourgeoisie occupations to access economic returns. However, within the context of ongoing austerity policies, Bourdieu’s economic capital does not fully account for the variegated forms of material resources these nascent enterprises draw on. Bringing Polanyi’s modes of economic integration – reciprocity, redistribution and exchange – to Bourdieu opens new questions on how hipster capitalism is the practice of intermediating between these ‘backstage’ material modes and the ‘frontstage’ selling of style.
Sociology
Keywords: BOURDIEU; Pierre; 1930-2002; austerity; capitalism; cultural capital; cultural production; cultural sociology; hipster; hipsters (subculture); micro-enterprise; modes of economic integration; new cultural economy; new petite bourgeoisie

Cooperate! A paradigm shift for health equity - Wei-Ching Chang; Fraser, Joy H. (International Journal for Equity in Health, 2017)
The role of competition and cooperation in relation to the goal of health equity is examined in this paper. The authors explain why the win-lose mentality associated with avoidable competition is ethically questionable and less effective than cooperation in achieving positive outcomes, particularly as it relates to health and health equity. Competition, which differentiates winners from losers, often with the winner-takes-all reward system, inevitably leads to a few winners and many losers, resulting in social inequality, which, in turn, engenders and perpetuates health inequity. Competitive market-driven approaches to healthcare–brought about by capitalism, neo-liberalization, and globalization, based primarily on a competitive framework–are shown to have contributed to growing inequities with respect to the social determinants of health, and have undermined equal opportunity to access health care and achieve health equity. It is possible to redistribute income and wealth to reduce social inequality, but globalization poses increasing challenges to policy makers. John Stuart Mill provided a passionate, philosophical defense of cooperatives, followed by Karl Polanyi who offered an insightful critique of both state socialism and especially the self-regulating market, thereby opening up the cooperative way of shaping the future. We cite Hannah Arendt's "the banality of evil" to characterize the tragic concept of "ethical fading" witnessed in business and everyday life all over the world, often committed (without thinking and reflecting) by ordinary people under competitive pressures. To promote equity in health for all, we recommend the adoption of a radically new cooperation paradigm, applied whenever possible, to everything in our daily lives.
Health Studies; Medicine
Keywords: capitalism; competition; competition (psychology); cooperation; cooperative movement; cooperativeness; ethical fading; health & social status; health equity; health services accessibility; health status indicators; interpersonal relations; paradigm shift; paradigms (social sciences)

From supply management to agricultural subsidies—and back again? The U.S. Farm Bill & agrarian (in)viability - Graddy-Lovelace, Garrett; Diamond, Adam (Journal of Rural Studies, 2017)
Farm subsidies have become increasingly maligned in agricultural policy debates, but the merits of subsidies are a distraction from deeper political, economic, and ecological problems in agriculture. Drawing on a history of the U.S. Farm Bill, this paper argues that a fixation on farm subsidies ignores why they came into being, and more generally glosses over the imperative for modern states to intervene into agricultural economies. Karl Polanyi's 'double movement' framework is used to situate the rise and fall of agricultural supply management within food regime theory. In the second, or surplus food regime, the U.S. government wielded excess commodities as geopolitical tools—even as domestic farm policy labored to contain overproduction, and thus support agrarian viability. In the subsequent corporate food regime, “free market” agriculture displaces and discredits supply management, even as massive government intervention into how food is grown and sold continues. Making space to remember historical price support programs, to situate their accomplishments and limitations, and to recognize residual supply-management mechanisms (such as farm cooperatives and agricultural marketing orders) is crucial for fostering agricultural viability in the US and beyond. Twentieth century supply management had flaws, but it cannot be wholly omitted. This paper highlights key motivations, elements, and contradictions of these policies and programs to begin the process of considering how supply management principles and strategies could be updated and enhanced for 21st century agriculture. Such a framework would need to pay more attention to diversity within domestic and international agricultures, and be more sensitive to the multi-scalar dimensions of food systems.
Geography
Keywords: agricultural economics; agricultural subsidies; agriculture & state; business food service; food supply

The Anthropocene and anthropology - Hann, Chris (European Journal of Social Theory, 2017)
Noting a lack of consensus in the recent literature on the Anthropocene, this article considers how social anthropologists might contribute to its theorizing and dating. Empirically it draws on the author’s long-term fieldwork in Hungary. It is argued that ethnographic methods are essential for grasping subjectivities, including temporal orientations and perceptions of epochal transformation. When it comes to historical periodization, however, ethnography is obviously insufficient and proposals privileging the last half-century, or just the last quarter of a century, seem inadequate. Influential theories, which define ‘modernity’ in terms of developments emanating from the countries of the North Atlantic in the sixteenth to the nineteenth centuries (Gellner, Polanyi, Wolf), remain partial and Eurocentric. To comprehend the social preconditions of the Anthropocene in a holistic fashion (the crucial contribution of comparative anthropology), it is necessary to follow Jack Goody and trace how the urban revolutions of the Bronze Age united Eurasia through the diffusion of new forms of economy, polity and cosmology.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; Hungary; anthropocene; anthropocene epoch; anthropology; cosmology; ethnology; social anthropology; socialism

State–peasant movement relations and the politics of food sovereignty in Mexico and Ecuador - Henderson, Thomas Paul (Journal of Peasant Studies, 2017)
This contribution argues that the articulation between the state and peasant organizations’ internal structures – the class characteristics of their mass bases, their leaderships and the modes of interaction between the two – is critical for determining the nature of contemporary struggles guided by the discourse of food sovereignty. It will show that that counter-hegemonic demands are not synonymous with counter-hegemonic practice; rather than struggling to replace the neoliberal food regime, many peasant organizations employ the food sovereignty discourse as a political tool in their negotiations with the state in order to access resources from within the prevailing neoliberal model, not to transform it.
Development Studies
Keywords: GRAMSCI; Antonio; 1891-1937; Via Campesina; agriculture & state - Ecuador; agriculture & state - Mexico; food regime; food sovereignty; hegemony; peasant organizations; peasant studies

Brexit and its Consequences - Pettifor, Ann (Globalizations, 2017)
In this brief essay, I argue that the ‘Brexit’ vote is but the latest manifestation of popular dissatisfaction with the utopian ideal of autonomous markets beyond the reach of regulatory democracy. Brexit represented the collective, if (to my mind) often misguided, efforts of those ‘left behind’ in Britain to protect themselves from the predatory nature of market fundamentalism. In a Polanyian sense, it is a form of social self-protection from self-regulating markets in money, trade and labour.
Economics
Keywords: BREXIT Referendum; 2016; Brexit; business; countermovement; democracy; double movement; financialization; markets; utopias

Financialization and Society's Protective Response: Reconsidering Karl Polanyi's Double Movement - Watkins, John P. (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Financialization challenges Karl Polanyi's thesis of double movement, the thesis that efforts to extend the market evoke efforts to protect humans, nature, and means of production from market forces. Financialization refers to the increased power of financial institutions. The government protects the incomes and assets of financial institutions, but it does little to protect the incomes and assets of households, which are necessary for people to afford healthcare, education, emergencies, retirement, and so on. Polanyi criticized nineteenthcentury civilization for transforming land, labor, and the means of production into commodities, using economic insecurity to motivate humans. The development of intangible property allowed business to expand the market in two ways: (i) restricting output to drive up profits and (ii) liquefying consumer assets to provide credit to consumers to increase spending. The implications of that process manifested themselves in the financial crisis of 2008. Market capitalism represented the attempt to organize commodities based on economic rationality. Similarly, the twentieth- and twenty-first-century capitalism represents the effort to "rationally" organize society according to the value of intangible assets. Both efforts failed, indicating the continued relevance of Polanyi's thesis.
Economics
Keywords: asset management; commons; double movement; financial services industry; financialization; global financial crisis; 2008-2009; intangible property; socioeconomic factors

Reviving Hayek’s Dream - Worth, Owen (Globalizations, 2017)
This short piece suggests that the roots of the successful Brexit vote can be found in the free market purity that was implicit within the ideals behind Thatcherism. Whilst the rhetoric of populist and British (or in many parts English) nationalism were utilised in order to win support, the ideological driving force implicit within many Brexit figureheads rested in the belief that the EU watered down their visions of a harder neoliberal reality. Yet, by stimulating right-wing reactionary forces, they may have created more than they bargained for. I concur with Karl Polanyi that free market liberalism tends to generate the forces of its own demise.
Political Science
Keywords: Brexit; Brexit Referendum; 2016; free enterprise; liberalism; market idealism; neoliberalism; populism; the far right

The Elusive Karl Polanyi - Luban, Daniel (Dissent (00123846), 2017)
The article focuses on author Karl Polanyi and his works including "Origins of the Cataclysm," "Freedom from Economics" and "The Liberal Utopia." It mentions the role Polanyi and his works during the Great Recession and in the analysis of the social movement in the age of Porto Alegre and Seattle as they can be compared to a totem for social democracy such as Karl Marx for communism and Hayek for neoliberalism. It adds that during the Great Recession, Polanyi was considered a master theorist of the welfare state. It also cites Polanyi as a social leader and an uneasy fit to a social order.
N/A
Keywords: Liberal Utopia; The (Book); MARX; Karl; 1818-1883; Origins of Cataclysm; authors; authorship; communism; social democracy; social movements

Deindustrialisation and the Historical Sociological Imagination: Making Sense of Work and Industrial Change - Strangleman, Tim (SOCIOLOGY-THE JOURNAL OF THE BRITISH SOCIOLOGICAL ASSOCIATION, 2017)
Following recent calls for a more self-aware and historically sensitive sociology this article reflects on the concept of deindustrialisation and industrial change in this spirit. Using EP Thompson’s classic The Making of the English Working Class and his examination of industrialising culture with its stress on experience, the article asks how these insights might be of value in understanding contemporary processes of deindustrialisation and work. Drawing on a range of sociological, cultural and literary studies it conceptualises the differences and similarities between two historic moments of industrial change and loss. In particular it draws on the literary concept of the ‘half-life of deindustrialisation’ to explore these periods. The article has important implications for how we think about contemporary and historical industrial decline.
Sociology
Keywords: THOMPSON; E. P. (Edward Palmer); 1924-1993; half-life of deindistrialisation; historical sociology; work meaning and identity

Progressive Responses to Populism: A Polanyian Critique of Liberal Discourse - Yarrow, David (The Political Quarterly, 2017)
This article explores the recent rise of populist politics from the perspective of Karl Polanyi's theory of the ‘double movement’. It firstly introduces Polanyi's understanding of interwar populism, and relates this to his broader critique of liberal economic thought. This framework is then used to analyse three prominent explanations for populism which emerged in the wake of the UK's 2016 EU referendum: globalisation; cultural reaction; and social media. I show how each of these explanations exogenises contemporary populist movements, narrating them as something external to the liberal economic restructuring pursued globally since the 1980s. Failing to diagnose adequately the causes of contemporary populist movements, which lie in this utopian attempt to treat labour as a commodity, they cannot support an intellectually coherent progressive response to Brexit. Finally, I outline a political agenda centred on labour de-commodification, which could directly address populist grievances and reclaim the discourse of ‘taking back control’ for the left.
Political Science
Keywords: Brexit; commodification; double movement; labour; liberal discourse; populism

Reintegrating economy, society, and environment for cooperative futures: Polanyi, Marx, and food sovereignty - Tilzey, Mark (Journal of Rural Studies, 2016)
This paper attempts to ‘put in their place’ (Sum and Jessop 2013) some key issues that frame the question of ‘the more-than-economic dimensions of co-operation’. In particular, it asks why capitalism deconstructs socio-natural reality into the ‘common-sense’ and discrete institutional spheres of ‘economy’, ‘society’ and ‘environment’, an institutional constellation in which the ‘economy’ is usually afforded pre-eminence. Building on this, the paper further asks: why does the organization of society around the commodity form, and specifically around the generalization of the commodity form to labour-power that is the defining feature of capitalism, have the tendential effect of fragmenting, atomizing, and marginalizing social collectivities and cooperative behaviour? This question is answered through examination of the work of Polanyi and Marx, arguing that it is the latter who is best able to explain the nature and dynamics of capitalism, and its relationship to cooperative activity. The paper elaborates the Marxian approach and suggests strong linkages with the ‘radical’ fraction of the food sovereignty movement. The latter, like Marx, appears to invoke unconstrained cooperation as ‘actual’ autonomy; the paper asks what the political and ecological prerequisites for the realization of this social imaginary might be.
Rural Studies; Agroecology
Keywords: MARX; Karl; 1818-1883; agroecology; cooperation; food sovereignty; political ecology; rural studies

Karl Polanyi: A Life on the Left - Moravcsik, Andrew (Foreign Affairs, 2016)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); biography; book review; nonfiction; sociologists

Think tanks and the pressures for planning reform in England - Haughton, Graham; Allmendinger, Phil (Environment & Planning C: Government & Policy, 2016)
This article examines how advocacy think tanks have sought to influence the remaking of the English planning system. Pressure for planning reform has come particularly though not exclusively from the political right, which has sought to portray planning as a form of bureaucratic regulation, out of touch with the needs of modern, global economies and the needs of society. This research involved 27 interviewees, the majority of whom have worked in think tanks, whilst others worked in government or in advocacy and professional groups. We explore how despite years of critique and many reforms to the planning system, it is still portrayed as failing. Drawing on ideas around the experimental state, we seek to develop a better understanding of the dynamics behind the process of continuous calls for planning reform before turning to some of the implications for both planning and our understanding of how think tanks seek to influence policy.
Geography
Keywords: advocacy groups; environmental protection planning; experimental state; markets; planning reform; political reform; research institutes; think tanks

Moral economy: Rethinking a radical concept - Palomera, Jaime; Vetta, Theodora (Anthropological Theory, 2016)
This article argues that the original thrust of the moral economy concept has been understated and attempts to cast it in a new light by bringing class and capital back into the equation. First, it reviews the seminal works of Thompson and Scott, tracing the origins of the term. It deals with the common conflation of moral economy with Polanyi’s notion of embeddedness, differentiating the two concepts and scrutinizing the ways in which these perspectives have been criticized. Second, it dispels dichotomist conceptions separating economic practice from morality, or embedded configurations from disembedded ones. Against binary views of the market as a boundless realm penetrating previously untainted moral spheres, it posits that social reproduction is characterized by an entanglement of values, which can only be fully grasped by delineating the contours and characteristics of capital accumulation. Third, it contends that moral economy is a dynamic concept because it accounts for class-informed frameworks involving traditions, valuations and expectations. Finally, it argues that moral economy can enrich the concept of hegemony because it pays attention to the often-contradictory values that guide and sustain livelihood practices, through which cultural domination is reproduced or altered.
Anthropology
Keywords: SCOTT; James C.; THOMPSON; E.P.; capital; class; economics - moral & ethical aspects; embeddedness; hegemony; moral economy; saving and investment; social reproduction

Counterbalancing marketization informally: Georgia’s new-institutionalist reform and its discontents - Rekhviashvili, Lela (Debatte: Review of Contemporary German Affairs, 2016)
Discussing the case of institutional change and its discontents in the Georgian context, this article critically engages with one of the most influential perspectives on informal economic practices, namely the new institutionalist perspective. The examination of the responses to the new-institutionalist remedies reveals counterintuitive outcomes to allegedly successful market-enhancing reforms. The reforms were resisted and they failed to deliver the promise of improved entrepreneurial opportunities and eased social vulnerability. I suggest that the new-institutionalist prescriptions result in counterintuitive outcomes as they are based on two misleading assumptions. First, they read informal practices as a priori market-like and second, they see the transition to a market economy as a relatively harmonious process. I argue that, informal economic practices are not necessarily market-like, nor is the establishment of market-enhancing reforms uncontested by informally operating actors. Instead, the persons operating informally draw on non-commodified resources and suffer significant social and economic losses when the state-supported process of marketization deepens. The process of adjusting to marketization and coping with its costs inevitably involves elaboration of practices and interventions that defy and contradict the market logic. Precisely, this dismissal of the need for non-market-based solutions in current theory and practice leads to informalization of the resistance against marketization.
Political Science
Keywords: Eastern Europe; Georgia; Polanyian institutionalism; informal economic practices; informal sector (economics); marketization; markets; new-institutionalism; organizational change

Climate change and the welfare state? Exploring Australian attitudes to climate and social policy - Spies-Butcher, Ben; Stebbing, Adam (Journal of Sociology, 2016)
Despite growing evidence of significant impacts from human-induced climate change, policy responses have been slow. Understanding this policy inertia has led to competing explanations, which either point to the need to build a consensual politics separated from economic partisanship, or which encourage solidarities between environmental and social movements and issues. This article analyses a recent successful mobilisation, leading to the passage of the Clean Energy Act in Australia, to explore the relationship between attitudes to environmental and social protection, particularly among the core constituency in favour of stronger climate action. Using social survey data from the Australian Election Study, the article finds evidence of independent associations between prioritising environmental concerns and support for welfare state expansion, and a realignment of materialist and post-materialist values. This we argue is consistent with Polanyian analysis that posits a link between social and environmental causes based on resistance to commodification.
Sociology
Keywords: clean energy; climate policy; climatic changes - government policy; commodification; law and legislation; political attitudes; social policy; welfare state

Polanyi and Political Consumption: A Modern Theoretical Application of the Double Movement - Frank, Phillip M. (Society for Marketing Advances Proceedings, 2016)
There has been an increase in literature on a growing field recently termed, "Political Consumption" (Baumann et al., 2015). Political consumption is defined as the choice or avoidance of products or brands with the aim of changing ethically or politically objectionable institutional or market practices (Shah et al., 2007). The following paper posits a theoretical model for the conceptualization of political consumption. Specifically, the author presents Karl Polanyi and his "Double Movement" as the underpinning theoretical conceptualization of Political consumption. The author also proposes empirical research to test such a theoretical model.
Business; Marketing
Keywords: brand choice; branding (Marketing); consumer behavior; consumption (economics); double movement; political consumption; product management

Moving targets: Carbon pricing, energy markets, and social movements in Australia - Pearse, Rebecca (Environmental Politics, 2016)
Reporting on the origins and directions of social movement strategy on climate and energy issues in the last decade, the shifts in ‘climate movement’ practice are discussed using a neo-Polanyian account of the political economy of climate change combined with sociological analysis of the strategic decisions campaigners reported making. Since the mid-2000s, Australia’s climate movement has been engaged in three concurrent arenas of political contestation. The longest-standing arena of movement activity has been negotiations over climate policy. More recently, activists and communities are engaged in a struggle over the expansion of fossil fuels. A third contest has been waged over the present and future position of renewable energy technologies in Australia’s electricity market. In the wake of climate policy failure, energy campaigns have been deepened, and it seems that a broader energy justice agenda is being forged. New strategic dilemmas are visible in the field.
Environmental Studies; Education
Keywords: Australia; carbon pricing; climate policy; climatic changes; economics; energy industries; energy markets; fossil fuels; renewable energy sources; social movements

Toward a Polanyian network analysis: market and non-market forms of coordination in the rice economy of Vietnam - Prota, Laura (Journal of Economic Geography, 2016)
The study proposes a network-based methodology linking Polanyi's ideal types of coordination and deductive blockmodeling to identify different forms of coordination within an economy. Using the proposed methodology, the economy of rice in postsocialist Vietnam is interpreted as a double movement responding to market liberalization. Qualitative and relational data were collected from 323 households and firms in two communes of the Mekong River Delta of Vietnam. Results show that in one case markets and redistribution co-existed as competing forms of coordination, entailing different relations of production and labor conditions; while in the other they blended and constituted a hybrid house-holding system.
Geography
Keywords: Vietnam; Vietnam transition; blockmodeling; corporate governance; economic coordination; embeddedness; liberalization (finance); local governance; markets; networks; rice - economic aspects; social networks

Embeddedness and migrant tourism entrepreneurs: A Polanyian perspective - Su, Xiaobo; Chen, Zhigang (Environment and Planning A, 2016)
Tourism embodies flows of tourists, capital and information, as well as migration, including migrants who operate businesses. How do migrant entrepreneurs negotiate social ties and economic activities in their destinations? To answer this question, the paper draws on Polanyi’s work on embeddedness to explore migrant tourism entrepreneurs (MTEs) and their modes of integration in the practice of social and economic life. We argue that MTEs are situated in a complex matrix in which they must build economic connections with locals and government officials, yet maintain a respectful distance with local groups, and develop embedded ties with other fellow migrants and tourists. Embeddedness, juxtaposed with distance, indicates that in tourist destinations, mixed patterns of economic and social relations significantly influence MTEs’ social and economic life. A Polanyian perspective on embeddedness can provide useful theoretical tenets to understand entrepreneurial activities in a mobile world.
Geography
Keywords: Lijiang ancient town; embeddedness; migrant tourism entrepreneurs; social and economic life; tourism production system

Karl Polanyi and the Reality of Society - Behrent, Michael C. (History and Theory, 2016)
This essay reconsiders Karl Polanyi's famous thesis about the “embeddedness” of the economy through an examination of two recent books: For a New West, a collection of previously unavailable essays by Polanyi, and Fred Block and Margaret R. Somers's The Power of Market Fundamentalism: Karl Polanyi's Critique. The guiding thread of this analysis is the claim that a constant in Polanyi's thought was his belief in what he called “the reality of society,” that is, that society exists as a social fact over and above the individuals that constitute it. The essay begins by tracing Polanyi's intellectual development, drawing primarily on the essays found in For a New West. Polanyi's quest to reconcile individual freedom with social solidarity led him first, in the years between the First and Second World Wars, to embrace liberal socialism, before his readings in anthropology persuaded him that traditional economies “embed” the economy in social relations and that the nineteenth-century liberal project of a “disembedded” economy (through the so-called free market) is a departure from this anthropological norm. The essay then examines and questions Block and Somers's claim that Polanyi maintained that the economy is always “already embedded,” arguing notably that Polanyi believed that the advent of market society entailed an economy that was actually disembedded from social relations, not merely one that was re-embedded in an alternative set of institutions.
History
Keywords: already embedded; anthropology; capitalism; embeddedness; liberalism; markets; reality of society; socialism; society

'Socialist Accounting' by Karl Polanyi: with preface 'Socialism and the embedded economy' - Bockman, Johanna; Fischer, Ariane; Woodruff, David (Theory & Society, 2016)
Ariane Fischer, David Woodruff, and Johanna Bockman have translated Karl Polanyi's 'Sozialistische Rechnungslegung' ['Socialist Accounting'] from 1922. In this article, Polanyi laid out his model of a future socialism, a world in which the economy is subordinated to society. Polanyi described the nature of this society and a kind of socialism that he would remain committed to his entire life. Accompanying the translation is the preface titled 'Socialism and the embedded economy.' In the preface, Bockman explains the historical context of the article and its significance to the socialist calculation debate, the social sciences, and socialism more broadly. Based on her reading of the accounting and society that Polanyi offers here, Bockman argues that scholars have too narrowly used Polanyi's work to support the Keynesian welfare state to the exclusion of other institutions, have too broadly used his work to study social institutions indiscriminately, and have not recognized that his work shares fundamental commonalities with and often unacknowledged distinctions from neoclassical economics.
Sociology; Political Science
Keywords: Keynesian economics; Keynesianism; embeddedness; neoclassical economics; social accounting; socialism; socialist accounting; socialist calculation debate; welfare state

Polanyi, political-economic opportunity structure and protest: capitalism and contention in the post-communist Czech Republic - Císař, Ondřej; Navrátil, Jiří (Social Movement Studies, 2016)
Drawing on Polanyian logic, we focus on the gradual institutionalization of capitalism in the Czech Republic and the protests accompanying this process. We hypothesize that different configurations of political economy, or what we term the political economic opportunity structure, trigger different popular responses and are a potent indicator of expected protest forms. To analyze this we chose to carry out a country case study, in which many variables commonly associated with political mobilization, in particular the state’s institutional structure, are kept constant. By contrast, models of political economy vary over time, as a function of the extent and form of the international integration of capitalism. We focus on three configurations of political economy – national, globalized and austerity models – and for each one, identify the characteristics and mechanisms, i.e. concrete policy measures, that shape particular protest patterns in the context of our case study. In theoretical terms, this paper seeks to present one possible response, in this case a Polanyian response, to recent complaints about the disappearance of capitalism from social movement studies. At the same time, given the focus of this special issue, our goal is to analyze the current wave of anti-austerity protest that emerged in relation to what has been labelled the Great Recession.
Sociology; Economics
Keywords: Czech Republic; anti-austerity; economic protest; political economic opportunity structure; political opportunity structure; social movement studies

Economic Exchange: Interdisciplinary Conceptualizations for Management Applications - Das, Roshni (Vilakshan: The XIMB Journal of Management, 2016)
The concept of 'Economic Exchange', taken in the neoclassical economics sense, has traditionally yielded a unilateral direction for business and management studies, that of profit maximization. This paper argues that, the same, when conceptualized from a sociological and anthropological point of view in particular, taking theorization by Polanyi (1946), Weber (1978) and Zafirovski (2001) into cognizance, can generate many alternative and interesting directions. Illustrations for the same have been provided in the form of management applications. Some controversies in the lifecycle of the concept have been noted such as that of the 'rational' man or Homo Economicus, which eventually led to the emergence of socio-economics and the consequential paradigmatic realignments among scholars, as a rebuttal to the dominant paradox. We undertake a conceptual exploration and synthesis of the relevant trans-disciplinary literature. Future implications for discursive research in management are discussed.
Management Studies
Keywords: WEBER; Max; 1864-1920; ZAFIROVSKI; M.; anthropology; economic exchange; economic man; homo economics; homo economicus; industrial management; methodological indivisualism; profit maximization; socioeconomics

Re-embedding Financial Stakes within Ethical and Social Values in Socially Responsible Investing (SRI) - Revelli, Christophe (Research in International Business and Finance, 2016)
The aim of this study is to understand how the definition of ethics in finance has steered socially responsible investing (SRI) towards a financial approach where ethics is guided by finance. Following a critical perspective of historical and modern SRI, we advocate a reconceptualization of the SRI paradigm through a framework that re-embeds finance in ethical and social values according to Polanyi's theory of embeddedness. To conclude, we propose an SRI model where impact measurement and extra-financial performance guide investments.
International Business
Keywords: economic anthropology; economic sociology; embeddedness; general financial markets: general (includes measurement and data) G10; social and economic stratification; social finance; socially responsible investing

Formal Economy, Substantive Economy, and Economism - Sobel, Richard; Postel, Nicolas (Philosophy of the Social Sciences, 2016)
Polanyi analyzes the historical deployment of a “formal” economic science starting from the “market-scarcity-instrumental rationality triptych.” This triptych, and the knowledge associated with it, is shown to be more than merely a “substantial” economic science’s interest in the triptych “need-nature-institution.” While we must agree with Polanyi that economism is ill-suited to the first triptych, we hesitate to accept his suggested alternative, a heterogeneous mixture of naturalism and institutionalism, essentialism and historicism.
Sociology; Economics
Keywords: capital shortages; capitalism; economic systems; economism; essentialism (philosophy); formal economy; historicism; institutionalism (religion); profit; rationality; scarcity; substantive economy

Beyond prices: The cultural economy of water in the Cordillera highlands of Northern Luzon, Philippines - Abansi, Corazon L.; Doble, Maria Consuelo C.; Cariño, Jessica K.; Rola, Agnes C. (Asia Pacific Viewpoint, 2016)
This paper analyses how the economic actions of water distribution and exchange are embedded in the culture of indigenous communities in the Cordillera highlands of Northern Luzon, Philippines. Such actions are fundamental to water access and provisioning. Data was derived from a series of focus group discussions conducted with various water users, including households, farmers, enterprises and local government officials, and from upstream, midstream and downstream communities along the Balili River, a critical watershed in the Cordillera highlands. The study area exhibits a mix of livelihood systems and both formal and traditional institutions of decision-making. Recognising that water is both an economic and social good, this paper draws inspiration from Polanyi's concept of embeddedness. Cases of three communities suggest that water distribution and exchange are embedded in the community's socio-cultural spaces, but the extent of embeddedness declines as communities transform from subsistence to market-based economies. Embeddedness also determines value and availability of water. The paper contributes to the discourse on the cultural economy of water and provides direction on new modes of decision-making on river management that promise more inclusive, equitable and ecologically sustainable outcomes.
Economics
Keywords: Philippine Cordillera; cultural economy; embeddedness; water distribution and exchange

Regulating class in the neoliberal era: the role of the state in the restructuring of work and employment relations - Howell, Chris (Work, Employment & Society, 2016)
The article argues that, in the last three decades, states have become more preoccupied with, and interventionist in, the regulation of class relations in order to facilitate a broad liberalization of employment relations institutions. Drawing on insights from Regulation theorists and Karl Polanyi, the article examines the market-making role of states during periods of transition from one growth regime to another. The more prominent role of the state follows from the stickiness of institutions and the role that states can play in compensating workers from the consequences of liberalization. The article illustrates the argument with an examination of France and Sweden in the period since the early 1980s. For all their differences, in both cases substantial liberalization of employment relations institutions took place and in both cases, but for the state, the process of liberalization would have been either stymied or much more uneven than it was.
Political Science
Keywords: class; employment relations; liberalization; state

The failure of regulation: Work, environment and production at Taranto’s ILVA - Greco, Lidia; Chiarello, Franco (Economic & Industrial Democracy, 2016)
The article focuses on the case of the largest steel plant in Europe, located in Taranto (Italy), to argue that its current crisis is not simply dictated by technological or managerial failings. Rather, the article contends that its problems stem from a regulatory crisis and, specifically, from the failure of the deregulation model pursued after the industry’s process of privatization. Such a model has hinged upon the logic of a big private firm that, on the one hand, has sought to disembed itself from the socio-institutional context and, on the other, has set and followed its own rules with disruptive effects on the local society and environment, as well as on the plant’s economic viability. Such a model entered a crisis when the other socio-institutional actors started to react to the disastrous situation existing in Taranto. To use Polanyian language, a ‘double movement’ has emerged: disruptive pressures have triggered defensive reactions.
Political Science
Keywords: Taranto (Italy); economic democracy; employee ownership; employee participation in management; financial crises; financial crisis; industrial democracy; institutional change; privatization - Italy; sociology; technological innovations

The business of the Anthropocene? Substantivist and diverse economies perspectives on SME engagement in local low carbon transitions - North, Peter (Progress in Human Geography, 2016)
The involvement of private sector actors in low carbon urban transitions is a neglected element of geographical analysis. Drawing on Polanyian, cultural economic geographies and the non-capitalocentric ethics of JK Gibson-Graham’s diverse economies perspective, the paper engages with the wider literature on the engagement of small and medium enterprises (SMEs) in environmental action, corporate social responsibility and low carbon transitions to develop a substantivist account of the contribution of SMEs to local low carbon transitions. The paper argues that, contra formalist economic analyses of economic rationality, SME owners should not be thought of as uncritical profit maximizers but as actors in favour of positive low carbon futures. Thus the paper argues that Polanyian economic geographies and diverse economies perspectives, which rarely speak to each other, can be drawn together, and concludes with suggestions for future research.
Geography
Keywords: Polanyian geographies; carbon offsetting; cultrual geography; diverse economies; environmental protection; local business representation; local economic development; low carbon transitions; small business; social responsibility of business; substantivist

Globalization and Its Countermovement: Marxian Contention or Polanyian Resistance? - Gemici, Kurtuluş; Nair, Manjusha (Sociology Compass, 2016)
This article surveys the scholarship on the countermovement against the diffusion of capitalism and market economy in the Global South. We identify two streams of analysis in the literature. On the one hand, scholars observe contentious politics instances where the spread of capitalist production relations enables the associational capacity and bargaining power of social classes. On the other hand, there are voluminous studies on contentious politics in the Global South where groups such as peasants, shopkeepers, and urban poor resist the intensification of the market economy. We use Beverly Silver's distinction between Marx-type and Polanyi-type protests, which focuses on how globalization makes and unmakes social groups, to unpack the heterogeneity of the impacts and experiences of globalization. We argue that although Silver's distinction is of great analytical value, there are strong warrants for separating the effects of the market economy from capitalism in studying contentious politics against globalization. Such an analytical strategy (i) expands the scope of the distinction between Marxian and Polanyian contention to social groups other than the working class and (ii) emphasizes that the roots of these struggles lie in the interconnected diffusion of capitalism and market economy.
Sociology
Keywords: Global South; MARX; Karl; 1818-1883; SILVER; Beverly; countermovement; global south; globalization

In search of Karl Polanyi's International Relations theory - Dale, Gareth (Review of International Studies, 2016)
Karl Polanyi is principally known as an economic historian and a theorist of international political economy. His theses are commonly encountered in debates concerning globalisation, regionalism, regulation and deregulation, and neoliberalism. But the standard depiction of his ideas is based upon a highly restricted corpus of his work: essentially, his published writings, in English, from the 1940s and 1950s. Drawing upon a broader range of Polanyi's work in Hungarian, German, and English, this article examines his less well-known analyses of international politics and world order. It sketches the main lineaments of Polanyi's international thought from the 1910s until the mid-1940s, charting his evolution from Wilsonian liberal, via debates within British pacifism, towards a position close to E. H. Carr's realism. It reconstructs the dialectic of universalism and regionalism in Polanyi's prospectus for postwar international order, with a focus upon his theory of 'tame empires' and its extension by neo-Polanyian theorists of the 'new regionalism and European integration. It explores the tensions and contradictions in Polanyi's analysis, and, finally, it hypothesises that the failure of his postwar predictions provides a clue as to why his research on international relations dried up in the 1950s.
Political Science
Keywords: CARR; Edward Hallett; 1892-1982; deregulation; international relations; liberalism; neoliberalism

Embedding Capital: Political-Economic History, the United States, and the World - Kramer, Paul A. (Journal of the Gilded Age & Progressive Era, 2016)
The article examines U.S. political and economical history in the context of its impact as well as influence to world affairs. Topics discussed include the Marxist's historical approaches to analysis of capital as in Karl Polanyi's take on American capitalism, "primitive accumulation" with regimes of commodification and the "new history of capitalism" hype. Also mentioned were transnational expansion of humanitarianism, international education sponsorship and Andrew Carnegie's philanthropy.
History
Keywords: United States - politics & government - history; capital; capitalism; economics - United States - history; embeddedness; humanitarianism

The New Washington Consensus: Millennial Philanthropy and the Making of Global Market Subjects - Mitchell, Katharyne; Sparke, Matthew (Antipode, 2016)
This paper outlines the emergence of a New Washington Consensus associated with leading philanthropies of the new millennium. This emergent development paradigm by no means represents a historic break with the market rationalities of neoliberalism, nor does it represent a radical departure from older models of early 20th century philanthropy. Rather, it is new in its global ambition to foster resilient market subjects for a globalized world; and new in its employment of micro-market transformations to compensate for macro-market failures. Focusing on reforms pioneered by the new philanthropic partnerships in education and global health, the paper indicates how the targets of intervention are identified as communities that have been failed by both governments and markets. The resulting interventions are commonly justified in terms of “return on investment”. But the problems they target keep returning because the underlying causes of failure are left unaddressed.
Geography
Keywords: development; education; global health; millennial philanthropy; neoliberalism; philanthropy; triple movement

Expanding the labor theory of value - Collins, Jane (Dialectical Anthropology, 2016)
This paper revisits debates over the labor theory of value in the 1970s and 1980s and proposes an expansion and revision for the neoliberal era. It draws on three empirical cases of social movements grappling with contemporary changes in the societal division of labor and argues that they can best be understood as 'revaluation' projects seeking to bring recognition to aspects of the economy that are necessary for its long-term sustainability but are not 'counted' as important.
Anthropology
Keywords: division of labor; domestic labor; environment; feminism; labor theory of value; labour theory of value; neoliberalism; public sector; shareholder value; social movements; sustainability

Apple, Foxconn, and Chinese workers’ struggles from a global labor perspective - Pun, Ngai; Shen, Yuan; Guo, Yuhua; Lu, Huilin; Chan, Jenny; Selden, Mark (Inter-Asia Cultural Studies, 2016)
To enrich the discussion of global labor, between 2010 and 2016, we studied Apple’s value chain, Foxconn’s mode of labor control, and Chinese workers’ struggles. Through our fieldwork in China we also examined Apple’s and Foxconn’s responses to the spate of worker suicides, workers’ resistance, the activism of scholar and student groups, and transnational justice campaigns. We conclude with reflection on global labor studies in light of the debates between Karl Polanyi’s counter movement and Karl Marx’s class-based struggle.
Sociology; Asia Studies
Keywords: Apple; Apple Inc.; China; Chinese workers; Foxconn; Foxconn Technology Group (Company); MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; countermovement; global labor studies; global labour studies; student and scholar activism; value chains; working class

The catastrophe of neo-liberalism Finance, emancipation and disintegration - Foster, Roger (Philosophy & Social Criticism, 2016)
My article provides a systematic interpretation of the transformation of capitalist society in the neo-liberal era as a form of what Karl Polanyi called ‘cultural catastrophe’. I substantiate this claim by drawing upon Erich Fromm’s theory of social character. Fromm’s notion of social character, I argue, offers a plausible, psychodynamic explanation of the processes of social change and the eventual class composition of neo-liberal society. I argue, further, that Fromm allows us to understand the psychosocial basis of the process that Polanyi calls cultural catastrophe. This requires an elucidation of the major social forces of financialization and emancipation which, I argue, proved to be important formative factors in the emergence of neo-liberal society. The cultural catastrophe of neo-liberalism concerns the working class, whose prevailing social character has become misaligned with the new expectations and requirements of neo-liberal society.
Philosophy
Keywords: FROMM; Erich; cultural catastrophe; emancipation; financialization; neo-liberalism; neoliberalism

The Hill and Knowlton Affair and the Marketization of the First Gulf War. a Polanyian Perspective - Petre, Silviu Valentin (Proceedings of the Scientific Conference AFASES, 2016)
The 1990-1991 First Gulf War became a classic manual of PR or manipulation, depends on the terms one chooses. Within the whole manipulative framework, Hill and Knowlton, one of USA’ s foremost advertising brands played a pivotal, ripple-making role. With the money provided by Kuwaiti government in exile, H&K faked several testimonies according to which Saddam’s soldiers had been responsible of appalling deeds by pillaging Kuwaiti hospitals, where they stole incubators and left newborn babies to die. Thus, President Bush gained legitimacy in front of the US Congress and international fora to assemble a coalition of the willing to deal with Iraqi aggression. This article will not only dwell upon the abovementioned episode, but shall also sketch an explanatory framework using Karl Polanyi’s writings.
Defence Studies
Keywords: BUSH; George H.W.; Gulf War; HUSSEIN; Saddam; Hill and Knowlton Strategies (Company); POLANYI; Karl; 1886-1964 - political and social views; Persian Gulf War; 1991; manipulation; manipulative behavior; public opinion; public relations & politics

Quality Work and the Moral Economy of European Employment Policy - Bolton, Sharon; Laaser, Knut; Mcguire, Darren (JCMS: Journal of Common Market Studies, 2016)
Following a decade of radical economic and workplace restructuring, it is important to understand how state employment policies support or deny human flourishing. This article utilizes a realist document analysis approach and reviews European employment policy through a moral economy lens. It fuses different moral economy approaches, drawing together the work of Karl Polanyi and Andrew Sayer a multi-layered conceptual lens is offered that explores the tensions between a commodification of labour and human needs. A dominant market ideology is revealed, highlighting how quality work has been subsumed by the flexicurity agenda in the EU.
Business & Management
Keywords: European employment policy; dignity; employment; flexicurity; management studies; moral economy; quality work

Public Capital and the Post-Communist Welfare State: The Case of Poland - Rae, Gavin (Polish Sociological Review, 2016)
This paper provides an overview of some of the main theories of the welfare state. It builds upon Polanyi's theory of the double-movement and relates this to Bourdieu's concept of multiple capitals. It argues that the welfare state can be understood as a form of public capital, both in an economic and sociological sense. The welfare state emerges and is maintained due to a social countermovement that at least partly removes areas of socio-economic life out of commodity relations. In turn this creates public capital, which is both economic and social. In the post-Communist countries most of this public capital was created during a period when almost the whole of economic and social life was controlled by the state. Once the Communist system collapsed, so the accompanying policy of full-employment and system of social welfare organised through state enterprises disappeared. This was met with a large rise in unemployment and labour deactivation, meaning that many social benefits were created during the initial years of the transition. Also, the post-Communist systems inherited large amounts of public capital in the form of public services such as health and education. Through the example of Poland this paper analyses how this public capital was initially maintained and even developed during the early transition period, but then how a process of commodifying it was later begun.
Sociology
Keywords: BOURDIEU; Pierre; 1930-2002; Poland; capital; communism; countermovement; post-communism; public welfare; social movements; social policy; social services; welfare state

Polanyi’s ‘substantive approach’ to the economy in action? Conceptualising social enterprise as a public health ‘intervention’ - Roy, Michael J.; Hackett, Michelle T. (Review of Social Economy, 2016)
For several decades now, critical public health researchers have highlighted the deleterious effects that pursuing neoliberal policies can have on the ‘causes of the causes’ of poor health and upon growing health inequalities. This paper argues that the conceptual tools of Karl Polanyi can help lend particular insight into this issue. The specific example that this paper focuses upon is the ‘social enterprise’: a form of organisation that combines both social and business objectives. The paper explores, conceptually, whether social enterprises may have the potential to act as one component of a neo-Polanyian countermovement: helping to re-embed the economy back into society, and offering greater recognition for a more comprehensive and socially imbued concept of health. Importantly, this potential is critically examined in the context of neoliberal hegemony, where challenges to the status quo have regularly been met with assimilation, co-option and/or repression.
Sociology
Keywords: health inequality; public health; social enterprise; substantive approach

For real: land as capital and commodity - Christophers, Brett (Transactions of the Institute of British Geographers, 2016)
With the aim of helping to revivify a stalled geographical literature on the place of land in capitalist political economies, this article presents a critique of the popular idea that land can be usefully conceptualised as a ‘fictitious’ form of capital or commodity. The critique is based primarily on a close and critical consideration of the grounds on which the identifiers and theorists of such fictitiousness – Marx/Harvey in the case of capital, Polanyi in the case of the commodity – distinguished it from ‘real’ variants. Those grounds, the article argues, are tenuous. And, far from disabling us, treating land as no more or less real than other forms of capital and commodity can empower us in productively revisiting and centring the question of land's political economy – a crucial undertaking in a world where the materiality of land to social relations is writ increasingly large.
Geography
Keywords: MARX; Karl; 1818-1883; capitalism; economic geography; fictitious capital; fictitious commodities; fictitious commodity; land; political economy; social economy

Fair trade certification as oversight: an analysis of fair trade international and the small producers' symbol - Clark, Patrick; Hussey, Ian (New Political Economy, 2016)
In this article we analyse Fair Trade as a form of non-state regulation, building on the literature on the internal politics and governance of Fair Trade International (FTI) certification. We focus on recent developments in the FTI certification system, including the split of Fair Trade USA from FTI and the emergence of the Small Producer's Symbol (SPP) as an alternative to FTI certification. We highlight the role of the three regional Producer Networks, in particular the Latin American Producer Network, the CLAC, in the politics and governance of the FTI system. In order to analyse these issues we employ an alternative reading of Karl Polanyi's work in relation to Fair Trade. We problematise the claim made by some in the literature that FTI certification is an example of Polanyi's concept of re-embedding. Instead, we draw on Polanyi's concept of oversight to analyse Fair Trade certification. We argue that the emergence of the SPP out of the CLAC shows promise for being a mechanism of oversight more reflective of Polanyian re-embedding than FTI certification. We also emphasise how the growth of the SPP and the pressure from the Producer Networks have prompted governance reform within the FTI system.
Political Science; Sociology
Keywords: Canada; Carleton University; European Union countries; certification; economic conditions; fair trade; financial crises; financial crisis; governance; liberalization (finance); municipal services; producer networks; small producers; unfair competition

Polanyian Pathways: A review of The Power of Market Fundamentalism: Karl Polanyi’s Critique by Fred Block and Margaret R. Somers and For a New West: Essays, 1919–1958 by Karl Polanyi; edited by Giorgio Resta and Mariavittoria Catanzariti - Peck, Jamie (Economic Geography, 2016)
Geography
Keywords: BLOCK; Fred; CATANZARITI; Mariavittoria; For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; RESTA; Giorgio; SOMERS; Margaret R.; The Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); book review; nonfiction

Neoliberalism, Polanyi's Protective Response, and Veblenian Waste - Wrenn, Mary V. (Journal of Economic Issues (Taylor & Francis Ltd), 2016)
As capitalism unfolds, continual technological advance – in combination with the relentless accumulation imperative – serves to amplify material progress. The expanding economic sphere begins to pervade the everyday lives and thinking of the individual. The institutionalization of the market fundamentally changes the structure of society and, in so doing, fundamentally changes the institutional structure through which individuals are socialized. The social dislocation generated therein prompts Karl Polanyi's protective response. Despite this market intensification, the existence of the economic surplus undermines the syllogistics of market-determined pricing. Evidence of the economic surplus and Veblenian waste as well as of the fact that the competitive law of value is not operable under neoliberalism is found in the lobby industry and campaign contributions. This research seeks to explicitly connect the concepts of Polanyi's protective response with Veblenian waste and the economic surplus in order to better understand how the irrational system of neoliberalism continues to evolve.
Sociology; Economics
Keywords: Veblen; capitalism; economic sociology; economic surplus; institutional economics; neoliberalism

Saving the Commons in an Age of Plunder - Batt, H. William (American Journal of Economics and Sociology, 2016)
Land ownership, as commonly understood today, originated with the enclosure movement during the English Tudor era almost four centuries ago. Karl Polanyi referred to this “propertization” of nature as the “great transformation.” That land, water, and air was a social commons is now archaic and forgotten, and with it the classical economic concept of rent, which was, in theory, once paid to royalty as the earth's guardian. Garrett Hardin's article, “The Tragedy of the Commons,” raised alarm about the abuse and loss of this realm, and he recommended constraints and privatization to prevent this. Most people view titles to landed property much as they do their household goods, but Henry George saw that the earth should be seen as a common resource and its value taxed to benefit everyone. This would restore economic equilibrium to market exchanges and pay for government services. The capture of natural resource rents can supplant taxes on wages and capital goods, and it comports with all textbook principles of sound tax theory. This policy can be the modern replacement for the commons, and implementing resource rent capture is both economically and technically feasible.
Economics; Sociology
Keywords: commons; propertization of nature

Beyond the Minsky and Polanyi Moments - Gemici, Kurtuluş (Politics & Society, 2016)
The period of very high foreclosure rates sets the 2007–8 financial meltdown apart from similar banking crises fueled by asset price booms. Why did the 2007–8 meltdown lead to a prolonged foreclosure crisis? Through a theoretical perspective built on Minsky’s financial instability hypothesis, Polanyi’s ideas about adverse consequences of commodity fiction, financialization of homes, and institutional coupling, I argue that commodifying houses as financial assets exposed mortgage loan holders to price fluctuations originating in capital markets and elevated their risk of default. I show how increased exposure to price fluctuations followed from the tight coupling between U.S. housing and capital markets, a coupling that resulted directly from the rising preponderance of securitization in U.S. housing finance. I provide further evidence from countries where housing finance was tightly coupled with capital markets (Iceland and Ireland) to countries where housing finance did not rely dominantly on capital markets (Canada and the Netherlands).
Sociology
Keywords: MINSKY; Hyman; United States; asset-backed financing; economic aspects; financial instability; financialization; foreclosure; great recession; housing foreclosures; institutional coupling; recessions - 2008-2013; securitization

The New Urban Fiscal Crisis - Kirkpatrick, L. Owen (Politics & Society, 2016)
Numerous U.S. cities suffered immense fiscal strain following the subprime mortgage crisis and financial crash of 2007–8. Diminished revenues, tightened credit, and speculative financing that went bad in the aftermath fueled widespread fiscal distress on the local scale. Although the current moment resembles fiscal crises that crested in cities in the 1970s–90s, two factors distinguish the current period. First, municipal affairs have become thoroughly financialized—dominated by speculative securities and volatile debt arrangements—such that local crisis can no longer be understood apart from financial market instability. Second, local fiscal politics have become increasingly removed from democratic oversight and control. This de-democratization hinders the capacity of political communities to reregulate markets and rebuild urban communities. An analytic model derived from the work of Hyman Minsky and Karl Polanyi emphasizes how cities become ensnared in a “financial instability” cycle and how communities seek to protect themselves by way of the “double movement.”
Sociology
Keywords: Chicago; Detroit; MINSKY; Hyman; United States - economic conditions; de-democratization; financialization; municipal bonds; municipal finance; recessions - 2008-2013; urban fiscal crisis

Countermovement, Neoliberal Platoon, or Re-Gifting Depot? Understanding Decommodification in US Food Banks - Lindenbaum, John (Antipode, 2016)
In this paper, I explore the decommodification that takes place in US food banks. I argue that food banks are neither Polanyian countermovements re-embedding the market in society nor tiny platoons of neoliberalism that advance market relations and state withdrawal. Rather, food banks are best understood as re-gifting depots that are part of the capital accumulation process. Recent scholarship on primitive accumulation, the disarticulations approach, and waste suggests that the devaluation of food products and the exclusion of human labor are everyday elements of capitalism. I conclude by examining the potential for progressive politics in US food banking.
Geography
Keywords: Polanyi - political & social views; Supplemental Nutrition Assistance Program (U.S.); United States Deptartment of Agriculture; commodification; decommodification; disarticulation; equality - social aspects; food banks; food security; primitive accumulation; re-gifting depot; waste

The Copenhagen Turn in Global Climate Governance and the Contentious History of Differentiation in International Law - McGee, Jeffrey; Steffek, Jens (Journal of Environmental Law, 2016)
The 2009 Copenhagen Accord marked a significant shift in global climate governance which has been substantially adopted in the 2015 Paris Agreement. At Copenhagen, binding targets for states to reduce emissions were replaced by voluntary pledges. We argue that the Polanyian 'double movement' offers a useful lens to understand the Copenhagen shift in global climate governance as part of ongoing contestation in the international law system between principles of economic liberalisation and redistributive intervention. In the second half of the 20th century, redistributive design of international legal institutions became evident in a number of issue areas including trade law, oceans law and the seminal climate treaties. However, there has been ongoing US lead opposition to 'redistributive multilateralism' (RM), particularly over the last decade of climate negotiations. The Copenhagen model of voluntary pledges, therefore, needs to be viewed as an outcome of this opposition to RM and a related weakening of differentiation in international environmental law.
Law; Environmental Studies
Keywords: Copenhagen; Copenhagen Accord; UNFCCC; climate change; differentiation of duties; environmental justice; environmental law; international cooperation; international law; political economy; regime design

Economy, Society and Earth in Polanyian and Wild Law Perspectives on Environmental Regulation: To Perform a Double or Triple Movement? - Pontin, Ben (Journal of Environmental Law, 2016)
Law; Environmental Studies
Keywords: BURDON; Peter D.; HAINES; Fiona; LANGE; Bettina; MALONEY; Michelle; Regulatory Transformations: Rethinking Economy-Society Interactions (Book); THOMAS; Dania; Wild Law: In Practice (Book); book review; double movement; environmental law; nonfiction; triple movement

Revisiting Free Market Utopia: A Hayek-Polanyi Reminder - Usenmez, Ozgur; Duman, Levent (Journal of Economic and Social Thought, 2016)
As pundits discuss the causes and results of the 2008 financial crisis and ensuing Great Recession, economists of various strands–led mainly by Keynesians–are slowly beginning to question the supposed wisdom of unfettered markets. Since Keynesian-liberal disputes revolve around the symptoms of the crisis rather than the historical and structural features of market economies, we thought that a Hayek-Polanyi comparison would be a timely intervention in order to understand the real nature of the subject. This comparison may also pave the way for the creation of an alternative to the vagaries of unfettered markets.
Political Science
Keywords: Austrian; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Keynesian; Keynesianism; business fluctuations; cycles; evolutionary; financial crises; financial markets; financial markets and the macroeconomy; general aggregative models: Keynes; history of economic thought: individuals; institutional; post-Keynesian

Governing by Panic - Woodruff, David M. (Politics & Society, 2016)
The Eurozone’s reaction to the crisis beginning in late 2008 involved not only efforts to mitigate the arbitrarily destructive effects of markets but also vigorous pursuit of policies aimed at austerity and deflation. To explain this paradoxical outcome, I build on Karl Polanyi’s account of a similar deadlock in the 1930s. Polanyi argued that a society-protecting response to malfunctioning markets was limited under the gold standard by the prospect of currency panic, which bankers used to push for austerity, deflationary policies, and labor’s political marginalization. I reconstruct Polanyi’s “governing by panic” theory to explain Eurozone policy during three key episodes of sovereign bond market panic in 2010–12. By threatening to allow financial panics to continue, the European Central Bank promoted policies and institutional changes aimed at austerity and deflation, limiting the protective response. Germany’s Ordoliberalism, and its weight in European affairs, contributed to the credibility of this threat.
Political Science
Keywords: European Central Bank; Eurozone; Eurozone crisis; Eurozone debt crisis; depressions (economics) - 1929; economic conditions; euro; governing by panic; ordoliberalism

The new agrarian double movement: hegemony and resistance in the GMO food economy - Carroll, Myles (Review of International Political Economy, 2016)
This paper draws on the work of Antonio Gramsci and Karl Polanyi in analyzing the consequences of legal regimes that regulate genetically modified foods. Against the tide of neoliberalism, a binding, precautionary agreement over trade in genetically modified organisms (GMOs) has emerged through the Cartagena Protocol on Biosafety. This Protocol exemplifies what Polanyi termed the ‘self-protection of society,’ the second phase of his double movement. The Protocol's final form was a product of European governments’ responses to public concerns over the potential environmental and health impacts of GMOs in an unregulated global economy. This ‘self-protective’ turn has been manifest at regional and national scales, including in Australia. Drawing on Gramsci, I argue that this unlikely turn emerged in the context of shifting public opinion, effective anti-GMO activism, and alternative discursive framings. It took hold with European publics and governments, generating the relations of force needed to become the hegemonic framing of GMOs globally. The objectives of this paper are thus to demonstrate how a double movement has occurred in the regulation of GMOs and to use Gramsci's relations of force to explain how this double movement has nonetheless failed to challenge the underlying neoliberal basis of GMO agriculture as it exists today.
Political Science
Keywords: Australia; GMOs; agriculture - Australia; biosafety; double movement; economics; hegemony; international political economy; law; political economy; relations of force; transgenic organisms

Orientating disability studies to disablist austerity: applying Fraser’s insights - Dodd, Steven (Disability & Society, 2016)
Many disabled people in Britain have experienced profound challenges brought about by a government policy programme characterised by ‘austerity’. Drawing on the work of Fraser and Polanyi, this article explores new ways in which disability studies can become theoretically orientated to the task of explaining and challenging what has become an issue of overbearing importance for many disabled people. It is argued that Fraser’s notion of bivalency encapsulates the combination of cultural and economic challenges which characterise ‘disablist austerity’. Fraser’s development of Polanyi’s work is used to argue that disability studies should be orientated to large-scale economic challenges as well as cultural and discursive concerns that are more often the object of study in the field.
Health Studies; Disability Studies
Keywords: Great Britain; austerity; budget; conceptual structures (information theory); culture; disability studies; disablism; government policy; marketisation; people with disabilities - psychology; practical politics; public welfare; recognition; redistribution; research methodology; social justice; socioeconomic factors; triple movement

A Concept of Eurasia - Hann, Chris (Current Anthropology, 2016)
To imagine Europe and Asia as constituting equivalent "continents" has long been recognized as the ethnocentric cornerstone of a Western, or Euro-American, world view. The amalgam Eurasia corrects this bias by highlighting the intensifying interconnectedness of the entire landmass in recent millennia. This article builds on the work of Jack Goody and others to analyze the unity-in-civilizational-diversity of the Old World. It draws on the substantivist economic anthropology of Karl Polanyi to postulate continuities between ancient ideals of economic embeddedness in the agrarian empires and various forms of socialism in the twentieth century. Today, when the human economy everywhere is again exposed to the domination of the market, the Eurasian dialectic has universal relevance. However, recognition and realization of pan-Eurasian affinities continues to be impeded by geopolitics, and sociocultural anthropology has a long way to go to overcome its Atlantic bias.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; economic anthropology; ethnocentrism; geopolitics; socialism; substantivist

Towards Another 'Great Transformation' - Mkandawire, Thandika (Africa Insight, 2016)
As Karl Polanyi indicates in the 'Great Transformation',1'the so-called self-regulating markets cannot exist for any length of time without destroying human society'. Three 'Great Transformations' have taken place. The first occurred in Europe at a time when it was widely believed that markets were nature's way of managing exchange in an efficient way and that interference in the workings of the market, as Adam Smith argued, was not only artificial, but against the laws of God.2 The second was about society's reaction in defending itself against the ravages of the market. The third was when neoliberalism launched a counter-movement that gave the market primacy. This paper argues that the assumption that the self-regulation expected from 'corporate social responsibility', or the instinct for self-preservation, would replace the state, had failed disastrously. The neoliberal model is therefore in trouble. It is important to contemplate a new global order that will be built on and facilitate social orders that are developmental, socially inclusive and democratic - which will be the fourth 'Great Transformation'. As the paper argues, there are two imperatives: the first imperative would be the creation of global institutions that would ensure that commitments to justice, equality and democracy are translated into global and national policies; and the second one would be the intellectual and ideological challenge of the views and discursive practices that, all too often, fetishised globalisation into some exogenous force that ineluctably imposes its laws on the human race.
Economics; Development Studies
Keywords: Africa studies; Europe; democracy; economic conditions; humanism; justice administration; socioeconomics

Organic farm volunteer tourism as social movement participation: a Polanyian political economy analysis of World Wide Opportunities on Organic Farms (WWOOF) in Hawai‘i - Mostafanezhad, Mary (Journal of Sustainable Tourism, 2016)
In recent years, Karl Polanyi's concept of the “double movement” has been resurrected to describe growing international resistance to neoliberal global capitalism. The double movement originally referred to counter-movements for social protection against the 19th and early 20th century laissez-faire market. Today, it describes the growth of new social movements which often resist neoliberal economic practices and ideologies. Drawing on Polanyi's concept of the double movement and on recent work on neoliberalism and new social movements, this article examines farm hosts' motivations for participation in World Wide Opportunities on Organic Farms (WWOOF). It argues that farm hosts tend to articulate their motivations as an attempt to proclaim solidarity with organic, spiritual, and educational new social movement agendas. It describes how a loosely articulated organic identity converges around three corollaryprotective counter-movements: organic food production and consumption, spirituality, and alternative education, exploring the creative ways people are resisting neoliberal capitalism at the intersection of alternative tourism and organic agriculture. Yet, despite hosts' intentions, the article illustrates how new social movement participation through WWOOF is in constant tension with the neoliberal agrarian and tourism marketplace in which it operates, as well as the perhaps unforeseen limits of its radical horizon.
Geography
Keywords: POLANYI; Karl; 1886-1964; agri-tourism; capitalism; critical theory; culture change; farm tourism; geography; neoliberalism; organic farming; sustainability; sustainable tourism; volunteer tourism

Market Reforms and Water Wars - Simmons, Erica S. (World Politics, 2016)
Responses to the imposition of market-oriented economic policies have varied. This article asks two questions: (1) How can we better understand when marketization will or will not prompt resistance? And (2) when people do mobilize, why are some movements broad-based while others draw on particular segments of society? The author argues that these questions can best be answered by focusing not only on the political contexts and resources available to potential social movements, but also on what is perceived to be at stake during marketization. These perceptions influence mobilization processes and the kinds of groups available for mobilization. When people understand markets as threatening to material wellbeing, as well as to widely shared community relationships, understandings, and commitments, heightened feelings of group belonging can contribute to broad-based mobilization. The author develops this argument through analysis of the broad-based, widespread movement that emerged to protest water privatization in Cochabamba, Bolivia, in 1999 and 2000. In the context of a history of agriculture, irrigation, drought, and conflict, water helped to produce and reproduce imagined communities of nation, region, and ethnic group, as well as quotidian communities revolving around the routine production and consumption of water. These meanings help to explain the dynamics of the resistance that emerged.
Political Science
Keywords: Latin America; marketization; political science; social movements; water wars

The contradictory logics of financialization: Bringing together hyman minsky and Karl Polanyi - Block, F. (Politics and Society, 2016)
This introduction explains the logic of bringing together the perspectives of Hyman Minsky and Karl Polanyi to analyze processes of financialization. Although Minsky and Polanyi have very different intellectual trajectories, there are important complementarities in their approaches. The introduction also explains the focus of the three papers in this special section written by Kurtuluşc Gemici, Lucas Kirkpatrick, and David Woodruff. © 2015 SAGE Publications.
Sociology
Keywords: MINSKY; Hyman; finance; financial crises; financial crisis; financialization; political economy; speculation

Human growth and avoiding European disintegration: lessons from Polanyi - Buzaglo, Jorge (real-world economics review, 2016)
Many economists, including mainstream economists, have declared the necessity of an ambitious public investment program for Europe. The continuation of the present laissez-faire and austerity approach, they say, will deepen the dissatisfaction of European peoples with the European project. In effect, in the absence of inspiring progressive alternatives, there is the real prospect of nationalistic reactions everywhere, with fragmentation and the end of the EU (or even worse) as a consequence. At the bottom of EU-fatigue there is dissatisfaction with the present economic paradigm, which implies social and economic strain and stagnation for a large majority, and growing wealth and privilege for a tiny minority (the “one percent”). A new social and economic paradigm should be necessary to reverse the negative and dangerous trends that the now more than 30 years old neoliberal paradigm has implied. To be effective, a new social and economic paradigm should underlie the new, ambitious European investment program. The guiding general idea of such a new, hopeful paradigm and program should be the idea of human growth. Human growth can be understood as the growth of human capabilities — the all-round development of individuals and societies. The paper summarizes a dynamic simulation model for the efficient allocation of investment. Investment efficiency is understood in the sense of the intersectoral allocation of investments being able to fulfil desired patterns of capability growth. That is, efficient investment programs are those that maximize the capacity of the production system — and in general, the socioeconomic system — of generating human growth.
Economics
Keywords: European Union; human growth

Domesticating the market: moral exchange and the sharing economy - Fitzmaurice, Connor; Ladegaard, Isak; Attwood-Charles, William; Cansoy, Mehmet; Carfagna, Luka; Schor, Juliet; Wengronowitz, Robert (Under review at Socio-Economic Review, 2016)
The sharing economy has generated enormous excitement with its promise of transforming work and consumption through technology and novel socio-economic relations. However, critics see the phenomenon as a further development of neoliberalism. Platforms such as Airbnb and TaskRabbit, monetize a previously uncommodified realm of life via renting of bedrooms, possessions, space and labor time. In this paper, we analyze the meanings and attitudes of sharing economy participants. On the basis of 100 interviews in two for-profit and three not-for-profit sites, we find that most see the sharing economy as an opportunity to build a radically different market, from the bottom up. They are critical of the neoliberal market order, and envision an economy of personalized exchanges that are morally attuned, based on ideals of community, and that help them achieve creative and financial autonomy in their working lives. To our respondents, the sharing economy is an opportunity to domesticate the market.
Sociology
Keywords: domestic production; economic sociology; hostile worlds; markets; morality; neoliberalism; sharing economy

Social Quality - Herrmann, Peter (International Journal of Social Quality, 2016)
A fundamental methodological problem is the relevance of an antagonism of capitalism. This needs to be classified in light of the developmental stage of the means of production: far too little attention is paid to the contradictory character of individualization and socialization. This brings us to Karl Polanyi's main argument of disembedding. He also deals with a shift from the socially integrated (and dependent) individual to the utilitarian market citizen. The French regulationist theory offers a major step toward understanding new forms of societal embedding linked to this "new personality." It will also allow us to move beyond the misleading juxtaposition or dichotomization of individualization-socialization. Investigating five major tensions, it ventilates the possible meaning of the digital revolution and the challenges for monitoring development. The main aim of the article, however, is to bring the economy back in and to go beyond the traditional duality between economics and politics.
Economics
Keywords: capitalism; change; development; disembedding; economics; economics and social science; economy & society; social quality; social sciences; theory of regulation; work

The Methodology of Polanyi's Great Transformation: Commentary - Mayhew, Anne (Economic Thought, World Economics Association, 2016)
A commentary on Asad Zaman's paper “The Methodology of Polanyi's Great Transformation”
Economics
Keywords: ZAMAN; Asad; capitalist systems; economic methodology; economic thought; history of economic thought; political economy

Distribution-Led Growth in the Long Run - Nikiforos, Michalis (Review of Keynesian Economics, 2016)
This paper examines the long-run fluctuations in growth and distribution through the prism of wage- and profit-led growth. It argues that the relation between distribution of income and growth changes over time and proposes an endogenous mechanism that leads to fluctuations between wage- and profit-led periods. The ephemeral character of distribution-led regimes needs to be taken into account when someone estimates empirically the effect of a change in distribution on utilization and growth. The model is a linear version of Goodwin's predator-prey model, but with a reversal of the roles for predator and prey; this is another way to conceptualize the symbiosis between the two classes within a capitalist economy. The aforementioned argument is also examined in relation to the double movement of Karl Polanyi and the inverse U-shaped curve proposed by Simon Kuznets.
Economics
Keywords: Kaleckian; Sraffian; aggregate factor income distribution; aggregate human capital; aggregate labor productivity; business fluctuations; capacity; capital; cycles; employment; general aggregative models: Marxian; intangible capital; intergenerational income distribution; investment; one; two; and multisector growth models; unemployment; wages

Critical reflections on social enterprise through a polanyian lens - Roy, M., S., Grant (Social Enterprise Research Colloquium Australasia, 2016)
N/A
Keywords: social enterprise

"Let Them Eat Stuffed Peppers": An Argument of Images on the Role of Food in Understanding Neoliberal Austerity in Greece - Sutton, David (Gastronomica, 2016)
This paper focuses on how discourses of food have shaped understandings of what is at stake in the Greek crisis. Drawing from Karl Polanyi's concept of "embeddedness," I argue that food is central to Greek interpretations of neoliberal policies and processes because of its centrality to Greek culture and identity. Food has also been a site of contested practices of "solidarity" and "charity" by which new social experiments are emerging in the wake of the breakdown of the welfare state. In arguing for food's centrality in the reshaping of Greek sociability, I will suggest that food be thought of not simply as a "topic" for anthropological investigation, but as a master-concept on the level of "kinship," "ritual," or "exchange" in any anthropological analysis of contemporary life.
Anthropology; Food Studies
Keywords: Greece; Greek crisis; Kalymnos; Oriental and African Studies; austerity (economics); critical food studies; food metaphors; food studies; kinship; neoliberalism; solidarity

Local Trade and Exchange/Employment Systems (LETS) in Future Eco-sustainable Societies - Westra, Richard (Anthropology in Action, 2016)
All communities of practice must face questions relating to the material economic foundations of future sustainable societies. David Graeber, Karl Polanyi and Karl Marx each have produced typologies of possible types of economy, synthesised as: (1) the principle of individual reciprocity, (2) the market principle of capitalism, and (3) the planning principle of the state. I apply this synthesis to recent proposals for community change advanced by Bill McKibben and David Korten concerning economic scale and the re-localising of production and consumption sundered by globalisation, focused on the local exchange and trading system (LETS). The operationalising of LETS draws upon Adam Smith's view of markets as face-to-face exchanges of goods taking place in small morality-bound communities. Smith, McKibben and Korten conflate two different meanings of the term 'exchange'. To understand the role LETS may play in future sustainable economies in communities of practice demands treatment of this problem.
Anthropology
Keywords: MCKIBBEN; Bill; 1960-; capitalism; communities of practice; community; eco-sustainability; economy; globalization; local exchange and trading systems; markets; sustainability; sustainable societies

The Methodology of Polanyi's Great Transformation - Zaman, Asad (Economic Thought, 2016)
Polanyi's book, The Great Transformation, provides an analysis of the emergence and significance of capitalist economic structures which differs radically from those currently universally taught in economic textbooks. This analysis is based on a methodological approach which is also radically different from existing methodologies for economics, and more generally social science. This methodology is used by Polanyi without explicit articulation. Our goal in this article is to articulate the methodology used in this book to bring out the several dimensions on which it differs from current approaches to social science. Among the key differences Polanyi provides substantial scope for human agency and capability to change the course of history. He also shows that the social, political and economic spheres of human existence are deeply interlinked and cannot be analysed in isolation, as current approaches assume. KM - see Mayhew's (2016) commentary on this paper.
Economics
Keywords: capitalism; liberalism; methodology; social science

The evolution of false self-employment in the British construction industry: a neo-Polanyian account of labour market formation - Behling, Felix; Harvey, Mark (Work, Employment & Society, 2015)
Governments in Europe and elsewhere have renewed their attention to the fiscal regulation of their economies in order to close tax loopholes and boost revenues in response to the financial crisis. The article uses a neo-Polanyian ‘instituted economic process’ approach to explore and explain the uniquely high level of bogus self-employment in the UK construction industry, facilitated by confused law and stimulated by a bespoke construction fiscal regime, resulting in endemic tax evasion. It examines how the co-evolution of employment status law and a sector-specific fiscal regime maps tightly onto the emergence of mass self-employment, as evidenced by comparative labour market and sectoral statistics. Seeing competition as an instituted process within these distinctive market arrangements, it identifies a form of ‘degenerative competition’, driving out both genuine direct-employment and self-employment, and driving in bogus self-employment, with its attendant substantial fiscal losses, failed skill reproduction and poor productivity.
Sociology
Keywords: British construction industry; Great Britain; bogus self-employment; business revenue; construction industry; economic sociology; instituted economic process; labour market formation; self-employment; tax evasion; tax loopholes

Ontario's infrastructure boom: a socioecological fix for air pollution, congestion, jobs, and profits - Nugent, James Patrick (Environment & Planning A, 2015)
Infrastructure projects provide a spatial fix by increasing the scale and rate of capital accumulation, and because infrastructure projects themselves absorb massive amounts of productive and finance capital. I seek to explain the timing, character, and consequences of a Can $85 billion infrastructure boom in Canada's largest province, Ontario, between 2003 until 2013. I focus on the expansion and privatization of environmentally oriented infrastructure in Ontario via three policies: the conversion of public coal power plants to private natural gas and nuclear facilities; the Green Energy Act (a renewable energy feed-in tariffs programme); and The Big Move (a Can $50 billion dollar rapid transit plan using a public–private partnership model). I employ a Polanyian– O'Connor approach to emphasize the role of labour, environmental groups, and other social movement groups in bringing these investments about. I argue that infrastructure investments are not only a spatial fix aimed at finding capital a safe long-term investment and addressing class struggles around job creation. In Ontario these infrastructure investments have also provided the state with a broader socioecological fix for the economic and political contradictions stemming from air pollution and congestion. Social movements have pressured the government to address what James O'Connor refers to as the underproduction of the conditions of production: that is, degraded human health and quality of life; a deteriorating environment; and inadequate public infrastructure. Throughout the paper I emphasize how the socioecological fix in Ontario is being accomplished by advancing the neoliberal governance of public infrastructure. I point to how these neoliberal socioecological fixes are simply displacing socioecological crises to new spatial and temporal scales.
Geography
Keywords: Canada; Ontario; Polanyian-O'Connor approach; air pollution; fictitious commodities; human ecology; infrastructure; infrastructure and the environment; neoliberal environmental fix; privatization; saving and investment; second contradiction of capitalism; social movements; socioecological fix; spatial fix

Sharing Economy: A Step towards the Re-embeddedness of the Economy? - Pais, Ivana; Provasi, Giancarlo (Stato e Mercato, 2015)
The expression "sharing economy" has spread exponentially in the past few years, a sign of the growing interest in a phenomenon that continues to maintain boundaries that are somewhat vague. The hypothesis of this paper is that this can be attributed not only to the pervasiveness and enabling power of new technologies but also to the need to fill a social vacuum due to the failures of the market and the state. The sharing economy is introducing collaborative social forms able (at least ideally) to embed economic relations within social ones. To test this hypothesis, the article uses the instrumentation implemented by Karl Polanyi to analyze the forms of integration of economy and society (exchange, reciprocity, redistribution). The political economy of the late twentieth century was especially interested in exchange (market) and redistribution (state), leaving social reciprocity in the background. However, we have to look at this more carefully to grasp any social and institutional innovation that the sharing economy can promote. The first part of this paper is devoted to an analysis of the forms of integration and, in particular, to reciprocity in its different variants. The second part, in light of the taxonomy proposed in the first, analyzes some of the most significant experiences of the sharing economy, seeking to determine the institutional characteristics and social dynamics that this could (at least potentially) engender and support. The conclusions will attempt to answer the questions formulated and indicate avenues for further research.
Economics; Sociology
Keywords: cooperative enterprises; economic anthropology; economic sociology; market structure; pricing; and design; open source products and markets; other economic systems: general; prices; public goods; reciprocity; renewable resources and conservation: demand and supply; sharing economy; social and economic stratification

Herculean efforts are not enough: diversifying the teaching profession and the need for systemic change - Schmidt, Clea (Intercultural Education, 2015)
Internationally educated teachers (IETs) seeking to resume their careers in Canada often demonstrate tremendous endurance, fortitude, and resilience in the process of navigating their new professional landscapes, yet neoliberalism and the myth of meritocracy obscure the pervasive systemic barriers characterizing their professional experiences. Critical action research undertaken with graduates of an academic and professional bridging program for IETs in Manitoba reveals a complex interplay of challenges with respect to diversifying the teaching force in intercultural settings. Data collected with IETs seeking full-time teaching positions suggest resuming their careers is by no means guaranteed for many IETs who, in spite of what can be deemed herculean efforts to follow the advice of mentors and make themselves as ‘marketable’ as possible, continue to face significant barriers to employment in a context largely characterized by an over-supply of qualified applicants. Guided by Cummins’ work on collaborative relations of power and a Polanyian critique of economic determinism, my analysis illuminates a multi-pronged systemic approach that has the potential to help ensure the numerous contributions of IETs in Canadian schools can be fully realized.
Education
Keywords: Canada; career development; collaborative relations of power; critical theory; economic determinism; equity; internationally educated teachers; professional education; systemic barriers; teacher development; teachers

Emancipation, marketisation, and social protection: the female subject within vocational training policy in Canada, 1960–1990 - Pullman, Ashley (Gender and Education, 2015)
This paper examines Canadian federal and cross-provincial higher education policy from 1960 to 1990, a critical time when provisions for vocational and adult training came under the auspices of governmental concern, justified under both an economic rationale and as a way to address persistent forms of inequality. The problematisation of skill during this period had particular gendered implications, as addressing inequality through education subsidies intersected with the perceived training needs of employers and the market. Employing Nancy Fraser's theory of a ‘triple movement’, the following paper ‘takes stock’ of how the three political forces of social movements, marketisation, and social protection have shaped gendered discourses of education and training, the implications for which are of continued relevance to those trying to understand the education and training within the contemporary neo-liberal state.
Education
Keywords: Canada; education policy; gender; historical sociology; history; institutional analysis; social protection; vocational education and training; welfare; workfare

Disembedded markets as a mirror of society - Deutschmann, Christoph (European Journal of Social Theory, 2015)
In the Marxist tradition, capitalism is understood as a commodified society based on markets. The article argues that the ultimate justification of this position does not lie in any ‘materialistic’ approach, but in the disembedding of markets that was the result of the historical ‘Great Transformation’ analysed by Karl Polanyi. Disembedded markets are not an economic subsystem within society but take the place of the most encompassing social system, which Durkheim had reserved for religion. The article distinguishes between spatial, social, material and temporal dimensions of disembedding, thereby elaborating and correcting the analysis of Karl Polanyi. As a genuine form of society, disembedded markets give rise to the epistemological dilemma, which, as Luhmann had shown, is fundamental to any encompassing social theory: Society as a whole cannot be viewed by any observer. According to this viewpoint, economic theories take on ‘theological’ functions, as they provide rationality and legitimacy to a reality that is unknowable.
Sociology
Keywords: Marxist philosophy; capitalism; disembedded markets; disembedding; markets; religion; social theory; uncertainty

Polanyi in the European Single Market: The Re- Regulation of Insurance - Mabbett, Deborah (Economic Sociology: The European Electronic Newsletter, 2015)
This article discusses the difference between a social policy approach to the regulatory embedding of a market and a moral economy approach using the insurance case wherein the European Union's Court of Justice ruled that insurers may not discriminate on grounds of sex in identifying risks.
Political Science; Sociology
Keywords: Court of Justice of the European Union; insurance; lawsuits & claims; reembedding; regulation; social policy

A hidden counter-movement? Precarity, politics, and social protection before and beyond the neoliberal era - Harris, Kevan; Scully, Ben (Theory & Society, 2015)
To grasp what might exist beyond neoliberalism, we need to rethink the history of development before neoliberalism. This article makes two arguments. First, for poorer countries, processes of commodification which are highlighted as evidence of neoliberalism often predate the neoliberal era. Third World development policies tended to make social and economic life more precarious as a corollary to capital accumulation before neoliberalism as an ideology took hold. Second, the intense theoretical and discursive focus on neoliberalism has obscured a tangible shift towards de-commodification in much of the global South. The most salient examples today are state-led social assistance programs that have been implemented across the former Third World. These emerged not out of technocratic fixes from above but often out of political and social struggles from below. The rise and spread of these programs are not only in stark contrast to popular conceptions of a neoliberal reinforcement, but are also specifically targeted at social strata whose precarity commonly originated in developmental policies before the neoliberal era. Utilizing a database of 183 active flagship social assistance programs in 84 developing countries, we present macro-level quantitative evidence of the rise and spread of social protection policies over the past two decades in the global South. We then detail these programs for four middle-income countries-China, Brazil, India, and South Africa. To those who lament that the 2008 crisis has produced no Polanyian double movement, we argue that these state-driven social assistance policies are such a mechanism.
Sociology
Keywords: Global South; abstracts; countermovement; developing countries; double movement; global south; ideology; labor studies; labour studies; middle-income countries; neoliberalism; peasant studies; social policy; social services; welfare studies

Markets, Nature, and Society Embedding Economic & Environmental Sociology - Kaup, Brent Z. (Sociological Theory, 2015)
Social scientists have drawn on theories of embeddedness to explain the different ways legal, political, and cultural frameworks shape markets. Often overlooked, however, is how the materiality of nature also structures markets. In this article, I suggest that neo-Polanyian scholars, and economic sociologists more generally, should better engage in a historical sociology of concept formation to problematize the human exemptionalist paradigm their work upholds and recognize the role of nature in shaping markets and society. Unearthing nature in the work of Karl Polanyi, I develop a theory of embeddedness that more closely accounts for the economic, the social, and the ecological. In doing so, I provide a way for scholars to conceptualize both how market societies shape nature and how nature shapes market societies.
Sociology
Keywords: ecology; embeddedness; environmental sociology; materiality; socionatural

The meta-crisis of secular capitalism - Milbank, John; Pabst, Adrian (International Review of Economics, 2015)
The current global economic crisis concerns the way in which contemporary capitalism has turned to financialisation as a double cure for both a falling rate of profit and a deficiency of demand. Although this turning is by no means unprecedented, policies of financialisation have depressed demand (in part as a result of the long-term stagnation of average wages) while at the same time not proving adequate to restore profits and growth. This paper argues that the current crisis is less the ‘normal’ one that has to do with a constitutive need to balance growth of abstract wealth with demand for concrete commodities. Rather, it marks a meta-crisis of capitalism that is to do with the difficulties of sustaining abstract growth as such. This meta-crisis is the tendency at once to abstract from the real economy of productive activities and to reduce everything to its bare materiality. By contrast with a market economy that binds material value to symbolic meaning, a capitalist economy tends to separate matter from symbol and reduce materiality to calculable numbers representing ‘wealth’. Such a conception of wealth rests on the aggregation of abstract numbers that cuts out all the relational goods and the ‘commons’ on which shared prosperity depends.
Economics
Keywords: abstraction; financialisation; financialization; materialisation; meta-crisis

Karl Polanyi and the Problem of Corporate Social Responsibility - Moncrieff, Lilian (Journal of Law and Society, 2015)
This article considers Corporate Social Responsibility (CSR) as part of the projects in ‘new governance and decentred regulation’, which draw social forces towards the regulation of economic behaviour. It uses Karl Polanyi to open up pertinent interfaces between society and economy for observation, and Gunther Teubner to substantiate a ‘regulatory’ view of the company's social relationships. The article finds that CSR combines movements for the recognition of social relationships, on an unprecedented scale, with rigorous simultaneous movements for market building and social abstraction. Twenty-first-century market economy is defined by a capacity to contain ‘the social,’ which is thrown between the two movements, creating opportunities for companies to void the market's social limits. The article counterposes that the social that ‘returns’ after marketization needs to find its way past market-building CSR, to constructively unshackle and redefine the framing of social conflicts that concern the corporation.
Law; Sociology
Keywords: CSR; corporate social responsibility; marketization

Benjamin Cohen on global political order: when Keynes meets realism – and beyond - Guzzini, Stefano (Contexto Internacional, 2015)
This article analyses the trajectory of Benjamin J. Cohen's work by focusing on his ongoing concern with the nature and governance of world order. It does so by playing out his debt to realism and to Keynesianism. In a first moment, Cohen criticises the economic determinism of dependency scholarship, while turning to political realism, and then to possible Keynesian co-operation under anarchy: agents have the power to affect positive change. Later, Cohen the disillusioned Keynesian, watching how the possible reform of financial markets is marginalised by politicians and academics alike, shifts his analysis to more structural aspects of governance or rule that affect actors' preferences. I draw two conclusions. First, in this shift towards theorising the global political order away from steering capacity towards impersonal rule and bias, Cohen also questions the very setup of the theories with which we deal with that world – only to see that this very inspiration of original IPE is abandoned in the course of the ongoing ‘professionalisation' of IPE as practised in the United States. Second, his analysis seems to incorporate a warning. The underlying grand question is nothing less than the bargain between capitalism and liberal democracy as we know it, since the present system undermines equality before the law – money trumps equal political rights – and undermines democratic accountability. One of the main achievements of the post-war Keynesian turn was the reappropriation of political space from anti-democratic forces. Therefore, the decline of Keynesianism could provoke a Polanyian nightmare in which the ‘double movement' by which the laissez-faire is answered by moves to protect society does not strengthen democracies, as in earlier times of ‘embedded liberalism', but undermines them instead.
Political Science; International Relations
Keywords: COHEN; Benjamin J.; Keynesian economics; capitalism; dependency; embedded liberalism; global governance; international finance; international relations; political realism; securities markets; structural power

The political economy of orphanage tourism in Cambodia - Guiney, Tess; Mostafanezhad, Mary (Tourist Studies, 2015)
A recent Aljazeera report on ‘Cambodia’s Orphan Business’ explains ‘how “voluntourism” could be fuelling the exploitation of Cambodian children’. Anti-orphanage tourism movements have emerged to resist the growth of Cambodia’s contested orphanage tourism industry, which is blamed for widespread corruption and the exploitation of children for profit. Taking a Polanyian political economy approach, this article illustrates how the emergence of and response to the orphanage tourism industry represent, in Karl Polanyi’s words, a ‘double movement’ between the neoliberalization of orphanages and the corollary protective countermovement by anti-orphanage tourism campaigns that challenge the industry’s morality and legitimacy. It argues that while resistance to the commodification of orphanages under the newly neoliberalized Cambodian economy reflects Polanyi’s double movement thesis, the limits of this resistance are also indicative of how countermovements are challenged by the broader political economy in which they operate.
Geography
Keywords: Cambodia; double movement; hospitality; leisure; sport & tourism; orphanage tourism; tourism; tourist studies; volunteer tourism

Land as fictitious commodity: the continuing evolution of women's land rights in Uganda - Naybor, Deborah (Gender, Place & Culture: A Journal of Feminist Geography, 2015)
In sub-Saharan Africa, colonial influences have altered traditional practices as a way to manage that which Polanyi labeled as ‘fictitious commodities’ of land, labor, and money. Land has now become a highly marketable commodity and an intrinsic part of the global economy. Over the past century, Uganda's land rights have evolved from communal rights to that of male-dominated, individual ownership practices that have excluded women. Despite constitutional provisions, which confer title of both a deceased husband's property rights and equal rights to property within a marriage to a wife, postcolonial patriarchal tradition prevails. This article examines historical changes in land rights in Uganda and discusses the impact of shifts in land rights from communal ownership to individual tenure, altering power structures and attempting to create marketable land title. The Ugandan women's movement's opposition to policies and implementation of laws that exclude women has been unable to facilitate the required changes in unbiased access to land rights, despite apparent victories in revisions to the letter of the law. Situated within contemporary interpretations of tradition and pressures of market demand, this article shows that women's access to landownership and use are restricted by misinterpretation of traditional law and a lack of enforcement of contemporary legal rights. To illustrate the impact of a lack of access to land, this article examines an empirical case study of widowed subsistence farmers in southern Uganda. Women in Uganda continue to lose ground, quite literally, decreasing the possibility of gender equity in terms of land. (English)
Geography
Keywords: Uganda; derechos de las mujeres; free enterprise; gender; género; land; land tenure; legal status of widows; legal status of women; property rights; tierra; viuda; widow; women's rights; 乌干达; 土地; 女性权利; 寡妇; 性别

Europe at a Crossroads: Failed Ideas, Fictional Facts, and Fatal Consequences - Thomasberger, Claus (Forum for Social Economics, 2015)
The crisis of the European Monetary Union has revealed the weakness and the fragility of the European integration process. The paper examines the institutional changes which are at the root of the instability. What are the driving forces behind the introduction of the euro? What role do theoretical considerations play in this process? What influence on European integration has been exerted by neoliberal beliefs and convictions? Relying on an approach that combines basic insights of Gunnar Myrdal with Karl Polanyi's idea of a "double movement," it concentrates on the institutional transformation that is at the basis of the European integration process. The relationship between (misleading) ideas and facts is at the center of the study. It examines the influence of ideas and theoretical models on European integration, the Single Market Program, the Maastricht process, the increasing imbalances since the introduction of the euro, and the strategies applied during the recent crisis.
Economics; Philosophy
Keywords: economic integration; financial aspects of economic integration; financial crises; international institutional arrangements

Hard cash, easy credit, fictitious capital: Critical reflections on money as a fetishised social relation - Jessop, Bob (Finance and Society, 2015)
Sociology
Keywords: Marxism; commodity; credit; debt; fictitious capital; money

Marketization: Theoretical Reflections Building on the Perspectives of Polanyi and Habermas - Ebner, Alexander (Review of Political Economy, 2015)
The concept of marketization denotes the expansion of market coordination into non-market coordinated social domains as well as its intensification in already market-dominated settings. This article sets out to reconstruct an institutionalist theory of marketization. As a point of departure, it critically examines the related contributions of Karl Polanyi and Jürgen Habermas. The analytical strength of Polanyi's theory of marketization lies in the discussion of the contested embeddedness of markets and the view of marketization as a politically shaped process of institutional change. This concern with the societal expansion of markets is further developed in the Habermasian thesis of the ‘colonisation of the lifeworld’. However, both Polanyi and Habermas lack a specification of the social substance of markets and thus tend to underestimate the complexity of marketization. To address this issue, the present article utilizes the concept of collective goods to introduce new arguments about the institutional dynamics of marketization in the diverse fields of society.
Sociology; Political Science
Keywords: HABERMAS; Jurgen; collective goods; economics; embeddedness; marketization; markets; socioeconomics

Goody, Polanyi and Eurasia: An Unfinished Project in Comparative Historical Economic Anthropology - Hann, Chris (History & Anthropology, 2015)
Goody's essay overlaps with his recent work on the “search for metals” and, more generally, with his many books expounding the commonalities of Eurasian history. His critique of Eurocentrism remains invaluable. This review article argues that his emphasis on diffusion can be usefully supplemented with a concept of civilization, to facilitate comparative structural analysis. Goody's perspective might also be enhanced by an engagement with the literature on “Axial Age” cosmologies and with substantivist economic anthropology. It is worth revisiting Karl Polanyi's efforts to grasp the position of the economy in society, in order to recover in the neoliberal present the long-run Eurasian dialectic between redistribution and market exchange.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; civilization; culture diffusion; economic anthropology

Polanyi, Hayek, and the Impossibility of Libertarian Ideal Theory - Lindsay, Peter (Polity, 2015)
In 1944, two seminal works of political and social theory appeared: F.A. Hayek's The Road to Serfdom and Karl Polanyi's The Great Transformation. Both works focused on society's spontaneous resistance to the 'marketization' of life. Yet, the authors arrived at opposite normative conclusions. This article attributes the normative distance to a methodological clash over the role and limits of normative theorizing in the concrete and sometimes uncooperative world of politics. This clash, in turn, illuminates recent debates about 'ideal' and 'non-ideal' theory, and suggests limits to the applicability of the former.
Political Science
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Road to Serfdom (book); free enterprise; free markets; ideal theory; laissez-faire; libertarian theory; non-ideal theory

Marketization and the public-private divide - Rekhviashvili, Lela (International Journal of Sociology & Social Policy, 2015)
Purpose – The purpose of this paper is to critically examine the reasons behind a decade long contestations between the Georgian government and the petty traders over the access to the public space for commercial use. Design/methodology/approach – The paper relies on the repeated ethnographic fieldwork conducted in Tbilisi in 2012 and 2013. The ethnographic interviews with legally operating traders and illegal street vendors are supplemented by the in-depth interviews with the representatives of the city government and secondary literature on Georgia’s post-revolutionary transformation. Findings – Bridging the critical literature on the politics of the public space with Polanyi’s theory on commodification of fictitious commodities as a precondition of establishment of a market economy, the author argues that for the Georgian government control of the public space was necessary to pursue neoliberal marketisation policies. These policies required removal of the petty traders from public spaces because the state needed to restrict access to public space and limit its commercial usage to delineate public and private property and allow commodification of the urban land and property. As the commodification intensified and the rent prices started growing and fluctuating, the access to the public space became even more valuable for the petty traders. Therefore, the traders developed subversive tactics undermining the division between public and private space and property. Originality/value – The paper demonstrates the importance of enforcing the public-private divide in the process of establishing a market economy in transitional settings. Moreover, it illustrates little discussed social costs of establishing such a divide.
Sociology
Keywords: Tbilisi; commodification; fictitious commodities; informal economy; marketization; municipal government; neoliberalism; petty trade; public space; public spaces; public-private sector cooperation; transition economies

The Neoclassical Origins of Polanyi’s Self-Regulating Market - Gemici, Kurtuluş (Sociological Theory, 2015)
This article shows, through a detailed examination of Karl Polanyi’s published works and unpublished writings, that Polanyi relies heavily on the neoclassical economics of his time in his conceptualization of the market in capitalist societies. This approach is instrumental to the thesis of The Great Transformation concerning the destructive impact of the market on society. However, such an analytical perspective neglects the social character of the market economy. This perspective is also deficient in capturing why the market is destructive to the social fabric. By identifying the origins and limitations of Polanyi’s self-regulating market, this article contributes to critical reevaluations of his work that aim to expand the scope of Polanyian analysis. In particular, this article outlines how the analysis of the market’s contradictory place is not predicated on the notion of self-regulation. Polanyi’s own historical work, as opposed to his theoretical articulations, illustrates such an analysis.
Sociology
Keywords: double movement; neoclassical economics; self-regulating market

Migration, Precarization and the Democratic Deficit in Global Governance - Schierup, Carl-Ulrik; Ålund, Aleksandra; Likić-Brborić, Branka (International Migration, 2015)
This article attempts to provide a critical understanding of the dual signification of “precarity”. It explores what “precarity” as a concept may potentially offer to studies of the changing contemporary political economy of migration. It discusses shifting trends in global migration and point to tendencies for a possible convergence between “South” and “North”, “East” and “West”. Based on a review of current advances in research, it discusses, with reference to the classical work of Karl Polanyi, the potential for a contemporary “countermovement” which would challenge the precarity of migrants. Bringing forward the issue of the “space for civil society” the article addresses a still lingering democratic deficit in the global governance of migration. Policy Implications The article is relevant to policymakers, trade unions and civil society organizations. It contributes to the understanding of policy making processes in emerging multilevel global governance and focuses on issues of precarization, migration, and the implementation and accountability of human, migrant and labour rights.
Sociology; Anthropology
Keywords: countermovement; democratic deficit; ethnicity; global governance; migration; precarity; social welfare studies

Book Review Essay: The Environmental Crisis and Its Capitalist Roots: Reading Naomi Klein with Karl Polanyi*—Naomi Klein: This Changes Everything: Capitalism vs. the Climate - Adler, Paul S. (Administrative Science Quarterly, 2015)
An essay is presented on the relationship between climate change and capitalism, offering a reading of the argument in "This Changes Everything: Capitalism vs. the Climate" by Naomi Klein through the lens of the analysis in "The Great Transformation" by Karl Polanyi. The author suggests that Klein's argument is not clear on whether capitalism in any form or only the current, neoliberal version of capitalism is incompatible with effective action to address the problem of climate change. Topics include environmental externalities and policies addressing them, the environmental record of corporations, and the theory of the self-regulating market.
Business; Management Studies; Administrative Science
Keywords: Great Transformation; The (Book); KLEIN; Naomi; This Changes Everything (Book); business enterprises & the environment; capitalism; climatic changes; economic aspects; environmental policy; externalities

Between Marx and Polanyi: New labour mobilisations in the Italian crisis - Caruso, Loris (Capital & Class, 2015)
The current scenario in western countries is characterised by a crisis over the last thirty years of class conflict; by the mainly negative consequences of globalisation and of the transformations by production processes of the mobilising strength of work; by the cancellation of the relationship between labour and political representation; by the difficulties of traditional trade unionism; and by the emergence of the social movement unionism (SMU) paradigm. In this article, these phenomena are analysed from the point of view of the workers’ struggles against the closure of factories. The analysis concerns the mobilisation factors on which the struggle rests; the presence or absence, in the representations of workers, of references to class conflict; the major proximity of these mobilisations to the paradigm of traditional syndicalism or to the SMU paradigm; and the prevalence within them of the Marxist or the Polanyian root of conflict. This analysis is mainly based on an empirical study carried out in an engineering company in the province of Milan, Italy.
Sociology
Keywords: MARX; Karl; 1818-1883; class cleavage; class conflict; crisis; globalisation; globalizaton - research; labor mobility; labor unions; labour mobilisations; labour mobility; labour unions; research; social conflict; social movements

Hayek versus Polanyi: Espontaneidade e designio no capitalismo. (Hayek versus Polanyi: Spontaneity and Design in Capitalism. With English summary.) - de Almeida, Rafael Galvao; Garcia Fernandez, Ramon (Economica (Fluminense Federal University), 2015)
This work introduces the concept of spontaneous order, its development through many schools of economic thought and its importance to today's society. This paper gives emphasis to Friedrich Hayek, since he has the most known model of spontaneous order, how he started to elaborate from his research about the role of the information on the economy and his maturation in Law, Legislation and Liberty. As a counterpoint to the Hayekian model, this work includes criticism to the concept and the work of Karl Polanyi is analyzed. He diverged from Hayek about the role of the market in the society, when he affirmed that society protects itself from the invasion of the market in the other social spheres, through the process of double movement. Lastly, it is concluded that there is no evidence to discard the existence of spontaneous orders; the double, that double movement, because it is started with the individuals before taking legislative form, has the necessary characteristics to be considered a type of spontaneous order; and, due to the self-organizational trait of spontaneous order, there are practical problems in political anarchism.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; belief; communication; elections; history of economic thought; information and knowledge; learning; legislatures; lobbying; market structure; pricing; and design; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; rent-seeking; spontaneous order; unawareness; voting behavior

Strengthening Karl Polanyi’s Concepts of Reciprocity, Double Movement, and Freedom with the Assistance of Abductive Logic - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
My purpose here is to strengthen Karl Polanyi’s work through critique of and extension to abductive processes. Polanyi presented history woven into a new paradigm for analysis of socioeconomic systems, demonstrated discovery similar to abductive processes, and extended abduction into a holistic context. One of Polanyi’s most important contributions to socioeconomic analysis is the explanation of three integrated network models of socioeconomic reciprocity. They are coadjuvancy, redistribution, and market exchange. Polanyi extended abductive reasoning in two ways. First, he extended it beyond the cognitive logic of a person to inferences and societal belief changes of institutions. Second, he showed that, in the real world, beliefs are not only fixed like an abductive process, they are fixed in law. Throughout Polanyi’s historical presentation, market beliefs are being revised, thus serving as a demonstration of the abductive process. I make both positive and negative critique of a number of Polanyi’s concepts, with special attention to reciprocity, the double movement, and freedom. This critique and abduction extension strengthens Polanyi’s paradigm for future socioeconomic analysis with his integrative network models.
Economics
Keywords: abductive logic; beliefs; double movement; economic theory; freedom; production; reciprocity; reciprocity (commerce); socioeconomic; socioeconomics; stock exchanges

Gellner’s genealogy of the open society: Biopolitics as fragment and remainder - Ryan, Kevin (Thesis Eleven, 2015)
A decade before Foucault began to work with the related concepts of biopolitics and biopower, Gellner posed a series of questions which are suggestive of a similar line of inquiry. Gellner did not pursue this strand of his thought as an historical sociologist however. Instead he packaged it into a functionalist account of how industrial society reproduces itself. In Gellner’s writings, biopolitics is both present and absent, like a redacted text. This is the focus of this article, which locates Gellner’s method of inquiry within a corpus of genealogical studies that includes the work of Polanyi, Weber and Foucault. What distinguishes Gellner is that the history he reconstructs is a story of achievement in the face of terrible historical odds, but this culminates in a normative genealogy that limits the scope for critical analysis. The article concludes by adopting an alternative – yet still Gellnerian – approach to the question of social reproduction, thereby using Gellner to critique Gellner.
Political Science; Sociology
Keywords: FOUCAULT; Michel; 1926-1984; GELLNER; Ernest; biopolitics; biopolitics (philosophy); biopower; genealogy; historical sociology; realism; social aspects

Basic Income, Full Employment, and Social Provisioning: Some Polanyian/Keynesian Insights - Seccareccia, Mario (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
The purpose of this article is to offer a Polanyian perspective on the issue of guaranteed income (GI). In analyzing the debate over the Speenhamland system, especially as Karl Polanyi ([1944] 2001) describes it inThe Great Transformation, he offered an important criticism of a GI program that some contemporary Polanyian economists have been struggling to come to terms with in their writings. Instead of defending a GI policy by seeking to reject Polanyi’s analysis of the problem, I suggest that we should consider embracing Polanyi’s concern by proposing a comprehensive twin policy that would complement a basic income program with a Keynesian full employment commitment.
Economics
Keywords: English Poor Laws; Keynesianism; Speenhamland system; basic income; economists; full employment; full-time employment; guaranteed annual income; income; income supplementation

Provision of Social Costs and the Free Market: A Polanyian Perspective - Vidal, Gregorio; Marshall, Wesley; Correa, Eugenia (Journal of Economic Issues (Taylor & Francis Ltd), 2015)
In this article, we analyze at a conceptual level some of the more relevant effects of the neoliberal takeover on the provision of social costs, including employment, health care, and nutrition. Adopting key perspectives of Karl Polanyi and other thinkers, we develop our examination under the seemingly perpetual conflict between markets and social reproduction. We argue that financialization has both expanded market spaces and changed relationships within those spaces. The ever-greater domination of financial markets means that employment has become increasingly more precarious in the strict spaces of the labor market. At the same time, financialization has steadily eroded the social forms that exist outside of formal markets, greatly weakening the mechanisms through which societies can both defend themselves from predatory markets and reproduce themselves with some degree of purpose and hope for the future.
Economics
Keywords: employment (economic theory); externalities; externalities (economics); financialization; free enterprise; neoliberalism; nutrition; social reproduction

The course, contradictions, and consequences of extending competition as a mode of (meta-)governance: towards a sociology of competition and its limits - Jessop, Bob (Distinktion: Journal of Social Theory, 2015)
This article examines the use of competition as an object and mode of governance. It first considers how competition might become a principle of economic organization and, relatedly, how it may become part of state projects and practices. Second, it comments on the discursive and material dimensions of competition, considering it as a social construct and as a social constraint. Third, it examines the rather idealized representations of competition in the broader doxa of liberalism and neo-liberalism considered in terms of a rough threefold distinction among economic, political, and ideological imaginaries and the limits to the reproduction of these doxa in terms of the complexities of capitalist social relations. Fourth, it explores the complexities of competition in the actually existing world and their role in differential accumulation. In this context it distinguishes neo-classical, Austrian, and Schumpeterian views on competition and entrepreneurship and their contribution to equilibration or creative destruction. Fifth, it considers efforts to steer competition through, inter alia, the competition state and competition law. Sixth, it relates competition to other modes of governance and identifies limits to its role in this regard and introduces ‘meta-governance’ as a response to these limits. Finally, seventh, it comments on the fetishization of competition as a means to subsume society under the dominance of profit-oriented, market-mediated accumulation. It concludes with comments on the limits of competition in relation to fictitious commodities and goods and services that contribute to human flourishing.
Sociology
Keywords: commodification; competition; competition law; competition state; competitiveness; governance; neoliberalism; new public management; social theory

The Bioeconomy as Political Project: A Polanyian Analysis - Goven, Joanna; Pavone, Vincenzo (Science, Technology & Human Values, 2015)
The bioeconomy is becoming increasingly prominent in policy and scholarly literature, but critical examination of the concept is lacking. We argue that the bioeconomy should be understood as a political project, not simply or primarily as a technoscientific or economic one. We use a conceptual framework derived from the work of Karl Polanyi to elucidate the politically performative nature of the bioeconomy through an analysis of an influential Organization for Economic Cooperation and Development (OECD) initiative, The Bioeconomy to 2030. We argue that this initiative is a response to some of the most acute challenges facing the current neoliberal-capitalist accumulation regime, which seeks to protect and extend that regime, through both what it occludes and what it promotes. Rather than taking the bioeconomy as a description of some subset of economic activity, we regard it as a promissory construct that is meant to induce and facilitate some actions while deterring others; most explicitly, it is meant to bring about a particular set of political–institutional changes that will shape the parameters of possible future action. The bioeconomy concept highlights the potential dangers of failing to situate ethnographic examinations of horizontal micro-relations within a political–economic macro-context that enables and constrains. Scholarly work in science and technology studies and elsewhere that does not recognize the wider politics of the bioeconomy risks unintentionally contributing to the legitimation of this political project.
Political Science
Keywords: bioeconomy; commodification; cooperation; economics; ethnographic analysis; futures; inequality; literature; markets/economies; neoliberalism; organization; politics

Authoritarian Liberalism in the European Constitutional Imagination: Second Time as Farce? - Wilkinson, Michael A. (European Law Journal, 2015)
The current crisis in Europe recalls the theory and practice of authoritarian liberalism, the idea that in order to protect economic liberalism and respect for fiscal discipline, representative democracy must be curtailed. This configuration was first identified by Hermann Heller in late Weimar as a response to the imperative to maintain the ideological separation of state and economy and presented by Karl Polanyi as conditioned by broader geo-political pressure to maintain the gold standard in the inter-war period. Authoritarian liberalism is now conditioned by conflicting imperatives to maintain the project of the single currency, respect ordo-liberal concerns of moral hazard, and protect 'militant democracy' but only in one country. Does this reflect a broader geo-political disequilibrium, due to tensions between market integration, constitutionalism and democracy?
Law
Keywords: Europe; European Sovereign Debt Crisis; 2009-; HELLER; Hermann; 1891-1933; POLANYI; Karl; 1886-1964; authoritarianism; constitutionalism; democracy; equilibrium (economics); liberalism

After ideocracy and civil society Gellner, Polanyi and the new peripheralization of Central Europe - Hann, Chris (Thesis Eleven, 2015)
Behind only that of Bronislaw Malinowski, the influence of the Central European polymaths Ernest Gellner and Karl Polanyi on socio-cultural anthropology in the 20th century was profound. Gellner and Polanyi also influenced much wider swathes of scholarship. They belong to different generations and were raised in quite different settings in Prague and Budapest respectively. What these thinkers have in common is a philosophy of history which posits the industrial revolution in northwest Europe as a radical rupture in Weltgeschichte. Polanyi’s ‘great transformation’, with its focus on the economy, corresponds to Gellner’s metaphor of the ‘big ditch’ and focus on a new polity. The cultural homogenization of the nation-state and the disembedding of the economy from society in the era of free trade are two sides of the same coin. This paper argues that these complementary models derive to a considerable degree from the scholars’ background on the margins of industrializing Europe, in the ruins of the Habsburg Empire.
Anthropology
Keywords: Central Europe; GELLNER; Ernest; anthropology; civil society

To boldly go (Fund Strategy, 2015)
The article provides the author's view on issues concerning free market economics. He mentions Mr. Spock, a fictional character in the "Star Trek," whom critics of free market economics often cite as the epitome of rational economic man or Homo Economicus, as well as features Karl Polanyi, a Hungarian-American economist, who opposed the idea of humans as rational economic agents in his work "The Great Transformation." He also mentions human reason and cultural pessimism.
Economics
Keywords: Spock; Mr.; capitalism; economists; free enterprise

The limits to China's non-interference foreign policy: pro-state interventionism and the rescaling of economic governance - Gonzalez-Vicente, Ruben (Australian Journal of International Affairs, 2015)
China's foreign policy has been long committed to a principle of non-interference in the internal affairs of sovereign countries. While one could easily point out past and present-day inconsistencies in its implementation, this article argues that defenders and critics of the principle both rely on a limited interpretation of ‘interference’ or ‘intervention’ based on an ideology of Westphalian sovereignty. Particularly problematic is the conceptual distinction between the ‘political’ or ‘diplomatic’, on the one hand, and the ‘economic’, on the other. As Polanyi's concept of embeddedness reminds us, markets, society and politics occur simultaneously, and can only act as discrete realms in epistemological abstractions. It is thus argued that non-interference is a semi-formal institution that governs China's diplomatic engagements and affects its economic activities. While the totality of China's interactions with the world has diverse and sometimes contradictory impacts on global governance, non-interference itself has apparent consequences for the rescaling of regional economic governance. Specifically, this article contends that Chinese non-interference results in the empowerment of political elites at national levels, and thus in the (re-)emergence of the nation state as a gatekeeper and facilitator of the advancement of capitalist enterprises. As a result, through non-intervention, China's foreign policy undermines supranational regulatory approaches and fosters state-based regional architectures.
Development Studies; International Relations
Keywords: China; China - foreign relations; People's Republic of China; Westphalians - foreign countries; bilateralism; economic policy; embeddedness; foreign policy; non-interference; socioeconomic theory; supranationalism

Explaining Political Tunnel Vision: Politics and Economics in Crisis-Ridden Europe, Then and Now - Mudge, Stephanie L. (European Journal of Sociology, 2015)
The grip of austerity in European politics since 2008 presents a double puzzle: electorally weak center-left parties offering no definite alternative, and the surprisingly efficient pursuit of “fiscal consolidation”. To understand this double puzzle this article investigates the institutional bases of alternative economic thinking during the 1930s versus the post-2008 crisis years. Noting the recent prominence of a new social type, the European economist-technocrat (eet), I highlight the historically specific order to which the eet is indigenous: rarefied, international professional circuits that tend to work over, not through, party politics. This contrasts sharply with the nationally-based, party-connected economists who developed new economic orthodoxies between the 1930s and 1960s, including Keynes himself. Approaching the study of economic culture in the public sphere in a Polanyian moral markets framework, I argue that the linkages between European economics and financial technocracies help to explain Europe’s double puzzle. Theoretically, I argue that a focus on expertise and parties, and not just states, is central to our understanding of economic culture in the public sphere. (English)
Sociology
Keywords: European Union; Europäische Union; Frachkenntnisse; Sparmaβnahmen; Union européenne; austerity; austerité; compétence; economics; economists; expertise; partis politiques; political parties; politics and economics; politischen parteien; public sphere; technocracy; wirtschaft; économie

A Neo-Polanyian Theory of Economic Crises - Block, Fred (American Journal of Economics and Sociology, 2015)
This article seeks to use Karl Polanyi's book, The Great Transformation, first published in 1944, to understand the global financial crisis that began in 2008. Polanyi's basic premise was that a great crisis must result from powerful causes. He argued that the crisis of the 1930s was a consequence of three distinct processes: deep imbalances in the global trading system, a crisis within the global financial mechanism that was supposed to manage those imbalances, and a failure of adaptation in the world's leading economy, the United States. The same processes can be seen at work in the last decade.
Sociology
Keywords: global financial crisis

Pursuing a Great Transformation - Evans, Peter (Sociology of Development, 2015)
Polanyi offers a powerful vision of a “great transformation” that will reverse the subordination of society to the economy and reassert the primacy of social protection in the context of modern society. Pursuit of the great transformation is one way of conceptualizing the quest for “development” in the positive sense of ecologically sustainable human flourishing. This paper explores how the contemporary interaction of national and global political dynamics affects the trajectory of Polanyi's “double movement.” Does the shift of economic power to globally organized capital while the space for contentious politics remains primarily at the national level “checkmate” the movement for social protection? Or is there more potential for political contestation and policies supporting social protection at the national level than the “global checkmate” thesis claims? And, if so, can this potential be magnified by productive, synergistic alliances between national and global movements, resulting in a global auxiliary effect instead of a global checkmate effect? Answering these questions requires analyzing the relative autonomy of national political regimes vis-à-vis global capital as well as evaluating the ability of movements to connect effectively across levels.
Sociology
Keywords: Great Transformation; The (Book); double movement; global capital; social protection; transnational social movements

The power of market fundamentalism: Karl Polanyi's critique - Gamble, Andrew (Cambridge Review of International Affairs, 2015)
Political Science
Keywords: BLOCK; Fred; Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; markets; nonfiction; review

Protecting Markets from Society: Non-Pecuniary Claims in American Corporate Democracy - Gershenson, Carl (Politics & Society, 2015)
The state incentivizes investors to entrust capital to public corporations by granting shareholders enforceable rights over managers. However, these rights create legal “access points” through which social movements can make nonpecuniary claims on the corporation. I use original historical research on the Securities and Exchange Commission’s administration of federal securities law to show that concern over nonpecuniary claims motivates the state to enact the role of “market protector.” In this role, the commission insulates managers of corporations from shareholders’ claims that it deems illegitimate because they are insufficiently profit-oriented. Thus the inverse of Polanyi’s observation that society protects itself from markets is also true: the state creates market boundaries so that “always embedded” markets function more like autonomous, profit-oriented markets. Accordingly, the extent to which corporate democracy represents general, social interests or narrow, profit-oriented interests is largely a function of political contestation and state policy.
Sociology
Keywords: United States; United States Securities & Exchange Commission; corporate accountability; corporate democracy; corporations - government policy; economic sociology; legal status of stockholders; markets; markets - government policy; political sociology; social responsibility of business - United States

Reading The Great Transformation - Martin, Isaac William (Contemporary Sociology, 2015)
Karl Polanyi’s book The Great Transformation is a classic... it has come to be recognized as a founding charter for economic sociology. It anticipated major accomplishments of late-twentieth-century social science (including, among others, Ben Bernanke’s studies of the Great Depression and Amartya Sen’s work on famine). Its core problems—how do societies respond to globalization? how do they address the risks of market failure?—are central to contemporary macrosociology. It is probably time to recognize the canonical status of this book and put it on the classical theory syllabus alongside Marx, Weber, and Durkheim. But The Great Transformation is also—can we admit this about our classics?—a mess. It is conceptually sloppy. Some key terms (such as “market society” and “social dislocation”) are never explicitly defined. Others (such as “a ‘movement’”) are defined with pedantic care, and then used willy-nilly, as if Polanyi forgot what he said the words meant. Important steps in the argument assume what is to be proven. Inconsistencies abound. The treatment of historical sources is casual. To round it all off, the book concludes with a breathtakingly wrong prediction: namely, that the era of market liberalism is over for good—as of 1944. To salvage a theory from all this, let alone one that we can apply to societies in the present day, surely requires a heroic effort of interpretation. Fred Block and Margaret R. Somers undertake the salvage effort...
Sociology
Keywords: BLOCK; Fred L.; Great Transformation; The (Book); Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; book review; nonfiction

Mobilizing the depths of the market: Motivation research and the making of the disembedded consumer - Schwarzkopf, Stefan (Marketing Theory, 2015)
Twentieth-century consumer society was characterized by a process of disembedding as described by Karl Polanyi in The Great Transformation (2001 [1944]). The Austro-American consumer researcher Ernest Dichter played a key role in preparing the ideological framework necessary for this process to succeed. In order to assess Dichter’s role and that of psychoanalytic motivation research in general in the creation of the idea of the disembedded consumer, this article presents an analysis of Dichter’s unpublished consumer research reports ranging across different countries and industries between 1939 and 1973. Through content analysis and historical contextualization, I show that Ernest Dichter in particular and psychoanalytic motivation research in general were instrumental in removing from market relationships the invisible hand of social norms. The case of the consumer psychoanalyst Ernest Dichter thus provides new insights into the sociocultural mechanisms by which theorizing in consumer research can influence the objects of its theorizing.
Business; Marketing
Keywords: DICHTER; Ernest; consumer research; disembedding; interpersonal relations; market society; marketing; motivation research; pleasure principle; psychoanalysis; therapeutic ethos

Mutating Neoliberalism: The Promotion of Italian Investors in Slovakia before and after the Global Financial Crisis - Sellar, Christian; Pástor, Rudolf (International Journal of Urban & Regional Research, 2015)
In the context of the literature on 'actually existing neoliberalisms', this article analyzes the policies and services supporting Italian foreign direct investment (FDI) in Slovakia. It identifies a group of organizations, both Slovak and Italian, which shape and deliver neoliberal pro-FDI policies. By studying such an 'investment promotion community' (IPC) before and after the global financial crisis of 2009, and during Italy's prolonged crisis, this article shows both the persistence and adaptability of neoliberal policies and institutions. In so doing, it highlights some of the transnational flows underpinning the 'domestication' of neoliberalism in Slovakia. These findings support recent literature arguing that post-crisis neoliberalism can be interpreted as a stunted Polanyian double movement, in which the state has improved some of its regulatory functions but without questioning the overarching neoliberal principles. Specifically, it shows that FDI policies and the support of Italian investors rest upon a professional community that has not changed much since the 2009 crisis. This community played a crucial role in embedding neoliberal rationalities in Slovakia and supports the persistence of this ideology in the post-crisis environment.
Political Science; Public Administration
Keywords: Bratislava; Italy; Košice; Kralovsky Chlmec; Slovakia; Slovakia - economic conditions; Slovakia - foreign economic relations; capitalists & financiers; double movement; financial crisis; foreign direct investment; foreign investments; global financial crisis; 2008-2009; neoliberalism

Embedding and disembedding of political elites: a filter system approach - Davis, Aeron (Sociological Review, 2015)
This article looks at the issue of political disengagement in mature democracies and the growing tendency towards disconnect between citizens and their political representatives. It locates itself in relation to 'demand-side' (external to politics) and critical 'supply-side' (focused on the political centre) explanations of disengagement. It concentrates on the latter and, accordingly, builds on critical, post-Marxist and elite-oriented work. As such it follows on from earlier calls in the journal for a return to elite-based research ( Savage and Williams, 2008). Drawing on general concepts in economic sociology ( Polanyi, Granovetter) the article presents an alternative embedding-disembedding paradigm for explaining and evaluating this tendency towards political elite disengagement. The propensity for politicians to disembed from wider society is explained by way of a series of eight 'filters'. Such filters work, alone or cumulatively, both to socially embed political elites within the institutions and networks of formal politics and also to disembed them from wider society and the populace they represent. The interpretive framework outlined here draws on a combination of secondary literature and ongoing interview-based research with some 150 political actors (politicians, journalists, officials) working at Westminster. As such, the filters and embedding-disembedding paradigm focuses primarily on the UK case. However, the framework is easily adaptable to other nations and systems.
Sociology
Keywords: Great Britain - politics & government; communication; disengagement; elite (social sciences); embedding/disembedding; organizations; political communication; political elites; political organizations; political participation laws; politicians

The New ‘Passive Revolution’ of the Green Economy and Growth Discourse: Maintaining the ‘Sustainable Development’ of Neoliberal Capitalism - Wanner, Thomas (New Political Economy, 2015)
This paper analyses the rapidly emerging discourse of a green economy based on green growth. It highlights inherent conflicts and contradictions of this discourse such as the myth of decoupling growth from the environment, pollution generations and resource consumption. Using key theoretical constructs of both Gramsci and Polanyi, the paper argues that the green economy/growth discourse can be seen as a Gramscian ‘passive revolution’ whereby the dominant sustainable development discourse, subsumed by capitalist hegemony, is protected in the context of global environmental, economic and development crises. The ‘neoliberalising of nature’, or in other words, the privatisation, marketisation and commodification of nature, akin to Polanyi's fictitious commodities, continues and intensifies with green economy/growth strategies. Greening the economy and associated strategies of green growth divert attention from the social and political dimensions of sustainability and issues of social and international justice. In this way, the inexorable march or ‘sustainable development’ of neoliberal capitalism is maintained. This paper goes on to argue that contesting the claims of green economy/growth discourse through political struggles by civil society against the neoliberalisation of nature is a sign of a slowly emerging counter-hegemonic ‘double movement’ which challenges capitalist hegemony and the commodification of society–nature relations.
Geography
Keywords: GRAMSCI; Antonio; 1891-1937; environmental economics; fictitious commodities; green economy; green growth; neoliberalising nature; neoliberalism; passive revolution; privatization; research; social justice - environmental aspects; sustainable development

Facing an unequal world - Burawoy, Michael (Current Sociology, 2015)
To face an unequal world requires us to interpret and explain it, to be sure, but also to engage it, that is, to recognize that we are part of it and that we are partly responsible for it. In other words, inequality is not just something external to us, but also invades our own world. I begin, therefore, by examining the global community of sociology through the lens of inequality. I then consider two recent perspectives on our unequal world from outside sociology: the moral radicalism of Pope Francis that emphasizes exclusion from market society, and the innovative research of the economist Thomas Piketty that emphasizes unequal inclusion in market society. These two faces of global inequality mirror the social movements reverberating from the economic crisis of 2008 but which have their roots in a reaction to a broader wave of marketization, the third to engulf modern capitalism. To explore the meaning of third-wave marketization, otherwise known as neoliberalism, and the social movements it provokes I draw on two concepts from Karl Polanyi – ‘fictitious commodities’ and ‘countermovement’ – as well as a theory of the dynamics of capitalism. I conclude with three challenges facing a global sociology that centers social movements: to develop a theory that speaks to the globally diverse experiences of commodification; to develop a methodology that recognizes that we are unavoidably participants in the world we study; and to develop a politics that defends a particular vision of that world, a vision that has defined the sociological tradition from its beginning, namely one that upholds the centrality of civil society against the over-extension of market and state.
Sociology
Keywords: globalization; inequality; markets; social movements; sociology

Karl Polanyi's Environmental Sociology - Fenner, Weston Henry, IV; Brechin, Steven R. (Conference Papers – American Sociological Association, 2015)
Drawing upon The Great Transformation (1944), we outline Karl Polanyi's environmental sociology by presenting his major insights on economic substantivism, fictitious commodities, and double movements. Polanyi wrote his opus in challenge to Von Mises' Austrian School of Economics and its pursuit of an autonomous, self-regulating global free market. Polanyi's recognized the social and environmental limits of a fully free market and reasoned that inevitable market excesses would result in the rise of society self-protection to preserve land along with labor and money. We believe Polanyi's insights make him an important classical contributor to environmental sociology on par with Robert Malthus, Karl Marx, Max Weber, and Emile Durkheim. We conclude by outlining possible connections to established environmental sociology theories and literatures.
Sociology
Keywords: double movement; double movements; economic substantivism; environmental sociology; fictitious commodities; market fundamentalism; social theory

Challenging Dominant Market Theories in Five Ways[1] - Janoski, Thomas (disClosure, 2015)
This article discusses why many social scientists including Karl Polanyi, Max Weber, and Karl Marx are dissatisfied with an overreliance on markets, and a conceptualization of markets being efficient, fair and rational. Topics include five types of arguments critical of markets including the Marxian approach to markets, the rise of Karl Polanyi's view that markets are fragile, and a more complex decision-making approach starting with Max Weber's view of social action.
Sociology
Keywords: MARX; Karl; 1818-1883; WEBER; Max; 1864-1920; markets; social action; social scientists

Toward a Sartrean Economics - Kail, Michel; Sobel, Richard (Rethinking Marxism, 2015)
Despite the absence of a systematic analysis of economics in Sartre's work, we argue that a Sartrean economics can indeed be said to exist, even if it is an economics that still awaits development. The status that Sartre accords to the concept of scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason but should be considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man's confrontation with a typically ungrateful nature but should rather be articulated through the concept of the world as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: POLANYI; Karl; 1886-1964; SARTRE; Jean-Paul; 1905-1980; economic systems; economism; scarcity; world

The Limits of Transformation: Contemporary Applications of Karl Polanyi - England, Christopher (Journal of Australian Political Economy. Summer2015/16, Issue 76, 2015)
The article explores the conception of the Great Transformation (GT) by economic historian Karl Polanyi and its contemporary applications. Topics covered include the continued existence of free market fundamentalism as a prominent ideology and as a living political project, the persistence of free market utopianism, and Polanyi's genealogy of the market system. Also discussed are his conception of industrialism and his use of functionalist theory to build a unified image of the social system.
Political Science
Keywords: economics; free enterprise; functionalism; industrialism; political economy; social systems; utopias

A Reversed Double Movement in Brazil: The (Controversial) Evolution of the Partido dos Trabalhadores' Education Policy since 1980 - Guedes-Neto, Joao Victor (Journal of International Studies, 2015)
Karl Polanyi identified a double movement which took place during the bourgeoisie hegemony when, instead of liberalism, it has made use of interventionism to perpetuate its domination over the working class. Several studies have tried to update his analysis by identifying the double movement nowadays. Nevertheless, the academia has not addressed the possibility of a reversed phenomenon where the working class would make use of liberalism to perpetuate itself in power. This paper aims at analyzing the Brazilian case where the Partido dos Trabalhadores, a proxy for the working class, has implemented pro-market policies in higher education. Whereas the party has not passed through structural reforms such as the British and German working class parties, it has drastically changed its approach to policy-making and campaigning since its origin in 1980. The study concludes that a reversed double movement may occur when the working class is in charge of the government.
Political Science; International Relations
Keywords: double movement; economic development; education; education: government policy; human development; human resources; income distribution; migration; national government expenditures and education

Law, Fugitive Capital and Karl Polanyi's the Great Transformation - Kendall, Walter J. III (Indonesian Journal of International & Comparative Law, 2015)
Law
Keywords: embeddedness; law and economics; law and society; legal philosophy; legal reform; liberalism

Critique and transformation: On the hypothetical nature of ecosystem service value and its neo-Marxist, liberal and pragmatist criticisms - Melathopoulos, Andony; Stoner, Alexander (Ecological Economics, 2015)
Ecosystem service valuation (ESV) attempts to transform the opposition of human economic necessity and ecological conservation by valuing the latter in terms of the services rendered by the former. However, despite a number of ESV-inspired sustainability initiatives since the 1990s, global ecological degradation continues to accelerate. This suggests that ESV has fallen far short of its goals of sustainable social transformation—a failure which has generated considerable criticism. This paper reviews three prominent lines of ESV criticism: 1) the neo-Marxist criticism, which emphasizes the “fictitious” character of ecosystem commodities; 2) the liberal criticism through Friedrich Hayek's concept “scientistic objectivism”; and 3) the pragmatist criticism of “value monism”. Although each form of criticism provides insight into the limitations of ESV, all share ESV's inability to discern what kind of social transformation is possible . Unable to provide an account of their own immersion in social and historical context, these approaches operate in the hypothetical . In light of these shortcomings, this paper advances a critical theory approach, which we contend provides conceptual tools uniquely well-suited to more adequately address the question of social transformation.
Economics
Keywords: Marxian economics; ecosystem services; neoliberalism; pragmatism; social development

Economics Humanized - Pearson, Dan (Issues in Science & Technology, 2015)
Science & Technology
Keywords: BLOCK; Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; book review; economics; nonfiction; science and technology

Contesting 'Actually Existing' Neoliberalism - Ryan, Matthew (Journal of Australian Political Economy, 2015)
The article explores the established conception of actually existing neoliberalism. Topics covered include free-market neoliberalism, the nature of neoliberal theory, and the distinction between esoteric and exoteric neoliberalisms. Also discussed are the ideas of scholars Karl Polanyi and Ha-Joon Chang about the role of the state in capitalist development, and scholar Damien Cahill's idea that neoliberalism is defined by microeconomic policies of privatization, marketization and deregulation.
Political Science
Keywords: CAHILL; Damien; CHANG; Ha-Joon; esotericism; free enterprise; neoliberalism; political economy

The politics of Piketty: what political science can learn from, and contribute to, the debate on Capital in the Twenty-First Century - Hopkin, Jonathan (The British Journal of Sociology, 2014)
Thomas Piketty's imposing volume has brought serious economics firmly into the mainstream of public debate on inequality, yet political science has been mostly absent from this debate. This article argues that political science has an essential contribution to make to this debate, and that Piketty's important and powerful book lacks a clear political theory. It develops this argument by first assessing and critiquing the changing nature of political science and its account of contemporary capitalism, and then suggesting how Piketty's thesis can be complemented, extended and challenged by focusing on the ways in which politics and collective action shape the economy and the distribution of income and wealth. Although Capital's principal message is that ‘capital is back’ and that without political interventions active political interventions will continue to grow, a political economy perspective would suggest another rather more fundamental critique: the very economic forces Piketty describes are embedded in institutional arrangements which can only be properly understood as political phenomena. In a sense capital itself – the central concept of the book – is almost meaningless without proper consideration of its political foundations. Even if the fact of capital accumulation may respond to an economic logic, the process is embedded in a very political logic. The examples of housing policy and the regulation, and failure to regulate, financial markets are used to illustrate these points.
Sociology
Keywords: capital; inequality; institutions; political science

Environmental protection as market pathology?: carbon trading and the dialectics of the 'double movement' - Carton, Wim (Environment & Planning D: Society & Space, 2014)
Polanyi's concept of the 'double movement' is frequently interpreted as the opposition between the problematic and unsustainable dynamics of the market and the benign and normatively desirable reaction against this by 'society'. This paper questions this dualistic interpretation of the double movement and undertakes a problematization of the Polanyian idea of social and environmental protection. It does this by revisiting the concept of the double movement in light of the recent proliferation of market-based mechanisms for environmental regulation. Through an exploration of the different interpretations of Polanyi's work, the paper presents a dialectical reading of the double movement that conceptualizes the idea of social protection within a broader capitalist framework. This is then illustrated with the case of emissions trading as a particular form of environmental protection. Carbon trading as a mitigation strategy, it is argued, corresponds to the Polanyian idea of 'social protection' in that its protective potential to reduce emissions is itself constrained by the socioeconomic framework within which it operates. This in turn points to the need for a critique of climate mitigation efforts that goes beyond a focus on current problems with emissions trading schemes.
Geography
Keywords: EU Emissions Trading Scheme; carbon offsetting; climate change; countermovement; emissions trading; environmental protection; pathology; socioeconomics

Towards a Polanyian Sociology - Gemici, Kurtuluş (European Journal of Sociology, 2014)
Sociology
Keywords: BLOCK; Fred L.; Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); SOMERS; Margaret R.; anthropology; nonfiction; review

Capital in the Twenty-First Century by Thomas Piketty translated by Arthur Goldhammer (Cambridge, MA, Harvard University Press, 2014) - Milkman, Ruth (European Journal of Sociology / Archives Européennes de Sociologie, 2014)
KM - A book review of Capital in the Twenty-First Century that points out the glaring omission of Polanyi.
Sociology
Keywords: Great Transformation; The (Book); PIKETTY; Thomas; book review

Polanyian Reading of the Socio-Economic Transformations of the European Union - Savevska, Maja (Journal of Contemporary European Studies, 2014)
In an attempt to analyse the socio-economic transformations of the European Union, an increasing number of scholars have resorted to Polanyi's double movement thesis. In doing so, some scholars, by looking at the evidence of intensified marketisation of social relations, consider the EU disembedded; whereas others identify a re-embedding tendency in the recent surge of socio-environmental protection. The paper follows Lacher, Burawoy, Dale and Streeck's readings of Polanyi and argues that the exiting socio-environmental provisions do not re-embed the economy. Socio-environmental protection does not eclipse the neoliberal accumulation strategy which continues to propagate the disembedding tendency, because it fails to decommodify fictitious commodities. The EU is characterised by a heightened intensification of both disembedding and protective tendencies, which Polanyi contends is disruptive in nature. What emerges out of the dialectics between neoliberalisation and socio-environmental provisions is a decelerated rate of change, which, although it temporarily secures the habitation of man, prevents the inception of a synthesis that is capable of sublating the contradictions of the marketisation/protection binary. Moreover, we have a paradoxical situation wherein the socio-environmental measures, despite their protective invocation, are predicated on deepened commodification.
Political Science
Keywords: European Union; commodification; disembedded; double movement; international political economy; neoliberalism; socioeconomics

Polanyian Themes: From Budapest to the Caribbean - Block, Fred (Development & Change, 2014)
KM: Book review of "From the Great Transformation to the Great Financialization"
Sociology
Keywords: FROM the Great Transformation to the Great Financialization (Book); From the Great Transformation to the Great Financialization (Book); LEVITT; Kari; 1923-; POLANYI LEVITT; Kari; economic development; nonfiction

Towards a neo-Polanyian approach to money: integrating the concept of debt - Saiag, Hadrien (Economy & Society, 2014)
This paper aims to reconsider Polanyi's approach to money. His best-known writing on money uses is deeply original and presents strong insights that dissociate money from the concept of the market. Polanyi also developed an interesting non-dichotomous understanding of money in hisThe great transformation. However, taken together, these two contributions lead to some unresolved questions: his critique of the orthodox approach to money is ambivalent; his argument to separate payment from account is weak; and, most important, he ultimately makes an incomplete break with the classical real/monetary dichotomy. This paper proposes a distinction between money as a set of instruments and practices and money as a concept, through the integration of John Commons's concept of debt into Polanyi's framework. This reformulation allows us to resolve Polanyi's unresolved questions while preserving his major contributions, and leads to a more complex understanding of money.
Economics; Anthropology
Keywords: COMMONS; J.R.; COMMONS; John; Great Transformation; The (Book); debt; debt management; economic anthropology; economic aspects; economics; money plurality; political aspects; theories of money

The Precariat - Standing, Guy (Contexts: Understanding People in Their Social Worlds, 2014)
Economist Guy Standing explains how millions of people are in the precariat, and in defining this emerging class, points to the dangerous political and social consequences as well as the exciting progressive revival that this class could produce.
Economics
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; class inequality; economics; labor; labour; politics; precariat; precarity; social classes; welfare economics

The Anthropology of Money and Finance: Between Ethnography and World History - Hart, Keith; Ortiz, Horacio (Annual Review of Anthropology, 2014)
We review here recent developments in the anthropology of money and finance, listing its achievements, shortcomings, and prospects, while referring back to the discipline's founders a century ago. We take our departure from the work of Marcel Mauss and Karl Polanyi, both of whom combined openness to ethnographic research with a vision of world history as a whole. Since the 1960s, anthropologists have tended to restrict themselves to niche fields and marginal debates. The anthropological study of money and ethnographies of finance, in particular, have been the focus of much research since the 1980s. Despite taking on new objects and directions, anthropologists still find it difficult to connect their situated analyses with global processes and world history. We propose some conceptual and empirical directions for research that would seek to overcome these limitations by integrating ethnography more closely with human history, while stressing the importance of money in shaping world society and attempts to reform it.
Anthropology
Keywords: MAUSS; Marcel; 1872-1950; distribution; economic anthropology; ethnology; exchange; finance; globalization; history; money; politics; world society

Income Inequality in Advanced Capitalism: How Protective Institutions can Promote Egalitarian Societies - Kollmeyer, Christopher (Comparative Sociology, 2014)
This study develops a Polanyian perspective on income inequality in advanced capitalist countries. Polanyi's historical account of the rise and fall of classic liberalism in Britain illustrated how social groups and society at large devised "protective institutions" to shield themselves from socially destructive market forces. Recent qualitative applications of this idea identify three protective institutions as being the most important - the public sector economy, trade unions, and the family. Using data from 16 Western countries from 1970 to 2010, this study demonstrates that cross-national and temporal variations in these protective institutions explain a considerable amount of the observed patterns of income inequality among these countries, helping to explain why some countries have recently experienced rising inequality but others have not. The study ends by arguing that a Polanyian perspective provides more analytical and theoretical leverage than other sociological approaches to understanding income inequality.
Sociology
Keywords: The Great U-Turn; capitalism; economic sociology; income distribution; income inequality; labor unions; labour unions; liberalism; protective institutions; research; social groups - research

On the Dialectics of Global Governance in the Twenty-first Century: A Polanyian Double Movement? - Patomäki, Heikki (Globalizations, 2014)
Following decades of economic globalisation and market-oriented reforms across the world, Karl Polanyi'sdouble movementhas been invoked not only to explain what is happening but also to give reasons for being hopeful about a different future. Some have suggested a pendulum model of history: a swing from markets to society leading, in the next phase, to a swing from society to markets, and so on. The double movement can also be understood dialectically as a description of an irreversible historical development following its own inner laws or schemes of development. Going beyond a thesis–antithesis–synthesis pattern, I maintain that conceptions and schemes drawn from dialectics, and especiallydialectical critical realism, can provide better geo-historical hypotheses for explaining past changes and for building scenarios about possible future changes. I analyse political economy contradictions and tendencies, and focus on normative rationality, to assess substantial claims about rational tendential directionality of world history. I argue that democratic global Keynesianism would enable processes of decommodification and new syntheses concerning the market/social nexus. A learning process towards qualitatively higher levels of reflexivity can help develop global transformative agency. Existing contradictions can be resolved by means of rational collective actions and building more adequate common institutions. These collective actions are likely to involve new forms of political agency such as world political parties. (English)
Political Science
Keywords: 21st century; Keynesian economics; contradiction; critical realism; dialectic; double movement; economics - history; global governance; globalization; market; political economy; political parties; scenario; utopia

Class Struggle or Embedded Markets? Marx, Polanyi and the Meanings and Possibilities of Social Transformation - Selwyn, Benjamin; Miyamura, Satoshi (New Political Economy, 2014)
Marx and Polanyi both held that socialism, in one form or another, was a preferable and possible alternative to capitalism. Their ideas are seen to offer theoretical tools to understand the tensions and contradictions of capitalism, and to inform ways to overcome them. This paper discusses Polanyi's work from a Marxist perspective in order to illuminate his strengths and weaknesses. Its main focus is to discuss Polanyi's juxtaposing of commodification against exploitation, in diagnosing the problems of capitalist expansion. We suggest that by juxtaposing these two moments, Polanyi not only misses out on a crucial arena of capitalist activity (exploitation), but also undermines his own explication of processes of commodification. This has deleterious consequences for his understanding of the prevalence of poverty under capitalism. It also means that his vision of social transformation and of socialism is profoundly different, and potentially antithetical, to that of Marx. We suggest that for Polanyi's conception of de-commodification to gain greater traction it needs to be combined with Marx's analysis of exploitation and class struggle.
Political Science; Economics
Keywords: MARX; Karl; 1818-1883; Polanyi; commodification; exploitation; historical materialism; institutionalism

Informalizing the Economy: The Return of the Social Question at a Global Level - Breman, Jan; van der Linden, Marcel (Development and Change, 2014)
The classical conceptualization of the working class, of workers’ collective action and, especially, of trade unionism, was implicitly or explicitly based on the Standard Employment Relationship that, for a few decades, has been dominant in North America, Europe, Japan and Australasia. The ‘classical’ model of collective bargaining, which has shaped the world's traditional labour movements, was based on this conceptualization. However, it is now increasingly undermined by the rapid spread of ‘informal’ or ‘precarious’ labour in the global North. It is our contention that the ‘classical’ view of the working class and workers’ collective action is fundamentally biased and takes as a norm or standard what was in fact an historical exception. The real norm or standard in global capitalism is insecurity, informality or precariousness, and the Standard Employment Relationship is an historical phenomenon which had a deep impact in a limited part of the world for a relatively short period of time. If, as we argue, the ‘Rest’ is not now becoming like the ‘West’, but the other way round, then the ‘traditional’ forms of collective action that have developed in the North Atlantic region during the last two centuries are gradually losing much of their impact. New forms of collective action are emerging, though these are often still at an embryonic stage. It is, therefore, high time to rethink the concept of the working class and the ways in which it can further its interests.
Sociology
Keywords: informalization; precarity

Introduction: The ‘Labour Question’ in Contemporary Capitalism - Chhachhi, Amrita (Development and Change, 2014)
The recent upsurge in workers’ struggles globally has bought labour again to the forefront, despite predictions that the working class was no longer relevant as a force for social transformation. Neoliberal globalization, with the hypermobility of capital, has led to the emergence of new forms of flexible work/labour, the co-existence of old and new working classes, and an extreme rise in inequality, realigning class structures nationally and globally. Financialization has ushered in a new regime of accumulation and there is a deepening crisis of reproduction. Can a Marx plus Polanyi theoretical integration capture contemporary dynamics of capitalist globalization and the role of labour? What do the trajectories of such struggles in the South tell us about the limits and potentialities for a counter-capitalist movement? More crucially, is the route to full social citizenship entitlements still possible via employment (with its further extension universally), or is it to be reached by directly demanding citizenship rights, bypassing labour-based demands? How do recent collective actions express workers’ interests/identities as workers, citizens and consumers? What role is the state playing in responding/mediating/facilitating these struggles? The Introduction delineates some of these contentious issues which frame this Forum Debate. The contributors all offer different perspectives and critical insights on the connections between forms of labour, possibilities for action and organization, the relationship between labour struggles and social citizenship and the role of the state in contemporary capitalism. The conclusion reflects on some of the equally controversial proposed alternatives and argues for going beyond minimalism and for the imperative of radical rethinking to ensure dignified work and full social citizenship entitlements as part of a new social emancipatory political project.
Development Studies
Keywords: MARX; Karl; 1818-1883; capitalism; globalization; labor question; labour question; neoliberalism

Reclaiming Karl Polanyi, Socialist Intellectual - Clark, Timothy David (Studies in Political Economy, 2014)
The crisis of neoliberal globalization has led many scholars back to Karl Polanyi in their search for alternatives to the present malaise. The dominant reading appropriates the concepts of embeddedness and the double movement in support of a system of regulated, welfare-state capitalism. This article contends, however, that the concepts of embeddedness and the double movement point not towards the need to regulate capitalist markets, but towards the radical supersession of capitalism itself.
Political Science
Keywords: Canada; capitalism; globalization; radical change

Alienated Politics: Labour Insurgency and the Paternalistic State in China - Friedman, Eli (Development and Change, 2014)
Is there a labour movement in China? This contribution argues that China does not have a labour movement, but that contestation between workers, state and capital is best characterized as a form of ‘alienated politics’. Widespread worker resistance is highly effective at the level of the firm because of its ability to inflict losses on capital and disrupt public order. But authoritarian politics in China prevent workers from formulating political demands. Despite the spectacular repressive capacity of the state, the central government has in fact responded to highly localized resistance by passing generally pro-labour legislation over the past decade. The consequence of this is that worker unrest has produced important political shifts at the national level, but these have come about without workers’ direct involvement in the process. In other words, workers are alienated from the political object that they themselves have produced. As a consequence, when the state intervenes in labour politics, it appears to be doing so of its own accord, i.e. paternalistically. This framework helps us to understand how worker unrest in China has become highly antagonistic towards employers and the local state, while maintaining the stability of the system as a whole.
Sociology; Labor Studies
Keywords: China; alienated politics; labor movement; labour movement; paternalistic state

Capital–Labour and State Dynamics in Export Horticulture in North-east Brazil - Selwyn, Ben (Development and Change, 2014)
This article argues for the primacy of class relations and struggles as determinants of developmental processes and outcomes, emphasizing the evolving, dialectical nature of these relations. It does so by providing a case study of export horticulture in North-east Brazil. It documents how the region's rural trade union has been able, through mobilizing its membership base, to achieve significant improvements in their livelihoods, pay and conditions. It also shows how the region's employers have responded to these gains by restructuring the labour force in order to attempt to fragment and weaken it. The article pays particular attention to the gender dynamics of class relations.
Development Studies
Keywords: Brazil; Polanyian approaches; class relations; development

Understanding the Precariat through Labour and Work - Standing, Guy (Development and Change, 2014)
This article sets out a framework for analysing the globalizing labour process, arguing that the old dualisms of ‘capital’ versus ‘labour’ and ‘formal sector’ versus ‘informal sector’ are inadequate and unhelpful. It begins by making conceptual distinctions between work and labour and between labour and labour power, and goes on to identify a globalizing class structure in which a ‘precariat’ is emerging as a potentially transformative new mass class. Denied so-called ‘labour rights’ and social entitlements that went with twentieth century industrial citizenship, the growing precariat needs new systems of regulation, social protection and redistribution. These should be based on work and occupation rather than subordinated labour, will require new forms of collective action and representation, and should seek to redistribute the key assets of twenty-first century tertiary societies, including income security, control of time, financial capital and the commons. INTRO: That should be the starting point in trying to come to terms with what has been happening in the ‘Global Transformation’, the painful construction of a global market system, analogous to Karl Polanyi's Great Transformation (1944), which was about the construction of national market systems. The Global Transformation, in which the globalization era may be seen as the disembedded phase, has yielded global class fragmentation, or a globalizing class structure superimposed on preceding class structures across the world. This contention has raised the hackles of some Marxists adhering to nineteenth century imagery. But understanding twenty‐first century developments is surely easier if we see a more nuanced structure than the old Marxist dualism of capitalist (bourgeoisie) and proletariat.
Economics
Keywords: precariat

The Food-Energy-Climate Change Trilemma: Toward a Socio-Economic Analysis - Harvey, Mark (Theory, Culture & Society, 2014)
The food-energy-climate change trilemma refers to the stark alternatives presented by the need to feed a world population growing to nine billion, the attendant risks of land conversion and use for global climate change, and the way these are interconnected with the energy crisis arising from the depletion of oil. Theorizing the interactions between political economies and their related natural environments, in terms of both finitudes of resources and generation of greenhouse gases, presents a major challenge to social sciences. Approaches from classical political economy, transition theory, economic geography, and political ecology, are reviewed before elaborating the neo-Polanyian approach adopted here. The case of Brazil, analysed with an `instituted economic process’ framework, demonstrates how the trilemma is a spatial and historical socio-economic phenomenon, varying significantly in its dynamics in different environmental and resource contexts. The paper concludes by highlighting challenges to developing a social scientific theory in this field.
Sociology
Keywords: climate change; climatic changes; economic geography; energy consumption; energy shortages; food consumption; food security; instituted economic process; limits to growth; peak oil; political ecology; socioeconomics; sociogenesis

Spatial egalitarianism as a social ‘counter-movement’: on socio-economic reforms in Chongqing - Lim, Kean Fan (Economy & Society, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million m2of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely (i) the caste-like categorization of populations according to ‘urban’ and ‘rural’; and (ii) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ‘counter-movement’ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.
Geography; Sociology
Keywords: China; Chongqing; double movement; economic reform; equality; hukou; public welfare; social change; spatial egalitarianism; state–market relations; substantivist; urban–rural integration

Communication Policy and the "Double Movement" - Ashley, Seth (Javnost-The Public, 2014)
Karl Polanyi's concept of a "double movement" has been used to describe the protectionist measures taken by governments to mitigate damage caused by the expansion of markets. Through a lens of political economy and historical institutionalism, this article uses Polanyi's framework to examine competing notions of the public interest as exemplified by the socially constructed nature of American and British broadcasting and the legitimating discourse that produced divergent outcomes. A historical analysis points to a decline of the double movement in communication policy, particularly in the U.S., and lends support to calls for noncommercial, public media structures and increased regulation of communication industries.
Communication Studies; Sociology
Keywords: communication policy; double movement; economic research; institutionalism (religion); marketing research; media system structure; protectionism

White Knights from the Gulf: Sovereign Wealth Fund Investment and the Evolution of German Industrial Finance - Haberly, Daniel (Economic Geography, 2014)
The period leading up to and following the global financial crisis has been characterized by rising global financial diversity and multipolarity, a process underscored by the growth of so-called sovereign wealth funds (SWFs). To date there has not been any systematic examination of the interactions between this rising global financial diversity and national economic institutional diversity. Here I apply an institutional 'comparative capitalisms' perspective to the analysis of Gulf Cooperation Council ( GCC) SWF investment in German industry since the onset of the global financial crisis. The evidence demonstrates that a growing number of German industrial firms-particularly the major automotive firms at the heart of German industry-have recruited long-term GCC SWF investment as an adaptive response to the stresses of financial restructuring, most importantly the appearance of hostile takeovers as a feature of the German corporate governance landscape. These patterns lend partial support to 'varieties of capitalism' ( VOC) arguments that institutional complementarity and comparative institutional advantage are likely to produce path dependent trajectories of national institutional evolution. They also lend partial support to critiques of VOC, emphasizing, on the one hand, the importance of the Polanyian 'double movement' of market expansion and containment and, on the other, the transnational foundations of national institutional diversity. I conclude that to fully explain these patterns, both VOC theories of institutional complementarity and comparative advantage, and Polanyian theories of the double movement, must be grounded in a 'generalized Darwinian' analysis of population-level selection dynamics.
Geography
Keywords: Germany; Gulf Cooperation Council; Polanyian double movement; capitalism; economic geography; financial globalization; foreign investments; generalized Darwinism; industries; liberalization (finance); sovereign wealth funds; variegated capitalism; varieties of capitalism

Embracing ambiguity - lessons from the study of corporate social responsibility throughout the rise and decline of the modern welfare state - Schneider, Anselm (Business Ethics: A European Review, 2014)
In the work of Karl Polanyi, the negative effects of a self-regulating market economy are described as being limited by societal forces such as the policies of the welfare state. With the decline of the modern welfare state since the late 1970s, social activities of business firms are increasingly regarded as an important complement to or even as a substitute for welfare state policies by a part of the literature. However, and controversially, another stream of argumentation regards these activities as being aimed at advancing the reach of market forces. To fully grasp the ambiguous nature of the social activities of business, in this paper I provide an account of affirmative as well as of critical interpretations of these activities throughout the history of modern capitalism. On this basis, the power of critique to disentangle the diverse motivations that underlie the social engagement of business is highlighted as a condition for facilitating a role of business in society that balances economic and social considerations.
Business
Keywords: POLANYI; Karl; 1886-1964; business ethics; capitalism; public goods; research; social responsibility of business; value creation; welfare state

Law and Politics in Europe's Crisis: On the History of the Impact of an Unfortunate Configuration - Joerges, Christian (Constellations, 2014)
EXCERPT [KM]: Karl Polanyi has experienced a renaissance in recent years.13 We refer to his work in our remarks on the failures of the European project for three interrelated reasons: (1) Polanyi has underlined that modern markets were not generated by some evolutionary process but established by political planning.14 Europe's “internal market project” is the best conceivable confirmation of his thesis. (2) One of the most important insights of his work concerns the “social embeddedness” of markets and the economy.15 These insights are of crucial importance because Europe has on the one hand realized that the functioning of markets requires comprehensive regulatory activities but at the same time tends to disregard the economic, political and cultural variety and dependence of markets. (3) Polanyi can also provide clarity with regard to the growing skepticism about so many firmly held beliefs about the benefits of ever more European integration. EXCERPT 2: Led by the prompting of its highest court, Europe is waving the flag of economic freedoms of Europe's market citizens and is retreating from its commitment to collective labor law – once the institutionalized countermovement to the commodification of labor.1
Law; Political Science
Keywords: European Union; economic law; fictitious commodities; internal market project; social embeddedness

Polanyi in Brussels or Luxembourg? Social rights and market regulation in European insurance - Mabbett, Deborah (Regulation & Governance, 2014)
The decision of the Court of Justice of the European Union to ban sex discrimination in insurance has shown the potential reach of the principle of non-discrimination. This paper discusses the different positions taken by participants in the policy process leading up to the decision, in order to reveal the potential and limitations of non-discrimination as the basis for market-regulatory social policy. It is shown that the European Commission's initial support for prohibiting insurance discrimination faltered with the realization that the measure would have little efficacy as a distributive social policy. It was left to the Court to assert that non-discrimination rights are constitutive for European markets, regardless of their functional and instrumental limitations. The Court's focus was on the market-integrative potential of rights as sources of norms for the conduct of insurance relationships. It is argued that this form of constitutive regulation is distinct from distributive social policy as it does not require that outcomes are egalitarian, but, rather, that the processes governing market relations should respect fundamental rights.
Political Science
Keywords: Gender Directive; discrimination; insurance; rights; social regulation

Can productivity be socially embedded? Reflections on some productivity measures of 2000s - Kocer, Ruya Gokhan (International Journal of Productivity & Performance Management, 2014)
Purpose – The purpose of this paper is to give an overview of items that are included in recent productivity programmes in various countries and integrate these items with the ideas of virtuous circuit of productivity and socially embedded productivity. Design/methodology/approach – In depth analysis of an illustrative set of productivity measures. The analysis reveals how each measure/programme could make sense to the industrial relations actors. A new conceptual reformulation of analysed measures and programmes. Findings – Bilateral productivity deals between trade unions and employers are not necessarily good from the perspective of national policy making. For this kind of uncoordinated productivity measures, though may be good for individual enterprises, may increase unemployment by pushing other domestic competitors out of the market or compelling them to lay-off workers in a reactive fashion. By drawing on Polanyi, one may argue that it is possible to strike a good balance between productivity concerns and societal interests by embedding the former into the latter. Research limitations/implications – The purpose is to introduce a new conceptualization, thus the empirical material is meant to be illustrative rather than extensive. Originality/value – By using graphical displays and empirical argumentation two new concepts are introduced: first, virtuous circuit of productivity and second, socially embedded productivity.
Sociology
Keywords: employees; employers; industrial relations research; labor productivity; labor unions; labour productivity; labour relations; labour unions; productivity; research; social embeddedness; social partners

Living permanent liminality: the recent transition experience in Ireland - Szakolczai, Arpad (Irish Journal of Sociology, 2014)
Modernity, or the combination of market economy, liberal democratic polity and a society driven by technological progress, we are led to believe, is the end-state of history; the glorious condition of a fully enlightened society of free citizens equipped with equal rights at which all traditional societies are bound to arrive, after a period of transition which might involve some temporary difficulties or 'sacrifices'. However, and in contrast to this, modernity rather involves an infinite period of transition, in which the stable elements of social life, representing not just rigid external constraints on individual freedom, but also the condition of possibility of meaningful life, are one by one liquidated. This article argues that the anthropological concept 'liminality' is particularly helpful in understanding the formative aspects of transition experiences, like the Celtic Tiger phenomenon in Ireland. It also helps to move beyond the conventional 'transition to modernity' framework by pointing out that advanced modernity is identical to a permanent state of transitionality.
Sociology
Keywords: FOUCAULT; Michel; 1926-1984; Ireland; POLANYI; Karl; 1886-1964; capitalism; genealogy; liminality; manners & customs; modern society; modernity; technological innovations & economics; tradition; trickster

Moral versus Commercial Economies: Transylvanian Stories - Velicu, Irina (New Political Science, 2014)
Historically, the production of a market society has depended on the commodification of valuables such as land and labour, which has also meant the disembedding of capital from elements of the “primordial,” such as kinship, spiritual relations, and identities. Today we are still witnessing the invocation of such elements of moral economies as a basis for people's collective mobilization against market pressures. The case study in this article refers to Rosia Montana, a semi-urban village in Transylvania where a Canadian corporation is planning to create the largest cyanide opencast mine in Europe. Through attempts at privatizing and commodifying whole areas of social life, the market logic promoted by the corporation in the last twelve years portrays the mine as the “only alternative” for the development of the region. Rosieni and activists have blocked the project for more than fourteen years by reclaiming other fundamental values related to spirituality, ancestry, land, and nature. They challenge the prevailing violence of the market by problematizing the logic of the commercial economy and by re-evaluating what the corporate project devalues. How does the post-communist context inspire a moral critique of global corporate capitalism and a democratic socialist alternative? In this article Polanyi's argument related to the “fictitious commodities” of the market will be used to support the argument that moral principles inspire forms of resistance against commodification in the former Eastern bloc and may produce future alternative forms of development. If one noticed an increase in social and environmental activism in Romania over the last five years would it also be due to the perseverance of Rosieni and its supporters in challenging not only a corporation and some co-opted/corrupted officials, but an entire dominant discourse of neoliberalism?
Political Science
Keywords: Canadian corporations; Rosia Montana; Transylvania (Romania); commodification; corporate capitalism; disembeddedness; economic aspects; moral economy; neoliberalism

Different Meanings of ‘Knowledge as Commodity’ in the Context of Higher Education - Kauppinen, Ilkka (Critical Sociology (Sage Publications, Ltd.), 2014)
Commodification has been and still is one of the key processes within capitalist market economies. Since the 1970s, different forms of knowledge have increasingly been subjected to this process. In this paper the commodification of knowledge in the field of higher education is defined in a broad sense as an example of the intensive enlargement of capitalism. I argue that knowledge shares some features of public goods and can be subjected to commodification both as an educational product and academic research itself. However, the simple dichotomy of public vs. private good is not nuanced enough to understand the status of knowledge within higher education. How to reconstruct this dichotomy, whether knowledge should be commodified, and how to justify one’s normative stance in this respect are three important issues for further study.
Sociology
Keywords: academic capitalism; capitalism; capitalists & financiers; commodification; commodification of knowledge; commodity; higher education; knowledge; public goods

Urban poverty and regulation, new spaces and old: Japan and the US in comparison - Mahito Hayashi (Environment & Planning A, 2014)
After the 1970s the new urban poverty (NUP) ballooned in Japan and the US, and it evoked policy responses that produced new, rescaled regulatory spaces to contain the poor on the fringe of social rights and the capital circuit. The paper illuminates this process through the comparison of Japanese and US trajectories, both of which, evolving through economic crises, have established unique pathways. The author first constructs a theoretical framework based on Marxian, Polanyian, and Lefebvrean traditions. Then, he compares national-scale poverty regulation in Japan and the US from the 1950s through the 2000s. Lastly, the author examines how the countries' regulation of a major aspect of the NUP–homelessness–intensified multiscalar reseating processes. The paper concludes that regulation of the NUP represents a significant instance of uneven spatial development of capitalism mediated by the state that requires synthetic research.
Geography
Keywords: Japan; United States; capitalism; comparative studies; economic development; financial crises; financial crisis; ghettoization; homelessness; rescaling; the capital circuit; the new urban poverty; the regulation approach; uneven spatial development; urban poor

The Return of Karl Polanyi - Somers, Margaret; Block, Fred (Dissent, 2014)
In the first half century of Dissent’s history, Karl Polanyi almost never made an appearance in the magazine’s pages. On one level this is surprising, because Polanyi was a presence in socialist circles in New York City from 1947 through the mid-1950s, the period of Dissent’s gestation. On another level it is unsurprising, in that Polanyi was a heterodox thinker—even among fellow socialists. With some significant exceptions, it has taken decades to recognize the extraordinary theoretical contributions to socialist thought that he made in his masterpiece, The Great Transformation: The Social and Political Origins of Our Time,first published in 1944.
Sociology
Keywords: Vienna (Austria); democracy; economics; primacy of politics; socialism

Feminist Reflections on the Scope of Labour Law: Domestic Work, Social Reproduction, and Jurisdiction - Fudge, Judy (Feminist Legal Studies, 2014)
Drawing on feminist labour law and political economy literature, I argue that it is crucial to interrogate the personal and territorial scope of labour. After discussing the “commodification” of care, global care chains, and body work, I claim that the territorial scope of labour law must be expanded beyond that nation state to include transnational processes. I use the idea of social reproduction both to illustrate and to examine some of the recurring regulatory dilemmas that plague labour markets. I argue that unpaid care and domestic work performed in the household, typically by women, troubles the personal scope of labour law. I use the example of this specific type of personal service relation to illustrate my claim that the jurisdiction of labour law is historical and contingent, rather than conceptual and universal. I conclude by identifying some of the implications of redrawing the territorial and personal scope of labour law in light of feminist understandings of social reproduction.
Legal Studies; Labor Studies
Keywords: decommodification; feminist theory; fictitious commodities; labour law; triple movement

Sociology as a vocation: Moral commitment and scientific imagination - Burawoy, Michael (Current Sociology, 2014)
Public sociology and the sacrifices it entails, richly described in the case studies in this monograph, are driven by moral commitment. This is one element of sociology as a vocation. The other element is sociology as a science. The case studies are built on an embryonic sociology of commodification, understood in its historical dimensions and its global consequences. This sociology of commodification examines the disasters created by third-wave marketization and the bleak future for human existence, thereby, fueling the original moral commitment of public sociology.
Sociology
Keywords: countermovement; double movement; fictitious commodities; marketization; public sociology

Marketisation, public services and the city: the potential for Polanyian counter movements - Warner, Mildred E.; Clifton, Judith (Cambridge Journal of Regions, Economy and Society, 2014)
Marketisation of urban service delivery gained renewed intensity in the crisis. Mobilising Polanyi’s concept of double movement, we analyse how marketisation of public services both creates and constrains the potential for urban counter movements in the USA and Europe. We identify three main urban responses: ‘hollowing out’, where cities engage in service cut backs; ‘riding the wave’, where cities attempt to harness the market; and ‘push backs’, where cities and citizen movements oppose marketisation. Although the city is constrained by marketisation at national and international levels, we find evidence of push back and, in it, the potential for public service alternatives.
Geogrpahy; Political Science
Keywords: city; crisis; double movement; marketisation; public services; urban studies

Karl Polanyi in Vienna - Dale, Gareth (Historical Materialism, 2014)
In this article I discuss Polanyi's intellectual formation in early twentieth-century Budapest and in 1920s Vienna, focusing in particular upon his relationship to Guild Socialist and Marxist theory and to Austrian Social Democracy. It was a period in which Marxism was evolving rapidly, and Polanyi was too. In his twenties, he reacted forcefully against what he saw as the evolutionary and deterministic traits of Marxist philosophy. In his thirties, his relationship to Marxism underwent a 'double movement': his long-held doubts about Marxism crystallised into an forceful critique, swiftly followed by a sympathetic dialogue with the ideas and politics of Austro-Marxism, the 'Rousseauian' commitments of which were not unlike his own. I examine Polanyi's relationship with Marxism in each of these phases, and explore the affinities between Guild Socialism and Austro-Marxism. The final section introduces the distinctly un-Polanyian analysis of Austrian Social Democracy offered by Polanyi's wife, Ilona Duczynska.
Political Science; History
Keywords: 20th century; Austria; Austro; Austro-Marxist school; DUCZYNSKA; Ilona; Hungary; Marxism; Marxist philosophy; ROUSSEAU; Jean-Jacques; Vienna (Austria); biography; communism; determinism; functional theory; guild socialism; history; intellectual life; social democracy

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
History; Anthropology
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights

Innis and Polanyi: The Search for the Substantive Economy - Rotstein, Abraham (Journal of Economic Issues; Abingdon, 2014)
Economics and the economy have an uneasy relationship. Economics is akin to the logic of mathematics in contrast to the term "economy," which is an institutional framework to provide for material wants. While they overlap in the modern market economy, economics provides distorted results when applied to tribal societies, the economies of antiquity, or modern state-organized economies. Harold A. Innis and Karl Polanyi both attempted to find a different conceptual framework for a truly general economic history. [PUBLICATION ABSTRACT]
Economics
Keywords: INNIS; Harold; business & economics - economic systems and theories; economic history; substantiveness; supply and demand

Neo-pluralist political science, economic sociology and the conceptual foundations of the comparative capitalisms literatures - Bruff, Ian; Hartmann, Eva (Capital & Class, 2014)
In this paper, we critically assess two of the key conceptual foundations for the comparative capitalisms (CC) literatures, neo-pluralist political science and economic sociology, in order to identify more clearly the deep intellectual roots of these literatures. Principally, we focus on how the strengths of neo-pluralism and economic sociology – their attention to detail in considering the huge range of ‘types’ of capitalism that exist across the world – come at a high price. Put briefly, the redefinition of ‘capitalism’ as ‘the economy’ concentrates research agendas on the specific political and social conditions found across the world, leaving ‘the economy’ relatively untouched. In consequence, ‘capitalist diversity’ is quickly, and often silently, equated to ‘political diversity’ or ‘social diversity’. As such, a key weakness of CC scholarship, identified by various authors in this Capital & Class special issue – that it does not provide a satisfactory theoretical understanding of capitalist societies – is a problem that runs deeper than the limitations that can be observed in contemporary debates. The implications of our argument are discussed in the conclusion.
Political Science; Business
Keywords: capitalism; capitalist diversity; comparative capitalisms; economic sociology; neo-pluralism; political economy

The Debate on Globalization and International Revitalization of Labor. A Critical Review - Fleming, Daniel; Søborg, Henrik (Nordic Journal of Working Life Studies, 2014)
This article discusses some alternative or critical theoretical contributions regarding globalization and labor. The main question in this discussion is if there are changes in direction of a possible revitalization of labor movements and if international solidarity can increase due to globalization. This question also relates to discussions of changes in division of work, the concept of work, working class, commodification, decommodification, and new centers of global production–all related to different paradigms or new concepts. The reason or need for reconceptualizing comes from the great transformation of capitalism in forms of neoliberal globalization, in a different direction than predicted by Polanyi. That is, instead of increased public sector decommodification (not profit- or market-oriented production) and national regulation, embedding capitalist markets, as seen after 1945, the last three decades have witnessed a countertransformation and large-scale recommodification by privatizing, disembedding, and deregulating global markets. As a consequence, inequality in income and working life conditions has increased in most countries and been used to press trade unions. Western industrial unions have been declining as many industries and labor-intensive, low-paid jobs moved to developing countries. Most blue-collar jobs are now in Asia, especially China, with about one-third of its employment blue collars. Is the center of global capital-labor contradictions and dynamics moving to the South, with a possibility of a new revitalization of labor and international solidarity? We discuss different optimistic and pessimistic views on a possible international revitalization of labor.
Sociology
Keywords: commodification; decommodification; globalization; income distribution; international solidarity; knowledge workers; labor organizing; labour organizing; occupational citizenship; precariat; revitalization of labor; skill capture; work environment; working class; working class concept

Radical, reformist, and garden-variety neoliberal: coming to terms with urban agriculture's contradictions - McClintock, Nathan (Local Environment, 2014)
For many activists and scholars, urban agriculture in the Global North has become synonymous with sustainable food systems, standing in opposition to the dominant industrial agri-food system. At the same time, critical social scientists increasingly argue that urban agriculture programmes, by filling the void left by the “rolling back” of the social safety net, underwrite neoliberalisation. I argue that such contradictions are central to urban agriculture. Drawing on existing literature and fieldwork in Oakland, CA, I explain how urban agriculture arises from a protective counter-movement, while at the same time entrenching the neoliberal organisation of contemporary urban political economies through its entanglement with multiple processes of neoliberalisation. By focusing on one function or the other, however, rather than understanding such contradictions as internal and inherent, we risk undermining urban agriculture's transformative potential. Coming to terms with its internal contradictions can help activists, policy-makers and practitioners better position urban agriculture within coordinated efforts for structural change, one of many means to an end rather than an end unto itself.
Geography
Keywords: United States; agricultural sociology; alternative food networks; community gardens; food production; food security; neoliberalism; urban agriculture; urban farming; urban studies

Group learning as relational economic activity - Saito, Eisuke; Atencio, Matthew (Educational Review, 2014)
The purpose of this paper is to discuss group learning in line with economic perspectives of embeddedness and integration emanating from the work of Karl Polanyi. Polanyi’s work defines economy as a necessary interaction among human beings for survival; the economy is considered inextricably linked from broader society and social relations rather than autonomous and driven by self-interest in free market conditions. He specifically outlines three key forms of integration that are crucial to economic stability, involving the notions of reciprocity, redistribution, and exchange. These patterns of integration are described as key elements that co-mingle within and structure contemporary group learning within classrooms.
Education
Keywords: collaborative learning; cooperative learning; economic activity; education; embeddedness; embeddedness (socioeconomic theory); group learning; group work in education; reciprocity (commerce); social integration

Three Shades of Embeddedness, State Capitalism as the Informal Economy, Emic Notions of the Anti-Market, and Counterfeit Garments in the Mauritian Export Processing Zone - Neveling, Patrick (Research in Economic Anthropology, 2014)
Purpose – This paper furthers the analysis of patterns regulating capi-talist accumulation based on a historical anthropology of economic activ-ities revolving around and within the Mauritian Export Processing Zone (EPZ). Design/methodology/approach – This paper uses fieldwork in Mauritius to interrogate and critique two important concepts in contemporary social theory – "embeddedness" and "the informal economy." These are viewed in the wider frame of social anthropology's engagement with (neoliberal) capitalism. Findings – A process-oriented revision of Polanyi's work on embedded-ness and the "double movement" is proposed to help us situate EPZs within ongoing power struggles found throughout the history of capital-ism. This helps us to challenge the notion of economic informality as supplied by Hart and others. Social implications – Scholars and policymakers have tended to see eco-nomic informality as a force from below, able to disrupt the legal-rational nature of capitalism as practiced from on high. Similarly, there is a view that a precapitalist embeddedness, a "human economy," has many good things to offer. However, this paper shows that the practices of the state and multinational capitalism, in EPZs and elsewhere, exactly match the practices that are envisioned as the cure to the pitfalls of capitalism. Value of the paper – Setting aside the formal-informal distinction in favor of a process-oriented analysis of embeddedness allows us better to understand the shifting struggles among the state, capital, and labor.
Anthropology
Keywords: Mauritius; capitalism; economic anthropology; embeddedness; embeddedness (socioeconomic theory); ethnohistory; export processing zones; informal sector (economics); neoliberalism

The Polanyian Perspective Meets the Varieties of Capitalism: Inspecting the Consequences of the Institutional Changes in South Korea since 1997 - Šitera, Daniel (Perspectives: Central European Review of International Affairs, 2014)
This article attempts to combine the Polanyian perspective on the issue of market societies with an the analysis of the institutional foundations of capitalism that is facilitated by the Varieties of Capitalism(VoC) approach. The article departs fromthe argument that the VoC school has upgraded our insight into the institutional working ofmodern capitalism, but became entrapped in an overt structuralismwhich considers institutional change as just an interplaywithin a self-odering institutional structure.However, the article employs Karl Polanyi's doublemovement, the dialectic of marketizing dis-embedding and socializing re-embedding, to demonstrate that the institutional changemust be rather conceived as embedded in a social life. Only then can one recognize considers that such a change is primarily conditioned by social contests among sentient agents which engage in an ideational struggle over its final outcome. These theoretical reconsiderations are tested on the empirical terrain of Korean capitalism after the Asian Crisis of 1997 and the Global Crisis of 2007. First, the double movement is used to demonstrate that the post-crises institutional changes have transformed Korean capitalism's institutional and societal model from developmentalism to embedded neoliberalism. Second, it is documented that this transformation has been characteristic of certain ideational struggles which turned into a socially contested, largely contradictory, uneven, and open-ended process.
Political Science
Keywords: Asia; POLANYI; Karl; 1886-1964; South Korea; capitalism; developmentalism (economics); double movement; financial crises; global financial crisis; 2008-2009; international affairs; neoliberalism; varieties of capitalism

Embedding Trade Liberalisation in Social Policy: A Research Agenda on Social Regionalism and the Global South [article] - Ashiagbor, Diamond (Northern Ireland Legal Quarterly, 2014)
Underpinning this article is the proposition that regional integration with a social dimension has the potential to engender a more equitable pattern of globalisation. The empirical focus of the article is on the ex)tent to which the insights of 'embedded liberalism' associated with regional economic integration between he industrialised nations of the European Union (EU)can be applied to regional economic integration within sub-SaharanAfrica. The article contends that EU market liberalisation has been embedded within labour market institutions and institutions of social citizenship at the domestic level. These have served as social stabilisers to counter the far-reaching effects of the internal market and global trade. Less industrialised nations have never enjoyed adjustment mechanisms of this sort, raising the question for this article, and for further research: in which legal and institutional structures can these nascent forms of market integration at regional and sub-regional level be embedded? In examining the interaction between trade liberalisation and labour standards, I draw on the work of Karl Polanyi. Central to his key work, The GreatTransformation,is the assertion that all economies are enmeshed in non-economic institutions, although the forms and depth of this social embedding may differ. Drawing on Polanyi, I argue that laissez-faire economic liberalism may be offset by principles of social protection at national and, in some instances, regional level - a 'counter-movement' to the economic insecurity arising from globalisation.
Law
Keywords: United Kingdom; social regionism; trade liberalisation

The Pyrrhic Triumph of Finance Capital and the Return of Polanyi - Harrison, Trevor W. (Athens Journal of Social Sciences, 2014)
This paper examines the declining support for centrist parties in many western countries. Using the seminal ideas of Karl Polanyi, the paper argues this decline is attributable to the rise of neo-liberal free market policies that have resulted in widespread insecurity and led many voters to seek out political alternatives on the right and left. The paper further examines possible reasons why parties of the right, rather than the left, have been more successful at this historical juncture in channeling political disenchantment.
Sociology
Keywords: countermovement; fascism; finance capital; neoliberalism

From the Apocalypse to the Revolution - Pellicani, Luciano (Telos, 2014)
The article discusses the emergence of millennialism, which is considered as one of the outcomes of the spiritual victory of Christianity over the Greco-Roman culture. The formulation of the historical-sociological category of cultural catastrophe by Hungarian economic historian Karl Polanyi is tackled. The presence of a divine messenger as one of the three elements of a messianic movement is cited. The concepts of revolutionarism, Jacobinism and Marxism are also addressed.
Sociology
Keywords: Christianity; POLANYI; Karl; 1886-1964; communism; critical theory; cultural catastrophe; messianism; millennialism

Kari Polanyi: Nine Decades of Scientific and Militant Life - Rioux, Michele (Revue interventions economiques/Papers in Political Economy, 2014)
Political Science
Keywords: biography; history of economic thought: individuals

The Renewal of a Critical Theory of Capitalism and Crisis – A Comment on Nancy Fraser’s Interpretation of Polanyi’s works - Deutsche Digitale Bibliothek - Sparsam,, J.; Eversberg, D.; Haubner, T.; Mader, D.; Muraca, B.; Hanno, P. (Working Paper 7/2014 of the DFG-Kollegforscher_innengruppe Postwachstumsgesellschfaten., 2014)
The paper examines Nancy Fraser’s Polanyian reading of the current capitalist crisis and her expansion of Polanyi’s notion of the ‘double movement’–social forces struggling for marketization and social protection– into a ‘triple movement’ by adding the struggle for emancipation as a third factor. In its first part, the paper reviews Fraser’s central arguments with a special focus on her reading of Polanyi’s idea of the “fictitious commodities” land, labor, and money. Second, the authors examine Fraser’s conceptualization of social forces, domination and emancipation drawing on Environmental Philosophy, Political Ecology, Marxism, Feminism, Social Philosophy as well as Polanyi himself. In the end, the paper argues that Fraser’s conception of capitalism and emancipation are in need of improvement if critical theory wants to adequately grasp the current crisis of capitalism.
Sociology
Keywords: FRASER; Nancy; fictitious commodities; interpretation; triple movement

The Mystery of Capital or the Mystification of Capital? - Obeng-Odoom, Franklin (Review of Social Economy, 2013)
In contemporary political economic analyses of development processes, Hernando De Soto'sThe Mystery of Capital, has been one of the most discussed, albeit controversial, books. Although well received by global development agencies such as the World Bank, a key exponent of De Soto's work, positing that the creation and institutionalisation of individual property in housing and land revives “dead capital” and creates the conditions that will enable the poor to emerge from abject poverty, has been widely criticised. These criticisms show that (1) the thesis is flawed, (2) the flaw is due to implementational problems and (3) the practical implications arising from the thesis are largely neutral and will neither improve nor worsen poverty. Although agreeing with the first criticism, this paper argues that the second critique must be nuanced, and the third is entirely mistaken. Utilising insights from Joseph Schumpeter, Karl Polanyi and Henry George, it makes the case that applying De Soto's ideas through policy would be ineffective in curbing urban poverty, and actually serve to simultaneously entrench and augment it. Moreover, while finding that De Soto's assumption that the poor possess some economic agency is sound and may, indeed, secure socially beneficial outcomes through pursuing innovative and entrepreneurial endeavours, De Soto's conception of such processes remains largely emasculated from broader political economic considerations.
Development Studies
Keywords: dead capital; economic research; fictitious commodities; fictitious commodity; political economic analysis; poverty; progress amid poverty; property; social innovation

Indigenous Development and the Cultural Captivity of Entrepreneurship - Peredo, Ana María; McLean, Murdith (Business & Society, 2013)
This article argues that thinking about entrepreneurship as a potential instrument for relief from endemic poverty and disadvantage, especially among the Indigenous, has all too often been captive to a concept of entrepreneurship that is built out of constrained economic and cultural assumptions. The authors develop this argument from a critical discussion of contributions by Karl Polanyi and Robert Heilbroner. The result is that approaches to venture have been encouraged that are sometimes a poor fit for the circumstances of those they are meant to benefit, and other forms that could have considerable promise have gone unexplored. This article outlines some features of Indigenous culture and build on the analysis of David Harper to construct an improved notion of entrepreneurship that allows for these distinctive features. The article concludes that research and policy making concerning entrepreneurship as an instrument of development among the Indigenous need to be undertaken with this reconstructed understanding of entrepreneurship that is a better fit for the realities of Indigenous culture.
Environmental Studies; Business Studies
Keywords: HEILBRONER; Robert; Indigenous development; Indigenous peoples; POLANYI; Karl; 1886-1964; cultural diversity; entrepreneurship; entrepreneurship and culture; poverty

Transforming Capitalism: The Triple Crisis - Kirby, Peadar (Irish Journal of Sociology, 2013)
This article identifies a triple crisis of capitalism based on the three fictitious commodities as identified by Karl Polanyi: labour, money and land. This framework is used to integrate the environmental crisis into the wider crisis of capitalism. It argues that international actions required to reduce greenhouse gas emissions are going to present major challenges for capitalism with implications for the current dominance of market power and the subservience of state and social power. The article critically examines the potential of climate capitalism to achieve a low-carbon society by 2050 and introduces the need to face the challenges of degrowth.
Sociology; Political Science
Keywords: climate capitalism; climate change; de-growth; degrowth; development models; fictitious commodities; sustainability

The political economy of public sector trade union militancy under Keynesianism: The case of local government - Gill-McLure, Whyeda (Capital & Class, 2013)
Public service labour’s distinctiveness is insufficiently understood or recognised; and in its ad hoc growth under liberal ideologies of state intervention (those of Mill and Keynes), it has been treated both as if it were and were not public service labour. This paper teases out some of the crucial links between liberal ideologies of state intervention and the social praxis of public service unionism, outlining the latter’s historical struggle against this paradoxical treatment, which culminated in 1970s militancy. The paper supports this argument with a Marxist analysis of public sector labour, drawing on Polanyi’s ‘double-movement’ to understand the limitations of liberal ideologies of state intervention.
Business; Public Administration
Keywords: Marxist analysis; civil service; distinctiveness of public service labour; double movement; ideology; labor process; labour process; liberalism; political economy; public sector union militancy

Capitalism: restless and unbounded? Some neo-Polanyian and Schumpeterian reflections - Harvey, Mark; McMeekin, Andrew (Economics of Innovation & New Technology, 2013)
This paper first explores the notion that the limitlessness of knowledge is a privileged source of the restlessness of capitalism [Metcalfe, J. S. 2001. “Institutions and Progress.”Industrial and Corporate Change10 (3): 561–586; 2002. “Knowledge of Growth and Growth of Knowledge.”Journal of Evolutionary Economics12 (1): 3–13; 2004. “The Entrepreneur and the Style of Modern Economies.”Journal of Evolutionary Economics14 (2): 157–175; 2010. “University and Business Relations: Connecting the Knowledge Economy.”Minerva48 (1): 5–33] when combined with incentives of entrepreneurialism in a market society. Metcalfe gives a central paradigm of evolutionary economics a distinctive turn, with knowledge the pre-eminent source of variation, and markets the primary arena of selection. The paper engages this approach with a neo-Polanyian approach of ‘instituted economic process’, in which the variation and selection dynamic is itself seen as instituted within a particular historical economic context. The paper develops a critique of the evolutionary paradigm firstly by suggesting variations in instituted ‘economies of knowledge’ within a multi-modal conception of capitalism. Further breaking with the bipolar variation-selection paradigm, the paper argues that there has been a significant role of the state as a distinctive source of variation and selection in innovation and economic transformation. This leads us finally to analyse the shifting place of economy in society and polity, and the strategic responses in the USA, Brazil and Europe to the historically novel conjuncture of peak oil and global climate change, as a further source of variation. We conclude that a choice between evolutionary and historical approaches to innovation and economic transformation is a false one, once a universalising and unbounded paradigm of variation and selection is abandoned.
Sociology
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; capitalism; economic development; entrepreneurship; evolution; evolutionary economics; instituted economic process; mixed economy; multi-modality; organizational change; variation and selection

Polanyi in the Pilbara - Peck, Jamie (Australian Geographer, 2013)
This paper outlines a ‘substantivist’ approach to the regional economy of the Pilbara in Western Australia, inspired by a constructive reinterpretation of Karl Polanyi's methodological legacy. Beyond the metaphor of embeddedness, it makes the case for a more wide-ranging methodological engagement with Polanyi's brand of substantivist socioeconomics, in dialogue with the empirical investigation of actually existing and variegated socioeconomic formations. A Polanyian optic, amongst other things, calls attention to enduring sources of heterogeneity in this distinctive regional-economic formation, even under the hegemonies extractive capitalism and neoliberal developmentalism.
Geography
Keywords: Aboriginal economies; economic geography; mining; the Pilbara

Union Campaigns as Countermovements: Mobilizing Immigrant Workers in France and the United Kingdom - Tapia, Maite; Turner, Lowell (British Journal of Industrial Relations, 2013)
In this article, we compare recent innovative union campaigns: the ‘sans papiers’ campaign in France and the ‘Justice for Cleaners’ campaign in the United Kingdom, both based on a sustained grass-roots mobilization of immigrant workers. Rather than focusing on the ‘usual suspect’ explanatory factors, such as contrasting national settings, union power structures or traditions, our cross-national comparison highlights important underlying similarities in unions' strategic responses to a growing precarious immigrant workforce. In the absence of established channels of representation, both unions decided to act like social movements fighting for social protection. Using Polanyi's framework, we view both case studies as examples of countermovements against heightened levels of global liberalization and precarious employment.
Business; Industrial Relations; Labour Studies
Keywords: comparative labour; countermovement; human resources; international labour; unions

The Politics of Dispossession: Theorizing India’s “Land Wars” - Levien, Michael (Politics & Society, 2013)
While struggles over land dispossession have recently proliferated across the developing world and become particularly significant in India, this paper argues that existing theories of political agency do not capture the specificity of the politics of dispossession. Based on two years of ethnographic research on anti-dispossession movements across rural India, the paper argues that the dispossession of land creates a specific kind of politics, distinct not just from labor politics, but also from various other forms of peasant politics that have been theorized in the social sciences. It illustrates how the process of land dispossession itself shapes the targets, strategy and tactics, organization, social composition, goals, and ideologies of anti-dispossession struggles. It concludes with reflections on why land conflicts are less easily institutionalized than labor conflicts and may therefore constitute a significantly disruptive force in the emerging centers of global capitalism for the foreseeable future.
Sociology; Political Science
Keywords: India; accumulation by dispossession; agrarian change; agriculture; capitalism; eviction; land grabs; peasant politics; peasants; property rights; social movements

Responding to the crisis: food co-operatives and the solidarity economy in Greece - Rakopoulos, Theodoros (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
This article discusses a case of popular social response to imposed austerity and recession in Greece. It focuses on the anti-middleman movement in an Athens suburb. It also addresses the broader picture of the current Greek crisis, explaining how participants in this grassroots response extend their activity beyond food distribution, beginning to imagine modes of economic conduct and interaction different from those currently dominant in Greece. I explore their efforts to turn the food market they have established in Athens into a formal co-operative which links consumers in their neighbourhood directly to selected farmers through bonds of solidarity, and to work with others to create a network of similar co-operatives which will span the whole country. I argue that their endeavours strongly resemble the co-operativism and practical socialism advocated by important social theorists such as Mauss and Polanyi, and suggest that it may be important for the young activists in Athens to learn more about their ideas.
Anthropology
Keywords: Greece; Greek crisis; MAUSS; Marcel; 1872-1950; anthropological research; anti-middleman movements; economic development; financial crises; financial crisis; food co-operatives; food industry; horizontal co-operative networks; recessions; solidarity economy; sovereign debt crisis

Towards a human economy: reflections on a new project - Sharp, John (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
The University of Pretoria's Human Economy project began at the end of 2010. To date it has involved eighteen post-doctoral fellows, drawn from around the world, and eight doctoral candidates, all from Africa. This paper reviews the project's progress, drawing attention to how its participants have come to construe the notion of a 'human economy' and the main social theorists on whom they have drawn in doing so. The development of our thinking regarding a human economy is explained by reference to the two edited volumes, comprising contributions from all the post-doctoral fellows, which will be published in the near future. Challenges for future research are considered in the final part of the paper.
Anthropology
Keywords: MAUSS; Marcel; 1872-1950; South Africa; University of Pretoria; doctoral degree; economic development; human economy; market exchange; mutuality; plural economy; reform; revolution; social development; social sciences

Cosmologies and Regionalisms from ‘Above’ and ‘Below’ in the post-cold war Americas: the Relevance of Karl Polanyi for the 21st century - Roncallo, Alejandra (Third World Quarterly, 2013)
Drawing on a Polanyian analysis of the land question, this article aims to analyse both Western and Indigenous cosmologies of Abya Yala—the name that indigenous peoples give to the American continent—to understand the relationship between human beings and land and nature. These cosmologies are at the heart of the way in which two distinct societies construct their regional space, one from ‘above’, the other from ‘below’, and they are therefore key to understanding today’s climate change problématique. Following this nexus it is argued that, since the end of the Cold War, a new regional ‘double-movement’, unleashed by the quest for land and natural resources has been in the making. This is a superstructural or legal battle between Western transnational regime-making and a law that originated at the ‘centre of the Earth’. The article explains both regionalisms and the dialectical interaction between them and demonstrates that Karl Polanyi’s legacy remains relevant for the 21st century.
Political Science; International Relations
Keywords: climate change; cosmologies; double movement; indigenous land question

Polanyi in an Hourglass: The Two Lives of a Sociological Classic - Frerichs, Sabine (Studies in Law, Politics & Society, 2013)
This article aims to show that studies of transnational risk regulation can benefit from Polanyian and neo-Polanyian research agendas in the field of law, economy, and society. Risk regulation would then be under-stood as a corrective force within the market society. Drawing on the relevant literature in the field, Karl Polanyi's work is contextualized both in the past ("scholarship before and beside Polanyi") and in the present ("scholarship after and beyond Polanyi"). The review considers developments within sociology, its neighboring disciplines economics and jurisprudence, and the interdisciplinary research fields of "economy and society," "law and society," and "law and economy." The article demon-strates that Polanyi is a "late classic" who shares the holistic orientation of classical historical scholarship. At the same time, it is argued that his "early revival" is due to the topicality of his criticism of the market society, and its inherent risks, in an era of neoliberalism and globaliza-tion. By going back and forth in time, the article situates Polanyi in a line of holistically minded scholarship that combines insights of general, economic, and legal sociology in what can be called the "economic sociol-ogy of law." This is "old" and "new," at the same time.
Sociology
Keywords: classical sociology; contemporary sociology; economic sociology; economic sociology of law; general review; interdisciplanary research; law and economics; market society; neoliberalism; risk regulation; sociological research

After a Romantic Aspiration to Society: Harnessing the Regulatory Capacity of a Social Sphere - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This introduction unpacks the key question that informs the articles in this special issue. How does a social sphere inform regulation and, more specifically, how can the regulatory capacity of a social sphere be har-nessed, as an alternative or significant complementary force to state reg-ulation and reliance on the self-regulatory capacity of markets? This question is salient and topical also in light of the search for new regula-tory strategies and perspectives in the aftermath of the 2007 financial and subsequent EU sovereign debt crises, which have led to a major rea-lignment of economy and society in a number of countries. This introduction argues that economic sociology is a crucial reference point for understanding more about the social practices that constitute business behavior. It enables to explore the scope and significance of often interlinked social and legal norms for regulating various transna-tional risks that economic activity can give rise to. The introduction therefore locates the quest for understanding more about the regulatory capacity of a social sphere in debates that draw on Karl Polanyi's analy-sis of the embedding, disembedding, and re-embedding of economic activ-ity into social norms. The introduction highlights one of the key themes developed in this special issue, the idea of society within economy which questions an assumed conceptual distinction between economy and society. This introduction concludes by specifying how the accounts of risk regu-lation developed in this special issue chart a path that is different from recent explorations of the role of a social sphere in regulation, which were conducted under the banner of "the sociological citizen," "regula-tory sociability," and "collaborative governance."
Law; Sociology
Keywords: European Sovereign Debt Crisis; 2009-; European Union; crisis; economic sociology; economic sociology of law; financial crisis; international business enterprises; regulation; social sphere; socio-legal studies; state regulation; transnational risk

From Polanyi to Discourse Theory - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This article starts from the assumption that economic sociology, including Karl Polanyi's work, can contribute fresh perspectives to regulation debates because it opens up new understandings of the nature of economic activity, a key target of legal regulation. In particular this article examines Polanyi's idea that society drives regulation. For Polanyi the "regulatory counter-movement" is society's response to the disembedding – in particular through the proliferation of markets – of economic out of social relationships. Section One of the article identifies three key chal-lenges that arise from this Polanyian take on regulation for contempor-ary regulation researchers. First, Polanyi focuses on social norms restraining business behavior, but neglects social norms embedded in law as also shaping regulation. Second, he seems to imply a clear-cut concep-tual distinction between "economy" and "society." Third, his analysis sidelines the role of interest politics in the development of regulation. Addressing the first of these three key challenges, Section Two of this article therefore argues that a Polanyian vision of "socialized" legal reg-ulation should build on contemporary accounts of responsive law and reg-ulation, which focus attention on social norms informing legal regulation. Section Three of this article tackles the second key challenge raised by Polanyi's work for contemporary regulation researchers, that is, how to transcend a modernist perspective of "economy" and "society" as clearly demarcated, distinct fields of social action. It argues that discourse the-ory is an important alternative theoretical resource. Drawing on Laclau and Mouffe, the article suggests that understanding "economy" and "society" as performed by open and relationally constructed discourses helps to capture interconnections between "economy" and "society" that become particularly visible when we analyze how specific regulatory regimes work at a medium- and small-scale level. These points are further brought to life in Section Four through a discussion of the European Union (EU) regulatory regime for trade in risky, transgenic agricultural products, and in particular the current reform debates about the consideration of the "socioeconomic impacts" of such products.
Law; Sociology
Keywords: European Union; European Union regulation; discourse theory; economic sociology; embeddedness; embedding theorems; responsive regulation; socio-economic impacts; socioeconomics; transgenic agricultural products

A Systems Theory Perspective on Polanyi's Great Transformation: The Case of Financial Derivative Contracts - Paterson, John (Studies in Law, Politics & Society, 2013)
Whereas much of the renewed interest in Polanyi's Great Transform-ation speculates that the rebalancing of economy and society he foresaw might now be emerging in the context of the financial crisis, the systems theory perspective adopted in this article concludes that there are good reasons to believe that such a shift may be no closer. From an examina-tion of credit default swaps and corporate bonds, the article suggests that finance may best be understood as an internally differentiated subsystem of the economy and thus perhaps peculiarly proof against efforts to exert control over it. Concluding that Polanyi's analysis lacks the conceptual tools to cope with contemporary conditions when compared to systems theory, the article nevertheless suggests that his approach may usefully be extended by adding a fourth fictitious commodity - risk – to the familiar trio of land, labor, and money.
Sociology
Keywords: POLANYI; Karl; 1886-1964; contracts; corporate bonds; derivatives; economic aspects; economic sociology; economy; markets; prices; society; swaps (finance); systems theory

Trust and Regulation: Insights from the Mining Industry - Schiavi, Petrina (Studies in Law, Politics & Society, 2013)
This article develops Polanyi's (2001) theme of harnessing the regula-tory capacity of a social sphere by focusing on trust as an emotion for framing risk regulatory regimes. Using the global mining sector as its focus, it explores the role of trust in the regulation and corporate man-agement of social and environmental risk Sociological perspectives on trust are employed to identify and analyze dynamics of trust in the mining industry. The article draws on data col-lected between 2004 and 2008 by way of participant observation, docu-ment analysis, and in-depth qualitative interviews with around 40 representatives of the mining industry, NGOs, and regulators. Trust-rela-tionships are an example of harnessing the regulatory capacity of a social sphere, but they can also undermine regulatory effort where trust is abused. The effectiveness of trust-based regulation would be enhanced by sanctions for nonperformance that target corporate motivations and financial performance. This research focused on a selection of large, multinational mining corporations with a presence in Australia. Generalizations could not be made from this research about smaller mining entities or single-country or state-owned corporations. A better understanding of corporate trust-building behaviors and motiva-tions can help inform more effective regulatory strategy for improving corporate, social, and environmental impacts. This article contributes to the body of knowledge about the regulation of the social and environmen-tal performance of the mining industry. This is important as many of the remaining accessible mineral deposits across the globe are in areas of environmental and social significance.
Sociology; Law
Keywords: POLANYI; Karl; 1886-1964; corporate responsibility; delegated legislation; environmental risk assessment; financial risk; mineral industries; mining industry; regulation; risk; social responsibility of business; trust

Sovereign Debt Restructuring in the Eurozone: A Polanyian Reading of Private Law Enforcement - Thomas, Dania (Studies in Law, Politics & Society, 2013)
The social protests ort the streets of indebted sovereigns in crises across the Eurozone have made debt restructuring an imperative. Further delay in achieving this expeditiously and equitably significantly exacerbates the social costs of crises from which current and future generations will struggle to recover. This article examines the feasibility of the drastic and widespread debt restructuring needed to resolve the problem in the face of existing private law sanctions that protect individual creditor rights. It relies on an analysis of US policy in the transition to a securi-tized market and of key sovereign debt cases to reveal the historical con-tingency of private law protections. It concludes by showing that the effectiveness of private law protections have always been constrained by the overriding imperative to achieve debt sustainability with negotiated and consensual workouts. This can be achieved in the Eurozone with stat-utory constraints on enforcement action pending the settlement of debt workouts as suggested in a recent proposal.
Economics; Law
Keywords: European Sovereign Debt Crisis; 2009-; Eurozone crisis; Eurozone debt crisis; POLANYI; Karl; 1886-1964; US debt litigation; civil law; contingency theory (management); international finance; private law enforcement; securitization; sovereign bond contracts; sustainability

"Etiquette and Magic": Between Embedding and Embedded Corporate Social Responsibility - Voiculescu, Aurora (Studies in Law, Politics & Society, 2013)
This article looks at corporate social responsibility (CSR) as a discur-sive social practice that attempts to interrogate the global market econ-omy and its neoliberal underpinnings and that reflects as well as frames and shapes domestic and global politics and institutions. Drawing upon Karl Polanyi's notions of reciprocity and redistribution while also emphasizing the normative content of the concept, the article inquires into the position that the CSR discourse occupies in addressing the cor-porate transnational risks derived from social tensions and conflicts and more generally, in answering social expectations for justice. The Polanyian perspective highlights the CSR discursive quest for a missing conceptual consistency and implicitly, for a constructive "critical" core. From this perspective, the article shows CSR to reside within controver-sial conceptual boundaries; a discursive social practice that engages with the social aspiration of embedding market economy in society while it is also in need of reclaiming its critical core and its potential for social change.
Sociology; Law
Keywords: civil economy; corporate social responsibility; embedding theorems; neoliberalism; reciprocity (commerce); reciprocity and redistribution; social change; social embeddedness; social responsibility of business; socio-legal studies

How Markets Work: The Lawyer's Version - Weidemaier, W. Mark C.; Gulati, Mitu (Studies in Law, Politics & Society, 2013)
This article combines two sources of data to shed light on the nature of transactional legal work. The first consists of stories about contracts that circulate among elite transactional lawyers. The stories portray law-yers as ineffective market actors who are uninterested in designing super-ior contracts, who follow rather than lead industry standards, and who depend on governments and other outside actors to spur innovation and correct mistakes. We juxtapose these stories against a dataset of sover-eign bond contracts produced by these same lawyers. While the stories suggest that lawyers do not compete or design innovative contracts, their contracts suggest the contrary. The contracts, in fact, are consistent with a market narrative in which lawyers engage in substantial innovation despite constraints inherent in sovereign debt legal work. Why would lawyers favor stories that paint them in a negative light and deny them a potent role as market actors? We conclude with some conjectures as to why this might be so.
Law
Keywords: POLANYI; Karl; 1886-1964; contracts; international finance; lawyers; lead industry; socioeconomics; sovereign debt; transactional marketing

Polanyi's Magnum Opus ? Assessing the Application of the Counter-Movement in International Political Economy - Worth, Owen (International History Review, 2013)
The concept of the ‘counter-movement’ has had a significant impact within studies in International Political Economy (IPE). In the light of the credit crisis and the growth of growing resentment to the notion of the free market, the idea of the counter-movement has been utilised to understand social reaction to neoliberalism. This article argues that whilst the counter-movement has been used in unique and innovated ways, Karl Polanyi himself used the term largely to refer to a specific period in nineteenth-century British history. This article argues that whilst the counter-movement remains interesting, its application remains open to scrutiny. It questions whether the concept was indeed central to Polanyian economic thought and how much can be given to it in today's contemporary era of neoliberalism. It also suggests that by focusing merely on the counter-movement, Polanyian accounts within IPE are in danger of ignoring much of his wider critique of market economics.
Political Science; History
Keywords: capitalism; countermovement; economic policy; equilibrium (economics); foreign investments; free enterprise; international economic relations; international political economy; neoliberalism

Is Environmental Management Really More Collaborative? A Comparative Analysis of Putative ‘Paradigm Shifts’ in Europe, Australia, and the United States - Benson, David; Jordan, Andrew; Smith, Laurence (Environment and Planning A, 2013)
It is a truism that environmental management has experienced a significant change in the locus of governing, in which centralised forms of steering have been gradually replaced by more collaborative management approaches organised at the ecosystem scale. Whereas much research capital has been expended on informing their design and promoting their uptake, surprisingly little systematic comparative empirical research exists on the precise nature and extent of what is often described as a ‘paradigm shift’ in governing. We address this gap by examining how one issue often deemed to require deeper ‘collaboration’, namely, catchment management, has been addressed in three comparable federal political systems: the European Union; the USA; and Australia. On the basis of a fresh and more comparable account of the forms and modalities of collaboration, we reveal that, although collaboration has undoubtedly grown in recent decades, its depth and extent remains highly variable both across and within the three cases. We also examine what these subtly different geographical ‘contours of collaboration’ imply for future research and practice.
Environmental Science; Environmental Studies
Keywords: catchment management; central control; collaboration; environmental science; federalism; governance; neoliberalism; paradigm shift

From Neoliberalism to Pluralism: A Response to Mulheirn and Jacobs - Finlayson, Alan (The Political Quarterly, 2013)
This essay puts into context the debate between Michael Jacobs and Ian Mulheirn, exploring the theories and themes underpinning their arguments, published in issue 84 1 of the Political Quarterly. It discusses, firstly, the roots of Mulheirn's approach in European neoliberalism and, secondly, the roots of Jacobs' approach in a range of sources currently contending for authority over debates within the Labour party. These include themes drawn, broadly, from Polanyi, Keynes, Schumpeter and Schumacher. In a conclusion the article makes the case for a ‘pluralistic’ to the organisation of political and economic power in the UK.
Political Science
Keywords: neoliberalism; pluralism; political economy; social market

Turning Financial Markets inside Out: Polanyi, Performativity and Disembeddedness - Muellerleile, Chris (Environment and Planning A, 2013)
In light of the spread of markets across the globe and deeper into daily life, this paper argues for a more robust analysis and application of Karl Polanyi's conception of (dis)embedded markets coupled with the performativity thesis authored mainly by Michel Callon. It suggests that while disembeddedness as a concept is necessary for an analysis of contemporary financial markets that are increasingly self-referential, it is not sufficient. Despite the suggestion of a gulf between Polanyian and Callonian economics, there are important similarities in the two frameworks. The similarities are considered along with the considerable difference, all in an attempt to develop a more robust methodological framework for analyzing financial markets. Performativity, it is argued, can help fill the gaps in Polanyi's embeddedness framework, albeit only when that concept's tendency to produce aspatial and apolitical arguments are taken seriously. The paper uses an abbreviated case study of the development of US financial derivative markets in the 1970s and 1980s to argue that markets must be considered in light of both their institutional and geographic entanglements as well as their (dis)embeddedness in systems of calculativeness and mathematical modeling. Specifically the paper analyzes the tension between the derivative origin story authored by Donald MacKenzie, which focuses on neoclassical pricing models like the Black—Scholes—Merton option pricing formula, and my own empirical research, which suggests the urban-economic geography of Chicago played a key role in the development of these instruments.
Geography
Keywords: Black—Scholes; CALLON; Michel; Chicago; disembeddedness; economic geography; embeddedness; financial derivatives; markets; performativity; urban geography

Disembedding Polanyi: Exploring Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
The paper provides an introduction to a theme issue devoted to the influence—and the potential—of the work of Karl Polanyi in the field of economic geography. Polanyi has been an inspirational figure in the heterodox field of ‘socioeconomics’, where the inseparability of the economic and the social is taken to be axiomatic. He has also made recurrent appearances in economic geography since the early 1990s, as a progenitor of the ‘networks and embeddedness’ approach and in his role as a prescient critic of market fundamentalism. But the potential of Polanyian approaches in economic geography has only been fitfully explored. In this context, the contributions to this theme issue make the case for a more sustained—but also open, critical, and creative—engagement with Polanyi's legacy.
Geography
Keywords: economic geography; embeddedness

For Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
Karl Polanyi has been an influential but also somewhat elusive figure in economic geography. Best known for his evocative notion of social embeddedness, it is perhaps fitting that Polanyi's presence has been more metaphorical than substantive. The paper asks what a more engaged Polanyian economic geography might look like. Focusing on methodological affinities, a response is developed in terms of a commitment to the substantivist (as opposed to formal) analysis of actually existing economic formations, together with a more purposive embrace of institutionalism, holism, and comparativism.
Geography
Keywords: comparative economy; economic geography; institutionalism; substantivism

Living without Fruit Flies: Biosecuring Horticulture and its Markets - Phillips, Catherine (Environment and Planning A, 2013)
In this paper, informed by more-than-human and biosecurity literatures, I attend a neglected nonhuman considered a serious agricultural pest: the fruit fly. In addressing what it takes to live without fruit flies, biosecurity is theorised as ongoing, enacted achievement sustained (or not) by everyday and eventful interactions of heterogeneous spaces, strategies, and participants—human and nonhuman. Relations of fruits, flies, and people are explored through one vital attempt to biosecure life: Australia's Fruit Fly Exclusion Zone (FFEZ), a tristate pest-free area established to protect commercial horticulture from the fruit fly. Fruit flies become problematised as their appetites and mobilities confound fruit production and marketing, and affiliated biosecurity controls. Making fruit safe enrolls policy and agricultural sectors, but also more dispersed agents (travellers, residents, trees) and management sites (primarily off-farm). Since its introduction, the FFEZ's ongoing biosecuring normalised, with only occasional outbreak events. However, recent unprecedented outbreaks evoke questions about the FFEZ's future status. In such eventful times, it is worth reflecting on what kinds of living are possible in biosecurity zones—for flies, for resident human communities, and for agrifood networks.
Geography
Keywords: Australia; Queensland fruit fly; agriculture; biosecurity; more-than-human

Men and Things: Karl Polanyi, Primitive Accumulation, and Their Relevance to a Radical Green Political Economy - Prudham, Scott (Environment and Planning A, 2013)
Now is an important moment to be thinking and talking about a critical and normative green political economy. Whether via attempts to develop effective and socially just climate policies at multiple scales of governance [including REDD (reducing emissions from deforestation and degradation) schemes], or to develop proliferating and controversial neoliberal instruments for dealing with undesirable environmental change, environmental governance, and environmental change in the context of contemporary global capitalism are on the agenda. What would a critical and normative green political economy for the current moment look like? This paper draws on Karl Polanyi's The Great Transformation as a resource for answering that question. In particular, Polanyi's discussion of problematic and dualistic notions of nature and society in early political economy and the role he accords social struggles over land in developing his theory of fictitious commodities, embeddedness and the double movement are revisited. The paper stresses how Polanyi's ideas, at once conceptual and polemical, draw centrally on Marx's theorization of primitive accumulation as an inherent, ‘extra-economic’ facet of historical—geographical capitalism, a differentiated unity linking the commodification and objectification of human and nonhuman natures as exchange-values. In this respect, Polanyi offers (or seems to offer) a potential reconciliation of a politics of nonhuman and human nature through his emphasis on primitive accumulation as a site of both political struggle and epistemic transformation.
Geography
Keywords: Karl Polanyi; economism; green political economy; primitive accumulation

Institutional Mobility and Mutation in the Global Capitalist System: A Neo-Polanyian Analysis of a Transnational Cotton Standards War, 1870–1945 - Quark, Amy A. (Environment and Planning A, 2013)
This paper explores the dynamics of institutional change in periods of instability in the global capitalist system. Two recent bodies of literature—actor-centered institutionalism and the ‘policy mobilities’ approach—emphasize how contextual and historical specificities drive transformation as institutions move across space. However, scholars in both traditions give less attention to the systematic patterns of social conflict that influence how policies move and mutate. Drawing on the case of a standards war in the global cotton trade from 1870 to 1945, I build on these literatures by linking them to a neo-Polanyian theory of social conflict within periods of market-led development. From this view, we must understand institutions, their mobilities, and mutations as constituted by and constitutive of struggles over how the global capitalist system should be organized and in whose interests. This requires building on, but also deepening Polanyi's analysis. While Polanyi emphasized the destructive effects of liberal market projects that generate social conflict, the ‘push-backs’ against liberal market projects are more diverse than Polanyi suggested, and social conflict can also emerge out of the creative moments of liberal market expansion.
Geography; History
Keywords: cotton; double movement; history; interfirm competition; interstate competition; market expansion; standards

Marketization beyond Neoliberalization: A Neo-Polanyian Perspective on China's Transition to a Market Economy - Zhang, Jun (Environment and Planning A, 2013)
This paper proposes a neo-Polanyian framework of neoliberalization-as-marketization for understanding geohistorically embedded marketization based on five interlinked theoretical conceptualizations: embedded marketization, hybrid integration, double movement, active society, and qualitative state. I argue that this framework can be useful to supplement existing theorizing of neoliberalism, and to facilitate comparative case studies across vastly differently contexts. This framework is then taken to analyze China's post-Mao transition to a market economy. I argue that China's gradualist transition from a centrally planned economy to a mixed economy has been maneuvered by a self-regulating party-state (dis)embedded in a deactivated (active) society. Due to the existence of multiple veto players and intraparty ‘double movement’, the marketization was able to be mostly socially progressive until 1993. However, it was no longer the case when the ‘socialist market economy’ was enshrined and, without political liberalization, the Chinese version of neoliberalization has become even bleaker than elsewhere.
Geography
Keywords: China; double movement; marketization; neo-Polanyian; neoliberalization

The boundaries of cosmopolitanism: Karl Polanyi and the 'Magyar-Jewish mongrel' - Dale, Gareth (Environment & Planning A, 2013)
The author offers his opinion on Hungarian historian Karl Polanyi and the views Karl expressed in a series of letters he sent to his brother Michael Polanyi. In these letters Karl wrote about the Germans attitude towards other Jews and the developing volatile social environment in Budapest, Hungary at the beginning of the 20th Century. He also wrote on the animosity between the Germans and the Jews.
Geography
Keywords: Baltic States; Germans; Jews; POLANYI; Michael; 1891-1976; biography; cosmopolitanism; history; social development

The Institution, the Economy and the Market: Karl Polanyi's Institutional Thought for Economists - Maucourant, Jerome; Plociniczak, Sebastien (Review of Political Economy, 2013)
This paper aims to clarify the logical structure of Karl Polanyi's concept of institution, especially with regard to his most important contribution to political economy—the conception of self-regulating markets as institutions. Although Polanyi did not provide a well-developed concept of institution, this article argues that such a concept exists in his work. Moreover, there is in Polanyi's work a sophisticated institutionalist account of the self-regulating market that has been largely overlooked as Polanyi does not present it explicitly. Analyzing the economy as an institutionalized process, as Polanyi does, reveals that the market is neither a natural nor a spontaneous phenomenon—a conclusion that runs counter to conventional economic thinking. Polanyi's approach enables us to view capitalism (the ‘market society’ in Polanyi's language) through a highly specific cultural fact: the fiction of the self-regulating market. This institutional perspective needs to be reassessed beyond new-institutionalist theoretical constructions.
Economics; Sociology
Keywords: economic structure; free enterprise; institutions (philosophy); philosophy of economics; social facts

Polanyian pedagogies in planning and economic geography - Rankin, Katharine N. (Environment & Planning A, 2013)
The author offers his opinion on social economic planning and the educational courses available on them. The author states that planning social economy was a part of Hungarian economist Karl Polanyi's policy in early 20th century to stabilize the economic conductions in Hungary at that time. The auditor says that Polanyi's book "the Great transformation" formed the basis. which if acted upon, would have preevented the Global Financial Crisis of 2008.
Geography
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; central economic planning; global financial crisis; 2008-2009; nonprofit sector

Class and situated knowledge in Polanyi's The Great Transformation - Schoenberger, Erica (Environment & Planning A, 2013)
The author offers his views on a controversial fundraising organized by then U.S. Presidential Candidate Mitt Romney in May 2012 where he commented that he won't be bothered about a section of society who only have access to national income but have not contributions or income tax to give. The author cites this as one the reason why Romney was not successful and states that Hungarian Economists Karl Polanyi's socioeconomics theory is relevant in the 21st century.
Geography
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; ROMNEY; Mitt; 1947-; income tax; national income; political fundraising; socioeconomics; voters

Polanyi, double movements, and political economic transformations - Smith, Adrian (Environment & Planning A, 2013)
The author offers his opinion on Hungarian Economist Karl Polanyi's opinion on social economy. The auth through use of recent events such as the Arab Uprising since 2011 and the post communism societies discusses Polanyi's views with those of political economic planners. The author states that social change within a society post the economic recession could have been avoided had Polanyi's views being taken seriously.
Geography
Keywords: Arab Spring Uprisings; 2011-; Arab countries; POLANYI; Karl; 1886-1964; double movement; history; nonprofit sector; political economic analysis; postcommunist societies; social change

The two Karls, or reflections on Karl Polanyi's The Great Transformation - Walker, Richard (Environment & Planning A, 2013)
The article reviews the book "The Great Transformation," by Karl Polanyi.
Geography
Keywords: Great Transformation; The (Book); book review; nonfiction; socioeconomics

'Marketless Trading in Hammurabi's Time': A Re-appraisal - Dale, Gareth (Journal of the Economic & Social History of the Orient, 2013)
In this article I revisit Karl Polanyi's writings on ancient Mesopotamia. I begin by situating them in the context of his general approach to trade, markets and money in the ancient world. Next, I reconstruct his major theses on Mesopotamia, drawing upon his published works as well as unpublished documents in the Karl Polanyi and Michael Polanyi archives. Finally, I provide a critical assessment of the merits and demerits of his contribution, with reference to Assyriological research published in the decades that have elapsed since his death in 1964.
History; Economics
Keywords: Mesoporamia; Mesopotamia; ancient history; assyriology; commerce; economic history; historiography; history; markets; money; trade

Rudderless in a Sea of Yellow: The European Political Economy Impasse for Renewable Transport Energy - Harvey, Mark; Pilgrim, Sarah (New Political Economy, 2013)
Faced with the twin challenges of anthropogenic climate change and ‘peak oil’, the need for an urgent and radical transformation of transport energy has been widely recognised. Adopting a neo-Polanyian economic sociology approach, this article asks what conditions European governance capacity to respond to these challenges, at either national or regional levels, using biofuels as a case study. It asks if the complexity of its political institutions, and the heterogeneity of interests and economic organisations, present ‘the biggest obstacle of all’ (Cohen 2007) to reduce fossil fuel dependency. By examining the European Commission level and comparing five countries, evidence is produced for a political failure in terms of continued fossil fuel dependency. Incumbent interests in the agricultural sector and a distinctively European legacy of a transport fleet dependent on fossil diesel, have led to a marriage of convenience between rapeseed farmers and vehicle manufacturers. As a consequence, rather than escaping from the path dependency on fossil fuels (Unruh 2000), Europe has gone down a cul-de-sac of rapeseed biodiesel inherently limited in scope, and with the low levels of greenhouse gas emissions savings. Ironically this outcome is in part an unintended consequence of opposition to biofuels from environmentalist groups and politics.
Sociology; Biology
Keywords: agriculture; biodiesel fuels; biofuels; biomass energy research; climate change; climate change research; economics; peak oil; politically instituted markets; rapeseed

Interests, Resources and Status: The Distribution of Income, Work and Authority in the Family in a Northern Hungarian Village - Sárkány, Mihály (Acta Ethnographica Hungarica, 2013)
The author deals with two interconnected features of contemporary Hungarian rural family life from a historical perspective based on fieldwork carried out in Varsány in the early 1970s and between 2000 and 2005. The first is the intertwining of the lives of successive generations of families in a period when other segments of Hungarian society were becoming more individualistic. This case puts into question whether economic models of the direction of the flow of goods between generations (linear, altruistic or exchange models) are applicable for this situation. The author suggests that Polányi's ideas may be of help in understanding this phenomenon. The second is the balance of genders within families. Tatjana Thelen, who did fieldwork in another Hungarian village, Mesterszállás, pointed out a decline in the status of women. She holds the Hungarian policy of privatisation and reprivatisation responsible for it, which followed the great socio-economic and political change from socialism to capitalism in 1990. As a similar decrease in the status of women did not occur in Varsány, the author argues that other factors also should be taken into consideration for analysing such situations, like the role of commuting, education, and women's share in landed property.
Anthropology
Keywords: Hungary; authority; distribution (economic theory); families; gender; generation; income distribution; research; rural family; transfer of income; work

Unravelling the Embedded Liberal Bargain: Labour and Social Welfare Law in the Context of EU Market Integration - Ashiagbor, Diamond (European Law Journal, 2013)
European economic integration with a minimalist social policy at EU level was in part made possible by strong domestic labour market and social welfare institutions. The main contention of this paper is that EU market liberalisation was embedded within institutions of social citizenship at domestic level, which served to counter the liberalisation of the internal market. But this settlement has been put under strain. In addition to the challenges posed to the sustainability of European welfare states by the global economic crisis, the internal market jurisprudence of the Court of Justice casts doubt on the sustainability of the ‘embedded liberal bargain’. This paper focuses on the role of the Court, in particular in its jurisprudence on the interaction between (EU) market freedoms and (national) labour law, which undermines the ability of states to retain their regulatory autonomy over labour or social welfare law and, arguably, speeds up the unravelling of the ‘embedded liberal bargain’.
Law
Keywords: European Union; embedded liberal bargain; market liberalisation; market liberalization; social citizenship

A variety of capitalism … with Chinese characteristics? - Peck, Jamie; Zhang, Jun (Journal of Economic Geography, 2013)
The ‘varieties of capitalism’ framework represents an influential methodological innovation in the field of comparative political economy. It seeks to account for enduring spatial variations in national economic performance by recourse to macroinstitutional analysis, drawing ideal-type distinctions between liberal market economies, modeled on USA, and coordinated market economies, modeled on Germany. Moving beyond critiques of varieties literature—for instance, its methodological nationalism; its preoccupation with limited, formal registers of (national) institutional variety; its growing reliance on rational-choice, firm-centric methods; its failure to account for the pronounced interpenetration and mutual dependence of capitalist economies and its tendency to privilege typological elaboration over causal explanation—this article explores the critical (counter?) case of Chinese capitalism. It considers the extent to which the Chinese economy can be meaningfully characterized as capitalist; the character of its state form and recent development path and its position within—or beyond—conventional understandings of capitalist variety.
Geography
Keywords: China; Chinese capitalism; capitalism; developmental state; economic structure; economic systems; free enterprise; socialist state; variegated capitalism; varieties of capitalism

On Life as a Fictitious Commodity: Cities and the Biopolitics of Late Neoliberalism - Rossi, Ugo (International Journal of Urban & Regional Research, 2013)
Building on a biopolitical understanding of the economic crisis, this essay contends that the occurrence of the crisis warns that life is not a real commodity but - to put it in Karl Polanyi's terms - a 'fictitious commodity'. This means that life cannot be integrally subsumed within the economy, and therefore the crisis is to be seen as a pathological way in which societies react to the pervasiveness of capitalist relations, showing the illusory character of self-regulating markets and ownership ideologies. Two mutually contradictory biopolitical responses to the neoliberal crisis, led by the state and grassroots movements respectively, are discussed in the concluding section of the essay.
Geography; Urban Studies
Keywords: biopolitics; biopolitics (sociobiology); capitalism; consumers; crisis; fictitious commodities; global financial crisis; 2008-2009; government regulation; home ownership; housing; late neoliberalism; neoliberalism; urban economics

Promoting Freedom of Association in China? Putting Transnational Corporate Social Responsibility into a National Context - Chan, Chris King-Chi (Journal of Comparative Asian Development, 2013)
Using the findings of an intensive case study of a corporate social responsibility (CSR) project in China, this paper argues against the view that CSR and the state's regulations are mutually exclusive. It contests that the theorization of the transnational social movement (TSM) should not ignore the development of the state regime, which in turn is shaped by the power relations in the workplace and the community, and is embedded in the national political history. The findings of this research support the Polanyi-inspired approach which sees CSR as being embedded in the changing patterns of business–government–society relations. This approach highlights that the behaviour of the state and the engagement of civil society have actively shaped the scope and the implementation of CSR. Following this line of argument, this paper provides evidence of the dynamics and paradox of workers' and grassroots NGOs' engagement in CSR in China. The specificity of China stems from the state, on the road of China's transition from a state socialist country to being a part of global capitalism. Workers' and NGOs' frustration at the denial of freedom of association (FOA) under the CSR projects at this stage reflects well the legacy of Chinese state socialism, in particular the nature of the official trade unions and the suppressive function of the local state–global capital nexus. Therefore, the state is by no means being excluded from either business or civil society, as the orthodox view of CSR presumes.
Development Studies
Keywords: CSR; China; NGOs; corporate social responsibility; delegated legislation; freedom of association; labor unions; labour unions; migrant labor; migrant labour; migrant workers; nongovernmental organizations; social responsibility of business; workers’ committee

Ignorance, denial, internalisation, and transcendence: a post-structural perspective on Polanyi's double movement - Holmes, Christopher (Review of International Studies, 2013)
In this article, I suggest what an engagement between post-structuralism and the work of Karl Polanyi might look like. I do this by presenting a reading of Polanyi's concept of ‘double movement’ as a form of problematisation through binary opposition. I suggest that the central opposition that the double movement depicts – between economy and society as reflected in processes of marketisation and social protection – presents itself in such a way that the problems emanating from the opposition can only be solved through its transcendence. On one hand, the terms of transcendence are limited by the terms of the opposition. On the other hand, since transcendence is never reached, the double movement problematisation stabilises the existence of a lacuna between the lived experience of market society and the discursive field of that market society. As such, the form of the problematisation places a double-limit upon the ways in which ‘solutions’ can be presented. I present this thesis in relation to two instances of double movement discussed by Polanyi in his book, The Great Transformation. I then apply the argument to invocations of the economy-society opposition in contemporary political economic discourse, where it remains as ubiquitous as ever.
Political Science
Keywords: Great Transformation; The (Book); denial (psychology); double movement; ignorance (theory of knowledge); political economic analysis; postmodernism; poststructuralism; social aspects

Rethinking ‘Embeddedness’: Law, Economy, Community - Cotterrell, Roger (Journal of Law and Society, 2013)
Ideas (of Karl Polanyi and others) that economies and markets are ‘socially embedded’ are central to recent research in economic sociology, closely paralleling socio-legal claims for studying law in ‘social context’. But the concept of embeddedness is imprecise and inadequate: a sociology of law and economy cannot rely on it but must address intellectual and moral-political concerns that its use reflects. Max Weber's writings on law and economy have inspired advocates of a new economic sociology of law, but some of Weber's key claims may be outdated, and he treats law and economy as distinct spheres rather than as facets of the social. Sociological research on law and economy should focus on ‘networks of community’ and their regulation, thus illuminating the social character of both law and economic relations. Viewing the social (including economic life) through a ‘community lens’ makes it possible to analyse cultural factors in regulating markets, while emphasizing links between economic relations and other aspects of social life.
Law; Sociology
Keywords: embeddedness

Law, Social Policy, and the Constitution of Markets and Profit Making - Veitch, Kenneth (Journal of Law and Society, 2013)
This article explores the relationship between law, society, and economy in the context of the contemporary British welfare state. Drawing on themes in Polanyi's The Great Transformation, it identifies the constitutive role of contemporary social policy and law in the creation and maintenance of markets and opportunities for the private sector in the field of welfare, focusing on the institutional mechanisms being put in place to encourage this. What emerges is a reformulation of the function of the welfare state and related law, as these are no longer predominantly driven by a logic of social protection via redistribution to those in need, but increasingly reflect the state's desire to create openings for the private sector within welfare. The institutions that once contributed to ensuring the embeddedness of the market economy in society now play an important role in processes of disembedding – with potentially detrimental consequences for those seeking assistance from the welfare state.
Law; Sociology
Keywords: Great Britain; disembeddedness; welfare state

A More Perfect Commodity: Bottled Water, Global Accumulation, and Local Contestation - Jaffee, Daniel; Newman, Soren (Rural Sociology, 2013)
Bottled water sits at the intersection of debates regarding the social and environmental effects of the commodification of nature and the ways neoliberal globalization alters the provision of public services. Utilizing Polanyi's concept of fictitious commodities and Harvey's work on accumulation by dispossession, this article traces bottled water's transformation from elite niche item to a product consumed by three fourths of U. S. households. Drawing on ethnographic research with participants in two cases of proposed spring water extraction from rural communities by industry leader Nestlé Waters, we make two principal arguments. First, the case of bottled water necessitates a reevaluation of existing theoretical frameworks regarding water privatization and commodification. Municipal tap water networks pose substantial barriers to capital accumulation, leading one influential scholar to frame water as an 'uncooperative commodity.' However, bottled water's characteristics enable it to evade many of these constraints, rendering it a 'more perfect commodity' for accumulation. Second, expansion of the market good of bottled water alters the prospects for the largely publicly provided good of tap water. We conclude that the growth of this relatively new commodity represents a more serious threat to the project of universal public drinking water provision than that posed by tap water privatization.
Sociology
Keywords: HARVEY; David; bottled water; commercial products; drinking water; ethnographic analysis; fictitious commodities; globalization; households; municipal services; primitive accumulation; privatization; research

Homo Economicus and the Economics of Property Rights: History in Reverse Order - Milonakis, Dimitris; Meramveliotakis, Giorgos (Review of Radical Political Economics, 2013)
This article challenges some fundamental propositions of property rights theory by revealing the inability of new institutional economics to fully grasp the notion of property, as reflected in its narrow and problematic definition of property rights. The concept of property relations is proposed as better suited to capture the social and institutional aspects of property. By reconsidering the case of the Montagnais, originally used by Alchian and Demsetz for illustrative purposes, and drawing on the works of Polanyi and McManus, we show that the historical explanation of the emergence of (private) property rights provided by Alchian and Demsetz is flawed.JEL Codes: D02, D23, P14
Economics
Keywords: civil rights; economics; emergence; historical specificity; homo economicus; human rights; institutional economics; property; property relations; property rights; redistribution

Decommodification and Welfare State: the Case of Workplace Accident Victims - Tabin, Jean-Pierre; Probst, Isabelle; Waardenburg, George; Dransart, Dolores Angela Castelli; Pasche, Geneviève; Bolzman, Claudio (Dekommodifizierung und Wohlfahrtsstaat: der Fall von Opfern von Arbeitsunfällen., 2013)
To what extent does the social treatment of workplace injury in Switzerland enable victims to be decommodified in the sense given by Gøsta Esping-Andersen (1990) to this concept, i.e. enable them to leave the labor market in a way that allows them to uphold a socially acceptable standard of living? After a sociological discussion about the concept of decommodification, we present the results of a qualitative study conducted in Switzerland about workplace accident victims and show that the kind of index proposed by Esping-Andersen in order to compare welfare states is based on a faulty premise. (English)
Sociology
Keywords: Arbeitsunfall; POLANYI; Karl; 1886-1964; Schweiz; Suisse; Switzerland; Wohlfahrtsstaat; accident du travail; accident insurance; commodification; cost & standard of living; decommodification; dekommodifizierung; démarchandisation; kommodifizierung; labor laws & legislation; labour laws & legislation; marchandisation; qualitative research; welfare state; work-related injuries; workplace accident; état social

Towards the Great Transformation: (5) Materialisms, old and new: theory, sources, and praxis (an introduction) - Catterall, Bob (City, 2013)
One of the major critical claims of this series is that the social and socio-spatial sciences, in their currently dominant form, cannot, for lack of a de-familiarising agenda, one that leads to an appropriate and continually tested strategy (praxis), effectively counter the normalized and naturalized forms and processes of late capitalist urbanization, normalized by mainstream theory in the service of established power, and their extrapolation into a ‘planetary future’. Critical urban theory presents/presented a step forward but it is losing some critical momentum and thus purchase on present and future realities in its neglect of aspects of its own intellectual heritage, of ‘extra-scientific’ resources including the cognitive aspect of the arts/humanities and ordinary experience (‘the university of the streets’), and in its too restrictive theoretical, spatial and temporal foundations.1 It thus, to a significant extent, fails to give an adequate account, a representational and ethical/normative accounting, of ‘the great transformation’ of marketisation/capitalism as told and analysed notably by Polanyi and Marx, and to the possibilities of and its relationship to praxis for a post-marketised/capitalist great transformation. We need a purposeful reading of the full range of the lived materialities of the planet (not just abstracted away into a distinctly immaterial usage of the notion of the ‘planetary’ and, indeed, of ‘urbanization’). We need in fact a sensuous materialism, an old but still unrealized project. This, the first of two futher episodes, is a brief retrospective and prospective survey, drawing on earlier work in this series and sketching in future directions, of such a materialism (materialisms, old and new): theory, sources and praxis.
Geography
Keywords: capitalism; cities & towns; cultural studies; de-familiarisation; marketisation; marketization; materialism; monsters; urban community development; urbanization

From Blue to Green and Everything in Between: Ideational Change and Left Political Economy after New Labour - Finlayson, Alan (British Journal of Politics & International Relations, 2013)
This article argues that ideational and institutionalist approaches to the study of policy continuity and change should be complemented by research into political ideologies, and with exploration of an 'intermediate' public sphere in which there is extensive intra-ideological dispute. Exploring contemporary left-wing debate about political economy in Britain it is shown that ideational change takes place in the context of disputes rooted in ideological tradition, involving the rearrangement of concepts, the emphasising of some and the marginalisation of others. In the present moment that debate is marked by what may be thought of, heuristically, as 'Keynesian', 'Polanyian', 'Schumpeterian' and 'Schumacherian' points of reference. Assessing the likelihood of this debate developing into a coherent 'crisis narrative' it is shown that the development of the relationship between these poles will be decisive but that at present they stumble over the conceptualisation of 'equality' and 'the state'.
Political Science
Keywords: Great Britain; discursive and rhetorical institutionalism; economic conditions; equality; labour party; political doctrines; political economy; political ideology; politics and government; social attitudes

Globalization and the Privatization of Welfare Administration in Indiana - Aman Jr., Alfred C. (Indiana Journal of Global Legal Studies, 2013)
This article explores the relationship of globalization to domestic law in the context of privatized welfare services in Indiana. It examines the ways that privatization can affect vulnerable populations such as welfare recipients by, in effect, partially dis-embedding the market from the state. It applies Karl Polanyi's conception of a double movement to illustrate how the political process can, in effect, re-embed the market in the state. Utilizing Indiana's recent experiences with welfare administration privatization, this article shows that re-embedding is not a simple question of reversing decisions already taken, but rather a complex sequencing of political and legal engagements. It recommends law reforms aimed at more easily triggering the kinds of political actions anticipated by Polanyi's analysis.
Law; Legal Studies
Keywords: GLOBALIZATION; INDIANA; Indiana; POLANYI; Karl; 1886-1964; POLITICAL participation laws; PRIVATIZATION; Public welfare; double movement; global legal studies; globalization; political participation laws; privatization; public welfare

The Economic-Environment Relation: Can Post-Keynesians, Regulationists and Polanyians Offer Insights? - Chester, Lynne; Paton, Joy (European Journal of Economics and Economic Policies: Intervention, 2013)
As the environmental debate has intensified, post-Keynesians, Regulationists and Polanyians remain relatively silent. All treat time as historical, consider economic issues subordinate to politics and have plenty to say about growth, institutions, uncertainty, and path-dependent events. These concepts seem pertinent to understanding the economic-environment problematic. This article explores the 'environmental potential' of these three heterodox economic traditions. We examine the conception of nature underpinning each methodological approach and the ability of their key conceptual tools to explain the economic-environment relation. Methodological pluralism and a project driven by the neoclassical agenda, we posit, seriously weakens the possibility of a post-Keynesian-grounded coherent environmental perspective. On the other hand, the Regulationists and Polanyians provide cogent analytical frameworks to advance explanations of the economic-environment relation and the contemporary environmental challenge.
Economics
Keywords: Keynesian; Keynesianism; Sraffian; capitalist systems; current heterodox approaches: institutional; economic methodology; environment and development; environment and trade; environmental accounts and accounting; environmental economics: government policy; environmental equity; evolutionary; general aggregative models: Keynes; general aggregative models: Marxian; institutional; political economy; population growth; post-Keynesian; sustainability

A Triple Movement? - Fraser, Nancy (New Left Review, 2013)
Philosophy; Political Science
Keywords: double movement; social protection; triple movement

Insurgency and institutionalization: the Polanyian countermovement and Chinese labor politics - Friedman, Eli (Theory and Society, 2013)
Why is it that in the nearly 10 years since the Chinese central government began making symbolic and material moves towards class compromise that labor unrest has expanded greatly? In this article I reconfigure Karl Polanyi's theory of the coutermovement to account for recent developments in Chinese labor politics. Specifically, I argue that countermovements must be broken down into two constituent but intertwined "moments": the insurgent moment that consists of spontaneous resistance to the market, and the institutional moment, when class compromise is established in the economic and political spheres. In China, the transition from insurgency to institutionalization has thus far been confounded by conditions of "appropriated representation," where the only worker organizations allowed to exist are those within the state-run All China Federation of Trade Unions. However, in drawing on two case studies of strikes in capital-intensive industries in Guangdong province, I show that the relationship between insurgency and institutionalization shifted between 2007 and 2010.
Sociology; Labor Studies
Keywords: ACFTU; China; countermovement; economic capital; insurgency; labor; labour; social movements

Nature and Power - Radkau, Joachim (Social Science History, 2013)
Nature and Power is to be understood not only as human power against nature but also as power by nature in the sense of Michel Foucault's biopouvoir (biopower) or Francis Bacon's "Naturae non imperator nisiparendo" (Only by obeying nature may we dominate nature). The fragile human attempts to get power over nature and by nature have a long history, reaching back over millennia until prehistoric times, and much of world history may be explained in part by the unstable relationship between humans and nature. The environmental approach offers afresh look at global history. The great change that has happened in modern times seems to have been described best by Karl Polanyi (1944) in his Great Transformation, which also refers to a revolution in the human relation to nature. There are primeval symbioses of humans and nature that are the basis of environmental history until modern time. A global history of the environment may be written for a long time along the three great commons of history: woodlands, water, and pasture. The dark tune of Garrett Hardin's (1968) "Tragedy of the Commons," to be sure, does not dominate the whole melody of environmental history. There is also a lot of historical evidence for Elinor Ostrom's rehabilitation of the commons. But it is better to be cautious with dogmatic theories and sweeping judgments. In modern times Hardin may be right, at least in this or that regard. Ostrom's concept applies only to local, not to global commons. The underlying philosophy of Nature and Power is neither optimism nor pessimism but possibilism.
History
Keywords: BACON; Francis; 1561-1626; FOUCAULT; Michel; 1926-1984; Nature & Power: A Global History of the Environment (Book); POLANYI; Karl; 1886-1964; RADKAU; Joachim; environmental history; environmentalism; nature and civilization

Mechanism of Governance of Economic Relations - Rus, Andrej (Teorija in Praksa, 2012)
The problem of the governance of economic transactions arises from the fact that they are sequential. This creates uncertainty regarding the fulfilment of implicit or explicit contracts. Institutional economics understands this uncertainty as arising from opportunism and seeks a solution in specialised contract enforcement institutions. Economic sociology understands the uncertainty as a result of misunderstanding and finds a solution in mechanisms of governance that, in addition to sanctions, allow for coordination among participants in a transaction. In this paper, we confront the arguments made by sociology and economics regarding the mechanism of governance of economic transactions. Following Polanyi, we distinguish three governance mechanisms of economic relations and note that, to be operational, each of them requires a different social structure and social regulation.
Sociology; Economics
Keywords: economic activity; economic sociology; economics; governance mechanisms; institutional economics; social structure; socioeconomics

Polanyi and Hayek on Freedom, the State, and Economics - Filip, Birsen (International Journal of Political Economy, 2012)
This paper examines the relationship that prevails between the state, economics, and freedom according to the works of Friedrich Hayek and Karl Polanyi. Hayek, who was one of the most important contributors to the development of the modern market economy and liberalism, formulated a concept of freedom that includes economic and negative freedom as significant components; his objective was to demonstrate the superiority of liberal capitalist societies over all other forms of organizing a society in terms of achieving freedom. Meanwhile, Polanyi, who confronted all forms of totalitarian regimes and argued that a "self-regulating market … was a utopian project," formulated a concept of freedom that rejected the self-regulating mechanism of the market economy as a component of freedom; he supported regulated markets and included moral, ethical, and social values among the key components required for the realization of freedom. This paper shows that Hayek failed to foresee the destructive social consequences and dehumanizing aspects of modern market capitalism, and promoted the free market economy as a guardian of freedom primarily for its instrumental value. Conversely, Polanyi was able to anticipate the modern market economy's potential to engender disastrous consequences for the whole of humanity and provided an honest and objective analysis of the modern market system that is indispensable for understanding the dilemmas, issues, and contradictions of economic globalization.
Philosophy
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalism; economics; globalization; modern market economy; negative freedom; open society; political philosophy; positive freedom

Adam Smith's Green Thumb and Malthus's Three Horsemen: Cautionary Tales from Classical Political Economy - Dale, Gareth (Journal of Economic Issues (Taylor & Francis Ltd), 2012)
This essay identifies a contradiction between the flourishing interest in the environmental economics of the classical period and a lack of critical parsing of the works of its leading representatives. Its focus is the work of Adam Smith and Thomas Malthus. It offers a critical analysis of their contribution to environmental thought and surveys the work of their contemporary devotees. It scrutinizes Smith's contribution to what Karl Polanyi termed the "economistic fallacy," as well as his defenses of class hierarchy, the "growth imperative" and consumerism. It subjects to critical appraisal Malthus's enthusiasm for private property and the market system, and his opposition to market regulation. While Malthus's principal attraction to ecological economists lies in his having allegedly broadened the scope of economics, and in his narrative of scarcity, this article shows that he, in fact, narrowed the scope of the discipline and conceptualized scarcity in a reified and pseudo-scientific way.
Political Science; History
Keywords: MALTHUS; T. R.; SMITH; Adam; 1723-1790; classical political economy; consumerism; ecological economics; economistic fallacy; environmental economics; environmental policy; growth imperative; natural capital; scarcity

Conventions, the Great Transformation and Actor Network Theory - De Munck, Bert (Konventionen, die große Transformation und Actor Network Theory., 2012)
This article proceeds from the field of tension between the synchronical approach of the economics of convention and the diachronical approach of economic anthropology (in the tradition of Karl Polanyi). It is argued that the economics of convention remain problematic to historians in that they fail to capture the long term transformations traditionally referred to as the emergence of modernity and the coming about of homo economicus. As a possible solution, the use of concepts and insights from Actor Network Theory is proposed. While this cluster of theories enables an historical perspective without considering modernity as a natural process, it confronts changing relationships between subjects, objects and cultural systems of meaning head on.
History
Keywords: CALLON; Michel; actor-network theory; conventions; economic anthropology; economic aspects; history; manners & customs; modernity; performativity

An Analytical Framework for the Relationship between Environmental Measures and Economic Growth Based on the Regulation Theory: Key Concepts and a Simple Model - Okuma, Kazuhiro (Evolutionary and Institutional Economics Review, 2012)
This paper proposes an analytical framework using the regulation approach and consisting of explanations of some concepts and a simple way of modeling; the concepts and modeling are developed by focusing on the distributive aspect of environmental issues and using environmental costs as key indices. As a basis for the framework, we refer to the ideas of Polanyi and the surplus approach, and we recognize the socio-economic system as interlinked triple reproductions of the economy, humans, and the environment. This recognition is formalized as an equation of three-dimensional distributions among profits, wages and rents. The "economy-environment nexus," which represents the relationship between the natural environment's reproduction and economic reproduction, is analyzed as one of the institutional forms. The dynamics of institutional coordination are specified with attention to distributive conflicts between relevant actors, leading to the idea of "spatial and temporal gaps of coordination." Environmental costs are identified and incorporated into the equation of distribution as key information to characterize specific forms of the economy-environment nexus. The economy-environment nexus influences growth regimes through multiple routes, including investment, trade, and productivities. In order to analyze the aggregate effects, we propose a variant of the Kaleckian growth model incorporating environmental costs as key variables. Using this model, we specify conditions for the "paradox of costs for environmental measures," where environmental measures raise the profit rate. This framework is expected to be used in historical or comparative analyses of particular economies, including those using periodized specification of the economy-environment nexus.
Economics
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; distributional effects; employment effects; environment and development; environment and growth; environment and trade; environmental accounts and accounting; environmental equity; pollution control adoption costs; population growth; sustainability

Polanyi defanged - Turner, Stephen (Social Studies of Science (Sage Publications, Ltd.), 2012)
A literary criticism of the book "Michael Polanyi and His Generation: Origins of the Social Construction of Science," by Mary Jo Nye is presented. The author discusses the significance of Michael Polanyi in the history of science studies and provides insight on his life and his relationship with his brother Karl. He analyzes how the book presents the origins of science studies, Polanyi’s activities as an economist, and his fight against Communism.
Sociology
Keywords: Dahomey and the Slave Trade; James Bryant Conant; Karl Polanyi; Michael Polanyi & His Generation: Origins of the Social Construction of Science (Book); NYE; Mary Jo; POLANYI; Michael; 1891-1976; communism & science; economists; planning of science; science - study & teaching

The ‘Double Movements’ of Neighbourhood Change: Gentrification and Public Policy in Harlem and Prenzlauer Berg - Bernt, Matthias (Urban Studies (Sage Publications, Ltd.), 2012)
This article explores the interrelation of gentrification and public policies in the neighbourhoods of Prenzlauer Berg (Berlin) and Harlem (New York City). It draws on Karl Polanyi’s concept of a ‘double movement’ and argues that gentrification is fundamentally a political process. Thus, while demise in the face of market forces, or even an active support of gentrification, is clearly visible in both neighbourhoods, the relation between public policies and gentrification is also highly unstable and contradictory. The cases studied highlight that the resources to push or prevent gentrification are contingent; they are not built into the essence of urban development.
Geography; Urban Studies
Keywords: Berlin (Germany); Germany; Harlem (New York; N.Y.); economic conditions; gentrification; government policy; social conditions; urban planning; urban renewal

Addiction: The Urgent Need for a Paradigm Shift - Alexander, Bruce K. (Substance Use & Misuse, 2012)
Severe addictions to drug use and to countless other habits are causing enormous harm around the globe. Massive expenditures and dedicated efforts of police, doctors, addiction therapists, and self-help groups have failed to bring the problem under control, although many individual addicts have been helped. What can society do when our best efforts continue to fail and a menacing problem continues to grow? This paper proposes that a major paradigm shift is required. The currently dominant paradigm assumes that addiction is either an individual disease or an individual moral breach. But this individually oriented paradigm has failed. Instead, addiction needs to be understood socially, as a way that large numbers of people adapt to the breakdown of psychologically sustaining culture under the global influence of free-market society. This new paradigm is based on the social thinking of Karl Polanyi and other social scientists rather than on the individual thinking of neuroscientists, doctors, or psychologists.
Psychology
Keywords: addiction; addictive consumption; alienation; compulsive behavior; economic aspects; free-market society; globalization; paradigm shifts; paradigms (social sciences); psychological factors; psychosocial integration; social problems; social psychology; social support; socioeconomic factors

A second double movement? Polanyi and shifting global opinions on neoliberalism - Levien, Michael; Paret, Marcel (International Sociology, 2012)
Karl Polanyi’s theory of the ‘double movement’ has gained great currency in recent years to explain the global growth of contemporary social movements resisting neoliberalism. However, there has been no statistical research demonstrating whether these protest movements represent a more general trend of growing discontent with ‘disembedding’ markets from public control. This article uses questions from the World Values Survey to construct an ‘embeddedness’ index measuring public opinion on the desired relationship between states and markets. Focusing on public opinion in 20 countries during the 1990s, the analysis poses three questions: First, is there evidence of increasing global support for ‘re-embedding’ markets? Second, how does such opinion vary across regions of the world? Finally, what is the class and gender composition of this latent countermovement? The results provide substantial evidence of an emerging countermovement in public opinion over the 1990s with complex class, gender, and geopolitical variation.
Sociology
Keywords: countermovement; double movement; embeddedness; neoliberalism

China's Decentralized and Inegalitarian Developmental State - Nordhaug, Kristen (Forum for Development Studies, 2012)
This article investigates China's market reforms and rapid economic development from the late 1970s. The following questions are posed: (1) How did the Chinese 'peasant revolution' and the rural policies and institutions of Mao China influence the market reforms and subsequent economic development? (2) How does China's development after the market reforms relate to Marxist and Polanyian notions of proletarization and commodification of land and labour as preconditions of capitalist development? (3) To what extent and why does China's development after the market reforms diverge from East Asian growth with equity? (4) How does China's 'decentralized developmental state' influence its growth model and distribution? (5) The present Chinese government tries to promote greater equality and more domestic consumption. Is this a Polanyian 'double movement' in response to commodification of land and labour? How likely are these policies to succeed? These questions are addressed through historical-comparative analyses with comparisons of long-term rural dynamics of Mao China and the former Soviet Union. China after the market reforms is compared with England during its transition to agrarian capitalism and industrial capitalism from the sixteenth century through the early nineteenth century and with Taiwan and South Korea from the late 1940s until the 1980s.
Development Studies; Economics
Keywords: Marxian; Sraffian; aggregate factor income distribution; current heterodox approaches: socialist; inflation; institutions and growth; institutions: design; formation; and operations; macroeconomic analyses of economic development; money; socialist systems and transitional economies: national income; product; and expenditure; structure; scope; and performance of government

Consumer markets and national income inequality: A study of 18 advanced capitalist countries - Kollmeyer, Christopher (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2012)
Sociologists have paid scant attention to the possibility that the structure of the macro-economy is an important determinant of income inequality. Although prior research finds negative links between the size of the public sector and income inequality, no study to date considers whether the size of consumer markets has distributional consequences as well. To investigate this possibility, the present study measures the size of national consumer markets with the System of National Accounts used by governments to calculate gross domestic product (GDP). Based on data from 18 advanced capitalist countries over nearly a 40-year period, two-way random effects regression models reveal a strong and positive link between the size of consumer markets and income inequality. This finding is robust to the inclusion of numerous control variables, and to the consideration of endogeneity within the causal relationship. The proposed theoretical explanation centers on ideas developed by Polanyi, and suggests that economic activity in consumer markets creates higher levels of individual differentiation, and hence higher levels of income inequality, than economic activity in other sectors of the economy. The study concludes by highlighting ways future research can advance our theoretical and empirical understanding of this topic.
Sociology
Keywords: Keynesian economics; Keynesianism; consumer goods; consumer markets; distributive justice; economic aspects; economic sociology; equality - economic aspects; income distribution; income inequality; markets - social aspects; research; social classes; social stratification

Reconfiguring the Politics–Law Relationship in the Integration Project through Conflicts–Law Constitutionalism - Everson, Michelle; Joerges, Christian (European Law Journal, 2012)
This paper argues that the relationship between law and politics must be reconfigured within the European Union. Dissecting recent crises in economic, social and political organisation within Europe with reference to the three ‘fictitious’ commodities of Karl Polanyi, we find that law in Europe has contributed to de-legalisation, de-socialisation and disenfranchisement. Moving on to review the potential for law to respond to crisis through new paradigms of conflict resolution as suggested by Ralf Dahrendorf, we find that the steering capacity of law is nevertheless limited if it fails to establish a sustaining relationship with politics. Our conclusions are modest: conflict–law constitutionalism cannot solve Europe's many crises. However, it does represent a new paradigm of law within which relations between European law and European politics might be re-established—a vital step to overcoming crisis.
Law
Keywords: European Union; constitutionalism; economic law; fictitious commodities

Exchange Rising? Karl Polanyi and Contentious Politics in Contemporary Latin America - Silva, Eduardo (Latin American Politics and Society, 2012)
Free-market reforms in the last quarter of the twentieth century weakened the point of production—labor unions—as the source of effective nonparty political countermovement to liberal capitalism. Has another significant source of societal resistance arisen in association with the resurgence of market economics? Building on the work of Karl Polanyi, this article argues that circuits of exchange—the commodification of labor, land, and money—can be powerful sources of movement against contemporary forms of free-market capitalism. It draws on the cases of Argentina, Bolivia, and Ecuador to explore how Polanyi's exchange-based approach helps to elucidate three phenomena: the great variety of identities behind the myriad movements against free-market capitalism, the emergence of community as a powerful locus for organizing, and the proliferation of new forms of transgressive and highly disruptive direct action to reinforce the debilitated effectiveness of the strike.
Political Science
Keywords: Latin America; circuits of exchange; countermovement

Twentieth-Century Jewish Émigrés and Medieval European Economic History - Mell, Julie (Religions, 2012)
This essay discusses the intellectual contributions of five Jewish émigrés to the study of European economic history. In the midst of the war years, these intellectuals reconceptualized premodern European economic history and established the predominant postwar paradigms. The émigrés form three distinct groups defined by Jewish identity and by professional identity. The first two (Guido Kisch and Toni Oelsner) identified as Jews and worked as Jewish historians. The second two (Michal Postan and Robert Lopez) identified as Jews, but worked as European historians. The last (Karl Polanyi) was Jewish only by origin, identified as a Christian socialist, and worked first as an economic journalist, then in worker's education and late in life as a professor of economics. All five dealt with the origin of European capitalism, but in different veins: Kisch celebrated and Oelsner contested a hegemonic academic discourse that linked the birth of capitalism to Jews. Postan and Lopez contested the flip-side of this discourse, the presumption that medieval Europe was pre-capitalist par excellence. In doing so, they helped construct the current paradigm of a high medieval commercial revolution. Polanyi contested historical narratives that described the Free Market as the natural growth of economic life. This essay explores the grounding of these paradigms in the shared crucible of war and exile as Jewish émigrés. This shared context helps illuminate the significance of their intellectual contributions by uncovering the webs of meaning in which their work was suspended.
History
Keywords: Europe; European economic history; Jewish émigrés; KISCH; Guido; LOPEZ; Robert; OELSNER; Toni; POSTAN; Michael; biographical; economic history; historical literature; identity (philosophical concept); immigrants; intellectuals; medieval economic history; research

Processes of disembedding and displacement: anomie and the juridification of religio-ethnic identity in post-New Order Bali - Ramstedt, Martin (Asian Ethnicity, 2012)
This article applies Karl Polanyi's observation of a double movement of law in the history of nineteenth and early twentieth-century Europe to an analysis of Bali's integration into the global cultural economy. It describes how the increasing disembedding of the island's tourist industry from local norms and institutions, and the parallel disjuncture between Balinese religiosity and Indonesian state religion have created a condition of increasing collective anomie that has in turn provoked endeavors to juridify the Balinese religio-ethnic identity. Conceding the partial success of the juridification process that has been facilitated by the recent governance reform, and that has indeed effected a significant degree of re-embedding both tourism and religion into local culture, the article argues that not only has the anomic condition not been attenuated; the potential for internal conflict and division has even been enhanced.
Law; Anthropology
Keywords: Bali; Balinese (Indonesian people); Europe; POLANYI; Karl; 1886-1964; anomie; decentralization; decentralization in government; disembedding; ethnicity; identity; juridification; religiousness

Solidarity Economy in Brazil: Movement, Discourse and Practice Analysis Through a Polanyian Understanding of the Economy - Lemaître, Andreia; Helmsing, A. H. J. (Bert) (Journal of International Development, 2012)
Solidarity economy (SE) initiatives constitute a worldwide phenomenon that is today at the heart of numerous economic and social debates. They are active in very diverse economic sectors, aiming for example to create employment for poor and low-qualified workers. We begin with presenting a Polanyian framework for the analysis of such economic activities, which enables us to develop a plural and integral conception of a productive organisation. We draw on Polanyi's thesis that economy is a political and institutionalised process and present a historic overview of the construction of the SE ‘sector’ in Brazil. We put forward the hypothesis that the SE today in Brazil represents a social movement. Then, we ask ourselves if the SE movement led to a change in grassroots economic initiatives, such as ‘people's cooperatives’. We present the results of exploratory research undertaken on 15 people's cooperatives in the State of Rio de Janeiro and its conclusions. Copyright © 2012 John Wiley & Sons, Ltd.
Political Science; Development Studies
Keywords: Brazil; inclusion; international development; local development; people's cooperative; social movement; solidarity economy

Problems and opportunities in Polanyian analysis today - Holmes, Christopher (Economy & Society, 2012)
The three books under review in this article all demonstrate the beginnings of a shift in the tone of literature on or derived from the work of Karl Polanyi. On one hand, the authors all show a willingness to admit a variety of problems and weaknesses in his work. But on the other hand, it is precisely this degree of critical introspection that enables the authors under review to identify some of the most important and contemporarily relevant aspects of Polanyi's thought. In the two main sections of this article – on Polanyi's concepts of ‘embeddedness’ and ‘double movement’ – I define the problems highlighted in previous iterations of Polanyian literature, moving on to examine how the texts under review address those problems, laying particular emphasis on the ideational components of Polanyi's thought. I conclude by suggesting future directions for Polanyian scholarship, mooting the possibility of a distinctively ‘post-Polanyian’ perspective in which ideas, discourse and framing are placed centre stage.
Sociology
Keywords: DALE; Gareth; HANN; Chris; HART; Keith; Karl Polanyi: The Limits of the Market (Book); Market & Society: The Great Transformation Today (Book); book review; discourse; double movement; economic anthropology: history; ethnography; critique; economic ideas; embeddedness; nonfiction; post-Polanyi

The missing movement: a Polanyian analysis of pre‐crisis America - Herman, Dan (International Journal of Social Economics, 2012)
The purpose of this paper is to seek to apply Polanyi's theory of the double movement as a response to the effects of economic liberalization and globalization to the pre‐2007 American economy. In so doing, it seeks to ascertain the reasons why this assumed double movement did not materialize until after the post‐2007 global economic crisis. Design/methodology/approach – This paper is structured as a theoretical and historical analysis, building upon Polanyi's nineteenth century observations and applying them to contemporary policy economic and social experience in the USA in the late twentieth century. The argument proposes a correlation between the missing and/or delayed movement and the role of access to debt and participation in equity markets. Findings – This paper argues that Polanyi's concept of a societal countermovement has been absent from the post‐1970 period of economic liberalism and globalization until just recently due to an explicit attempt by the forces of capital to circumvent its role in lessening the harmful effects of American capitalism. In particular, the double movement that should have sought to lessen income inequality, unemployment and wage stagnation was instead replaced by access to cheap credit and the democratization of market investments that spurred consumer purchases and a false belief that what was good for the markets was good for working class Americans. Research limitations/implications – This paper highlights the need for ongoing research into the sociotropic nature of trade and of economic policy, and its evolution throughout the contemporary period of economic uncertainty and economic transition. Practical implications – The paper proposes several policy implications arising from the contemporary application of Polanyi's double movement, notably related to international trade and public and political support for ongoing trade liberalization. Social implications – This paper highlights important connections in the relationship between economic policy and the day‐to‐day lives of those who are governed by it. Building on “everyday political economy”, it provides a foundation for arguments that a new balance must be found between economic globalization and transnational capital interests and domestic stability. Originality/value – This paper promotes a novel approach to understanding the political economy of pre‐2007 America, in particular the reflexive nature of economic policy and societal perceptions.
Political Science
Keywords: countermovement; double movement; economic liberalization; global economic crisis; globalization

Karl Polanyi: The Limits of the Market - By Gareth Dale - Langton, Robert W. (Political Studies Review, 2012)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Political Science
Keywords: DALE; Gareth; Karl Polanyi: The Limits of the Market (Book); book review; nonfiction

The point is to keep going: the global sub-prime mortgage crisis, local labour market repositioning, and the capital accumulation dynamic in Singapore - Lim, Kean Fan (Journal of Economic Geography, 2012)
The global subprime mortgage crisis in 2007–2008 led to an economic recession in Singapore, but the economy recovered strongly to post a 14.5% expansion in 2010. This article examines how labour market repositioning policies contributed to this recovery. Following Karl Polanyi's conceptualization of the economy as an ‘instituted process’, I explore how these policies function as state-driven redistributive strategies aimed at triggering reciprocal responses from employers and workers within the putatively self-regulatory local labour market. The Singapore case foregrounds the causal roles of place- and time-specific state–firm–labour interactions in precluding what Polanyi calls society's ‘double movement’ against market-driven regulation. This successful preclusion exemplifies how the conditions and relations of economic production are not reproduced solely through market exchange; to sustain the capital accumulation dynamic, complementary acts of reciprocity and redistribution from different socio-economic stakeholders could be equally, if not more, important.
Geography
Keywords: Singapore; capital accumulation dynamic; economic recovery; global financial crisis; instituted economy; labor market; local labour market; saving and investment; spatio-temporal variation; spatio–temporal fix

Development Theory and the Constitution of Market Society: A Polanyian View - Scott, Alan (Comparative Sociology, 2012)
Abstract This paper argues that development studies could benefit from a closer engagement with the arguments of Karl Polanyi. Firstly, a Polanyian perspective gives greater weight to non-economic and non-material factors in making, maintaining and modifying markets. Secondly, it focuses research on the problematic, state- sponsored and contested process of bringing the market actor into being. Finally, a Polanyian approach might better link a, broadly speaking, leftist analysis to 'real world' policy debates about the relative balance between market freedoms and regulation. The conclusion elaborates this final point.
Sociology
Keywords: POLANYI; Karl; 1886-1964; development; disembedding and reembedding; economic development; financial crises; globalization; market making and modifying; mixed economy; neoliberalism; regulation

The peaceful conspiracy: bond markets and international relations during the Pax Britannica - Flandreau, Marc; Flores, Juan H. (International Organization, 2012)
This article provides foundations to K. Polanyi's famed argument that monopoly power in the global capital market served as an instrument of peace during the Pax Britannica (1815-1914). We focus on the role of intermediaries and certification. We show that when information and enforcement are imperfect, there is scope for the endogenous emergence of 'prestigious' intermediaries who enjoy a monopoly position and as a result, control government actions. They can implement conditional lending: they subject the distribution of credit to the adoption of peaceful policies. Prestigious intermediaries act that way because of their concern with maintaining an unblemished track record when wars increased risks of default. Our analysis, which brings together insights from different disciplines, provides a significant extension to, and departure from, recent research on how countries accumulate reputational capital.
History
Keywords: Pax-Britannica; United Kingdom; bond markets; economic history; global capital market (1815-1914); international relations

The roots of the global economic crisis (Respond to this article at http://www.therai.org.uk/at/debate) - Hart, Keith (Anthropology Today, 2012)
The world economic crisis should be seen as an episode in the history of money. “National capitalism” was the main way of organizing money in the twentieth century and its symbol was national monopoly currency. This system has been unravelling since the US dollar de-pegged from gold in 1971. The result is a disconnect between politics which are still largely national and the money circuit which is decentralized and global. The work of Georg Simmel and Karl Polanyi is enrolled to explain this development which entails the loss of money's physical substance, a shift in the social institutions supporting it and a break-up of the forms and functions of “all-purpose money”. The euro crisis reveals the historical mistake of treating market economy as a driver of society and politics. Good intentions at this stage will not reverse what has become a Greek tragedy in more senses than one.
Anthropology
Keywords: global economic crisis

Economic and Ecological Crises: Green new deals and no-growth economies - Jessop, Bob (Development, 2012)
Bob Jessop applies cultural political economy to the global economic and ecological crisis. He presents theoretical preliminaries concerning economic and ecological imaginaries, and then goes on to highlight the multidimensional nature of the current crisis and struggles over its interpretation.
Sociology; Development Studies
Keywords: cultural political economy; ecological imaginary; economic imaginary; finance-dominated accumulation; finance-led accumulation; green new deal; neoliberalism; post-neoliberalism

What can Okun teach Polanyi? Efficiency, regulation and equality in the OECD - Hopkin, Jonathan; Blyth, Mark (Review of International Political Economy, 2012)
Arthur Okun famously argued that “effciency is bought at the cost of inequalities in income and wealth”. Okun's trade-off represents the antithesis to Karl Polanyi's view of the relationship that the more embedded markets are in society, the better the social and economic outcomes they produce. This paper refines both these views. We argue that not all forms of market embeddedness are created equal, and that the relationship between equality and efficiency can be both positive and negative. We show this by examining how different ways of embedding economic activity in society through market regulation produce different combinations of efficiency and equality. We identify empirically three broad patterns: market liberal regulatory frameworks that promote competitive markets without decommodifying institutions; embedded liberal regulations that allow markets to work efficiently, but within the framework of decommodification and equality; and embedded illiberalism, where regulations hinder markets in favor of powerful social groups and where decommodification undermines both efficiency and equality. Okun's trade-off emerges as a special case limited to the English-speaking democracies: other OECD countries tend to exhibit either efficiency and equality together, or inefficiency and inequality together. These findings suggest a corrective to both nave market liberal views of the incompatibility of efficiency and equality, but also to the more sophisticated Varieties of Capitalism framework, which pays insufficient attention to the ways in which markets can be embedded in stable but apparently dysfunctional institutional arrangements.
Political Science
Keywords: OECD; OKUN; Arthur; critique; embeddedness; international political economy; regulation

A Polanyian Analysis of Capitalism: A Commentary on Fred Block - Bandelj, Nina (Political Power & Social Theory, 2012)
This chapter responds to Fred Block's article about the weaknesses of the concept of capitalism because of its close association with Marxism, and his proposal for a Polanyian analysis of political economy. In this chapter, I interrogate what may be the commonalities as opposed to divergences between Marx and Polanyi, and I question whether the concept of capitalism is really so wedded to Marxism so as to loose its analytic value, and be better replaced by notions such as market society, or political economy, as used by Polanyi. I agree with Block that a Polanyian analysis importantly widens our view beyond economic reductionism to an understanding of economy and society as co-constitutive. However, I see utility in adding the qualifier "capitalist" to "political economy" to differentiate between socialist and capitalist political economies, for instance, and to properly characterize a system based on private property rights, guided by pursuit of material gain, which advantages some strata in society more than others, leading to endemic social inequality. I propose that a Polanyian focus on society and economy as co-constitutive is more effectively coupled with an analysis that considers capitalism not as a self-driven system of surplus extraction and accumulation, but as an institutional order dependent on political choices. Such a perspective would advance a Polanyian analysis of capitalism.
Sociology; Political Science
Keywords: BLOCK; Fred L.; Marxist philosophy; capitalism; economics; equality; market society; political economy; political science

Varieties of What? Should We Still Be Using the Concept of Capitalism? - Block, Fred (Political Power & Social Theory, 2012)
This article argues that social scientists should reconsider the analytic value of the term "capitalism." The paper argues that the two most coherent definitions of capitalism are those derived from classical Marxism and from the Worm System theory of Immanuel Wallerstein. Marx and Engels' formulation was basically a genetic theory in which the structure of a mode of production is determined by the mode of surplus extraction. During the course of the 20th century, however, Marxist theorists had to modify this framework and the result has been an uncomfortable hybrid. Wallerstein resolved these tensions by redefining capitalism in terms of the logic of a worm system. However, his argument has difficulty in explaining the consequential variations over time in the specific rules and institutional structures that operate at the global level. The article goes on to argue in favor of Karl Polanyi's concept of market society because it focuses attention on the political governance of market societies at both the national and the global levels.
Sociology; Political Science
Keywords: Marxist philosophy; capitalism; mixed economy; political science; public administration; variational principles

Double movements and pendular forces: Polanyian perspectives on the neoliberal age - Dale, Gareth (Current Sociology, 2012)
In the neoliberal era, Karl Polanyi’s notion of the ‘double movement’ has been widely deployed by social scientists as a critique of the prevailing order and a predictor of its demise. This article presents the double movement theorem, drawing upon Polanyi’s published and unpublished writings. It explores parallels between his explanation of the advent of the 19th-century free-market regime in Britain and recent Polanyian accounts of the rise of neoliberalism. Following an analysis of the ‘pendular’ refunctioning of Polanyi’s thesis, it closes by asking whether the recent global financial crisis heralds a pendulum swing from neoliberalism (or ‘market fundamentalism’) towards a form of socially coordinated capitalism, or towards ‘more of the same’. As of 2011, it appears that neoliberal policy and ideology remain hegemonic, not in reinvigorated form but as an ‘undead’ policy regime, one that has spawned a burgeoning literature on ‘zombie capitalism’ and ‘zombie neoliberalism’.
Political Science; Sociology
Keywords: Great Britain; Great Britain - economic conditions - 19th century; crise financière; crisis financiera; double movement; financial crises; financial crisis; free enterprise; international competition; mouvement double; movimiento doble; neoliberalism; neoliberalismo; néolibéralisme; social scientists; zombi; zombie

Marx, Weber, and the "Ceaseless Accumulation of Capital." - Ho-Fung Hung (Political Power & Social Theory, 2012)
Seeing capitalism as a system defined by the imperative of the ceaseless accumulation of capital, instead of using the definition based on wage labor or international trade as Block questions, I argue that the concept of capitalism is still too useful to be abandoned, and cannot be replaced by the Polanyian concept of market in our critique of political economy. As Fernand Braudel and Giovanni Arrighi contend, the capitalist logic of capital accumulation, which is affined to monopoly and state power, is antithetical to the logic of market exchange, which is decentralized and prioritizes livelihoods over profits. Historically, capitalism sometimes made use of the market and sometimes subjugated the market to facilitate accumulation. Likewise, globalization today is a combined movement of expanding free market in certain aspects of life through financial deregulation, privatization, trade liberalization, etc. on the one hand, and exclusion of various processes and costs outside the market through revival of extra-economic coercion, externalization of environmental costs, etc., on the other hand. The imperative of capital accumulation drive capitalists and capitalist states to foster marketization and demarketization in different times and spaces. The critique of and resistance to our capitalist system needs to be antimarket in some instances and pro-market in others. A Polanyian critique of the free market is surely powerful and helpful, but it is not enough for our full understanding of the economic malaises of our times. It is at best counterproductive to throw away the concept of capitalism altogether.
Sociology
Keywords: ARRIGHI; Giovanni; BLOCK; Fred; BRAUDEL; Fernand; 1902-1985; capitalism; economics; globalization; international trade; wages

Dispossession, Class Formation, and the Political Imaginary of Colombia's Coffee Producers Over the Longue Durée: Beyond the Polanyian Analytic - Hough, Phillip A.; Bair, Jennifer (Journal of World-Systems Research, 2012)
For more than a decade, social scientists have been analyzing the implications of the neoliberal turn in development policy and the implications of market-led agrarian reform for agricultural producers in the global South. Among this work is a spate of recent scholarship celebrating a number of flagship movements, such as the Zapatistas in Mexico or the landless movement in Brazil, which are interpreted as efforts by rural communities to resist the threat posed by the commodification of livelihoods and the privatization of natural resources. In this article, we aim to problematize what we diagnose as the "Polanyian analytic" underlying accounts of the current conjuncture which emphasize the imminent potential of neoliberalism to spawn protective counter-movements of the sort described in The Great Transformation. We do so through an analysis of the Unidad Cafetero Nacional (UCN) movement, an organization of Colombian coffee farmers that effectively mobilized large numbers of cafeteros in the 1990s to protest the liberalization of the global coffee market and the decline of state support for the domestic coffee sector. While the UCN may be read as a struggle to resist the dispossession of Colombian coffee farmers, we argue that it represented a particular segment of rural producers who wanted, first and foremost, a restoration of their relatively privileged status within the political economy of Colombian agriculture. Our interpretation of the UCN suggests that whether movements emerge in response to neoliberalism depends on the political imaginaries of the social actors who would create them, and further, that these imaginaries are produced through processes of class formation over the longue durée that shape the meaning of dispossession in particular contexts.
Sociology
Keywords: Colombia; agriculture; coffee growers; coffee plantations; commodification; liberalization (finance); neoliberalism; privatization

On Fred Block, Varieties of What? Should We Still Be Using the Concept of Capitalism? - Streeck, Wolfgang (Political Power & Social Theory, 2012)
There are good reasons for preferring the concept of capitalism over that of "market economy." A capitalist economy is one that depends on the commercialization-through-monetarization of ever more social relations. The result is disequilibrium as the normal condition of a society placed under pressure by its "economy" for continuous reorganization in line with a need for ongoing capital accumulation. A capitalist society enlists the possessive individualism of its members as its principal vehicle of social progress, measured as an increase in wealth-as-money. While Polanyian theory has pointed out important features of advanced capitalist societies, there is no need to sacrifice core Marxian concepts for it. Marxian theory helps avoid the trap of political voluntarism, which stipulates a priority of politics in the capitalist political economy or a fundamental difference between "varieties" of capitalism. Moreover, rather than regarding the capitalist economy as by definition "always embedded," political-economic theory must allow for a self-destructive, and indeed socially destructive, tendency of capitalist political economies to "disembed" themselves by struggling free from social controls and dictating to social life the imperatives of market efficiency and a market-conforming distribution of life chances.
Sociology
Keywords: BLOCK; Fred L.; Marxist philosophy; always embedded economy; capitalism; equilibrium (economics); saving and investment; social control; social theory; varieties of capitalism

Fight or Acquiesce? Religion and Political Process in Turkey's and Egypt's Neoliberalizations - Tuğal, Cihan (Development & Change, 2012)
The Polanyian expectation that disruptive marketization will lead to movements and policies that seek to 'embed' the market in society needs to be tempered by closer scrutiny to historical, religious and political contexts. This article studies how movements respond to marketization. The analysis proceeds through a comparison of the Turkish and Egyptian neoliberalizations, religious movements of the last decades, secular opposition, and finally recent processes, which have led to generally different social takes on neoliberalism. The irony of the Turkish case is that with the empowerment of the Islamists, religious opposition to neoliberalism was muted and secular opposition further marginalized and labelled as 'anti-democratic'. As a result, free market policies were not only sustained, but deepened and intensified, turning Turkey into a neoliberal 'success story'. The (thus far) sustained mobilization of youth and labour in Egypt makes a direct imitation unlikely. Another major factor that would prevent a 'Turkish' solution to Egypt's crisis is the contrasting structure of the religious fields. Moreover, while the passive revolution has further solidified the professional and unified religious field in Turkey, the revolutionary process in Egypt seems to reinforce the fragmentation of the religious field. The article points out that making Islam compatible with neoliberalism would be more difficult in a country with a fragmented religious field, such as Egypt. Although neoliberalism was imposed from above and resisted from below in both nations, in Turkey it came to be embraced in the name of Islam and democracy, whereas in Egypt it remains an imposition and popular struggles against it persist. It is suggested that this process and field-based approach to a Polanyian problem can also shed new light on discussions about 'actually existing neoliberalisms'.
Sociology
Keywords: Egypt; Turkey; Turkey - economic conditions - 1960; economic conditions in Egypt - 1952; economic policy; economics - religious aspects - Islam; neoliberalism; religion & politics

Global Climate Governance: A Legitimation Crisis - Van Vossole, Jonas (Review: A Journal of the Fernand Braudel Center, 2012)
This article frames the failure of COP19 in Warsaw, the problems of the RIO+20 summit, the failure of the Copenhagen COP15, and the problems of the carbon markets within a broader legitimacy crisis of global governance, a consequence of the crisis of the global capitalist socio-ecology. Two mechanisms give rise to the loss of legitimacy: unequal development and mercantilization, or the reconfiguration of the power balance and the destruction of social ties. As a consequence, both winners and losers contest the legitimacy of the institutions and mechanisms that govern global capitalism. In this article, we distinguish between Marx-type contestation, referring to emerging classes/states, and Polanyi-type contestation, referring to the victims of global mercantilization. As related to climate governance, the roles of the BRICs in climate negotiations and the global environmental justice movement represent these two types of contestation of the established organizational structures within the global capitalist socio-ecology.
Political Science
Keywords: 21st century; BRICS countries - environmental conditions; BRICS countries - politics & government; MARX; Karl; 1818-1883; alienation; capitalism; climate governance; decision making in environmental policy; globalization & politics; history; organizational legitimacy; power (social sciences); research

Shareholder Engagement in the Embedded Business Corporation: Investment Activism, Human Rights, and TWAIL Discourse - Dhir, Aaron (Business Ethics Quarterly, 2012)
The expansion of extractive corporations’ overseas business opera-tions has led to serious concerns regarding human rights–related impacts. As these apprehensions grow, we see a countervailing rise in calls for government interven-tion and in levels of socially conscious shareholder advocacy. I focus on the latter as manifested in recent use of the shareholder proposal mechanism found in corporate law. Shareholder proposals, while under-theorized, provide a valuable lens through which to consider the argument that economic behaviour is embedded within so-cial relations. In doing so, I situate my analysis within Third World Approaches to International Law (TWAIL) scholarship. Elsewhere, I have supported the use of corporate law tools in advancing the international human rights enterprise and argued that investment activism can be an essential component of this advancement. This paper represents a reflexive pause. Using the case study of a recent proposal submitted to Goldcorp Inc., I seek to problematize the shareholder proposal as a human rights advocacy tool and to examine it as a site of contestation.
Law
Keywords: Third World Approaches to International Law; corporate accountability; corporate law; law; shareholder rights

Embeddedness and regional integration: waiting for Polanyi in a Hayekian setting - Hopner, Martin; Schêfer, Armin (International Organization, 2012)
This article analyzes the social potential of regional integration processes by using the example of European integration. Recent case law from the ECJ has led some observers to argue that judicial decisions increasingly provide European politics with a ôPolanyianö drive. We test this claim by distinguishing three dimensions to European economic and social integration: market-restricting integration, market-enforcing integration, and the creation of a European area of nondiscrimination. We also identify two forms of integration that have different speeds, scopes, and potentials: political integration and judicial integration. The evidence shows that the EU has come closer to Hayek's vision of ôinterstate federalismö than is usually warranted because market-enforcing integration and European nondiscrimination policies have asymmetrically profited from ôintegration through lawö.
Political Science
Keywords: European-integration; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; embeddedness; regional integration; regional-integrationá

The Fundamental and Eternal Conflict - Parguez, Alain (International Journal of Political Economy, 2012)
This contribution aims at exploring what is today the new "normal" in economic policy, namely, austerity. It must be read as a homage to Karl Polanyi, the first who understood the tragedy, and to Kari Polanyi-Levitt, who expanded on her father's thought. Austerity has nothing to do with old anticyclical or stabilizing policies. It is a permanent regime devoid of any sound foundations. It is a pure quasi-religious policy that is self-reinforcing. The author emphasizes the fundamental conflict between its promoter, Friedrich Hayek, and its adversary, John Maynard Keynes, and points to the sole towering intellectual, Karl Polanyi, who understood that their conflict embodied two radically different visions of the world. Polanyi discovered that the core of the conflict was the merciless fight between the supreme rule of God-given market laws, the Hayekian order, and democracy enshrined in a peaceful society that is oriented toward the future. The Hayekian order abolishes the modern democratic state, sacrifices the future, and extols poverty for the sake of order. Polanyi was the first to have discovered the true message of Keynes, who had destroyed the logical foundations of Hayek's philosophy and economics. In conclusion, the author strives to explain why, early in the twenty-first century, the Hayekian legacy is the true road to serfdom because it ignores Polanyi and encourages belief in market laws. Early American "Keynesians," who knew nothing about Hayek, transformed Keynes into a new Léon Walras. These early Keynesians were doomed from the start and vanished when they endorsed the Philips curve as expressing the absolute truth.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; Keynesian economics; The General Theory of Employment; Interest & Money (book); austerity; banking industry – Social aspects; consumption (economics); economic history; employment (economic theory) - social aspects; equilibrium (economics); flexibility; free enterprise; government policy; history of economics - 20th century; international political economy; investments - social aspects; market laws; mixed economy - social aspects; money; money - social aspects; scarcity - social aspects; state

Critique of Current Neoliberalism from a Polanyian Perspective-Politics, Philosophy, and Economics - Seccareccia, Mario (International Journal of Political Economy, 2012)
An introduction is presented which discusses articles within the issue on topics including neoliberalism, the Austrian economist Karl Polanyi's perspective on the history of industrial society during the nineteenth and twentieth centuries and free enterprise.
Economics; Political Science
Keywords: POLANYI; Karl; 1886-1964; free enterprise; neoliberalism; political economy

Beyond Neoliberalism? Crisis and the Prospects for Progressive Alternatives - Cahill, Damien (New Political Science, 2011)
The onset of the current global economic crisis was hailed by many as signalling the demise of neoliberal hegemony. Two years on however, neoliberalism appears to be quite durable. Indeed, after a brief period of Keynesian-type responses, states, on the whole, have embraced neoliberal solutions to the fiscal problems generated by the crisis. Greece, for example, is now following an IMF programme of privatisation and cuts to social expenditure, while other European nations are pursuing austerity policies. In the USA, state and municipal governments are selling off public assets in response to mounting deficits. This paper explains the durability of neoliberalism and the opportunities and challenges it creates for non-neoliberal progressive policy agendas. Drawing upon Karl Polanyi's conceptual framework, this paper argues that neoliberalism is best understood as a historically specific process of state and economic restructuring that is socially embedded through three mechanisms: ideological norms, class relations, and institutional rules. This paper examines responses by states to the crises and concludes that, although the ideological legitimacy of neoliberalism has been somewhat weakened, there is little evidence to suggest that the three mechanisms, through which neoliberalism is socially embedded, have been significantly eroded. The implication for progressive politics is that, just as neoliberalism is socially embedded, so would a successful progressive non-neoliberal political programme need to be socially embedded: through the articulation of a coherent alternative ideology; through the mobilisation of social forces; and through the institutionalisation of non-neoliberal rules and norms within the apparatuses of the state.
Political Science
Keywords: Keynesian economics; economic policy; global financial crisis; 2008-2009; neoliberalism; progressivism; social embeddedness

Toward a new countermovement: a framework for interpreting the contradictory interventions of migrant civil society organizations in urban labor markets - Martin, Nina (Environment & Planning A, 2011)
Low-wage migrant workers in the United States confront a perilous labor market, where wages are low, the risk of injury on the job is high, and the fear of apprehension by immigration authorities is widespread. There is increasing empirical evidence that civil society organizations are becoming involved in mediating labor-market problems, but work remains to be done in developing a robust theoretical conception of why such organizations are involved in this arena and how we might evaluate the impacts of their interventions. This paper presents a framework for interpreting the role of migrant civil society organizations as labor-market intermediaries, by extending Karl Polanyi's theory of the 'double movement' and more recent writing to neoliberalism and precarious work. On the basis of data collected from migrant nonprofit organizations in Chicago, I theorize migrant civil society organizations as part of the creation of a new countermovement that protects the interests of both workers and employers from the destructive nature of an unregulated labor market, as predicted by Polanyi. I catalogue organizations' responses to precarious work and create a generalizable framework for evaluating the contingent outcomes of their strategies. Organizations' work is interpreted as complex and sometimes contradictory: the potential to shield workers and advocate for progressive change is in constant tension with the neoliberal patterns of state and economic restructuring that such organizations can support.
Geography
Keywords: United States; civil society; immigrants; industrial mediation; labour market; migrant labor; migrant labour; neoliberalism; salaries; wages; etc.; societies; etc.

Embedded Markets: A Dialogue between F.A. Hayek and Karl Polanyi - Migone, Andrea (Review of Austrian Economics, 2011)
The recent economic crisis has once more underscored the close connection between markets and social life, thrusting this point at the centre of the analysis of economic and political activity and has once more asked the question of whether and how individuals are embedded in both. Here I argue that an analysis and partial reconciliation of the positions of F. A. Hayek and Karl Polanyi on the topic can help in this debate.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; capitalist systems; embedded markets; history of economic thought

The social economy of new rural reconstruction - Jia'en, Pan; Jie, Du (China Journal of Social Work, 2011)
This paper employs the concept of ‘social economy’ to reflect on the authors' experiences in rural reconstruction efforts in Mainland China, including work on peasant cooperatives and community-supported agriculture. In practice, the social and the economic can never be clearly separated. Economic problems, which may superficially appear to be independent, are in fact over-determined by all kinds of social and cultural factors, so a holistic perspective of ‘social economy’ is needed to re-embed the economic into its social context. Such a perspective can help expand the space of our practice and reflection thereon, in particular helping practitioners to understand the difficulties encountered in rural reconstruction.
Cultural Studies
Keywords: China; new rural reconstruction; perspective; social economy

KARL POLANYI'S METACRITIQUE OF THE LIBERAL CREED Reading Polanyi's Social Theory in Terms of Dialectical Critical Realism - Despain, Hans G. (Journal of Critical Realism, 2011)
This paper interprets Karl Polanyi through dialectical critical realism. The paper maintains that this interpretation offers Polanyi methodological coherence and philosophical support. It further provides dialectical critical realism with an exemplar of explanatory critique. It is argued that the social theory of Polanyi aims at the demystification of market-systems as they are theoretically constructed by both orthodox and heterodox accounts of capitalism. Dialectical critical realism is best capable of situating the theoretical accomplishment of Polanyi's historical and dialectical critiques of social being.
Economics
Keywords: capitalism; critical realism; economic theory; economics; explanatory critique; liberal creed; neoliberalism; ontology; social history; social theory

The Embedded Market and Ideology Critique - Johnson, Pauline (Critical Horizons, 2011)
The article examines the ideology critical potentials of the concept of the embedded market, made famous by philosopher and economic historian Karl Polanyi. It explores several readings of this concept and assesses their ability to revive critical powers of sociology. It discusses the book "The New Spirit of Capitalism," by Luc Boltanski and Eve Chiapello, as a specific take on such an idea. It also offers a re-examination of Polanyi's interpretations of the embedded markets thesis.
Sociology; Philosophy
Keywords: Boltanski and Chiapello; embedded markets; ideology; neoliberalism; philosophers; philosophy; social theory; sociology

Work and Neoliberal Globalization: A Polanyian Synthesis - Bandelj, Nina; Shorette, Kristen; Sowers, Elizabeth (Sociology Compass, 2011)
This article reviews sociological research about economic globalization’s impact on work and labor in developed and developing countries since the 1980s. We find that this period of neoliberal globalization influences work because of intensified activities of multinational corporations (MNCs), financialization of the global economy, and amplified prominence of international organizations, some of which diffuse neoliberal policy scripts while others mobilize a transnational civil society. Research we review generally points to liabilities of neoliberal globalization for workers. To understand these findings, we apply Karl Polanyi’s concepts of fictitious commodities, the self-regulating market, and the double movement. We propose that, on the one hand, the activities of MNCs, international financial organizations, and many states exemplify pushes for institutional separation of economy and society in effort to institutionalize the idea of a self-regulating market at a global scale, which increases labor commodification and global inequalities. On the other hand, the activities of social movements, including unions and transnational actors that target globalization’s impact on work, constitute the counter movement at national and global levels resisting marketization and pushing for labor decommodification. The aftermath of the ongoing economic crisis will tell to what extent this countermovement will be successful in generating an alternative to neoliberal globalization, and more protections for workers.
Sociology
Keywords: double movement; fictitious commodities; globalization; neoliberalism; self-regulating market

Polanyi and Post-neoliberalism in the Global South: Dilemmas of Re-embedding the Economy - Sandbrook, Richard (New Political Economy, 2011)
Although Karl Polanyi Studied a different epoch and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era. The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi's reflections on progressive alternatives to liberalism clarify contemporary debates on development alternatives in the Global South? I contend that democratic socialism – Polanyi's preferred remedy to the ‘demolition’ of society and nature occasioned by market civilisation – is problematical in light of what we have learned from the twentieth century, but his framework for evaluating alternatives – featuring the re-embedding of economy in society – remains as powerful as ever, I support this argument with an exploration of socialism and social democracy – as well as community – based alternatives arising from ‘reciprocity’. Each possibility raises distinctive dilemmas, as an analysis of cases reveals.
Political Science
Keywords: Global South; communitarianism; development alternatives; global south; globalisation; globalization; political economy; post-neoliberalism; social democracy; socialism

Embedding Markets in Temporal Structures: A Challenge to Economic Sociology and History - Eisenberg, Christiane (Die Einbettung von Märkten in temporalen Strukturen: Eine Herausforderung für Wirtschaftssoziologie und Geschichte., 2011)
The essay examines from a historian's point of view the approaches to the analysis of market exchange in new economic sociology and explores in which way sociology and history can cooperate in embedding markets in temporal structures. In a first step the author sharply criticises the favourable reception given to Karl Polanyi's work "The Great Transformation" in the field of new economic sociology. In particular she discusses the narrowing of research perspectives and its negative side effects on the sociology of markets. There then follows a second step: in order to find a linking point for interdisciplinary cooperation, beginning with the current state of historical research, the author makes several considerations on the significance of temporal structures and the time factor in general in analysing markets and market societies.
History
Keywords: Continental Europe; England; Great Britain; economic history; economic sociology; history - methodology; interdisciplinary approach to knowledge; interdisciplinary research; longue durée; market society; socioeconomics; time structures

Contracts in the English NHS: Market levers and social embeddedness - Hughes, David; Petsoulas, Christina; Allen, Pauline; Doheny, Shane; Vincent-Jones, Peter (Health Sociology Review, 2011)
This paper draws parallels between the market trend in the English NHS and Polanyi's (1957) The Great Transformation account of how the rise of markets provokes a self-protective counter-reaction that tries to re-embed economic relations in social relations. We report findings from a qualitative study of NHS contracting, which examines the recent move to harder-edged contracts with greater use of financial penalties and incentives. In practice, use of these techniques tended to be confined to nationally-mandated sections of the contract rather than emerging from local bilateral agreements, and when things went wrong the parties relied more on cooperative behaviour than on the provisions of the contract to find solutions. Making the current contracting system work depended more on existing relational networks than on the incentive structures created by recent 'marketisation' initiatives, but the inability of the market to evolve as expected has encouraged policy makers to publish plans for further radical reforms.
Sociology
Keywords: England; English NHS; NHS reforms; competition (economics); contracting; contracting out; cooperativeness; decentralization in management; financing of research; government agencies; health sociology; incentives in industry; information storage & retrieval systems - medical care; institutional cooperation; interviewing; marketisation; meetings; methodology; national health services; negotiation; organizational effectiveness - evaluation; organizational structure; organizational change; pay for performance; purchaser/provider relations; qualitative research; research methodology; risk management in business; secondary analysis; social context; sociology; theory

Nature, Capital and Neighborhoods: 'Dispossession without Accumulation'? - Kappeler, Aaron; Bigger, Patrick (Antipode, 2011)
The ongoing economic crisis, which originated in the USA and has since spread rapidly to capital markets worldwide, is massive, complex, and many times contradictory. One could say the same for responses to the crisis as governments, firms and multi-national institutions struggle to grasp the full magnitude of the event. This article interrogates the key commodities involved-land, labor and money-and the always-uneasy relations between spaces of social reproduction and capital. Such ambivalence is critical to understanding how new economic realities are formed in light of retreating neoliberalism as markets become destabilized. The analysis provided suggests the commodities involved in the housing crisis are the basis for a countermovement against dispossession.
Geography; Anthropology
Keywords: MARX; Karl; 1818-1883; United States; capital market; capitalism; housing market; international business enterprises; labor; labour; mixed economy; neoliberalism; social aspects

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Sociology; Anthropology; Environmental Studies
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

Karl Polanyi: The Limits of the Market - Barnes, Tom (Journal of Australian Political Economy, 2011)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE; Gareth; KARL Polanyi: The Limits of the Market (Book); Polanyi; Karl; 1886-1964

Embedding Economic Relationships through Social Learning? The Limits of Patient and Public Involvement in Healthcare Governance in England - Vincent-Jones, Peter (Journal of Law & Society, 2011)
The strategy for NHS modernization in England is privileging individual choice over collective voice in the governance of healthcare. This paper explores the tension between economic and democratic strands in the current reform agenda, drawing on sociological conceptions of embeddedness and on theories of reflexive governance. Building on a Polanyian account of the disembedding effects of the increasing commercialization of health services, we consider the prospects for re-embedding economic relationships in this field. An analysis is provided of the limits of the present legal and regulatory framework of Patient and Public Involvement (PPI) in establishing the democratic and pragmatist conditions of social learning necessary for effective embedding. We show how the attainment of reflexive governance in the public interest is dependent on such conditions, and on the capacities of patients and the public to contribute to debate and deliberation in decision making, including on fundamental policy questions such as how services are provided and by whom.
Law; Sociology
Keywords: Great Britain; National Health Service; disembeddedness; embeddedness; medical care; public interest; social learning

Would You Barter with God? Why Holy Debts and Not Profane Markets Created Money - Semenova, Alla (American Journal of Economics and Sociology, 2011)
Attempting to revitalize the substantive approach to economics in the tradition of K. Polanyi, this paper revives the neglected substantive theory of money's origins by Bernhard Laum and thus disputes the formal approaches that see the origins of money in the context of trade. A wide range of evidence, from archeological to etymological, is utilized to demonstrate that relations between men and God, carried out through the intermediary of state-religious authorities, played a causal role in the genesis of the ox-unit of value and account, and, further, in the origins of money, and, subsequently, coinage. The substantive state-religious approach presented in this paper is also compared and contrasted to the Chartalist perspective on money's origins. It is concluded that the substantive approach presented in this paper differs from the more formal approaches (e.g., Metallism) because it does not rely upon a projection of modern institutions and habits of thought (e.g., a medium of exchange; monetary taxation) into ancient societies.
Economics; Sociology
Keywords: ancient societies; money; substantive approach

The Polanyi-Stanfield Contribution: Reembedded Globalization - Brown, Doug (Forum for Social Economics, 2011)
This essay describes and interprets J. Ron Stanfield's analysis of Karl Polanyi. Stanfield has helped to clarify Polanyi's "double-movement" thesis by arguing that the double movement of self-regulating market forces and the protective response is essentially about freedom versus security. These insights provide an analysis that takes Polanyi into the twenty-first century by developing a theory of "reembedded globalization." This is not something that Polanyi experienced before his death in 1964. Corporate globalization and the escalation of free-market rhetoric have led to a new round of disembedding since the 1970s, and this is evident by both the top-down, corporate globalization of privatization, deregulation, and marketization, as well as, by the challenges to it from the "movement of movements" coalescing around the World Social Forum. The most conspicuous evidence of this neo-protective response and its challenge to corporate-driven market forces is that between the security needs of the world's globalization victims and the freedom of transnational corporations to make profits anywhere and in any way throughout the world. Understanding the clash in this way suggests that for humanity to save itself, it must struggle to reembed globalization and put security ahead of unbridled freedom. Reembedding globalization requires asserting democratic security ahead of the economic freedom of big business.
Economics
Keywords: MARX; Karl; 1818-1883; Marxian; Sraffian; capitalist systems; current heterodox approaches; globalization; history of economic thought; international economic order; political economy; reembedded; socialism

Lineages of Embeddedness: On the Antecedents and Successors of a Polanyian Concept - Dale, Gareth (American Journal of Economics & Sociology, 2011)
Since the 1980s, much debate has revolved around Karl Polanyi's concept of the 'dis/embedded economy,' generating some light and not a little heat. This paper looks at three reasons that account for part of the 'heat.' It begins by tracing the sources upon which Polanyi drew. They include Karl Marx, Ferdinand Tönnies, and Max Weber, along with anthropology of the inter-war period, and German and American Institutionalist economics. After exploring the differing ways in which these varying currents conceptualize the relationship between economy and society, I explore the different interpretations of what Polanyi means by embeddedness, and the different purposes to which contemporary economic sociologists have put the term. For some, he is held up as the originator of a line of sociological analysis that treats 'the economy' as a subsystem 'embedded in' a social system. In this reading the emphasis is upon the moral underpinnings of market behavior, in contrast to the naturalism of Ricardo, Malthus and their heirs. For others, his 'disembedding' thesis contains a more radical tale: of the market economy coming to dominate 'society,' bringing forth a sorcerer's apprentice world of untrammeled market forces that, although human creations, lie beyond conscious human control.
Political Science; Sociology
Keywords: MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; TONNIES; Ferdinand; 1855-1936; WEBER; Max; 1864-1920; economic philosophy; economics; embeddedness; influence (psychology); intellectual life - history; socioeconomics

Redistribution in Aegean Palatial Societies Redistribution and the Political Economy: The Evolution of an Idea - Earle, Timothy (American Journal of Archaeology, 2011)
Whether the Bronze Age Aegean economies can be described as "redistributive" depends on how one defines the term. The concept of redistribution itself has undergone several decades of critical archaeological analysis, much of it stemming from my early work in Polynesia. I consider here how Polanyi's ideas about redistributive economies have been expanded since the 1970s. My review complements the article in this Forum by Nakassis et al. and the contribution by Haistead, who discusses why and how the concept of redistribution still matters in studies of the Minoans and Mycenaeans. To some degree, we all agree: chiefs, and later kings, who sought power in archaic societies did so through many highly variable, contingent, and changing means, all designed to support political-economic strategies based on multiple systems of finance. The Bronze Age Aegean societies provide excellent examples of this process, as demonstrated by the contributors to this Forum.
Anthropology; Archaeology
Keywords: Aegean civilization; Bronze age; chiefdoms; economic aspects; kings & rulers; metals; redistribution; wealth

Redistribution in Aegean Palatial Societies Redistribution in Aegean Palatial Societies: Terminology, Scale, and Significance - Halstead, Paul (American Journal of Archaeology, 2011)
Nakassis et al., in their contribution to this Forum, argue that the term "redistribution" has been used with a range of meanings in the context of the Aegean Bronze Age and so obscures rather than illuminates the emergence and functioning of political economies. They call for detailed empirical investigation rather than reliance on ambiguous idealized types. Lupack and Schon concur, arguing respectively that the palace shared control of the Mycenaean economy with sanctuaries and local communities and that centralized production of craft goods (an,d thus elite strategies of wealth finance) developed late at the palace of Pylos. Pullen finds little archaeological support for Renfrew's extrapolation of centralized redistribution to the Early Bronze Age, while Christakis uses evidence of storage to argue the same for Prepalatial Crete and to play down the scale and importance of elite redistribution in the Minoan palaces. The calls for circumspect use of the term "redistribution" and for detailed empirical investigation are applauded, although these five papers arguably do not all attack the same form of redistribution. This response argues that redistribution sensu Polanyi, Finley, and Killen (i.e., centrally administered movements of goods and services without equivalence of value) retains considerable heuristic value in investigation of both textual and archaeological evidence for Bronze Age political economies.
Anthropology; Archaeology
Keywords: Aegean civilization; Eleia (Greece); Greece; Mycenaean civilization; Pylos site (Eleia; Greece); archaelogy; bronze age; economics; redistribution

Economic Surplus, Social Reproduction, Nurturance and Love - O'Hara, Phillip Anthony (Forum for Social Economics, 2011)
This paper examines the contributions of James Ronald Stanfield to social and political economy. We start the analysis with Stanfield's contribution to institution building through his education of PhD students, building a graduate program in political economy, and through the associations of social and political economy. Then we go on to scrutinise his creative developments and applications of the notions of economic surplus and social reproduction. This is followed by his extensive work on Karl Polanyi and the disembedded economy. Finally we explore his path-breaking analysis of the great capitalist restoration, the nurturance gap and love. Stanfield was one of the greatest institutionalists and social economists of the last hundred years, and these four areas of energetic creativity are his prime achievements in the area.
Economics
Keywords: Marxian; Sraffian; current heterodox approaches: socialist; history of economic thought: individuals

Conceptualizing the Economic Role of the State: Laissez-Faire, Technocracy, and the Democratic Alternative - Sabeel Rahman, K (Polity, 2011)
This article contrasts three visions of political economy that appear in the writings of Keynes, Hayek, and Polanyi, and discusses their relevance to current debates over economic policy in the United States. Keynes proposed optimizing market practices through technocratic governance. In recent decades, this influential approach has proven vulnerable to the revival of Hayek's laissez-faire arguments. Polanyi, by contrast, introduced a framework that criticizes both laissez-faire conceptions and the technocratic approach pioneered by Keynes. Because of its emphasis on democratic participation, Polanyi's reasoning provides the building blocks for a new type of contemporary progressive politics.
Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; KEYNES; John Maynard; 1883-1946; United States; economic policy; free enterprise; government regulation; progressivism; the state

Some Social Economics Concepts for Future Research - Stanfield, James Ronald (Forum for Social Economics, 2011)
Under the guidance of a recrudescent nineteenth century ideology, the governance of the global economy has been profoundly altered in the past three decades; indeed, a veritable Great Capitalist Restoration has emerged. It is important to view the transitioning economies and emerging market economies as part of this massive shift in governance. The concept of economic surplus offers a useful perspective on the political economy of governance regimes. Karl Polanyi's post-Marxian view of lives and livelihood provides important insight into the nature of the Great Capitalist Restoration, its ideologically-driven impetus, and its eventual foundering on the shoals of instability, insecurity, inequality, and social and ecological unsustainability. The ineluctable crisis of the Great Capitalist Restoration provides another opportunity to construct a viable democratic economic future, one that avoids the pitfalls that brought down the corporate-welfare state, and offers more than inauthentic, joyless commodity consumption. To build the Road to this Future, we will need a powerful heterodox economic analysis of agency and governance, guided by a vision of an economy which is subordinate to the lives it provisions.
Economics
Keywords: Marxian; Sraffian; capitalist systems: political economy; current heterodox approaches: socialist; international economic order; social economy

Does the human capital discourse promote or hinder the right to education? The case of girls, orphans and vulnerable children in Rwanda - Balsera, Maria Ron (Journal of International Development, 2011)
This paper studies the implications of considering education as a human right and examining it through the lens of the human capital discourse. It uses Polanyi's idea of decommodification, as discussed by Offe and Esping-Andersen, as well as Foucault's concept of governmentality, to analyse the changes that are taking place in the education sector in post-genocide Rwanda. It focuses on the consequences of the human capital discourse for girls, orphans, children with disabilities and Batwa in Rwanda. The paper concludes that although the human capital discourse has brought attention and resources to education, the situation has worsened for some marginalised groups leading to growing inequalities and discrimination. Copyright © 2011 John Wiley & Sons, Ltd.
Education; Educational Sciences
Keywords: Rwanda; commodification; decommodification; human capital; neoliberal governmentality; right to education

The second great transformation: Towards a solidarity society - Brie, Michael; Klein, Dieter (International Critical Thought, 2011)
The double transition to a society based on unfettered capital valorisation, which attempts to legitimize itself by claiming to be a democratic society founded on human rights, can be defined as the first great transformation of the contemporary period. These bourgeois capitalist societies are now in a crisis of their reproduction, integration, rule and security. Three possible scenarios can be discerned: the first attempts to continue the present development (conventional world), the second, the formation of authoritarian fortresses in the centres within an ocean of insecurity and degradation, or, the third, a new transformation to a solidaristic social development. This transformation would begin in capitalism and at the same time point beyond it to a society whose most important goal is the development of free individuals through solidarity-based associations in the economy, in politics and in culture. Its basis would be a solidarity-based multi-sector economy and a participatory democracy. Although the totality of a new society cannot be anticipated, concrete entry projects for a new second transformation can be developed.
Philosophy; Political Science
Keywords: capitalism; double transformation; socialism; solidarity economy

Karl Polanyi's Institutional Theory: Market Society and Its "Disembedded" Economy - Cangiani, Michele (Journal of Economic Issues, 2011)
A fundamental principle of Karl Polanyi's institutional outlook is that any economic system has to be considered as a whole and as a historically specific social organization. This principle implies a comparative method and a critique of conventional economics. Besides, the problem of the interrelation between the economic system and other aspects of social life cannot be avoided. On this basis, Polanyi points out the peculiar "economic" nature of the market-capitalist society and explains the institutional transformations characterizing its history. The opposition "embedded/disembedded," used by Polanyi to distinguish pre-modern economies from the market economy, has been widely adopted in recent times, particularly by economic sociologists, as a key for understanding current complex economic phenomena. However, the reference to Polanyi often presupposes a distorted interpretation of his theory, and a different kind of institutional approach.
History; Economics
Keywords: comparative economics; disembedded economy; economic policy; economic systems; embedded economy; institutional economics; institutional method

The moral economy of the Didache - Draper, Jonathan A. (Hervormde Teologiese Studies, 2011)
This article applies the model of the moral economy in the ancient world, as formulated by Karl Polanyi and applied by Halvor Moxnes, to the economic relations reflected in the Didache. The study partly confirms Aaron Milavec's contention that the instructions in the text would provide an 'economic safety net' for members of the community by putting in place a system of generalised reciprocity and redistribution, although Milavec's depiction of the community as an 'urban working class' movement is found to be anachronistic. The 'communion of the saints' is very much an economic system with aspects of resistance to the Roman imperial system. However, the moral economy of the Didache is seen to reflect a number of ambiguities, particularly in its adoption of the Christian Housetable ethic but also in its adoption of the patron client terminology in the dispute between prophets and teachers on the one side and bishops and deacons on the other.
Religion Studies; Theology
Keywords: Bible; Bible - terminology; Bible - theology; Christian ethics; MILAVEC; Aaron; ambiguity; economic systems; moral economy; theology

Another ‘Great Transformation’ or Common Ruin? - Smart, Barry (Theory, Culture & Society, 2011)
In the aftermath of the 1930s Great Depression, and as the Second World War was drawing to a close, Karl Polanyi concluded a critical analysis of market capitalism on an optimistic — and with the benefit of hindsight we can add premature — note, remarking that the ‘primacy of society’ over the economic system had been ‘secured’. Eighty years later, amidst the unresolved turmoil of another comparable global capitalist economic crisis and accumulating signs of a growing environmental crisis, both a direct legacy of the operation of the ‘market economy’, the remedy advocated by governments and policy-makers is effectively a return to ‘business as usual’. Notwithstanding various manifestations of public expression of dissatisfaction with the consequences of global ‘free-market’ capitalism, which include increasing inequality, poverty, unemployment, depletion of scarce natural resources, environmental destruction, pollution and waste, the default policy setting remains to restore global economic growth, to generate further increases in production and cultivate ever-rising rates of consumption, even if the risk is ‘common ruin’. However, there are a number of realistic, progressive and radical alternatives proposed by critical analysts, including a political program for ‘de-growth’ , a reinvention of communism and detailed policy proposals outlining the measures necessary to promote a transition to a ‘post-capitalist’ society with a sustainable economy.
Sociology
Keywords: BAUMAN; Zygmunt; Farewell to Growth (Book); First As Tragedy; Then As Farce (Book); LATOUCHE; Serge; Living on Borrowed Time: Conversations With Citlali Rovirosa-Madrazo (Book); ZIZEK; Slavoj; 1949-; capitalism; communist hypothesis; de-growth; degrowth; economic growth; environment; financial crisis; nonfiction; sustainability

The Big Picture: 2010 Presidential Address to the American Society of Criminology* - Rosenfeld, Richard (Criminology, 2011)
Microanalysis holds sway over macroanalysis in contemporary criminology. All of criminology would be better off if greater attention were devoted to the big picture—the relationship between crime and the interplay of institutions in the social systems of whole societies. Microlevel researchers often assume that the reduction of individual criminal propensities leads ipso facto to reductions in aggregate crime rates, but the implied connection is illusive, has not been demonstrated, and is belied by the macroanalysis of crime. The perspectives, methods, and data of macrocriminology also need to be developed, however, if they are to advance our understanding of crime at the level of social systems. Emile Durkheim, Talcott Parsons, Karl Polanyi, and C. Wright Mills have contributed essential building blocks for the study of the big picture of crime. Improvements in the quality and timeliness of aggregate crime data, finally, are necessary to bolster the policy relevance of macrocriminology.
Criminology
Keywords: MILLS; C. Wright; PARSONS; Talcott; aggregate crime rates; macrocriminology; social institutions

Neoliberalism as a state-centric class project: The Italian case - Briziarelli, Marco (Continuum: Journal of Media & Cultural Studies, 2011)
This essay sheds light on the neoliberal aspects of the Italian political-economic system exemplified in the relationship between capital, state and media. The main argument is that the specific marriage between neoliberalism and neocorporatism that characterizes Italy reveals a distinctive characteristic of neoliberalism: a class project relying heavily on the state. As Polanyi has suggested through the concept of 'embeddedness', capitalism has consistently developed through the double movement of preaching the independence of the free market from the state and requiring the state's protectionist interventions. After describing this state-centric framework to interpret neoliberalism, in the second part of the paper, I consider the political-economic history of Italy's recent decades, paying particular attention to the media system. I will examine the 'communicative performance' of neoliberalism in Berlusconi's discourses and concrete political decisions taken in the name of neoliberalism. The articulated relationship between media and politics reveals the continuous attempts by the advocates of neoliberalism to seize the state, not to reduce its intervention but in fact to manipulate the market.
Communication Studies; Media Studies; Cultural Studies
Keywords: Italy; economic indicators; essays; mass media audiences; neoliberalism; political economic analysis

Positivism and 'Functional Theory' in the Thought of Karl Polanyi, 1907-1922 - Dale, Gareth (Sociology Compass, 2011)
Karl Polanyi is the author of a modern social science classic, The Great Transformation, as well as a number of well-known and widely debated essays collected in Trade and Market in the Early Empires and Primitive, Archaic and Modern Economies. These texts were researched and written either during his second exile in 1930s Britain or in wartime or post-war North America. Not so well known, however, are his Hungarian writings from the 1910s. Until recently, very few of these had been republished or translated, although this is in the process of being rectified [: Karl Polanyi: The Hungarian Writings]. With reference to new translations of his Hungarian writings, to interviews with his daughter, Kari Polanyi-Levitt, as well as to biographical essays by György Litván, Évá Gábor, Endre Kiss, and Zoltán Horváth, this article explores his early influences, drawing attention in particular to his flirtation with and then violent reaction against philosophical materialism and 'objectivist' sociology, his appreciation of Ernst Mach's positivism, and his adherence to the 'functional theory' of contemporary Guild Socialism.
Political Science; Sociology
Keywords: positivism; religion; social sciences; socialism

The Market and Falling Fertility: Why Darwin Needs Help From Polanyi - Yea, Sanghan (World Futures: The Journal of General Evolution, 2011)
Darwin said all living things tend to multiply. However, nowadays, maintaining fertility rate below the replacement level of 2.1, human beings appear to have opted to let their population shrink. Perplexingly, it occurs while the environment seems to become more suitable for their survival. In solving this puzzle, we get a great help from Polanyi. We proved that people choose to have fewer babies and consequently, usher in depopulation, because by giving them the chance to assess all the expenses necessary for raising children, the market makes the cost clarified increasingly, while the economic benefit from rearing their off-spring remains obscure.
Interdisciplanary
Keywords: DARWIN; Charles; 1809-1882; and memes; below replacement-level fertility; cultural transmission; demographic change; depopulation; exchange; futures research; general evolution; human fertility; markets; memes; reciprocity; redistribution

Crisis and renewal: the outlines of a twenty-first century new deal - Block, Fred (Socio-Economic Review, 2011)
Most analyses of the US financial crisis of 2007–2009 focus on the proximate causes. This article sees the crisis as a consequence of the decline of a long-term pattern of accumulation in the USA and seeks to outline the requirements for a new period of dynamic economic growth. Drawing on work done by the French Regulation theorists and the US analysts of Social Structures of Accumulation, the paper attempts to describe the types of institutional changes that would be needed to spark a new period of stable economic growth in the USA and in the rest of the world economy. The paper outlines what a green mass consumption economy might involve.
Sociology
Keywords: United States; capitalism; capitalist systems; crises; economic change; economic reform; financial crisis; green economy; institutional change

NAFTA and Gatekeeper: A Theoretical Assessment of Border Enforcement in the Era of the Neoliberal State - Ackerman, Edwin (Berkeley Journal of Sociology, 2011)
The coexistence of border-enforcement policies such as Operation Gatekeeper and economic liberalization programs such as NAFTA is arguably paradoxical given the simultaneous push towards afree flow of products but curtailed flow of labor. This paper presents a critical review and reassement of existing accounts of neoliberal statehood to make sense of this apparent puzzle. While some have argued that the state is eroding under neoliberal globalization, a more sophisticated analysis has focused on how it has been transformed. David Harvey and LoIc Wacquant focus on the role of the repressive apparatus in upholding neoliberalism. Building on Harvey and Wacquant, and returning to Karl Polanyi, I emphasize the ways in which the state has tried to make use of a repressive apparatus as a claim to social protection a function that becomes necessary as the state advances liberalization. The coexistence of NAFTA and Gatekeeper should be not be understood as an anomaly but rather as an expected feature of contemporary statehood.
Sociology
Keywords: North American Free Trade Agreement (NAFTA); United States; border security; finance; free trade; liberalization; neoliberalism; social protection

Food crises, food regimes and food movements: rumblings of reform or tides of transformation? - Holt Gimenez, Eric; Shattuck, Annie (Journal of Peasant Studies, 2011)
This article addresses the potential for food movements to bring about substantive changes to the current global food system. After describing the current corporate food regime, we apply Karl Polanyi's 'double-movement' thesis on capitalism to explain the regime's trends of neoliberalism and reform. Using the global food crisis as a point of departure, we introduce a comparative analytical framework for different political and social trends within the corporate food regime and global food movements, characterizing them as 'Neoliberal', 'Reformist', 'Progressive', and 'Radical', respectively, and describe each trend based on its discourse, model, and key actors, approach to the food crisis, and key documents. After a discussion of class, political permeability, and tensions within the food movements, we suggest that the current food crisis offers opportunities for strategic alliances between Progressive and Radical trends within the food movement. We conclude that while the food crisis has brought a retrenchment of neoliberalization and weak calls for reform, the worldwide growth of food movements directly and indirectly challenge the legitimacy and hegemony of the corporate food regime. Regime change will require sustained pressure from a strong global food movement, built on durable alliances between Progressive and Radical trends.
Geography
Keywords: corporate food regime; corporations; food movements; food prices; food security; food sovereignty; food supply; global food crisis; hunger; neoliberalism; peasant studies; right to food; social change; strategic alliances (business)

On the Nation-Specific Features of Modernization in Russia - Yadov, Vladimir (Social Sciences, 2011)
The article offers information on the features that contribute to the modernization in Russia. It discusses various value structure theories from various persons. It says that from the analysis of world survey statistics, Yevgeny Yasin concluded that Russians are more conservative compared to other western countries. Details regarding the mentality of Russian people are discussed including Russians' high score on cycloid scale and their tendency to fulfill their task at the last moment. Moreover, it says that Russia's activist theories, Karl Polanyi and Douglas North's path dependence theory, and the global world system theory as a new phase to human civilization's history are important features to the country's modernization.
Sociology
Keywords: Russia; Russia - social conditions; YASIN; Yevgeny; economic development; modernization (social science); modernization theory; nation-state; national interest; social development theory

Whither the Counter-Movement? Hayek, Polanyi, and the Politics of No Alternative - Mudge, Stephanie (Conference Papers – American Sociological Association, 2011)
This paper turns Karl Polanyi's concept of the "double movement" back on Polanyi and his intellectual contemporary, Friedrich Hayek, as a means to insight into the structural conditions of counter-movement in the second half of the 20th Century. After elaborating on the double movement concept, I contrast the trajectory of Polanyi and his greatest work, The Great Transformation, with that of Friedrich Hayek and his contemporaneous Road to Serfdom–treating each as protagonists in the movement/counter-movement system of relations that, for Polanyi, is the site of history's forward motion. Building on citation data, news articles, archival records and secondary sources, I argue that Polanyi's conditions of intellectual production–including a lack of economic allies in the capitalist West, professional instability, tenuous ties to academic economics, and a lifetime of financial insecurity–explain the ongoing quarantine of Transformation within the academic social sciences. These conditions of production contrast starkly with the Hayekian counterexample. Taken together, the analysis casts light on the ongoing hegemony of the "liberal creed" and the weakness of effective opposition: the trajectory of the two figures offers clues into how structures of intellectual production are linked to (or severed from) movement and counter-movement, offering insight into why, even in the face of financial crisis and significant public anger against the moneyed ranks of the financial sector, we continue to exist in a world of "no alternative".
Sociology
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; capitalism; intellectuals; protagonists (persons)

Karl Polanyi And The Great Transformation - Örmeci, Ozan (Sosyal Bilimler Dergisi, 2011)
Özet: 20. yüzyılın önde gelen iktisatçılarından olan Karl Polanyi (1886-1964), Büyük Dönüşüm adlı eserinde ortaya koyduğu özgün tezler ile halen kapitalizme en ciddi eleştiriyi getirmiş kişilerden biri kabul edilmektedir. Polanyi'nin klasik ENG: Karl Polanyi is known as one of the most famous economists of the world who strongly criticized liberalism and the idea of self-regulating market. Polanyi’s masterpiece The Great Transformation is still accepted as one of the most powerful critiques of liberal economics and many writers from different political backgrounds refer to this book while criticizing the dominant liberal economic understanding. The Great Transformation is a very rich and complex book in which Polanyi analyzes the evolution of the free-market ideology and the counter movement against the damages of liberal economics. Although Polanyi called himself as a socialist, his ideas are very dense and it is not easy to label him as a defender of certain ideology.
Political Science
Keywords: Great Transformation; The (Book); review

Reading the Story of Law and Embeddesness through a Community Lens: A Polanyi-Meets-Cotterrell Economic Sociology of Law [article] - Perry-Kessaris, Amanda (Northern Ireland Legal Quarterly, 2011)
In this paper I propose that role of law in Karl Polanyi's concept of the 'always embedded economy' (Block 2003) can be enriched by the application of the lens of community (Perry-Kessaris 2008) developed by Roger Cotterrell (1996-present). I begin with Polanyi's suggestion that economic action and interaction are always 'embedded' in wider social life. Reading through the lens of community, we can be more specific: any actor is at once engaged, to different degrees (from fleeting to stable), in multiple types (whether focusing on instrumental, traditional, affective and/or belief-based action) of social life. I then explore a second, implicit, cornerstone of Polanyi's argument: that analytical and normative approaches to economy may become dis-embedded from wider social life. Reading through the lens of community we can again be more specific: In the transformation to a market society, the analytical and normative approaches that are central to economic actions and interactions are confused with, and privileged over, those that are central to non-economic actions and interactions. This confusion and privileging can have what we might call a performative effect on action and interaction. Finally, I explore Polanyi's story of law as a facilitator both of dis-embedding movements and of re-embedding counter-movements. The application of a law-and-community lens suggests some additional details of that storyline and that there are additional plotlines to be pursued. The practical potential of this Polanyi-meets-Cotterrell economic sociology of law is briefly illustrated with references to two 21st Century cautionary tales: the World Bank's investment climate programme and the 2008 financial crisis.
Law; Sociology
Keywords: COTTERRELL; Roger; United Kingdom; economic sociology of law; embeddedness; investment climate; law and community

Double Movements of Destruction and Regulation: Commodity Chains and a New Political Economy of the Environment - Roberts, J.; Carmin, JoAnn; Rudel, Thomas (Conference Papers – American Sociological Association, 2011)
Sociologists have examined the ways in which capitalism contributes to environmental degradation as well as how, in selected circumstances, it increases efficiency while reducing pollution and human injustices. In this review, we draw on Polanyi's concept of the double movement to illustrate how self regulating markets give rise to environmental degradation and inequities and, in response, how these conditions often stimulate the emergence of collective action in pursuit of regulatory and social reforms. This process is iterative, with capitalist initiated degradation of the environment followed by regulatory reform and then efforts to weaken the regulatory regimes. We illustrate how resource extraction contributes to environmental degradation and power inequalities, pollution from industrial production is unequally distributed among workers and communities, and how the desire to limit exposure to risk has opened new markets and led to policies that contribute to consumption.
Sociology
Keywords: capitalism; commodity chains; consumption (economics); double movement; environmental degradation; industries; pollution

Towards a Neo-Polanyian Political Economy of Development - Sandbrook, Richard (Conference Papers – International Studies Association, 2011)
The Global South has entered an era of ideological flux. The inadequacies of neoliberalism have spawned a widespread questioning of this dominant worldview. Intellectuals and political movements search for an alternative development ideology that explains what has gone wrong, provides a vision of a more desirable future and suggests a process for achieving this goal. Responding to these challenges, the World Bank and other purveyors of the dominant model have undertaken a gradual shift from an unpopular and inefficacious “Washington Consensus” to a more complex and politically progressive “Post-Washington Consensus”. This shift, though blunting the attack on neoliberalism, has moved the debate on legitimate development strategies to the left and towards more statist approaches. Socialism, the developmental state, social democracy, and emancipatory community-based development have moved back into development discourse. In an earlier era of ideological flux, Karl Polanyi probed the origins of the implosion of economic liberalism in the Great Depression and two world wars, as well as the alternatives that might, by re-embedding the economy in society, allow people to live freer and more secure lives. These reflections came together in The Great Transformation, his masterwork that appeared in 1944. Although Polanyi studied a different era (1830-1940) and focused on Europe, his ideas have inspired an outpouring of studies on contemporary problems and prospects in the neoliberal era (since 1980). The bulk of these studies pertain to industrial countries or global economic issues. However, the human, environmental and financial impact of market deregulation is arguably more devastating in the ‘developing’ countries than in the core. A question thus arises: do Polanyi’s reflections on progressive alternatives to liberalism clarify contemporary debates on progressive alternatives to neoliberalism in the Global South?
Political Science
Keywords: Global South; World Bank; economic development; global south; ideology; political movements; social democracy; socialism

“The Great Transformation” and Suicide: Local and Long-Lasting Effects of 1930 Bank Suspensions - Baller, Robert D.; Levchak, Phil; Schultz, Mark (Suicide and Life-Threatening Behavior, 2010)
Depression-era bank suspensions and failures are conceptualized as products of the first part of what Polanyi (1994) called “The Great Transformation,” which involved an imbalanced institutional arrangement in which the economy dominated other institutions. Relying on Durkheim (1897/1951) and Merton (1938, 1968), it is argued that these banking problems accentuated the type of chronic anomie that Durkheim theorized would create normative deregulation and elevated suicide rates over the long-term. Results from county-level analyses are supportive as the 1930 bank suspension rate is positively related to the 2000 suicide rate, controlling for contemporary and historical factors. The mediating roles of integration and chronic anomie are considered, with the latter measured using data from the geocoded General Social Survey.
Sociology
Keywords: DURKHEIM; Emile; MERTON; Robert; The Great Depression; anomie; countermovement; suicide; suicidology

Neoliberalism and the Biophysical Environment 2: Theorising the Neoliberalisation of Nature - Castree, Noel (Geography Compass, 2010)
There now exists a significant body of theoretically informed empirical research into ‘neoliberal environments’. It comprises numerous studies which together explore the connections between neoliberal principles and policies, on the one side, and the biophysical world on the other. However, making sense of them is by no means straightforward, despite their common focus on neoliberal environments. It is currently left to readers of these studies to synthesise them into a wider, joined-up account of neoliberal environments. This and two companion articles aim for precisely this sort of broad and coherent understanding. The contribution of this second instalment is to present an overarching political economic theory of ‘neoliberal environments’. By synthesising concepts from the work of Karl Marx, Karl Polanyi and James O’Connor, this article presents a framework for thinking about how neoliberal policies relate to the biophysical world.
Geography
Keywords: MARX; Karl; 1818-1883; O'CONNOR; James; neoliberal environments

Simultaneous Transitions: Democratization, Neoliberalization, and Possibilities for Class Compromise in South Korea - Kim, Wonik (Review of Radical Political Economics, 2010)
The purpose of this paper is to bring class compromise back into the study of South Korean political economy and present it as a possible alternative to the overwhelmingly one-sided neoliberal trajectory in South Korea. The process and conditions under which positive class compromise is acquired are identified in terms of the Polanyi-Gramsci nexus. This perspective suggests that the restoration of state-led developmentalism would be unfeasible under a democratic regime, while the implementation of a purely neoliberal blueprint may lead to unproductive class conflict. Employing this theoretical framework, I examine possibilities for positive class compromise in the context of the simultaneous transitions—democratization and neoliberalization—in South Korea. JEL classification: B5, H7, O53, P5
Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; Gramsci; class compromise; democratization; developmental state; neoliberalism

Polanyi's Double Movement and Neoliberalization in Korea and Japan - Kim, Wonik (Social Movement Studies, 2010)
This paper reformulates and extends Polanyi's main insights in The Great Transformations (2001 [1944]) and attempts to theorize the societal countermovement against neoliberalism by illustrating the cases of Korea and Japan. Polanyi's main approach was to synthesize three critical domains: the state, market, and society, and his notion of double movement should be understood as such. Predicated on his double movement, I analytically decompose the mechanism of societal countermovement, emphasizing the importance of social organizations that aggregate people's insecurities and translate them into a political voice capable of acquiring social protection. Applying this analytical framework of the double movement to Korea and Japan reveals that the problem with the conventional understanding of the double movement is that it necessarily arrives at social compensation equilibrium. This paper implies that a highly contentious society, like Korea's, and a highly docile society, like Japan's, may both hinder social welfare provision.
Political Science
Keywords: Japan; Korea; civil society; civil society organizations; double movement; neoliberalism; social movement studies

Labour as a (Fictitious) Commodity: Polanyi and the Capitalist ‘Market Economy’ - Paton, Joy (The Economic and Labour Relations Review, 2010)
In The Great Transformation, Karl Polanyi problematised the commodity status of labour. He described it as ‘fictitious' and asserted the human aspect of labour necessitates ‘protection’. In bringing Polanyi's mature works to bear on these claims, this article uses the ‘fictitious commodity’ concept to highlight the tension in neoclassical theory between concrete reality and its idealist construction of the economy. This contradiction directly challenges the veracity of the self-regulating market. The article develops two related themes. The first is Polanyi's critique of the neoclassical conception of ‘the economy’ as an ideal (market) construct which gave rise to the notion that labour could be regulated by the forces of supply and demand. The second is the lack of logic in the notion of a ‘self regulating’ market and Polanyi's appreciation of the concrete tendencies of capitalist economies to develop institutional arrangements that ensure the economy is always, and necessarily, more than ‘the market’.
Political Science
Keywords: capitalist economy; fictitious commodities; fictitious commodity; institutionalisation; labour; laissez-faire; markets; political economy; regulation; self-regulation; social embeddedness

From Pollyanna to the Pollyanna Principle. A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Caspersz, Donella (Global Labour Journal, 2010)
Business; Management Studies
Keywords: BURAWOY; Michael; labor studies; labour studies; pollyanna principle

'False' Optimism: The Key to Historic Breakthroughs? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Clawson, Dan (Global Labour Journal, 2010)
Sociology
Keywords: BURAWOY; Michael; borderline; global labor studies; global labour studies

From Critical Sociology to Combat Sport? A Response to Michael Burawoy's 'From Polanyi to Pollyanna: The False Optimism of Global Labour Studies' - Webster, Edward (Global Labour Journal, 2010)
Sociology
Keywords: BURAWOY; Michael; double movement; global labour studies; globalization

Decommodification and Egalitarian Political Economy - Vail, John (Politics & Society, 2010)
This article contends that decommodification is an appropriate concept for understanding diverse initiatives such as fair trade, microfinance, open source, social enterprises, and the environmental commons as component features of a common process. Decommodification is conceived as any political, social, or cultural process that reduces the scope and influence of the market in everyday life. Given recent transformations in market societies, a more expansive framework for decommodification is urgently required. Decommodification would insulate non-market spheres from market encroachments; increase the provision of public goods and expand social protection; promote democratic control over the market by creating economic circuits grounded in a logic predicated on social needs rather than profit; and undermine market hegemony by revealing the market’s true social costs and consequences. By ensuring basic needs, enhancing individual capacities and capabilities, and promoting social cooperation and collaboration, decommodification constitutes a central feature of an egalitarian agenda.
Sociology
Keywords: decommodification; double movement; icy silence; sociology

The Foundation of the Modern National Economy and Discipline over Its Monetary Discourse: A Consideration from the Perspective of Polanyian Economics - Wakabayashi, Shigetaro (Journal of Economic Issues (Taylor & Francis Ltd), 2010)
How does the causality between society and the economy run? After examining this fundamental question from the perspective of Polanyian economics, we conclude that the modern national economy is where bargained exchange is institutionalized by society to pre-exist with the aid of discipline over currency issues. However, this discipline is not provided with a proper institutional defense; and potential fragility of the modern national economy owing to this fact was most vividly revealed by central bankers' conduct in the great liquidity crisis of 2007/8. What are we to do for this?
Economics
Keywords: Polanyi's institutionalism; bankers' associations; banking industry - economic aspects; capitalists & financiers; commercial banking system; crises - economic aspects; currency discipline; discourse; discourse and discipline; liquidity (economics); monetary policy; money; negotiation - social aspects; society and the economy

The global financial crisis of 2008–2009: an opportunity for development studies? - Copestake, James (Journal of International Development, 2010)
This paper draws upon the five other papers presented in this volume, along with other presentations made at the 2009 Development Studies Association Conference, to reflect on the relationship between development studies and the 2008–2009 global financial crisis. It first analyses antecedents to the crisis by relating the papers presented by Gore (on long waves of capitalism) and Fischer (on China's integration into the world economy) to a Polanyian analysis. It then considers immediate policy responses with particular reference to India (based on the conference presentation by Mehrotra), China (based on the paper by de Haan) and the 2009 DFID White Paper. Third, it considers two possible additional sources of finance for developing countries: South Korean aid (discussed by Chun et al.) and new forms of international money (discussed by Hudson). The paper concludes that while the crisis is a reminder of structural global economic interconnectedness a challenge for development studies is to combine this fact with analysis that is also interdisciplinary, multi-tiered and policy relevant. Copyright © 2010 John Wiley & Sons, Ltd.
Development Studies
Keywords: 2009 DFID White Paper; China; capitalism; development economics; development studies; global financial crisis; international development; international economic integration

Power and Progress: The Swing of the Pendulum - Stewart, Frances (Journal of Human Development & Capabilities, 2010)
This paper uses Polanyi's 1944 analysis of policy change—in which there are long-term swings from state regulation to markets and back again, as the consequences of one regime lead to political reactions that in turn reverse the policies. It shows how the Polanyi analysis continued to apply throughout the twentieth and early-twenty-first century, well beyond when he wrote, and that the swings also apply to developing country policy-making. It argues that there are new signs of policy change—this time against market domination—in a number of developing countries. The paper concludes that Polanyi's view of the conditions behind policy change—notably long-term political movements, political struggle and political conflict—needs to be introduced into the analysis of policy change for the promotion of human development and the expansion of capabilities.
Development Studies; Economics
Keywords: developing countries; government policy; human development; legislation; policy sciences; policy swings; political economy; political planning

Five Theses on the Common - Roggero, Gigi (Rethinking Marxism, 2010)
I present five theses on the common within the context of the transformations of capitalist social relations as well as their contemporary global crisis. My framework involves “cognitive capitalism,” new processes of class composition, and the production of living knowledge and subjectivity. The commons is often discussed today in reference to the privatization and commodification of “common goods.” This suggests a naturalistic and conservative image of the common, unhooked from the relations of production. I distinguish between commons and the common: the first model is related to Karl Polanyi, the second to Karl Marx. As elaborated in the postoperaista debate, the common assumes an antagonistic double status: it is both the plane of the autonomy of living labor and it is subjected to capitalist “capture.” Consequently, what is at stake is not the conservation of “commons,” but rather the production of the common and its organization into new institutions that would take us beyond the exhausted dialectic between public and private.
Philosophy
Keywords: MARX; Karl; 1818-1883; Marxism; capitalism; class composition; cognitive capitalism; common; commons; financialization; model-based reasoning; operaismo; production (economic theory); subjectivity

Globalisation and the Commodification of Labour: Temporary Labour Migration - Rosewarne, Stuart (Economic and Labour Relations Review, 2010)
There has been a qualitative shift in the character of international labour migration with increased temporary labour migration. With circumscribed employment rights, the increased significance of temporary migrant workers underscores arguments that globalisation has engendered a more profound commodification of labour. The instrumentalist approach, especially of international financial institutions in promoting temporary labour migration as a panacea for development, reinforces this impression. Encapsulated in migration-development discourse, labour migration, like other commodities, is presented as a means of generating export revenue for the South. Karl Polanyi's critique of this market-defined construct of labour as a commodity, when labour can only ever be a fictitious commodity, provides a basis for contesting the representation of labour in the migration-development discourse. However, recourse to a Marxist method is held to be essential if we are to move beyond an appreciation of the process in order to interrogate the rationale that is driving the transformation of labour.
Economics
Keywords: Marxian; Sraffian; commodification; current heterodox approaches: socialist; fictitious commodities; geographic labor mobility; globalization; immigrant workers; labor migration; labour migration; migrant; migrant workers; migration; value theory

Uncertainty Markets and Carbon Markets: Variations on Polanyian Themes - Lohmann, Larry (New Political Economy, 2010)
Enormous new markets in uncertainty and in carbon have been created recently, ostensibly to enhance the cost-effectiveness of both finance and climate action. In both cases, however, creating the abstract commodity framework necessary to make sense of the notion of 'cost-effectiveness' has entailed losing touch with what was supposedly being costed, helping to engender systemic crisis. The new financial markets expanded credit and multiplied leverage by isolating, quantifying, slicing, dicing and circulating diverse types of uncertainty; the resulting unchecked pursuit of liquidity led to a catastrophic drying up of liquidity. The carbon markets, meanwhile, by identifying global warming solutions with reductions in an abstract pool of tradable pollution rights and linking them with 'offsets' manufactured through quantitative techniques, ended up blocking prospective historical pathways toward less fossil fuel dependence and thus exacerbated the climate problem. Unsurprisingly, both markets have provoked strong, if diverse and confused, movements of societal self-defence. This pattern of action and reaction constitutes a chapter in the political history of commodification as significant in some ways as that describing the movements to commodify land and labour analysed by Karl Polanyi.
Political Science
Keywords: atmospheric carbon dioxide; cap and trade; carbon credits; carbon offsetting; carbon trading; climate policy; derivatives; emissions trading; financial crisis; greenhouse gas mitigation; offsets

From Polanyi to Pollyanna: The False Optimism of Global Labor Studies - Burawoy, Michael (Global Labour Journal, 2010)
Sociology
Keywords: EVANS; Peter; 1944-; MARX; Karl; 1818-1883; counter-hegemonic globalization; critique; labor studies; labour studies

The Aporia of Power: Crisis and the Emergence of the Corporate State - Kapferer, Bruce (Social Analysis, 2010)
The argument focuses on the corporate state as an increasingly significant political assemblage that has enabled new configurations of power with related social effects. Here the discussion proceeds from Karl Polanyi's thesis in The Great Transformation. A critical idea that Polanyi pursued related to the state production of economism and individualism, which prepared the ground for the expansion of capital in its globalizing form. The essay develops this idea, indicating that the nationalist capitalism of the state led to a radical change in the political and social orders of states, gradually giving rise to the corporate state assemblage. The emphasis here is on the corporate state as a socio-political order that places radically distinct structural dynamics into impossible conjunction, leading to progressively disastrous social effects concerning poverty and the emergence of new configurations in which war and violence take specific shapes.
Anthropology; Sociology
Keywords: Great Transformation; The (Book); bureaucratic processes; corporate state; crisis; economism; globalization; individualism; nation-state; poverty; power (social sciences); reterritorialization; violence; war; war machine

Decency in Anglo-American Financial Centres? - Pixley, Jocelyn (Thesis Eleven, 2010)
How can a partial, revisable utopia of 'decent society' be used as a yardstick for assessing today's impersonal forms of social integration? In economic life - this essay's focus - Polanyi's hopes that the 'economic system' might cease 'to lay down the law to society' is a start. Recently, financial firms sold commodified promises and obligations on the allure of democratizing credit and providing financial 'choice' to millions. Yet these 'civilities' exploited people's hopes for a dignified life. Any new, partial utopia (as Keynes's was too - to remove the egregious, humiliating features of 'the society in which we live') is yet to be devised. Maria Markus's concept is useful to ask whether the instrumentalism of macro-economic concepts is a distortion of the institutions of money or intrinsic to them. Could solidaristic compromises through civil society minimize disrespectful relationships embedded in money to create decent institutions?
Sociology
Keywords: MARKUS; Maria; POLANYI; Karl; 1886-1964; decent economic institutions; economic democracy; economic systems; embeddedness; essay (literary form); financial centres; social integration; utopias

Cultural political economy and critical policy studies - Jessop, Bob (Critical Policy Studies, 2010)
This article introduces cultural political economy as a distinctive approach in the social sciences, including policy studies. The version presented here combines critical semiotic analysis and critical political economy. It grounds its approach to both in the practical necessities of complexity reduction and the role of meaning-making and structuration in turning unstructured into structured complexity as a basis for ‘going on’ in the world. It explores both semiosis and structuration in terms of the evolutionary mechanisms of variation, selection, and retention and, in this context, also highlights the role of specific forms of agency and specific technologies. These general propositions are illustrated from ‘economic imaginaries’ (other types of imaginary could have been examined) and their relevance to economic policy. Brief comments on crisis-interpretation and crisis-management give this example some substance. The conclusion notes some implications for research in critical policy studies.
Sociology; Political Science
Keywords: complexity; crisis; crisis-management; cultural political economy; cultural turn; finance-led accumulation; green new deal; neoliberalism

Globalization, Crisis and Social Transformation: A View from the South - Munck, Ronaldo (Globalizations, 2010)
The dominant narrative around the unfolding capitalist crisis is firmly focused on the dominant economies, and in particular the US. This is understandable given that the proximate causes of the crisis lie in the imperial heartlands and crisis resolution measures taken there will have a global impact. But a 'view from the South' is needed to redress the balance and prevent the decimation of global majority likelihoods being presented as mere collateral damage. The first section below tackles the crisis from a global (globalization) perspective emphasizing its impact in the South and what that it might mean in terms of political prospects. I then go on to develop a hybrid Karl Polanyi/Antonio Gramsci theoretical lens on counter-movements based on their writings responding to the last systemic capitalist crisis in the 1930s. Finally, I turn to the ways in which the international labour movement and the subaltern or post-colonial worlds are contesting the terrain vacated by unregulated market capitalism. As Gramsci would say the old is dying but the new has not yet been born. La narrativa dominante alrededor de la crisis capitalista revelada, esta firmemente enfocada a las economias dominantes, y particularmente E.E.U.U. Esto es comprensible, dado que las proximas causas de la crisis yacen en la region central imperial y las medidas de resolucion de la crisis que se tomaron alli tendran un impacto global. Pero se necesita un 'punto de vista desde el sur' para compensar el equilibrio y prevenir la devastacion de las posibilidades de las mayorias globales presentadas como simple dano colateral. La primera seccion abajo trata la crisis desde una perspectiva global (globalizacion), enfatizando su impacto en el sur y lo que eso puede significar en terminos de prospectos politicos. Luego procedo con el desarrollo de una lente teorica hibrida de Karl Polanyi/Antonio Gramsci sobre movimientos opuestos en base a sus escritos que responden a la ultima crisis capitalista sistemica en la decada de 1930. Finalmente, vuelvo a las maneras en las cuales el movimiento laboral internacional y los mundos subalternos o postcoloniales estan disputando el terreno vacio por el mercado capitalista sin regulacion. Como Gramsci diria, lo viejo se esta muriendo, pero lo nuevo no esta aun por nacer. [image omitted]
Sociology; Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; South; capitalism; countermovement; crisis; financial crises; financial crisis; globalization; hegemony; international markets; labour; post-colonial; social change; transformation

An Australian international political economy? The high road and the low road - Leaver, Richard (Australian Journal of International Affairs, 2010)
Drawing on Karl Polanyi's distinction between formal and substantive theory, this article argues that 'an Australian international political economy' could (and should) be erected on the historical study of Australia's substantive articulations with the global economy.
Political Science; International Relations
Keywords: Australia; economic policy; international economic relations; international relations; policy sciences

D/developments after the Meltdown - Hart, Gillian (Antipode, 2010)
Part of what makes the current conjuncture so extraordinary is the coincidence of the massive economic meltdown with the implosion of the neoconservative Project for a New American Century, and the reappearance of US liberal internationalism in the guise of “smart power” defined in terms of Diplomacy, Development, and Defence. This essay engages these challenges through a framework that distinguishes between “Development” as a post-war international project that emerged in the context of decolonization and the Cold War, and capitalist development as a dynamic and highly uneven process of creation and destruction. Closely attentive to what Gramsci calls “the relations of force at various levels”, my task in this essay is to suggest how the instabilities and constant redefinitions of official discourses and practices of Development since the 1940s shed light on the conditions in which we now find ourselves.
Geography
Keywords: GRAMSCI; Antonio; 1891-1937; US hegemony; United States; capitalism; capitalist crisis; development; economic development; essay (literary form); hegemony; militarism

A British Bureaucratic Revolution? Autonomy Without Control, or "Freer Markets, More Rules." - Le Galès, Patrick; Scott, Alan (Revue Française de Sociologie, 2010)
This paper addresses a puzzle: how to account for changes in the routine behavior of groups, organizations and individuals in Britain? Following a detailed analysis of state-market interdependence and the role of the state in creating the market, an analysis drawn from the thinking of Weber and Polanyi, we suggest adapting Weber's notion of bureaucratic revolution: in what we call the British bureaucratic revolution, the state has played an essential role in social change by creating institutions and rules that are lastingly reorienting actors' behavior. The example of the healthcare field is examined in order to identify the specific mechanisms that have been impacting on behavior within an approximately ten-year period; namely, the introduction of 1) competitive practices (sanction/reward) and 2) auditing and inspection. If this interpretation is valid, then it is reasonable to assume that the effects of this bureaucratic revolution extend beyond Britain.
Sociology
Keywords: Great Britain; bureaucracy; medical care; revolutions; social change

Now and Then - Watts, Michael J. (Antipode, 2010)
Antipode was launched into the firmament of the 1970s. We might reflect upon how well the journal and its contributors fully appreciated the historical gravity and weight of what was surrounding the project to create “a radical journal of geography”. What sort of radicalism was on offer? The language was “social relevance” from “a radical (Left) political viewpoint”. In writing to celebrate Antipode's birthday, this time in another, and similar, firmament there is still the need to confront the challenge of radicalism and its meanings. Whether we agree with Perry Anderson that the last vestiges of the 1960s have been finally swept away, that the “fluent vision” of the Right has no equivalent on the Left and that embedded liberalism is now as remote as “Arian bishops”, where do radical alternatives stand in relation to the fractured hegemony of neoliberalism? At the very least the need for alternatives is more pressing than ever. David Harvey has proposed rethinking the idea of “the right to the city”. But what other rights might we rethink? I reflect upon this question by returning to the 1960s and 1970s and Marxist debates over the law, and by thinking about the possibilities offered by this Polanyian moment.
Geography
Keywords: ANDERSON; Perry; Magna Carta; Marxist philosophy; Polanyi moment; Polanyian moment; common law - history; commons; essay (literary form); law; law - political aspects; markets; radicalism; scholarly periodicals

Who decides what is fair in fair trade? The agri-environmental governance of standards, access, and price - Bacon, Christopher M. (The Journal of Peasant Studies, 2010)
The agri-environmental governance of value chains can favour a Polanyian double movement seeking social protection and control over price setting markets or it can advance a neoliberal logic that strives to overcome the few remaining civic and ecologic obstacles to full market dominance. Coupled with a typology that contrasts corporate social responsibility and social economy Fair Trade models, this theoretical framework elucidates positions in the current policy debates about the minimum coffee price standard. Many Southern smallholders consider Fair Trade's standards, which for coffee include direct market accesses for smallholder cooperatives, minimum prices, and environmental criteria, among the best deals available. The smallholder empowerment benefits are often better than competing eco-labels. However, this study finds that Fair Trade minimum prices lost 41 percent of their real value from 1988 to 2008. Despite objections from several ‘market driven’ firms and national labelling initiatives, smallholders' collective advocacy and this research contributed to the Fairtrade Labelling Organisations International's (FLO) decision to mandate a 7–11 percent minimum price increase. The price debates demonstrate that Fair Trade governance is neither purely neoliberal nor social movement led – it is a highly contested socially embedded practice. Voices without votes, North–South inequalities, and dwindling prices paid to its stated protagonists indicate the need for governance reform, cost of living price adjustments, and additional investment in the innovative alternative trade and hybrid models.
Environmental Studies
Keywords: double movement; eco-labels; environmental and agricultural governance; environmental science; environmental studies; fair trade; peasant studies; standards; sustainability

Crisis, Continuity and Change: Neoliberalism, the Left and the Future of Capitalism - Castree, Noel (Antipode, 2010)
Abstract: This essay's point of departure is the coincident economic and environmental “crises” of our time. I locate both in the dynamics of capital accumulation on a world-scale, drawing on the ideas of Marx, Karl Polanyi and James O’Connor. I ask whether the recent profusion of “crisis talk” in the public domain presents an opportunity for progressive new ideas to take hold now that “neoliberalism” has seemingly been de-legitimated. My answer is that a “post-neoliberal” future is probably a long way off. I make my case in two stages and at two geographical scales. First, I examine the British social formation as currently constituted and explain why even a leading neoliberal state is failing to reform its ways. Second, I then scale-up from the domestic level to international affairs. I examine cross-border emissions trading—arguably the policy tool for mitigating the very real prospects of significant climate change this century. The overall conclusion is this: even though the “first” and “second” contradictions of capital have manifested themselves together and at a global level, there are currently few prospects for systemic reform (never mind revolution) led by a new, twenty-first century “red-green” Left.
Geography
Keywords: Britain; European Union; climate change; economic crisis; emissions trading; environmental crisis; social formation

Is the Globalization Consensus Dead? - Wade, Robert (Antipode, 2010)
The development economist Dani Rodrik recently declared that “the globalization consensus is dead”. The claim has momentus implications, because this consensus has steered economic policy around the world for the past quarter century. It emanates from the heartland of neoclassical economics, and defines the central tasks of the Washington-based organizations which claim to speak for the world. This essay answers two main questions. First, is Rodrik's claim true, and by what measures of “consensus”? Second, to the extent that the consensus has substantially weakened, is the state returning to the heart of economic life, as Karl Polanyi might have predicted? The answers? First, the globalization consensus about desirable economic policy has weakened, though it is far from “dead”. Second, the western state is returning to the heart of economic life in response to the current global economic crisis, but will retreat soon after national economies recover—because unless the crisis becomes a second Great Depression, the norms of more free markets and more global economic integration will be politically challenged only at the margins. New rules of finance may be introduced, but with enough loopholes that by 2015 Wall Street and the City will operate in much the same way as in the recent pre-crisis past.
Geography
Keywords: Washington consensus; catch-up growth; financial crisis; globalization consensus; income distribution; pension funds; poverty

Polanyian meditations on economy and society: a review of 'Market society: the great transformation today' - Dale, Gareth (Dialectical anthropology, 2010)
Anthropology
Keywords: book review; cultural ethnography; economic anthropology; market economy; society

Movement, Countermovement, and Investment Rules - Schneiderman, David (Conference Papers – Law & Society, 2010)
This paper examines the extent to which one manifestation of neoliberal transnational legality, represented by the investment rules regime, may be vulnerable to critical resistance in the post-recession environment. If the regime was experiencing a crisis of legitimacy before the global recession set in, it might now be portrayed as having broken down entirely. This paper argues, in contrast, that the regime has a constitution-like resiliency that is intended to adapt and last far beyond the present unsettled global scene. First, for many states in the global South, there is no possibility of a Polanyian countermovement without an influx of needed capital from sources such as international financial institutions or foreign investors. This has the effect of locking states further into the regime's web of disciplines. Second, international investment tribunals have been reflexive agents and have responded to legitimacy problems raised by state and social movement actors by adjusting their interpretation of investment treaty disciplines. It turns out that, as Foucault warned, everything is dangerous - states and social movements must move carefully as they proceed to navigate through the current conjuncture. ..PAT.-Unpublished Manuscript
Law
Keywords: Global South; countermovement; global south; investment rules regime; investment tribunals; neoliberal transnational legality

Fair Trade and the Double Movement: The Promise and Contradictions of Improving Labor Standards in the Global South via Market Mechanisms - Shorette, Kristen (Journal of Workplace Rights, 2010)
I examine Fair Trade (FT) as a social movement that emerges as a regulative force in response to the rise of neoliberalism. I apply Polanyi's (1944, 1957) classic concepts of embeddedness and the double movement to understand the conflict that arises within a coherently motivated social movement. Using interview and participant observation data along with content analysis of FT organization mission statements, this research examines the role of conflict within the FT movement over how best to improve the well-being of producers in the global South. I discuss the different, conflicting ways in which FT participants think about improving labor conditions in the global South and the inherent conflict in using market mechanisms to counter market forces. I conclude that while participants share the values of human rights, equality, and environmentalism, realizing these goals through concrete market activities reveals the tension between the benefits of liberalizing and the benefits of regulating the production and sale of FT goods that may impede the continued growth of the movement.
Sociology
Keywords: developing countries; double movement; embeddedness; fair trade; human rights; labor laws & legislation; labour laws & legislation; neoliberalism; production standards; social movements; unfair competition; workplace rights

Local Food: A Social Movement? - Starr, Amory (Cultural Studies/Critical Methodologies, 2010)
This article analyzes the development of “local food” institutions from a social movements perspective. Over the last decade, institutions that “shorten the links” between producer and consumer have developed through a diverse collaboration of many social sectors (farmers, agronomic experts, retailers, chefs, food writers, and several distinct consumer sectors). Some agronomists and rural sociologists critical of the globalization and industrialization of agriculture have recognized this development as heralding Polanyian “reembedding” of market exchanges in social relations. This article analyzes whether and how local food is a social movement, using new social movement theory as an analytic framework.
Sociology; Cultural Studies
Keywords: community-based economics; local food; local foods; localism; organic food; organic foods; social change; social movements; social psychology

Fair Trade Banana Production in the Windward Islands: Local Survival and Global Resistance - Torgerson, Anna McLoughlin (Agriculture and Human Values, 2010)
Fair trade banana farming in the Windward Islands of the Caribbean has emerged since the late 1990s in response to a crisis. Rulings by the World Trade Organization ended a longstanding trade dispute between the US and the EU by eliminating a system of preferential access of Windward Island bananas to the UK market. What followed was a period of rapid decline in banana exports from these small islands and a widespread abandonment of banana cultivation. Those banana farmers who remain are now primarily fair trade producers. Fair trade banana production in the Windward Islands can thus be conceived as a survival strategy that farmers have developed in response to a particular instance of neoliberal globalization. The paper considers this response especially in the context of recent fieldwork on the island of St. Vincent. In light of contributions by several scholars who have drawn upon the work of Polanyi to understand both fair trade and resistance to neoliberalism, fair trade banana production in the Windward Islands appears significant not only as a local survival strategy, but also as part of a larger countermovement that resists neoliberal globalization.
Geography
Keywords: agriculture in international trade; economic development: agriculture; energy; environment; international trade organizations; micro analysis of farm firms; farm households; and farm input markets Q12; natural resources; other primary products; trade policy

Karl Polanyi, Athens and us: the contemporary significance of Polanyi's thought - Wjuniski, Bernardo Stuhlberger; Fernandez, Ramón G. (Revista de Economia Política, 2010)
Karl Polanyi is considered one of the most prominent social scientists of the 20th century. In his writings, an important concern was the relationship between the markets and the society (therefore, the state) as a whole; to discuss it, he introduced the concept of "embeddedness", fundamental for his study of the origins and consequences of the Industrial Revolution. An important part of his heritage is the study of the economic history of what he called "ancient societies," especially of Classical Greece. Polanyi used these studies to compare the ancient societies with his own times, in an effort to understand them all. This paper aims to relate Polanyi's work on the Athenian society with his studies about the modern times, showing that it is possible to draw lessons from Polanyi's thought on the relationship between the society, the state and the market that can help to design a political agenda for our days. In the first part, we present the most important aspects o the life and work of Polanyi, and in the second we discuss the most important aspects of his worldview. Then, in the third part, we study his view of the early Athenian economy; mainly, we focus on the coexistence of a kind of state planning and a market, showing how this understanding is crucial for the whole Polanyian legacy, with its emphasis in the comparison of different societies and times. We conclude by underlining the relevance of this interpretation advanced by Polanyi to understand the societies of our days, focusing on some proposals to extend his approach to deal with our contemporary problems.
History; Economics
Keywords: classical Greek economy; economic history; embeddedness

The Rise and Fall of the Market Economy - Zaman, Asad (Review of Islamic Economics, 2010)
The core economic functions of production and distribution of goods can be handled by many different methods. After the fall of communism, the market mechanism has become nearly universal. Conventional economic theories argue that this is natural, because it is the best and the most efficient method for organizing economic affairs in a society. This paper, based on the analysis of Polanyi (1944) and Klein (2008) argues that the opposite is true. Market mechanisms conflict with natural mechanisms for production and exchange in traditional societies. Unregulated markets cause tremendous damage, as can be witnessed today in terms of countless economic crises, wars, environmental destruction, as well as damage to social networks. Because of this damage, market societies can only be maintained by force, as well as disinformation. To resolve crises on myriad fronts caused by the unregulated market, it is the need of the hour to find viable alternatives.
Economics
Keywords: capitalist systems: performance and prospects; comparative analysis of economic systems; cultural economics: religion; other economic systems: performance and prospects

The Role of the State in Making a National Market: The Evolution of the Grain Market in China (1978-2000) - Zhou, Wubiao (China Agricultural Economic Review, 2010)
The paper aims to examine Karl Polanyi's view of market evolution in the context of the emergence of a national grain market in China's transition economy. The dataset used includes information about inter-provincial grain trade on China's grain market from November 1999 to October 2000. A priori blockmodelling method is used for hypothesis testing. This paper finds that a partially integrated national grain market had emerged at the beginning of the twenty-first century in China in spite of local protectionism. Additionally, the emergence of this market is found to be partly a result of the reform-oriented state's attempt to create national wholesale grain markets.
Economics; Sociology
Keywords: agricultural policy; agriculture; agriculture: aggregate supply and demand analysis; collectives; communes; economic development: agriculture; energy; environment; food policy; natural resources; other primary products; prices

Managing Liberalization and Globalization in Rural China: Trends in Rural Labour Allocation, Income and Inequality - Dong, Xiao-Yuan; Bowles, Paul; Chang, Hongqin (Global Labour Journal, 2009)
China’s integration into the global economy, while rapid, has been managed as part of a wider liberalization process. The structural changes in the rural economy arising from these twin processes have led to widening intra-rural inequalities. To address these, the central leadership has, in Polanyian manner, moved to counter some of the adverse effects of liberalization and globalization. We discuss this dynamic as it has affected rural China. We analyze results from a national data set covering the period 1991-2006 to assess the extent to which the state has been successful in protecting society from the advance of market forces. We find positive outcomes in terms of real earnings growth and poverty reduction but negative outcomes in terms of the rise in open unemployment and in terms of increasing intra-rural income inequality, although this was noticeably more pronounced in the 1991-2000 period than in the 2000-2006 period when more active government redistributive mechanisms were in place.
Economics
Keywords: globalization; income inequality; labor studies; labour allocation; labour studies; liberalization; rural China

Globalization(s) and Labour in China and India: Introductory Reflections - Harriss, John (Global Labour Journal, 2009)
I find it helpful to view the events of the past twenty years or so in a Polanyian frame, and specifically to enquire as to the working out of the ‘double movement’ as the attempt has been made, in both China and India, albeit partially, to shift towards the self-regulating market.
Political Science
Keywords: China; India; double movement; globalization; labor; labour

Performing economy differently: Exploring economic personhood and local economic diversity - McKay, Deirdre (The Australian Journal of Anthropology, 2009)
Many popular conceptions of economy now delimit what counts as the ‘real’ economy by capitalist enterprises, market transactions and wage labour. Anthropologists describe such ideas of economy as abstract, dis-embedded (Polanyi 1957a, b) or virtual (Carrier and Miller 1998), arguing that these conceptions are not adequate to the empirical realities of lived experience. Beyond anthropology, there is a growing literature that theorises the ways academic accounts have themselves brought a dis-embedded or virtual version of economy into being (Mitchell 2002, 2008; Callon 2005; Callon and Caliskan 2005; Latour 2005; Gibson-Graham 2006). Scholars advocating a performative approach argue that academic notions of economy are not simply descriptive of empirical realities, but actively shape those realities, giving form to the ways that a ‘real’ economy emerges from particular socio-cultural fields. In the context of applied development anthropology, a performative reading of economy offers a helpful platform for applied research directed towards diversifying local economic understandings and practices. This paper explores the implications of performing economy differently through reflections on an action research project undertaken in the Philippines. Here, a performative approach recreated economy as a space of decision that demands active, ethical choices (Gibson-Graham 2006) and supported relational, rather than individuated, models of economic personhood.
Anthropology
Keywords: action research; disembeddedness; economic anthropology; performative approach

Industrial Policy in the United States: A Neo-Polanyian Interpretation - Schrank, Andrew; Whitford, Josh (Politics & Society, 2009)
The conventional wisdom holds that U.S. political institutions are inhospitable to industrial policy. The authors call the conventional wisdom into question by making four claims: (1) the activities targeted by industrial policy are increasingly governed by decentralized production networks rather than markets or hierarchies, (2) "network failures" are therefore no less threatening to industrial dynamism than market or organizational failures, (3) the spatial and organizational decentralization of production have simultaneously increased the demand and broadened the support for American industrial policy, and (4) political decentralization is therefore likely to improve the functioning of industrial policies designed to combat network failures.
Political Science
Keywords: United States; decentralization in government; economic activity; federalism; governance; industrial organization (economic theory); industrial policy; networks; production (economic theory)

Political Cycles, Political Institutions and Public Expenditure in India, 1980-2000 - Sáez, Lawrence; Sinha, Aseema (British Journal of Political Science, 2009)
In Western democracies it is held that parties and their positions affect how politicians choose to make public expenditure and investment. This article examines the public policy choices of politicians in India, a large well-established democracy with remarkable subnational variation. Public expenditure, from education and health to agriculture and irrigation, is analysed. Counterintuitive findings - that election timing and political factors play a strong role in the subnational states, and that party competition increases investment in education - are explained by highlighting the role economic and political uncertainty plays in politicians' choices. Building a 'Polanyi' argument enhanced by a supply-side mechanism highlights the importance of compensation and insurance and the imperatives of political stability for subnational politicians, who attempt to maximize re-election chances in an uncertain environment.
Political Science
Keywords: India; budget - law and legislation; elections; government purchasing; government spending policy; policy sciences; public administration; public spending; representative government; tax and expenditure limitations

Polanyi in Brussels: Supranational Institutions and the Transnational Embedding of Markets - Caporaso, James A.; Tarrow, Sidney (International Organization, 2009)
AbstractMany have argued that the success of European integration is predicated on reinforcing market structures and some have gone further to state that the creation of a transnational market results in a decoupling of markets from their national political and social frameworks, thus threatening to unravel historical social bargains. Drawing on the work of Karl Polanyi and John Ruggie and using their insights regarding the social embedding of markets, we dissent from this view by examining how the European Court of Justice (ECJ) has handled a key sector of the emerging European market—labor mobility. We argue that rather than disembedding markets, decisions of the ECJ—just as Polanyi and Ruggie would have predicted—activate new social and political arrangements. We find evidence for the development of a new legal and political structure, largely inspired by the Court but also imbricated in European Union legislation, at the regional level.
Sociology; Political Science
Keywords: European Court of Justice; embedded markets

No hay ganancia en la milpa: the agrarian question, food sovereignty, and the on-farm conservation of agrobiodiversity in the Guatemalan highlands - Isakson, S. Ryan (Journal of Peasant Studies, 2009)
Although they receive little recognition for their contribution, peasant farmers in the global South play a fundamental role in securing the long-term global food supply. Via their self-sufficient agricultural practices, they cultivate the crop genetic diversity that enables food crops to adapt to changing environmental conditions. In this paper I draw upon empirical data from the Guatemalan center of agricultural biodiversity to investigate the concern that market expansion will displace peasant agriculture and undermine a cornerstone of the global food supply. I find that even though peasants' livelihoods involve multiple forms of market provisioning, they also engage in a Polanyian 'double movement' to protect their subsistence-oriented agricultural practices from the potentially deleterious effects of markets. I also investigate the so-called 'agrarian question' about the effects of market expansion on the viability of peasant agriculture, finding that although new forms of market provisioning are likely exacerbating rural inequality, the income from market activities actually enables rural Guatemalans to reproduce the conditions for peasant agriculture. Ultimately, I observe that the conservation of agricultural biodiversity and, consequently, global food security are contingent upon the 'food sovereignty' of peasant farmers.
Geography
Keywords: Guatemala; agricultural biodiversity; agrobiodiversity; food crops; food industry; food sovereignty; food supply; globalization - social aspects; peasant differentiation; peasant livelihoods; peasant studies; peasants; right to food

‘Habitation vs. Improvement’ and a Polanyian Perspective on Bank Bail-outs - Watson, Matthew (Politics, 2009)
The bank bail-outs enacted by the Brown government in the wake of the 2007 credit crunch have had a distinctive political character. Despite the government's pronouncements on the merits of swift and decisive interventions, I argue that this does not amount to a return to the interventionist regulatory form associated with post-war British welfare capitalism. The Polanyian distinction between ‘habitation’ and ‘improvement’ is used to show that the bail-outs were designed by contrast to defend the underlying deregulatory logic of the existing financial regime. The only real change of note was to uncover forcibly the often hidden influence of the state in the making and regulation of an ostensibly market-led neoliberalism and the creation instead of a much more overt state-led neoliberalism. Habitation strategies were incorporated into a structure of financial deregulation, making it more rather than less difficult to rejuvenate state capacities consistent with enhancing societal welfare. The bank bail-outs offered short-term salvation for distressed firms within the financial sector without providing the state with socialised control over the conduct of banking business in order to promote forms of social policy consistent with post-war British welfare capitalism.
Political Science
Keywords: BROWN; Gordon; 1951-; Great Britain; Great Britain - politics & government - 2007-; bailouts (finance); banking industry; habitation

Industrial Relations Today: Reining in Flexibility - Streeck, Wolfgang (Economics, Management & Financial Markets, 2009)
The paper was presented as a keynote lecture at the 10th anniversary of the Amsterdam Institute for Advanced Labour Studies (AIAS) in April 2008. It surveys the trajectory of scholarly work on labor after 1945, from its initial emphasis on rights of industrial and social citizenship to its present preoccupation with "flexibility" and "flexicurity." It recalls the dissolution of the "Fordist" compromise in the 1970s and the subsequent gradual expansion of markets as the dominant mechanism for the allocation of life chances and the governance of society. Marketization encountered surprisingly little resistance, in real life as in the evolving conceptual apparatus of scholarly work. Liberalization proceeded and continues to proceed regardless of the social dislocations it causes, on a scale wholly unimaginable and indeed unacceptable under the postwar settlement. The paper ends with speculation on what if at all might be the forces today that could trigger a Polanyian counter-movement to the progress of capitalist social and economic relations. In particular it discusses whether demographic change, in terms of both a declining birth rate and increasing life expectancy, might bring about a new wave of market-containing social policy.
Sociology; Industrial Relations
Keywords: corporate growth; countermovement; industrial relations; international economic relations; labor laws & legislation; labour laws & legislation; socioeconomics; welfare economics

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Economics; Anthropology
Keywords: Athenian supremacy; Greece; 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Relaxing the shackles: The invisible pendulum - Stewart, Frances (Journal of International Development, 2009)
This note draws on Polanyi's pendulum in economic policies presented in the the Great Transformation—with swings back and forth between strong restrictions on the market and market domination, each resulting from excesses of the dominant model. The swing he described, when he wrote, was a reaction to the consequences of market domination, notably the Great Depression, and ushered in Keynesianism and the welfare state. In the late twentieth century, there was a swing back towards the market as a result of the inefficiencies associated with this interventionism. This note argues that the pendulum is swinging again, following the political and economic consequences of this market domination. Again market forces are being restrained by regulation, state takeovers, social protection and Keynesian macro-policies, while environmental factors have added to pressures for interventionist policies. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies; Economics
Keywords: Polanyi; interventionism; markets; pendulum

Headlong into the Polanyian Dilemma: The Impact of Middle-Class Moral Panic on the British Government's Response to the Sub-prime Crisis - Watson, Matthew (The British Journal of Politics & International Relations, 2009)
This article focuses on the discursive construction in Britain of a middle-class moral panic occasioned by the distress caused to self-styled ‘responsible mortgage borrowers’ by falling house prices. In the context of the move towards asset-based welfare the sub-prime crisis manifested itself most obviously in the popular consciousness as a threat to housing market wealth. The Labour government used the political space opened up by the narrative of middle-class moral panic in order to protect banks' balance sheets from the consequences of their own failed investments in mortgage-backed securities. The ensuing arrangements immunised banks from the implications of market self-regulation in the first-phase response to the sub-prime crisis while simultaneously allowing them to continue to impose the experience of market self-regulation on their customers. An increasingly asymmetric approach to banking regulation has arisen analogous to that which Karl Polanyi associated with the contradictory co-existence of market and non-market forms.
Political Science; International Relations
Keywords: market self-regulation; moral panic; protective re-embedding of finance; sub-prime crisis

Sociopolitical sustainability – the pendulum at globalisation's frontiers - Boutilier, Robert (Keeping Good Companies (14447614), 2009)
The article explores the potential roots of the unsustainability of the intersectoral dynamic. Political economist Karl Polanyi stresses that excesses of globalisation led to the unsustainability among the private, public and civic sectors. The backlash against globalisation and the private sector has its roots in the imbalance among the three sectors. The impact of the absence of regulatory regimes on globalisation's frontiers on the private sector is discussed, as well the process by which companies help stabilise their partners.
Development Studies
Keywords: economic sectors; globalization; international relations; private sector; sustainability

Drivers of development over the next 30 years: Some speculations - Harriss, John (Journal of International Development, 2009)
Class relationships are amongst the fundamental drivers of development, and it is argued here that over the next 30 years a major influence on the pattern and path of development will be exerted by the rise of the ‘new middle classes’ of Asia. At the same time, in the context of the blocked transition of the present, it seems unlikely that those who are marginalised and excluded will be able adequately to organise resistance, much less change structures of power, but poverty will be managed through welfare interventions like India's National Rural Employment Guarantee Scheme. Copyright © 2009 John Wiley & Sons, Ltd.
Political Science; Development Studies
Keywords: Asia; India; double movement; eastern hemisphere; economic development; middle class; new middle class; social change; social classes; social structure

Development's invisible hands: Introduction to special issue - Thomas, Alan; Sumner, Andy; Tribe, Michael (Journal of International Development, 2009)
This Special Issue comes from the Development Studies Association (DSA) 30th Anniversary conference in 2008. The theme was ‘Development's Invisible Hands’, focusing on the forces likely to influence global change and re-shape development agendas over the next 30 years. The first section comprises brief invited thinkpieces mainly from DSA past presidents. Interestingly, while some focus on Adam Smith's original ‘invisible hand’ analogy and others discuss a range of non-market issues, several invoke Karl Polanyi on the limitations of market society. The second and third sections consist, respectively, of ‘synthesis’ papers on parallel panel themes and papers developed from the best panel presentations. The papers demonstrate the range of issues raised by questioning the future of development and development studies—while the limitations of future gazing are pointed up by the unexpected challenge to current development models presented since the conference by the global financial crisis. Copyright © 2009 John Wiley & Sons, Ltd.
Development Studies
Keywords: Development Studies Association; POLANYI; Karl; 1886-1964; SMITH; Adam; 1723-1790 - political & social views; development economics; development studies; economic development; futures; invisible hand; mathematical models of economics

Polanyi in the United States: Peter Drucker, Karl Polanyi, and the Midcentury Critique of Economic Society - Immerwahr, Daniel (Journal of the History of Ideas, 2009)
Abstract:This essay explores the connections between Karl Polanyi's The Great Transformation (1944) and midcentury social theory in the United States. It argues that Polanyi shared with his U.S. colleagues a critique of market society. In particular, Polanyi's work bears close resemblance to the early thought of management theorist Peter Drucker, with whom Polanyi lived while writing his celebrated book. By comparing Polanyi to his contemporaries who advanced similar ideas, one gains a clearer sense of the particularities of Polanyi's project and of the fairly widespread movement in the United States to reject economistic thinking.
History
Keywords: DRUCKER; Peter; history; social theory

The unknown Karl Polanyi - Cangiani, Michele (International Review of Sociology, 2009)
History; Sociology
Keywords: biography; essence of fascism

Subaltern strategies and autonomous community building: a critical analysis of the network organization of sustainable agriculture initiatives in Andhra Pradesh - Kumbamu, Ashok (Community Development Journal, 2009)
This paper examines and analyses the organization and functioning of subaltern peasant sanghams (grassroot associations of the poor) and their place-based as well as network-based strategies in building autonomous local communities that challenge the consequences of neoliberal globalization in general and the commodification of agriculture and food in particular. The major objective of the counter-hegemonic organizational strategies is to build self-protective and subsistence communities, to mend the metabolic rift between nature and society, and to re-reconstruct social fabric within communities. The question remains is whether place-based autonomous communities can sustain in an increasingly globalizing world. To better understand these political dynamics, I use Karl Polanyi's concept of ‘double movement’ and examine the making of a double movement in Indian agriculture and its socio-political and ecological implications for the Indian peasantry. I use the organizational strategies and activities of the Deccan Development Society, a prominent non-governmental organization that has been working in Medak district for more than two decades, as an illustrative case study.
Sociology
Keywords: community development; community organizing; double movement; metabolic rift; peasant studies

Institutionalization of Trust as Response to Globalization: The Case of Consumer Cooperatives in South Korea - Choi, Hyejin (Transition Studies Review, 2009)
This paper explores an explanation which elaborates how individuals effectively enact and sustain trust in the sphere of social economy and the capability. I discuss how value employed by actors and the strategies and power relation in the socio-economic value sphere and focus on the function of ‘trust’ as the key mechanism of the interaction. This paper examine South Korean consumer cooperative Hansalim as a case of social economy which successfully institutionalize their system in competitive economic market arena.
Political Science
Keywords: disembeddedness; double movement; embeddedness; food trust; governance; public administration; risk socety; social economy

Exchange networks and free shops in Berlin: gifts and commodities in ‘alternative’ consumption experiences - Sabaté Muriel, Irene (Etnográfica. Revista do Centro em Rede de Investigação em Antropologia, 2009)
This paper is based on an ethnography of ‘alternative’ consumption practices in the inner city of the former East Berlin. Non-monetary exchange networks (Tauschringe) and ‘free shops’ (Umsonstläden) have been examined. In Umsonstläden, the contemporary ideology of the ‘pure’ gift (Parry 1986; Carrier 1995) is at play: objects are freely given and totally alienated from their owners. In turn, Tauschringe sometimes induce gift-giving practices entailing mutual obligation, as a result of frequent exchanges which bring participants socially closer. The ethnographic material I present challenges the suitability of a conceptual gift / commodity divide to examine these experiences, provided that different modalities of gift-giving are articulated with commoditisation trends. Considering this complexity, I propose a re-examination of the role of the gift in ‘alternative’ consumption practices promoted by social movements in Berlin., O artigo baseia-se numa etnografia de práticas de consumo “alternativas” nos bairros centrais da antiga Berlim-Leste. São aqui analisadas as redes de intercâmbio não monetário (Tauschringe) e as “lojas gratuitas” (Umsonstläden). As Umsonstläden são enquadradas pela ideologia contemporânea da dádiva “pura” (Parry 1986; Carrier 1995): os objectos são dados gratuitamente e totalmente alienados dos seus possuidores. Já as Tauschringe, por seu lado, induzem por vezes práticas de oferta que implicam obrigações mútuas, como consequência de trocas frequentes que aproximam socialmente os participantes. O material etnográfico apresentado põe em causa a adequação do binómio dádiva / mercadoria à análise dessas experiências, na medida em que diferentes modalidades de oferta se conjugam com tendências para a mercadorização. Face a essa complexidade, o artigo propõe uma revisão da análise do papel da dádiva em práticas de consumo “alternativas” promovidas pelos movimentos sociais em Berlim.
Anthropology
Keywords: Berlin; consumption; economic anthropology; embeddedness; exchange networks; fallacy of the market; free shops; gifts/commodities; social economy; social movements

Globalization and Backlash: Polanyi's Revenge? - Burgoon, Brian (Review of International Political Economy, 2009)
This paper investigates political-economic backlash to economic globalization in industrialized polities. It analyzes data on the content of party platforms to develop measures of party support for, or opposition to, political-economic closure, anti-democratic nationalism, and xenophobia in all party platforms of 23 Organization for Economic Cooperation and Development countries for all national elections between 1960 and 2003. These allow broader judgments of trends in autarky and autarchy than focusing on electoral success of particular extreme-right parties. Based on these measures, the paper quantitatively analyzes how international trade and capital openness and flows, and immigration flows, all influence the embrace or rejection of political-economic backlash among parties. The main explanatory finding is that immigration and capital flows and openness tend to increase marginally such backlash when national welfare compensation is very modest, but to reduce it when national compensation is generous, cushioning citizens from globalization's economic risks. This finding provides evidence that the current wave of globalization only marginally resembles the dark politics ending its nineteenth-century predecessor, and that welfare protection may help make the difference between political-economic backlash and liberalism in contemporary globalization.
Political Science
Keywords: elections; international business; international economic order; international factor movements; legislatures; lobbying; political processes; rent-seeking; voting

Paper assets, real debts: An ecological‐economic exploration of the global economic crisis - Kallis, Giorgos; Martinez‐Alier, Joan; Norgaard, Richard B. (Critical perspectives on international business, 2009)
Purpose – This paper sets out to investigate the potential contribution of the inter‐disciplinary field of ecological economics to the explanation of the current economic crisis. The root of the crisis is the growing disjuncture between the real economy of production and the paper economy of finance. Design/methodology/approach – The authors trace the epistemological origins of this disjuncture to the myths of economism – a mix of academic, popular and political beliefs that served to explain, rationalise and perpetuate the current economic system. Findings – The authors recommend ending with economism and developing new collective and discursive processes for understanding and engaging with ecological‐economic systems. Originality/value – The authors embrace the notion of sustainable de‐growth: an equitable and democratic transition to a smaller economy with less production and consumption.
Economics; Business
Keywords: commodification; commodification of nature

An Introduction to Destructive Coordination - Vahabi, Mehrdad (American Journal of Economics and Sociology, 2009)
Polanyi (1944, [1957]1968) has distinguished three “patterns of social integration,” namely, “reciprocity,”“redistribution,” and “exchange.” This triad has provided the starting point for most subsequent discussion. Our purpose is to introduce a further type of coordination, the “destructive mode of coordination.” This mode achieves coordination by intimidation, threat, and the use of non-institutionalized coercive means. Resources and human efforts are allocated in order to appropriate what other people produce. Two simple examples provide an introductory illustration: traffic circles (roundabouts) and prisons. Appropriation through pirating provides a further example of destructive coordination. More specifically, biopiracy (blood patenting) is discussed in order to clarify the relationship between destructive coordination and the institutionalization of property rights. Finally, we focus on the role of destructive coordination as a transitional mechanism that is supported by the institutional vacuum, ultimately yielding to other modes of coordination.
Economics; Sociology
Keywords: appropriation; destructive mode of coordination; social integration

Karl Polanyi in Budapest: On his Political and Intellectual Formation - Dale, Gareth (European Journal of Sociology / Archives Européennes de Sociologie, 2009)
AbstractA major thinker and inspiring teacher, Karl Polanyi's contributions have long been influential in a variety of disciplines, notably economic sociology and economic history. Two of his innovations, substantivist economic anthropology and the “double movement thesis,” are recognized as seminal. All of the works for which he is known, however, were written late in life, when in exile, and very little is known of his Hungarian writings, virtually none of which had, until now, been translated. Despite his fame, the biographical literature on Polanyi remains modest: some studies provide invaluable insights, yet all are brief. This article attempts to make some headway in remedying these lacunae. It sketches the contours of that extraordinary historical-geographical conjuncture in which he was formed, and explores his intellectual and political engagements in the Galilei Circle and the Radical Bourgeois Party. It seeks in particular to elucidate the complex roles played by questions of nation, ethnicity and class in the life of the young Karl Polanyi.
Political Science; Sociology
Keywords: Hungary; Jewish assimilation; biography; liberal radicalism

The Social Economics of Neoliberal Globalization - Stanfield, James Ronald; Carroll, Michael C. (Forum for Social Economics, 2009)
The recent period of intensive and extensive development of global economic integration, or globalization, has reached a crossroads. The regime of the neoliberal Great Capitalist Restoration is not sustainable and fundamental governance changes must be made. This paper adds perspective to the choices that must be made at this critical juncture of the global social economy by applying the master concepts of Schumpeter's Creative Destruction and Polanyi's Protective Response.
Economics
Keywords: capitalist systems: political economy; global social economy; international economic order; protective response; social economy

Economics, Anthropological Models and the Ancient Near East - Warburton, David A. (Anthropology of the Middle East, 2009)
This article discusses the evidence of markets in the Ancient Near East. The major points are (1) the shortcomings of the misguided application of the Polanyi model and (2) the ensuing implications of the failure to integrate economic history into modern economic theory. The analysis concentrates on Ancient Egypt, as it presents the most significant problem for economic history and theoretical modelling. Detailed criticism of the means by which the Polanyi model is upheld is coordinated with an argument in favour of recognising the importance of markets. The argument is that these markets are relevant both to long-term economic history and to modern economic theory – and that this must lead to a new debate about ancient and modern economies.
Anthropology
Keywords: Egypt; Middle East; ancient civilization; anthropology; economic history; economic theory; economics; markets; neo-classical synthesis; technology

Precarious Work, Insecure Workers: Employment Relations in Transition - Kalleberg, Arne L. (American Sociological Review, 2009)
The growth of precarious work since the 1970s has emerged as a core contemporary concern within politics, in the media, and among researchers. Uncertain and unpredictable work contrasts with the relative security that characterized the three decades following World War II. Precarious work constitutes a global challenge that has a wide range of consequences cutting across many areas of concern to sociologists. Hence, it is increasingly important to understand the new workplace arrangements that generate precarious work and worker insecurity. A focus on employment relations forms the foundation of theories of the institutions and structures that generate precarious work and the cultural and individual factors that influence people's responses to uncertainty. Sociologists are well-positioned to explain, offer insight, and provide input into public policy about such changes and the state of contemporary employment relations.
Sociology
Keywords: precarious work; precarity

Embeddedness of Social and Economic Relations in Systemic Transformation. Long-Term Evidence From the Post-Communist Transition in Poland, 1988-2003 - Wilk, Katarzyna (Polish Sociological Review, 2009)
This paper intervenes in the Granovetter-Polanyi debate by reassessing the level of embeddedness of social and economic relations under conditions of systemic transition. Using panel data collected in Poland, this analysis examines this relationship for three distinct periods of transition: initial (1988-1993), advanced (1993-1998), and post-transitional (1998-2003). This paper shows that during transition from communism to capitalism economic relations tended to disembed from social relations, but this relationship remained significant; friendship ties were conductive to an individual upward mobility, economic well-being and entrepreneurial activity. In contrast to Polanyi's argument, however, entrepreneurship—the most marketable area of individual advancement—is found to exhibit the highest degree of social-economic embeddedness. These results do not directly support either Polanyi's or Granovetter's arguments, however they do accord with a neo-Polanyian argument, as advanced in this paper.
Sociology
Keywords: (dis)embeddedness; Poland; capitalism; disembeddedness; embeddedness; entrepreneurship; friendship ties; political doctrines; practical politics; social classes; social networks; social status; socioeconomics; status attainment

Towards a Green Republicanism: Constitutionalism, Political Economy, and the Green State - Barry, John (The Good Society, 2009)
In lieu of an abstract, here is a brief excerpt of the content: Towards a Green Republicanism: Constitutionalism, Political Economy, and the Green State John Barry (bio) The republic is threatened—who will stand by the republic? Introduction The range of threats to modern society ranging from growing environmental stresses (water shortages, deforestation, soil erosion to climate change), food and energy insecurity, peak oil, rising poverty and inequalities within and between societies, increasing passivity of citizens within democracies and the inexorable rise of corporate power within and over the democratic state can be summed up as facets of 'unsustainability' or 'unsustainable development.' Just as it is commonplace to declare that the 21st century will be China's century, equally the politics of the 21st century are and will be the politics of sustain-ability. Taking it as given that the transition to sustainability will be the dominant challenge and opportunity facing all societies in the coming decades ahead, this article looks at two traditions of political thought—namely green political theory and civic republicanism—and seeks to conjoin them to outline a new political approach—'green republicanism'—which may respond and rise to this challenge. It needs to be pointed out from the outset that what is discussed below is 'green politics' and not 'environmentalism,' which is narrowly concerned with environmental preservation, species conservation or combating climate change. In broad terms green politics aims at 'sustainable development' which, inter alia, deals with securing basic human rights, lowering socio-economic inequalities, eradicating environmental injustices (within nation-states and globally as well as intergenerationally) and ensuring the demands of the human economy do not outstrip the regenerative capacities of the eco-systems upon which that economy depends. Sustainable development therefore is a radical proposal, indicating not simply the 'ecologising' or 'greening' of the current political and economic order. Such reformist proposals may be viewed as interim staging posts such as those represented by 'ecological modernisation' and discourses of 'natural capitalism,' but suggest the transformation to a different distinctly 'green' or 'sustainable' political order.1 While the metabolism between the human economy and its ecological systems is the most pressing and significant [End Page 3] dimension of sustainable development, questions of political economy and the economic order are always already present in any green analysis (whether explicit or not). In the same way that I take it as given that a sustainable society is one that is a post-carbon society (in terms of energy production and consumption), the green republican perspective offered here is also one which sees such a society as post-liberal, though not anti-liberal. Green politics can be viewed as 'post' not 'anti-liberal' in Robyn Eckersley's terms, and this can be seen to settle around the centrality of separating free market capitalism as the dominant organization of the economy, from liberalism (representative democratic governance, citizen freedoms, equality of citizens, etc.) in the creation of a sustainable society.2 In short, a green republicanism is one which asks the question 'How do we maintain and sustain liberty in a post-liberal political, post-capitalist economic and post-carbon, sustainable order?' In that context it is important to look at what are the political and institutional dynamics within, between and below the nation-state of this transformation away from current unsustainable development paths. If we are to live in a sustainable/green political order different than the current liberal democratic one based on the capitalist free market, what are the types of legal, constitutional and institutional innovations we might expect to see in a greening state or in a fully fledged 'green state?' Thus, while this article is critical of reformist ecological modernisation and strategies that focus on securing (often through technological innovation) the ecological conditions for the political economy of expansionist fossil-fuelled capitalism, it is also critical of radical green proposals (mostly anarchistic in character) which argue for the eradication or transcendence of the nation-state as a necessary condition of achieving sustainable development. Thus, the position outlined here is firmly within that school of green political thought which is concerned about the evolution and emergence of green states and pragmatic/strategic considerations about the 'greening' of existing liberal democratic states. Green Constitutionalism Given that constitutional provisions...
Political Science
Keywords: embeddedness; green republicanism; political economy

Informal Politics, Formalised Law and the ‘Social Deficit’ of European Integration: Reflections after the Judgments of the ECJ in Viking and Laval - Joerges, Christian; Rödl, Florian (European Law Journal, 2009)
The judgments of the European Court of Justice (ECJ) of December 2008 in Viking and Laval on the compatibility of national collective labour law with European prerogatives have caused quite a heated critical debate. This article seeks to put this debate in constitutional perspectives. In its first part, it reconstructs in legal categories what Fritz W. Scharpf has characterised as a decoupling of economic integration from the various welfare traditions of the Member States. European constitutionalism, it is submitted, is bound to respond to this problématique. The second part develops a perspective within which such a response can be found. That perspective is a supranational European conflict of laws which seeks to realise what the draft Constitutional Treaty had called the ‘motto of the union’: unitas in pluralitate. Within that framework, the third part analyses two seemingly contradictory trends, namely, first, albeit very briefly, the turn to ‘soft’ modes of governance in the realm of social policy and then, in much greater detail, the ECJ's ‘hard’ interpretations of the supremacy of European freedoms and its strict interpretation of pertinent secondary legislation. The conflict-of-laws approach would suggest a greater respect for national autonomy, in particular, in view of the limited EU competences in the field of labour law.
Law
Keywords: BLOCK; Fred; European Union; European constitutionalism; economic law; labour law; social embeddedness

Who is right about the modern economy: Polanyi, Zelizer, or both? - Steiner, Philippe (Theory and Society, 2009)
Zelizer’s work may be read as an attack on the central Polanyian thesis: that the market system threatens social life by the undue prominence it lends the economy in the organization of modern society. The recent publication of Viviana Zelizer’s The Purchase of Intimacy (2005a) is therefore an excellent opportunity to review the general trend of her work Zelizer 1979, 1985, 1994, and contrast her leading ideas to the central thesis that gives Polanyi’s work its particular flavor: the danger encapsulated in the use of modern money and the functioning of the market system.
Sociology
Keywords: ZELIZER; Viviana; market system; money

Beyond Social Democracy? - Gare, Arran (International Journal of Inclusive Democracy, 2009)
Towards an Inclusive Democracy, it is argued, offers a powerful new interpretation of the history and destructive dynamics of the market and provides an inspiring new vision of the future in place of both neo-liberalism and existing forms of socialism. It is shown how this work synthesizes and develops Karl Polanyi's characterization of the relationship between society and the market and Cornelius Castoriadis' philosophy of autonomy. A central component of Fotopoulos' argument is that social democracy can provide no answer to neo-liberalism, so the only viable alternative to neo-liberalism is the form of inclusive democracy he elaborates. Reviewing Castoriadis' concept of autonomy, it is argued that while Fotopoulos is certainly correct given the present deformed nature of social democracy, there is no reason to exclude social democracy as such from what Fotopoulos calls the tradition of autonomy. It is suggested that if the working class movement could free itself from the capitalist imaginary and return to its quest for autonomy, a synthesis of a radically reformed social democracy and inclusive democracy could greatly improve the prospects of each to successfully challenge not only neo-liberalism, but also the emerging liberal fascism of USA, Britain and Australia.
Philosophy
Keywords: CASTORIADIS; Cornelius; 1922-1997; democracy; fascism; neoliberalism; political doctrines; political science - study & teaching; review; social democracy; social movements; socialism

Keynes’s Stimulus, Polanyi’s Movement - Milberg, William S. (Harvard College Economic Review, 2009)
The foundations of Keynes and the principles of Polanyi offer insight into crafting a new American economy
Economics
Keywords: KEYNES; John Maynard; 1883-1946; economics

Second thoughts: on economics, sociology, neoliberalism, Polanyi's double movement and intellectual vacuums - Piore, Michael J. (Socio-Economic Review;2009, Vol. 7 Issue 1, p161, 2009)
The article presents a presidential address by Michael J. Piore, delivered at the Society for the Advancement of Socio-Economics (SASE) Annual Meeting 2008 in San JosÃ©, Costa Rica, in which he discussed the relationship between sociology and economics, and the role that this relationship plays at the current political juncture in the transition from neoliberalism to the formation of public policy.
Sociology; Economics
Keywords: double movement; economic sociology; neoliberalism

Human Rights and Business Practices: Double Movement or Neoliberal Hegemony? - Thomas, Mark (Conference Papers – American Sociological Association, 2009)
Throughout the 1990s and into the early years of the 21st century, campaigns by labor rights activists brought the issue of labor exploitation by Northern transnationals (TNCs) operating in the Global South into the centre of public debate. Labor rights scholars raised the possibility of a broader Polanyian 'double movement' in the global economy, as the polarizing effects of neoliberal globalization produced anti-globalization movements and shifts towards forms of social protection through emerging approaches to transnational labor rights regulation. One of the results of these processes was the adoption of a human rights discourse by TNCs as they sought to re-define their public image in response to growing public awareness and condemnation of sweatshop labor practices. Read through a Polanyian lens, these developments would seem to confirm that a double movement was in fact producing a more socially responsible capitalism where the 'satanic mill' of the sweatshop would be moderated through corporations proclaiming respect for human rights. In this paper, I examine the adoption of human rights principles by corporate actors as both normative framework and business practice. I argue that rather than a double movement from market liberalism to social protection, the dynamics present in this process indicate tendencies towards the construction of a new hegemonic discourse to support neoliberal globalization - that of the 'socially responsible' corporation where business practices and human rights principles intersect. ..PAT.-Unpublished Manuscript
Sociology
Keywords: employee rights; hegemony; human rights; neoliberalism; satanic mill; transnationalism

Endogenous Institutions and the Politics of Property: Comparing and Contrasting Douglass North and Karl Polanyi in the Case of Finance - Davis, Ann E. (Journal of Economic Issues, 2008)
The purpose of this paper is to contrast the work of Douglass North and Karl Polanyi regarding financial institutions associated in market economies. Both implicitly acknowledge the synergy between public and private financial markets, which can serve to solidify an alliance between wealth holders and the state, potentially at the expense of “sociery” at large. This alliance may stimulate growth, according to North, as well as impose the strain of the market, according to Polanyi. Taken together, these insights undercut the classical story of the neutral role of money, as well as the notion of a clear distinction between public and private, politics and markets.
Economics
Keywords: NORTH; Douglass; economic history; finance; property

Affect and the Rise of the Self-Regulating Market - Gammon, Earl (Millennium: Journal of International Studies, 2008)
This article outlines a post-rationalist approach to international political economy that factors in the role of affect in social causation. There are key historical junctures where social transformations cannot be neatly explained by instrumental logics, such as the profit motive or the pursuit of increasing productive efficiency. Affect, in the form of anxiety and aggression, overdetermines social behaviour in ways that belie conventional notions of rationality, premised on a clear ordering of needs or preferences by social actors. This analysis specifically reassesses the role of affect in the rise of market civilisation in Britain in the early part of the nineteenth century. It critiques Karl Polanyi's account, which privileges technology and pecuniary greed as the expedients of the institution of the self-regulating market. As an alternative, this article explains the rise of the self-regulating market as a retributive mechanism, whereby the market became conceived as a means of punishing and disciplining social behaviour in the early Victorian period. The market, I argue, was an aggressive response to anxiety that plagued Victorian society regarding social order, an anxiety precipitated by the waning belief in a natural moral economy guided by the hand of Providence.
Political Science; International Relations
Keywords: Great Britain; affect; critique; international political economy; post-rationalist IPE; self-regulating market; social causation

The Karl Polanyi Institute of Political Economy : A Narrative of Contributions to Social Change - Gomez, Ana (Revue Interventions économiques. Papers in Political Economy, 2008)
Introduction: In February of 1941 Karl Polanyi wrote to his daughter Kari about his intention to submit to the publisher the first three chapters of the book The Great Transformation. The Origins of the Cataclysm. About the book, he wrote “[I]t will be a very straight-forward, simple story, easy to read and mainly historical in character”. A week later he added a post-script. Referring to the Notes in the manuscript, he wrote, “[T]he book is seemingly so simple and unsophisticated that unless d...
N/A
Keywords: Karl Polanyi; double mouvement; double movement; encadrement; marchandise fictive; école substantiviste

Anthropology in the financial crisis - Hart, Keith; Ortiz, Horacio (Anthropology Today, 2008)
This editorial considers the opportunities opened up for anthropologists by the financial crisis of 2008. The chief of these is the exposure of cracks in the intellectual hegemony of free-market economics which contributed to an unnecessarily defensive posture on the part of most anthropologists during the period of neoliberal globalization. The authors claim that anthropology can bridge the gap between everyday life and the world at large by combining the study of ideas and social actions. We draw on Ortiz's research among financial professionals to show how working practices informed by economic liberalism can have extremely unequal consequences for the global distribution of resources. The perspectives of Mauss and Polanyi on political economy can help us to make sense of the current situation and to recommend a path forward beyond market fundamentalism. Their general ideas lend power to the concrete findings of field research. The mask of neoliberal ideology has been ripped from the politics of world economy. Anthropology's highest mission is to start from where people are and go with them wherever they take you. What better time to follow this imperative than when the model the world has been compelled to live by for three decades is in such disarray?
Anthropology
Keywords: finance; financial crisis

Law as the Interplay of Ideas, Institutions, and Interests: Using Polyani (and Foucault) to ask TWAIL Questions - Fakhri, Michael (International Community Law Review, 2008)
This paper sketches out some preliminary thoughts on political economy that stem from problematics that emerge from TWAIL. The TWAIL story of international law is one of frustration and disappointment because of the constant exploitation of the Third World despite all the historic changes in international legal ideas and institutions, but it also a story of hope in the moments of resistance. In order to better debate how particular international institutions should be changed or whether particular international institutions should be renounced, I suggest that we need to explicate the theories of political economy embedded within these institutions. Drawing from Karl Polanyi's The Great Transformation, bringing alongside the work of Michel Foucault, I sketch out one way of conducting a study of international political economy by suggesting that we can think of law as the interplay of ideas, institutions, and interests.
Law
Keywords: FOUCAULT; Michel; 1926-1984; TWAIL; economics; globalization; international agencies; international cooperation; international institutions; international law; international political economy; law

Karl Polanyi's The Great Transformation: perverse effects, protectionism and Gemeinschaft - Dale, Gareth (Economy and Society, 2008)
Drawing upon Karl Polanyi's journalistic writings and unpublished lectures from the 1920s and 1930s, this article reconstructs the lineaments of his research programme that was to assume its finished form in The Great Transformation. It identifies and corrects a common misinterpretation of the thesis of that book, and argues that Polanyi's basic theoretical framework is best conceived as Tönniesian: market society is Gesellschaft, while the ‘protective counter-movement’ of The Great Transformation is Gemeinschaft, understood dynamically. It examines the two central mechanisms by which, in Polanyi's understanding, Gesellschaft broke down in the mid-twentieth century: the ‘clash between democracy and capitalism’ and the ‘perverse effects’ whereby political intervention in markets impairs profitability and saps the vitality of the market system.
Political Science
Keywords: Ferdinand Tönnies; TONNIES; Ferdinand; 1855-1936; The Great Depression; capitalism; democracy; perverse effects doctrine

Karl Polanyi's Legacy - Hart, Keith (Development and Change, 2008)
Click on the article title to read more.
Anthropology; Development Studies
Keywords: biography

A New Alliance of De-legalisation and Legal Formalism? Reflections on Responses to the Social Deficit of the European Integration Project⋆ - Joerges, Christian (Law and Critique, 2008)
This paper will cover a wide range of issues. It will start with a reconstruction of the European Community’s ‘social deficit’, arguing that a credible response to this deficit would be a pre-condition for the democratic legitimacy of the deepened integration project. Such a response can be developed in a re-conceptualisation of European law as a new type of supranational/trans-statal conflict of laws – this is the thesis defended in the second section. This vision is contrasted in the third section, first with the steps towards Social Europe envisaged in the Draft Constitutional Treaty, and then with the messages of the recent judgments of the European Court of Justice (ECJ) in Viking and Laval. It goes without saying that the theoretical premises of the argument, let alone its many interdisciplinary dimensions and empirical background, can often only be signalled, but not developed systematically. " I wish to submit is that the ‘social embeddedness’ thesis can help us to understand why Europe has developed an ever more sophisticated regulatory machinery entrusted with the management of the internal market – and why the social deficit of the European construction has become a prominent part of the European agenda.
Law
Keywords: Social Europe; conflict of laws; ordoliberalism; social deficit; social embeddedness; socio-economic division; unity/diversity

"A Market Where We All Fit" Adult Education and the Fair Trade Movement - Sumner, Jennifer (Canadian Journal for the Study of Adult Education, 2008)
The global market continues to create the "great and permanent evils" so well outlined by Karl Polanyi in his book, The Great Transformatioit His description of the destructive effects of the emerging self-regulating market during the Industrial Revolution is reflected today in the ongoing erosion of social, environmental, and economic sustainability in both the North and the South. In this downward spiral of life parameters, fair trade opens up the possibility of a market where we all fit, not where we all ultimately fail. Adult education has a vital role to play in opening up spaces where fair trade can prosper and grow, thus contributing to a second great transformation to a more sustainable society.
Education
Keywords: Great Transformation; The (Book); POLANYI; Karl; 1886-1964; adult education - economic aspects; international trade; self-regulation of industries; unfair competition

Standing Polanyi on His Head: The Basic Income Guarantee as a Response to the Commodification of Labor - Caputo, Richard K. (Race, Gender & Class, 2008)
This paper examines unconditional basic income schemes proposed by Philippe Van Parijs and by Ross Zucker in light of Karl Polanyi's analysis of the 1795 Speenhamland Law and of Esping-Andersen's use of decommodification as a signifier of social provisioning in welfare states. It discusses tradeoffs between productive advantages of market-based economies and dehumanizing disadvantages of commodified labor. Contemporary redistributive schemes such as those of Van Parijs and of Zucker extol the productive virtues of market economies well beyond what Polanyi, who advocated for subjecting markets to social purposes, would consider acceptable. Further, Van Parijs's and Zucker's basic income schemes extol capitalism, perhaps mistakenly, as a means of achieving a more egalitarian social order of which Polanyi would in all likelihood approve, if such economies functioned as portrayed and were properly implemented to de-commodify labor, that is at a level considered adequate and acceptable to the society in which one lives.
Policy Studies; Social Work
Keywords: Speenhamland Law; United States - economic policy - 2001-2009; basic income guarantee; capitalism; commodified labor; decommodification; economic conditions - United States - 2001-2009; income; labor; labour; market economies; market economy; policy studies; social welfare states

Michael and Karl Polanyi: Conflict and Convergence - Gulick, Walter (Political Science Reviewer, 2008)
The article focuses on social philosophers and brothers Michael and Karl Polanyi. Particular attention is given to Michael's political, economic, and social thoughts and how they compare to Karl's. The author wishes to illuminate Michael's social though through this comparative study. Topics include the brother's family background, Michael's early thought, and divergent paths.
Political Science
Keywords: POLANYI; Michael; 1891-1976; biography; comparative studies; social theory

The Great Transformation: The Double Movement in China - Shaoguang, Wang (boundary 2, 2008)
KM: Both the title and the subtitle of this essay are adopted from Karl Polanyi, who published his famous book The Great Transformation: The Political and Economic Origins of Our Time in 1944. More than six decades have passed since its publication, but, as Joseph E. Stiglitz states in the preface of the recent new reprint, “the issues and perspectives Polanyi raises have not lost their salience . . . it often seems as if Polanyi is speaking directly to present-day issues.” ... China is experiencing “a transformation unprecedented in thousands of years” (qiannian weiyou zhi da bianju). More than one hundred years ago, the Qing official Li Hongzhang used these words to describe the era he was living in. Two decades later, the May Fourth generation had a similar take on their time, too. However, in terms of the economic foundation and the speed, depth, and scope of the social structure’s transformation, no other era can be compared to the last two decades or so.
Political Science
Keywords: China; Great Transformation; The (Book); double movement

Is an Alternative Globalization Possible? - Evans, Peter (Politics & Society, 2008)
Building on Polanyi's concept of the “double-movement” through which society defends itself against domination by the self-regulating market, this article sets out some key organizational and ideological hurdles that the contemporary “movement of movements” must surmount to challenge the hegemony of neo-liberal globalization. After outlining neo-liberalism's failures, it makes an argument for the possibility of “counter-hegemonic globalization,” defined as a globally organized project of transformation aimed at replacing the dominant (hegemonic) global regime with one that maximizes democratic political control and makes the equitable development of human capabilities and environmental stewardship its priorities.
Sociology
Keywords: double movement; globalization; neoliberalism; social movements; transnational networks

Personal Retirement Accounts & the American Welfare State: A Study of Income Volatility and Socioeconomic Status as Correlates of PRA Support - Caputo, Richard K. (Journal of Poverty, 2008)
Based on a sample (n = 6,407) from the National Longitudinal Survey of Youth, 1979 cohort, this study found a sizable majority (69.1%) of support to replace a portion of Social Security with Private Retirement Accounts. Logistic regression analysis showed that SES was a robust predictor of PRA support, particularly for upper class vs. lower class respondents. Findings suggested that there may be less support for a major pillar of welfare state social provisioning, despite successful Congressional attempts to block related legislation to date, especially since the opinions of more affluent persons tend to have greater resonance with policymakers than those of lower income individuals.
Policy Studies; Social Work
Keywords: United States; employee fringe benefits; personal retirement accounts; policy studies; privatization; regression analysis; social security; socioeconomic status; socioeconomics; surveys; volatility (finance); welfare state

After the disaster - Hart, Keith (Anthropology Today, 2008)
Naomi Klein's The Shock Doctrine offers a weak analysis of ‘neoliberalism’ linked to a defeatist ideology. If we wish to move beyond the global economic crisis, we should borrow ideas from Mauss, Polanyi and Keynes; but the political level for an appropriate response is not obvious.
Anthropology
Keywords: KLEIN; Naomi; neoliberalism

Karl Polanyi for Historians: An Alternative Economic Narrative - Knowles, Rob; Owen, John R. (The European Legacy, 2008)
The purpose of this essay is to provide the historian with a generic understanding of the term economy by examining some aspects of the work of the Hungarian “economic historian” Karl Polanyi (1886–1964). It does not seek to explain Polanyi's economic ideas to economists nor does it seek to locate his ideas within the discourses of the academic discipline of economics; there is abundant academic literature which carries out those tasks. This essay is intended to help fill a void in the historical understanding, especially the modern historical understanding, of the term economy, and of how the characteristics associated with it are generally understood. Yet, in reality, it is the neoclassical paradigm of economics which is typically and uncritically taken to be the touchstone for understanding the economy. This circumstance is problematic, however, when referring to the economy of societies earlier than the late nineteenth century or of societies whose culture differs radically from that of the advanced capitalist “west.” Polanyi's insights may help historians avoid the risk of either distorting or anachronistically misunderstanding the economy of such societies.
History
Keywords: economic history; economic theory; history

Tall among the trees: Organizing against globalist forestry in rural British Columbia - Prudham, Scott (Journal of Rural Studies, 2008)
In January of 2001, the TimberWest Corporation permanently closed its Youbou sawmill facility near Duncan, British Columbia, Canada laying off 220 workers. On the surface, the Youbou mill closure reinforced a pervasive sense that workers and communities in the province are increasingly vulnerable to an ever more globally integrated and footloose forest industry. But a funny thing happened in Youbou; the workers fought back. While the mill was completely dismantled and scrapped, with no discernable response from the provincial government, workers from the Youbou sawmill banded together to form a new NGO called the Youbou TimberLess Society. Since its inception, the YTS has developed into one of the most unique and compelling voices for forest policy reform in BC. In so doing, the YTS also represents something of an anomaly in exhibiting many of the characteristics of so-called new social movements, and yet emerging from the industrial working class. This paper explores the ways in which the YTS has served as a powerful arena in which the subjectivities of sawmill workers and other community members have been transformed through organized resistance to global capital. At the same time, informed by the YTS, the paper draws on Polanyi's idea of the dual movement to examine scales and terms on which globalization and competing notions of autonomy are contested in moral economies of both work and nature. Copyright (c) 2008 Elsevier Ltd.
Geography
Keywords: Canada; activists; double movement; employees - Canada; forest policy; forest policy - Canada; forest products industry; forests and forestry; lumber industry - British Columbia; lumber industry - Canada; rural studies; social movements; social movements - Canada

Rationality as a Social Construction: What Does Individual Behavior Have To Say About Development in an Amazon Community? - Gramajo, Andrés Marroquín (Journal of Economic Issues (Association for Evolutionary Economics), 2008)
This article argues that two different manifestations of rational behavior can coexist and collide in a relatively homogeneous society. In the Ticuna community of Arara in the Colombian Amazon; on the one hand, the majority of villagers tend to reach relatively lower levels of material wealth, following Polanyi's idea of the pre-modern man (1968a; 1968b; 1968c), and also Sahlins' (1972) idea of the original affluent man. On the other hand, community leaders and schoolteachers tend to accumulate material wealth, following Polanyi's idea of modern-man (1968a; 1968b). These behavioral frameworks help explain the limited success of certain types of development programs in the Ticuna community.
Economics
Keywords: Amazon River Region; Colombia; Tucuna (South American people); behavioral economics; communication in economic development; economic development; economic policy; economics - moral & ethical aspects; pre-modern man; rationality; reason; saving and investment; statics & dynamics (social sciences); wealth

The market and the nation: Austrian (dis)agreements - Karner, Christian (Social Identities, 2008)
This article relates contemporary Austria's much-discussed and internally contested identity politics to transnational socio-economic transformations and their far-reaching local/national effects. A qualitative analysis of (wide-ranging contributions to) current debates on the environment, food production, climate change, social inequality and welfare, higher education, art, migration, and unemployment reveals a recurring pre-occupation with expanding/encroaching markets, their advocated limits, assumed costs or promises. The negotiation of national identities is shown to unfold in relation to three inter-related phenomena: first, widening commodification; second, what Karl Polanyi termed the 'double-movement' between 'dis-embedded' economics and political counter-assertions; third, competing ideological visions of the relationship between economic activity/market forces and social order, group boundaries, solidarities and hence exclusions/inclusions.
Sociology
Keywords: Austria; commodification; economic anthropology; globalization; identity politics; markets; migration; nationalism; political science; public contracts; qualitative research; social order; socioeconomics

Going Global: The Transnational Politics of the Dalit Movement - Smith, Peter (Globalizations, 2008)
This article analyses the involvement of the Dalits (formerly 'untouchables') in the World Social Forum (WSF) processes. The focus will be on one networked organization in particular, the National Campaign for Dalit Human Rights (NCDHR) as a key organization which served as a catalyst for linking the Dalit struggle against neoliberal globalization and casteism with the social forum process and the global justice movement. The article argues that the Dalit struggle, domestically and internationally, can best be understood from a Polanyian perspective, as a countermovement for social protection against neoliberal globalization. It examines the dialectic of globalization within an Indian context first in terms of the impact of neoliberal globalization upon the Dalit community and then the NCDHR's decision to go global, to the WSF. In taking their cause beyond India, a central focus of Dalit activity remains rooted in making the Indian state serve as a means of social protection for the Dalit peoples. Este artículo analiza la participación de los Dalits (previamente llamados "intocables") en los procesos del Foro Social Mundial (WSF, por sus siglas en inglés). El enfoque se concentrará particularmente en una organización en red, la Campaña Nacional por los Derechos Humanos de los Dalits (NCDHR, por sus siglas en inglés) como una organización clave que sirvió como catalizadora por haber enlazado la lucha de los Dalits contra la globalización neoliberal y el casteísmo, con el proceso del foro social y el movimiento de justicia global. El artículo plantea que la lucha de los Dalits, tanto doméstica como internacionalmente, puede entenderse mejor desde una perspectiva polanyana, como un contramovimiento para la protección social en contra de la globalización neoliberal. El mismo examina la dialéctica de la globalización dentro del contexto indio, primero en términos del impacto de la globalización neoliberal sobre la comunidad de los Dalits y luego, en términos de la decisión de la Campaña Nacional por los Derechos Humanos de los Dalits (NCDHR) de tomar una dirección global, hacia el Foro Social Mundial. Al llevar su causa más allá de la India, el tema central sobre la actividad de los Dalits permanece arraigado obligando al estado indio a servir como un medio de protección social para los Dalits.
Political Science
Keywords: Dalits; class politics; countermovement; globalization - social aspects; human rights; international relations

Weber, Polanyi, and Finley - Tompkins, Daniel P. (History and Theory, 2008)
KM: a review article on Nafissi's book.
History
Keywords: WEBER; Max; 1864-1920; biography; review

Beyond Ethnic Entrepreneurship: An Embedded Market Approach to Group Affiliation in American Enterprise - Valdez, Zulema (Race, Gender & Class, 2008)
The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership and the particular structural conditions of the economy and society combine to facilitate ethnic enterprise. Yet, this model remains largely descriptive and imprecise with respect to how and why class and ethnic resources and structural opportunity matter. Furthermore, this approach neglects to consider the likelihood that other non-ethnic social groupings distinct from ethnicity, such as those rooted in class, gender, or racial group affiliation, might also influence entrepreneurship. To address these concerns, this article introduces an "embedded market" (Block, 2003; Polanyi, 1944) approach that situates the role of group affiliation within the context of American capitalism. This approach begins with the premise that the role of group affiliation in economic action originates in and is maintained and reproduced by the social structure of the capitalist system in which it is embedded. Specifically, the embedded market approach reconsiders ethnic group membership, along with other politically-influenced social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief in the form of social capital to augment market uncertainty in the modern market economy. This article uses the case of Latina domésticas to demonstrate the compensatory role of group affiliation and its corollary social capital in facilitating ethnic and "non-ethnic" enterprise in American capitalism.
Sociology
Keywords: United States; business enterprises - United States; capitalism; class; doméstica; embedded market; entrepreneurship; ethnic entrepreneurship; ethnic groups; gender; race; social capital; social classes

Karl Polanyi and the antinomies of embeddedness - Gemici, Kurtuluş (Socio-Economic Review, 2008)
While Polanyi argues that all economies are embedded and enmeshed in social relations and institutions, he tends to see market economy as disembedded, which reveals a tension in his thought. The main motivation for this paper is to understand the origins of this tension. On the basis of a systematic formulation of Polanyi's work, it is argued that Polanyi employs embeddedness in a dual manner: (a) as a methodological principle akin to methodological holism, and (b) as a theoretical proposition on the changing place of economy in society. These two formulations of embeddedness contradict each other. After tracing out the origins of this contradiction, this paper concludes by considering the implications of this analysis for economic sociology. It is argued that embeddedness as a methodological principle is the only acceptable usage of the term. Yet, in this capacity, embeddedness falls short of economic sociology's goal of providing a theoretical alternative to neoclassical economics.
Sociology; Anthropology
Keywords: Austrian history of economic thought; cultural economics; economic anthropology; economic sociology; economic systems; embeddedness; evolutionary; historical; institutional; relation of economics to other disciplines

Nano-worlds as Schumpeterian emergence and Polanyian double-movements - Randles, Sally; Dewick, Paul; Loveridge, Denis; Schmidt, Jan C. (Technology Analysis & Strategic Management, 2008)
The overarching question raised in this special issue is whether societies can, do or indeed should steer new and emergent science and technological development and its management on to trajectories construed as more or less 'desirable'. It therefore sits at the interface of two arenas. These are governance: processes of shaping/steering emergent technologies and markets; and sustainability: normative agendas incorporating a range of potentially competing conjectures and internally inconsistent desires such as to facilitate rather than stifle innovation, to enable economic development, to anticipate or deploy strategies to cope with risk and uncertainty, and to encourage technological developments that benefit rather than harm humans, their quality of life and the natural environment. Despite the potential for apparent empirical inconsistencies and contradictions that manifest as outcomes of the negotiation of these aims, there is (pace Karl Polanyi) a normative entry point to all of the articles and the material they draw upon, which is the idea that markets and technologies should be the handmaiden of societies, not vice versa. It is now widely recognized that 'nanotechnology' is a diverse set of feasible procedures emerging from scientific possibilities to enable the production of artefacts at the nanoscale creating new products, processes and services. Attention has to be paid to the desirability of these artefacts, which involve social, economic, ecologic, political and ethical matters that surround their emergence. The purpose of this special issue is to set out the current and future prospects for the widespread use (or innovation) of technological convergence at the nanoscale to create nano-artefacts, and the needs for governance and regulation that will accompany these innovations.
Sociology; Science and Technology Studies
Keywords: POLANYI; Karl; 1886-1964; SCHUMPETER; Joseph Alois; 1883-1950; double movement; economic development; editorials; emergence; governance; nano-; nanotechnology; new product development; quality of life; sustainability; technological innovations

Karl Polanyi's and Karl William Kapp's Substantive Economics: Important Insights from the Kapp—Polanyi Correspondence - Berger, Sebastian (Review of Social Economy, 2008)
Based on the unpublished Kapp-Polanyi correspondence, the paper analyzes the relationship between the two economists, as well as the meaning and origin of substantive economics, i.e. one of the key concepts of institutional economics with distinctly European roots. The correspondence shows how both economists influenced each other in their similar understanding of the substantive economy, and reveals that these similarities and the mutual influence date back to the 'planning debate' of the 1920s and 1930s. The documents also evidence the importance of Carl Menger's definition of substantive economics in the posthumous and untranslated second edition of the Grundsätze der Volkswirtschaftslehre (Principles of Economics) (1923). As a result, Kapp's political economy, i.e. his social minima approach appears in new light. The latter actualizes the full potential of substantive economics for a modern political economy by integrating insights from Polanyi's substantive economics, Menger's differentiation of human needs according to their urgency, and Max Weber's substantive rationality.
Economics
Keywords: KAPP; Karl William; environmental management; social economy; substantive economics

Reciprocity, Exchange and Redistribution. An experimental investigation inspired by Karl Polanyi’s The Economy as Instituted Process - Danese, Giuseppe; Mittone, Luigi (MyScienceWork, 2008)
Inspired by Karl Polanyi’s writings on three allocation modes, namely reciprocity, exchange and redistribution, we first tested a reciprocity ring with ten players. The baseline treatment, with no possibility of socialisation, displayed very low levels of allocative efficiency. Consistently with the Polanyian approach to reciprocity, we found that inducing the notion of symmetry among the players increased efficiency levels significantly. We then simulated a market exchange, with significant allocative efficiency gains. We conclude that indirect-reciprocity rings among anonymous players can seldom function in the absence of definite institutional refinements, promoting forms of symmetry-acknowledgement.
Political Science
Keywords: instituted economic process; reciprocity

Labour and the Transformation of East Asian Capitalism: A Regional View - Gray, Kevin (Conference Papers – International Studies Association, 2008)
Two of the most salient aspects of the recent shift towards financialisation and neoliberal restructuring since the 1970s have been the restructuring of global production towards China, and the growing threat to workersâ livelihoods posed by increased capital mobility. Both of these trends can be seen as capitalâs response to the crisis of profitability that has arisen from the unsustainable global social accord between workers and capital that was inherent in post-War US hegemony. Transnational manufacturing capital sought ever cheaper sites of cheaper and non-unionised labour, whilst there was at the same time a tendency for capital to withdraw from productive investment altogether and enter the financial market. This paper will seek to explore the implications of these developments for the working classes of East Asia as a region, and will take examine the present transformations from the perspective of Polanyi's depiction of social responses to earlier periods of financialisation. The emergence of China as the 'workshop of the world' has had profound effects on working classes in the rest of East Asia, and have changed the parameters within which political challenges can be mobilized. Similarly, the viability of the recent restructuring of the East Asian regional political economy is highly contingent upon how working class movements develop in China, and whether China can continue to act as a "spatial fix". Through an examination of the empirical evidence on what kind of strategies are being adopted by labour movements within the East Asian countries, the paper will attempt to adopt an explicitly regional view of the transformations of regional capitalism which overcomes the limitations of national-level analyses. ..PAT.-Unpublished Manuscript
Political Science; International Relations
Keywords: East Asia; capitalism; economic conditions in East Asia; economic structure; financialization; international economic relations; international trade

The Space of Rights: On Benjamin, Gramsci, and Polanyi - Holub, Renate (Conference Papers – International Studies Association, 2008)
For intellectual generations born at the end of the 19th century in Europe, the discourses on rights were to a large measure determined by proponents and detractors of various versions of Marxism. Hence the debates on justice and rights predominantly operated with the conceptual and analytical instruments of European political economy. These debates also were premised on assumptions about the status of the political economy of Europe and North America in the distribution of global space. But the intellectual generations born at the end of the 19th century, and particularly those with interests in the Marxist project – as Benjamin, Gramsci, and Polanyi were– were also witnesses to the facts of the Soviet Revolution and its evolution into the Stalinist state. In this paper I will first of all examine the ways in which Walter Benjamin, Antonio Gramsci, and Karl Polanyi elaborated and expanded the concept of transatlantic space inscribed into the Marxist project. I will then investigate to which extent their familiarity with the rights practices of Stalinism impacted their elaboration of new forms of the space of rights: Benjaminâs concept of the historical space of âmessianismâ that transcends the historical limits of the space of rights of historical materialism; Gramsciâs concept of cultural space as a struggle for rights that expands Marxâs terrain of political economy, and Polanyiâs concept of anthropological space that expands the conceptual space of economic analysis of classical Marxism. The purpose of the paper is to gain a measure of understanding of the links that obtain between conceptual apparatuses of leading intellectuals and global transformations in the first half of the twentieth century, particularly since these intellectuals developed their ideas relatively independently from the structures of organized knowledge production of universities and academies. ..PAT.-Unpublished Manuscript
Political Science
Keywords: BENJAMIN; Walter; 1892-1940; GRAMSCI; Antonio; 1891-1937; communism; human rights; political science

Transformations, Then and Now: The Appeal of Karl Polanyi - Karnik, Ajit (Economic and Political Weekly, 2008)
Karl Polanyi's views on the nature of "pre-market" society are influential not only among historians but also among economists concerned with present-day transitional and developing economies. This paper examines Polanyi's arguments about the "Great Transformation" from traditional to market society in the light of recent advances in economic theory and empirical evidence from a range of European and non-European societies. These theoretical and empirical considerations provide little support for Polanyi's views concerning fundamental discontinuities between traditional and market societies. The paper concludes that Polanyi's rosy view of pre-market society provides an inappropriate historical basis for addressing the challenges faced by present-day transitional and developing economies.
Economics
Keywords: critique; economic history; market economies; market economy; market mechanism; market mechanisms; money; peasant class; pre-market society; transitional economies

Movements of the World Unite! Assessing Prospects for Social Movement Unionism in Canada - MacArthur, Julie (Conference Papers – International Studies Association, 2008)
Within the field of critical political economy exists a literature urging a re-conceptualization of democracy (Munck 2002, Cox 1997, Webster and Adler 1998). Liberal, particularly neo-liberal, political systems are critiqued for their binary separation of economics and politics leading to substantive disenfranchisement and elitest governance. Robert Cox (1997) has called this âlimited democracyâ and argues that consumer choice and infrequent elections cannot be equated with democratic citizenship. One theorized response to this problem builds on the work of Karl Polanyi (1944) and his concepts of âembeddednessâ and the âdouble movementâ. Democracy can be deepened and strengthened by asserting social control over the economy and society at multiple levels and across issue areas. This is accomplished by a movement of social forces forcing a re-embedding in response to periods of increasing economic and elite consolidation. A problem in this literature has consistently been the agent or agents of change.This paper critically explores the argument that Social Movement Unionism (SMU), the organizational and theoretical blend of trade unionism and social movements, can and may serve as the agent of a Polanyian double movement in Canada. While theorists of SMU argue that labour necessarily needs to branch out laterally as a response to neo-liberal policies, I explore the tensions between âoldâ labour and contemporary social movements in Canada, such as the environmental movement. I ask: to what extent is organized labour taking on issues beyond their narrow collective-bargaining interests? Is there significant personnel overlap between labour and social movement organizations such as environmental, womenâs or anti-war groups? In answering these questions I intend to draw out the tensions between various actors these theories look to for change and assess their relevance in the Canadian context. By bringing together literature on transnational social movements, labour studies, political economy and international relations this paper takes an interdisciplinary approach to understanding these challenges. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Canada; democracy; economics; elite (social sciences); political science

Polanyi's Double Movement: A Critical Reappraisal - Maertens, Eppo (Social Thought & Research, 2008)
The article offers a critical reappraisal of Karl Polanyi's claim that the restructuring of the economy based on the ideals of the self-regulating market inevitably leads society to reassert itself against the commodification of land, labour and money. Dubbed as the "double movement," the author focuses his reappraisal on the two aspects of the movement. The first refers to the push for free market reforms by various groups in society, and the second refers to the counter-movements that he argues necessarily and spontaneously mobilize against it. In this paper, he argues that the first aspect is an area that deserves further attention, both from those who wish to apply his ideas as well as from those who wish to challenge them.
Sociology
Keywords: central economic planning; commodification; critique; double movement; dual economy; economic structure; free enterprise; market ideology; markets; public welfare

The Great Transformation: The Political and Economic Origins of Our Time - Meier, Brian (Social Thought & Research, 2008)
The article reviews the book "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polayni.
Sociology
Keywords: Great Transformation; The (Book); book review; economics; nonfiction

KARL POLANYI ABOUT INSTITUTED PROCESS OF ECONOMIC DEMOCRATIZATION AND SOCIAL LEARNING - Mendell, Marguerite (PEKEA Newsletter N° 14, April – June 2008 / ResearchGate, 2008)
This text will not focus on The Great Transformation but will deal with previous and following writings from Karl Polanyi where his emphasis is on the constitutive elements that define us as social beings and as agents of social change.
Economics; Political Science
Keywords: Great Transformation; The (Book); economic democratization; education; instituted economic process; social learning

In the Zone: Street Markets and Street Merchants in Socio-Legal Perspective - Morales, Alfonso (Conference Papers – Law & Society, 2008)
Typically when we think of street markets we think of chaotic places full of energy and vibrating with danger and opportunity. Traders or governments create markets to meet existing and emergent demands as well as the unintended consequences of other policy decisions. It is this institutional design, this governance, this regulatory process that provides access to the market and organizes the vending space therein. Public and private entities operating in fiscally constrained environments should attend to the variety of ways there are to establish and regulate markets. Municipalities typically assume that a detailed management scheme is the best approach to managing access to markets and organizing the distribution of space, the assumption being that chaos would result in the absence of the state. However, this is not necessarily the case, merchants' can self-organize access to space as well as a stable and flexible spatial order, and this self-organization can minimize costs, improve access, and contribute to social goods and goals associated with having a public market.This article provides an empirical justification for this claim by examining the creation of Chicago's Maxwell Street Market (hereafter the Market), and describing the subsequent changes in the regulatory scheme of that Market. This discussion recalls Polanyi's observation that all markets are regulated, one way or another, but that the forms and character of regulation obviously varies – and thus this article argues the thesis that even in apparently unregulated markets we will find regulation, self-created, that produces a social order, in this case a stable and flexible order that accommodates a variety of private and public circumstances and goals. Our case is Chicago's Maxwell St. Market, which between 1973 and 1994 resembled unfettered capitalism. An ethnically heterogeneous multitude of street entrepreneurs organized vending space with little violence in the absence of stable, state sponsored, legal expectations. But this self-organization is nested in an overall history of unregulated street commerce in the area, starting in the 1870s, followed by the City government's creation and regulation of the Market in 1912, then a period of regulation lasting 60 years, followed by a radical change in the regulatory regime that produced a self-organized Market for about 20 years, then finally the City recaptured the Market and has regulated it again since 1994. Planners and policy makers will find this case interesting for three reasons: first, it is an interesting history of public markets and planning interests, second, the data indicate how an ethnically heterogeneous population can self-produce a flexible and stable social order and third, planners and policy makers concerned with locally appropriate and economically efficient, combinations of government and self-regulation of economic activities might apply lessons from this case to the large and growing interest in public markets around the country. ..PAT.-Unpublished Manuscript
Law; Urban Studies
Keywords: government regulation; markets; municipal government; nation-state; policy sciences

Third Way Labor Law Reform in Chile - Rosado Marzan, Cesar F. (Conference Papers – Law & Society, 2008)
Latin America is currently undergoing Karl Polanyi's "double movement" at full swing, as most governments of the region are currently experimenting with policies that defy the neoliberal orthodoxy that has been reigning there for almost three decades. One of such governments has been the center-left Concertación governments of Chile, which have been elected since the restoration of democracy in 1990. In addition to poverty alleviation programs, Concertación has been in an ongoing process of reforming the country's labor laws, attempting to restore some of the labor rights existing prior to the 1973 coup, as well as creating new rights and institutions. The labor inspectorate has been strengthened and reformed under the framework of "Latin" systems of labor inspections, which are pedagogical rather than punitive in orientation. Labor courts are also being radically bolstered, providing workers with a renewed legal avenue to enforce their rights. Although the reforms fall short of full restoration of trade union rights, namely national collective bargaining, they do point to a clear break with the "stateless" regulatory, neoliberal model that Chile was once associated with and provide symbolic and intellectual fodder for further reforms in the country and beyond. ..PAT.-Unpublished Manuscript
Law; Sociology
Keywords: Chile; Latin America; labor laws & legislation; labour laws & legislation; law reform; mixed economy

Group Affiliation and Market Embeddedness in American Enterprise - Valdez, Zulema (Conference Papers – American Sociological Association, 2008)
In this article, Polanyi's (1944) notion of society as constituted by three forms of economic integration (market exchange, reciprocity, and redistribution) is applied to entrepreneurship. In advanced capitalism, the market-exchange relationship is the dominant form of economic integration; secondary relationships of reciprocity and redistribution, however, co-exist alongside relations of market exchange. Following Polanyi (1944), this article introduces an "embedded market" approach to enterprise. The embedded market approach considers the differential effects of primary and secondary relationships on entrepreneurial outcomes. The traditional ethnic entrepreneurship paradigm suggests that resource mobilization based on ethnic group membership is essential for entrepreneurial success, as measured by participation and earnings. The embedded market approach reconsiders ethnic group membership, along with other politically-influenced human social groupings (e.g. class, gender, nativity, and race) as non-essential relationships of reciprocity. In this conception, group affiliation provides the basis for compensatory relief from market uncertainty in the form of social capital. Ultimately, the embedded market approach provides a systematic and comprehensive approach to understanding the role of group affiliation in facilitating ethnic and "non-ethnic" enterprise in America.
Sociology
Keywords: Latino/a Sociology; United States; class and gender; commercial policy; entrepreneurship; ethnic entrepreneurship; inequality; international economic integration; new business enterprises; race

Double Movement in China - Wang, Shaoguang (Economic and Political Weekly, 2008)
This paper traces China's move towards a market economy in the mid-1980s, the near triumph of market forces in the 1990s, and the countermovement this engendered as inequalities between the rich and poor increased and social security networks collapsed. It focuses on the country's regional and healthcare policies to illustrate how it has dealt with issues of inequality and insecurity over time. The prevailing view now is that the market is necessary but it must be embedded in society. And the state must play an active role in the market economy to prevent a disembedded and self-regulating market economy from dominating society.
Political Science
Keywords: China; double movement; market economy

Charismatic Economies: Pentecostalism, Economic Restructuring, and Social Reproduction - Barker, Isabelle V. (New Political Science, 2007)
Pentecostalism is one of the world's fastest growing religions, expanding most quickly in Latin America, sub-Saharan Africa, and parts of Asia. To make sense of this expansion in so many developing regions, I suggest that Pentecostalism fosters norms and behaviors that harmonize with neoliberal economic restructuring. I frame this theoretically with Polanyi's notion of double movement. In our current era of weakened state governance vis-à-vis neoliberal trade and fiscal policy, non-state sites of reaction have emerged. Pentecostalism is one such site, and, in contrast with Polanyi's example, I suggest that Pentecostalism has embedded the self-regulated aspects of neoliberal capitalism. I make this argument by using the feminist political economy theorization of social reproduction to interpret a number of empirical studies of Pentecostalism. Pentecostalism addresses dilemmas of social reproduction engendered by neoliberalism, and so may be said to embed this form of economic organization in human social life in a way that reinforces neoliberal capitalism.
Political Science
Keywords: Pentecostalism; capitalism; double movement; economic systems; economics; neoliberalism; social interaction; social reproduction; social structure; socialization

The Poverty of the Global Order - Da Costa, Dia; Mcmichael, Philip (Globalizations, 2007)
This paper argues that the legitimacy of the global order depends not on economic progress alone, but on the progressive naturalization of its epistemological foundations, through 'new solutions' to old problems by states and development agencies. New solutions become methods of social control through which the dominant visions of what count as viable futures are reproduced. We critique efforts to humanize development (e.g., by the World Bank, Amartya Sen) as evidence of development's epistemological crisis. Deploying Karl Polanyi's distinction between formal and substantive economy, we consider examples of substantive economy, which realize equality through strategic sovereignty and representational power, in collective and individual terms. These represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects development studies and international relations. Este documento sostiene que la legitimidad del orden global no depende solamente del progreso económico, sino de la naturalización progresiva de sus fundamentos epistemológicos, a través de 'nuevas soluciones' a problemas antiguos mediante estados y agencias del desarrollo. Las nuevas soluciones se convierten en métodos de control social, a través de los cuales se reproducen las visiones dominantes de lo que cuenta como futuros viables. Criticamos los esfuerzos de humanizar al desarrollo (p.e. Banco Mundial, Amartya Sen) como evidencia de la crisis del desarrollo epistemológico. Utilizando la distinción de Kart Polanyi entre economía formal y economía sustancial, consideramos ejemplos de una economía sustancial, la cual realiza la igualdad por medio de una soberanía estratégica y un poder representativo, en términos colectivos e individuales. Estas, entre otras iniciativas, representan 'espacios de esperanza' prácticos y epistemológicos para criticar la crisis de la epistemología de mercado que infecta a los estudios de desarrollo y las relaciones internacionales.
Developent Studies; Sociology
Keywords: formal economy; international law; international relations; international trade; social control; social epistemology; sovereignty; substantive economy

The making of US monetary policy: Central bank transparency and the neoliberal dilemma - Krippner, Greta (Theory & Society, 2007)
This article explores the implications of the Federal Reserve’s shift to transparency for recent debates about neoliberalism and neoliberal policymaking. I argue that the evolution of US monetary policy represents a specific instance of what I term the “neoliberal dilemma.” In the context of generally deteriorating economic conditions, policymakers are anxious to escape responsibility for economic outcomes, and yet markets require regulation to function in capitalist economies (Polanyi ). How policymakers negotiate these contradictory imperatives involves a continual process of institutional innovation in which functions are transferred to markets, but under the close control of the state. Thus, under transparency, Federal Reserve officials discovered innovations in the policy process that enabled “markets to do the Fed’s work for it.” These innovations enlisted market mechanisms, but did not represent a retreat from the state’s active role in managing the economy.
Sociology
Keywords: Board of Governors of the Federal Reserve System (U.S.); United States; capitalists & financiers; monetary policy; neoliberalism; policy sciences; public spending

Poverty, Security and the Janus-Faced State - Eadie, Pauline (The British Journal of Politics & International Relations, 2007)
In this article Polanyi's double move and Wæver's securitisation argument inform an analysis of poverty as a security issue. The inclusion of poverty on the security agenda confirms and complicates, rather than marginalises, the state as a central referent of security. It is argued that analytically and pragmatically qualitative and socially contextualised analysis of poverty offers deeper understanding than quantitative approaches. It is also argued that the rhetoric of inclusion currently espoused by the likes of the World Bank seeks to secure institutional hegemony rather than state or human security. Neo-liberal solutions to poverty premised on growth, as opposed to redistribution, mean that the states and peoples poorly equipped to compete in the capitalist game will remain impoverished. Markets and neo-liberal institutions serve to splinter, rather than coalesce, state and society.
Political Science
Keywords: Copenhagen school; double movement; poverty; security

The Future of Sociology - Burawoy, Michael (Sociological Bulletin, 2007)
Like a hurricane, third-wave marketisation is picking up velocity and destroying societies in its path, destroying the very grounds upon which sociology grows. Sociology and humanity have a common interest in upholding civil society, and keeping state and market at bay. Working with Karl Polanyi's The Great Transformation, I diagnose three waves of marketisation associated with the commodification of labour, money and land, generating counter-movements at local, national and global levels. I argue that sociology is reshaped with each wave: in the first, it is utopian; in the second, it is driven by policy concerns; whereas emerging with the third wave marketisation is public sociology. The possibilities and challenges of public sociology as well as its relation to policy, critical and professional sociology are the subjects of this paper.
Sociology
Keywords: commodification; countermovement; government policy; humanity; labor; marketisation; markets; nature; public sociology; social sciences; societies; sociology; utopian socialism

Karl Polanyi and Return of the "Primitive" in Institutional Economics - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
This article discusses a renewed interest in the work of scholar Karl Polanyi and the incorporation of his work into the body of institutional economics. This article discusses the notion of time in Polanyi's work and how it differs from the metaphor of time inherent in neoclassical economics. The author discusses the definition of the word "primitives" and its relationship to social policy, and how Polanyi deployed the actual state of primitives in order to replace the economistic cost-benefit analysis of the Industrial Revolution with a "social cost" alternative.
Economics
Keywords: POLANYI; Karl; 1886-1964; corporate culture; cost effectiveness; externalities; externalities (economics); industrial psychology; industrial revolution; institutional economics; social policy; social psychology

Policymaking and Learning Actors, or Is A 'Double Movement' In Cognition Possible? - Ramazzotti, Paolo (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
This article discusses the relationship among economic constraints, social reform and societal pressures for a humane society, drawing on the insights of scholars Karl Polanyi and Herbert A. Simon. One of the key issues in Polanyi's work is the divergence between economic and societal values in modern capitalism. The divergence leads to a reaction against the rationale of the market and to what Polanyi refers to as the double movement. The distinction between internal consistency and external consistency is described to frame the role of institutions in the economy.
Economics
Keywords: POLANYI; Karl; 1886-1964; SIMON; Herbert A.; 1916-2001; capitalism; double movement; economic policy; economic sectors; evolutionary economics; markets - social aspects; socioeconomic factors; socioeconomics

The battle of the ancient economy - Hindess, Barry (Economy & Society, 2007)
Ancient Athens and Modern Ideology addresses the battle between primitivism and modernism over the ancient economy, focusing especially on the contributions of three major figures, Max Weber, Karl Polanyi and Moses Finley. Finally, a short Epilogue returns to the examination of Marx's puzzle and his manifestly unsuccessful attempt to resolve it. Mohammad Nafissi uses this discussion to put this dispute out of its misery by advancing his own resolution of the primitivist-modernist dispute. Unfortunately, the limitations he seeks to avoid are mostly those which the supporters of one or the other side have identified in the claims of their opponents. As a result, his attempted resolution fails to disrupt their shared assumptions regarding the special place of the ancient Greeks in human development.
Political Science; Sociology
Keywords: Athens (Greece); FINLEY; M. I. (Moses Israel); 1912-1986; Greeks; WEBER; Max; 1864-1920; book review; history of economics; ideology; primitivism; socioeconomics

Karl Polanyi and the Modernity-versus-Postmodernity Debate - Özveren, Eyüp (European Legacy, 2007)
The originality of Karl Polanyi's (1886-1964) work in the interwar period and his work in the 1950's has gained increasing recognition in recent years, during which time the major debate on modernity has erupted. In order to link Polanyi's work with this debate, the article first discusses his legacy on the controversial concept of progress and then relates his position to this debate. Polanyi's position combines the better aspects of the two rival approaches to modernity. The article then relinks Polanyi's thought to the intellectual figures, movements, and climate of his time and thereby discloses a curious affinity between his thought and the critical theory of the Frankfurt School. This affinity can best be understood within the parameters of the historical context that they once shared.
Economics
Keywords: POLANYI; Karl; 1886-1964; debates and debating; economics; modern society; modernity; postmodernism (philosophy); progress

The Early Debate on Economic Calculation in Vienna (1919-1925): The Heterodox Point of View: Neurath, Mises and Polanyi - Becchio, Giandomenica (Storia del Pensiero Economico: Nuova Serie, 2007)
This paper is based on the idea that the early debate on economic calculation in a planned economy conducted in Vienna among Neurath, Mises, and Polanyi (1919-1925) was the starting point for the development of a particular form of heterodox economic theory propounded by liberal thinkers like Mises and by socialists like Neurath and Polanyi. Mises claimed that solving the problem of calculation was impossible, and consequently that a centrally planned economy was not theoretically feasible. Neurath and Polanyi instead sought to solve the problem of calculation and, despite certain profound differences between their views, they proposed a socialistic model alternative to the orthodox Marxist one.
Economics
Keywords: MISES; Ludwig von; Marxism; NEURATH; Otto; economic calculation; economic thought; heterodox economic theory; heterodox economics; history of economic thought; history of economics; planned economy

Non-Trade Concerns in Agricultural and Environmental Economics: How J.R. Commons and Karl Polanyi Can Help Us - Barthélemy, Denis; Nieddu, Martino (Journal of Economic Issues, 2007)
Economics
Keywords: COMMONS; J.R.; economics; environmental economics; substantive economy

The Polanyian Way? Voluntary Food Labels as Neoliberal Governance - Guthman, Julie (Antipode, 2007)
Voluntary food labels that express ecological, social, and/or place-based values have been posed as an important form of resistance to neoliberalization in the Polanyian sense of protecting land, other natural resources, and labor from the ravages of the market. At the same time, these labels are in some respects analogs to the very things they are purported to resist, namely property rights that allow these ascribed commodities to be traded in a global market. After reviewing the Polanyian claims about these labels, the paper examines how these labels are operationalized and notes important differences in the sort of barriers to entry they erect, which in turn have quite different distributional consequences. It then goes on to discuss how these labels look to be an expression of roll-out neoliberalization. Following Heynen and Robbins who note four dominant aspects of neoliberalization of environmental governance (governance, privatization, enclosure, and valuation), to which a fifth (devolution) is added, the paper shows how these labels not only concede the market as the locus of regulation, but in keeping with neoliberalism's fetish of market mechanisms, they employ tools designed to create markets where none previously existed. In recognition that neoliberal political economies and subjectivities have delimited the possible, the paper also grapples with how these labels may produce political openings outside of their most proximate effects.
Geography
Keywords: agro-food governance; community studies; depletion allowances; fair trade; food labeling; government ownership; labeling; liberalism; natural resources; neoliberalism; organic food; privatization

Philosophizing with a hammer? A critique of Mirowski's markomata informed by continental philosophy - Juniper, James (Journal of Economic Behavior & Organization, 2007)
Abstract: Mirowski''s justification for replacing the foundational principles of neoclassical economics – methodological individualism and rational choice theory – with a theoretical framework informed by cybernetics, information theory, and computational biology, is subject to a critique informed by the work of Karl Polanyi, Michel Foucault and Jürgen Habermas. Mirowski''s proposed alterative is called into question on the basis of two crucial weaknesses. First there is Mirowksi''s penchant for what Polanyi has called Laplacian reductionism. Second there is Mirowski''s inability to develop a comprehensive and consistent theory of evolutionary economics. Mirowski''s work is questioned in terms of what social theorists call the ‘structuration paradox’.
Economics
Keywords: FOUCAULT; Michel; 1926-1984; MIROWSKI; Philip; continental philosophy; cybernetics; economic methodology; economics; social theory; structuration paradox

Globalization, inequalities and the “Polanyi problem” - Śliwa, Martyna (Critical perspectives on international business, 2007)
The purpose of this paper is to contribute to the debate on the consequences of globalization, in particular the increasing disparity between the wealth of nations and individuals in society. It discusses mechanisms which lead to perpetuation and reinforcement of the situation in which, despite being characterized by inequalities and fragmentation, societies remain by and large cohesive and stable. This article engages with the so-called “Polanyi problem” and with Polanyi’s and other authors’ responses to it. In the discussion, the analytical approach is adopted by reference to Aldous Huxley’s Brave New World, in particular his concept of soma. Using the metaphor of soma, developed into four interrelated dimensions, illustrations of social and organizational processes, which ensure sustainability of, and cohesion within, a society based on inequality and fragmentation, are indicated. It is argued that the existence of stratified societies, and inequalities of wealth within and between them, is accompanied by phenomena which support and sustain them. Drawing upon literary fiction can offer valuable insights into issues pertinent to contemporary academic debate. Engagement with Huxley’s work provides an alternative way of contributing to the globalization debate and, in particular, to the literature addressing the so-called “Polanyi problem”.
Business; International Business
Keywords: Brave New World (book); HUXLEY; Aldous; Polanyi problem; distribution of wealth; globalization; international business; society; soma

Neoliberalism, embedded neoliberalism and neocorporatism: Towards transnational capitalism in Central-Eastern Europe - Bohle, Dorothee; Greskovits, Béla (West European Politics, 2007)
This article analyses the key features and origins of three variants of transnational capitalism emerging in Central-Eastern Europe: a neoliberal type in the Baltic states, an embedded neoliberal type in the Visegrád states, and a neocorporatist type in Slovenia. These regimes are characterised by their institutions and performances in marketisation, industrial transformation, social inclusion, and macroeconomic stability. Explanations for regime diversity are developed at two levels. First, it is argued that the legacies of the past, and their perceptions as either threats or assets to these countries' future, have had deep impact on regime types. Legacies and initial choices were no less crucial for the degree of democratic inclusion, and the different patterns of protest and patience on the paths towards the new regimes. Second, the article demonstrates the importance of transnational influences in industrial transformation and social inclusion.
Political Science
Keywords: Central-Eastern Europe; embedded neoliberalism; neoliberalism; transnational capitalism

Public sociology vs. the market - Burawoy, Michael (Socio-Economic Review, 2007)
Building on Karl Polanyi's theory of a societal reaction to the unregulated exchange of what he called fictitious commodities—labour, money and land—this paper links the history of sociology to the history of the market. If the first wave of marketization in the nineteenth century dwelt on the commodification of labour, prompting utopian sociologies, and the second wave of marketization of the twentieth century was provoked by the commodification of money, generating national policy sociologies, then the third wave of marketization that began in the last quarter of the twentieth century includes the commodification of the environment (land, air, water), and calls for public sociologies of a global dimension.
Sociology
Keywords: commercial products; fictitious commodities; government policy; history of sociology; markets - social aspects; publicity - social aspects; social theory; socioeconomics; utopian socialism

Understanding the Diverging Trajectories of the United States and Western Europe: A Neo-Polanyian Analysis - Block, Fred (Politics & Society, 2007)
This article proposes a neo-Polanyian theoretical framework for understanding the dynamics within contemporary market societies. It uses this framework to analyze the divergence between the United States and other developed societies that has become more pronounced in the first years of the twenty-first century. The argument emphasizes the shifting political alliances of the business community in the United States and suggests that from 1994 onward, business lost power in the right-wing coalition to its religious Right allies. The growing power of a religious-based social movement is a critical ingredient in the unilateralist turn in the Bush Administration’s foreign policy.
Sociology
Keywords: U.S. business; economic sociology; embedded economy; embeddedness; social theory; varieties of capitalism

Principles of Institutional-Evolutionary Political Economy – Converging Themes from the Schools of Heterodoxy - O'Hara, Phillip Anthony (Journal of Economic Issues (Association for Evolutionary Economics), 2007)
The article examines the renewed interest in heterodox political economy. Institutionalists, post Keynesians, neo-Marxists, and feminists among others, and various sub-groups provide schools of thought on heterodoxy. The guidelines of institutional-evolutionary political economy (IEPE) are offered alongside socioeconomic analysis and complexity theories. The author outlines the conflict of individual v. structure. Other topics covered include social capital, heterogeneous agents, financial instability, cumulative causation, institutional environments, community and governance, and destructive creation.
Economics
Keywords: Keynesian economics; creative destruction; disembedded economy; economic policy; evolutionary economics; heterodox economics; heterodox political economy; infrastructure (economics); mixed ability grouping (education); political economic analysis; social capital; social theory

Embeddedness, Path Dependency and Social Institutions: An Economic Sociology Approach - Ghezzi, Simone; Mingione, Enzo (Current Sociology, 2007)
This paper argues for a theoretical approach based on embeddedness which assumes that the economic actor is not an atomized and utilitarian individual, but is in fact positioned within specific historical and institutional contexts in various social networks. This approach is based on Polanyi's critically debated contribution which allows for an empirical study of the diversity of institutional structures and of the significance of configurations of insertion within different social networks. Such diversity results from the double movement of disembeddedness and re-embeddedness caused by the spread of constantly emerging market opportunities, and by the importance held by the historically and culturally different selective processes of path dependency in the construction of the institutions of social regulation and of the socialized preferences of economic actors. Within these processes attention is given to the transformation of social systems based on reciprocity (household, kin, social capital networks, etc.), associations of shared interests, forms of economic organization (in a plurality of coexisting ‘economies’), unequal distribution of power, and political intervention.
Sociology
Keywords: abordaje de sociologí económica; culture; dependencia de camino e institutiones sociales; developing countries; dépendance au chemin parcouru; embeddedness; empirical research; entrepreneurship; imbricación; institutions sociales; kin network; market; path dependency; reciprocity; reciprocity (commerce); social groups; social institutions; social networks; social systems; socioeconomics; utilitarianism

The End of Potlatch: An Anthropological Approach to Nostromo - Juhász, Tamás (Research in Economic Anthropology, 2007)
This study contends that the various forms of archaic trade that anthropologists have reconstructed on the Northwest Coast of America are explanatory of plot-construction and characterization in Conrad's South-American novel. My thesis is that Nostromo is a figure defined by the practice of potlatch, and that his key presence in the plot entails the representation of a culturally dislocating transition from archaic transactions to modern commerce. The theoretical framework of this chapter hinges on the insights of Marcel Mauss, Claude Lévi-Strauss, Karl Polanyi, and Georges Bataille.
Anthropology
Keywords: CONRAD; Joseph; LEVI-STRAUSS; Claude; Nostromo (book : Conrad); archaic economy; embeddedness; history of commerce; plots (Drama; novel; etc.); potlatch; reciprocity; redistribution

Globalization, Inequality, and "Double Movement" in East Asia - Kim, Wonik (Conference Papers – New England Political Science Association, 2007)
The purpose of this paper is to analyze the effects of rising income inequality on the welfare state in East Asia. Specifically, I explore and test two causal links: 1) the effects of economic globalization on income distribution, and 2) the increase in income inequality on the prospect of socio-welfare policies. Building on Polanyi's politico-economic concept of "double movement," I hypothesize that rapid neoliberalization and financial globalization in East Asia since the early 1990s (after the Asian Financial Crisis) has de-constructed the traditional state apparatuses that supported a well-known state-led accumulation strategy. This shift in political arrangements and national growth strategy, in turn, has entailed rising income inequality in a society, calling for restructuring the traditional East Asian welfare state. The success and failure of the creation of a new welfare state for new social risks depends on the level of contentious politics and country specific traits. With this general theoretical framework, I conduct a comparative method of five East Asian countries - China, Japan, South Korea, and Taiwan - for the period from the 1990s to the present, and explain the similarities and differences among them. ..PAT.-Unpublished Manuscript
Political Science
Keywords: East Asia; equality; globalization; income distribution; international competition; neoliberalism

Rethinking the Categories of Feminist Theory: Diverse Feminist Responses to the Market Economy - MacLean, Lee (Conference Papers – New England Political Science Association, 2007)
Feminist theory is often articulated as a series of categories of thought: liberal feminism, socialist feminism, Marxist feminism, psychoanalytic feminism, etc. These categories have aided the recent development of feminist thought, but their prevalence sometimes limits discussion to predicable perimeters. My argument begins from the observation that feminists often have very different responses to the rise of the market economy as a separate institution largely free of control by political and kinship-based authorities. In particular, there is a difference of opinion about the liberating possibilities of participating in a largely self-regulating market economy. I think an investigation of this disagreement could provide a new way of conceptualizing the main lines of feminist argument. For example, feminists who emphasize that the market economy provides an opportunity for women to free themselves from gender restrictions expressed in family and kinship traditions might be called libertarian-type feminists. Other feminists, those who (from varying perspectives) are skeptical that participation in the free market results in freedom for women, might be termed free-market skeptics. Of course, one wants to avoid creating new rigid labels, but thinking about this conceptualization can help to destabilize old categories and to recast often divisive debates (for example, over issues such as prostitution, pornography and housework).The argument is inspired by thinking through descriptions of the historically changing relations between market, family and politics found in two works: Karl Polanyi's The Great Transformation and Linda Nicholson's "Feminism and Marx: integrating Kinship with the Economic." ..PAT.-Unpublished Manuscript
Political Science
Keywords: capitalism; families; feminism; feminists; kinship; women

Reforming Social Justice in Neoliberal Times - Brodie, Janine M (Studies in Social Justice, Vol 1, Iss 2, Pp 93-107 (2007), 2007)
This article unfolds in three stages. First, it locates the emergence of modern conceptions of social justice in industrializing Europe, and especially in the discovery of the “social,” which provided a particular idiom for the liberal democratic politics for most of the twentieth century. Second, the article links this particular conception of the social to the political rationalities of the postwar welfare state and the identity of the social citizen. Finally, the article discusses the myriad ways in which this legacy of the social and social justice has been disrupted, although not yet fully displaced, by the economic orthodoxies and individualization that inform the contemporary neoliberal governing project in Canada. The result, the article concludes, has been the institutionalization of insecurity, which demands the renewal of a social way of seeing and a politics of social justice on local and global scales.
Political Science
Keywords: criminology; neoliberalism; political economy; social and public welfare; social governance; social justice; social pathology; social policy; social sciences; sociology

Neoliberalism or Democracy: Competing Forms of Social Organization in Latin America - Dowd, Jeffrey (Conference Papers – American Sociological Association, 2007)
While political turmoil is not new to Latin America, the tension between neoliberalism and democracy can help explain present-day turmoil. The current political situation in Latin America is the result of a disconnect between the goals of democracy, in particular, between social justice goals, upon which the legitimacy of democratic government rests, and the neoliberal economic policy of the region. Polanyi's concept of the always-embedded economy states that a market economy must be embedded in a market society. Following Polanyi, I argue that markets and democracy require different forms of social organization. Markets and democracy are alternate and competing forms of social organization. The predominance of one often coincides with the restriction of the other. For example, neoliberal governance that maintains market society undermines electoral efficacy. While this may be a general attribute of neoliberalism, previous economic crisis in Latin America increased the need for rhetorical commitment to social justice goals. Latin America's structural position has not changed, however, and international finance and global organizations, like the International Monetary Fund and the World Bank, still constrain Latin American governments. I argue that any resolution to the tension between neoliberalism and democracy must accept the conflicting nature of these two forms of social organization. ..PAT.-Unpublished Manuscript
Sociology
Keywords: Latin America; always embedded economy; democracy; economic policy; embeddedness; free market; free-market; market; neoliberalism; political science; political theory; social justice

Moral Views of Market Society - Fourcade, Marion (Annual Review of Sociology, 2007)
Upon what kind of moral order does capitalism rest? Conversely, does the market give rise to a distinctive set of beliefs, habits, and social bonds? These questions are certainly as old as social science itself. In this review, we evaluate how today's scholarship approaches the relationship between markets and the moral order. We begin with Hirschman's characterization of the three rival views of the market as civilizing, destructive, or feeble in its effects on society. We review recent work at the intersection of sociology, economics, and political economy and show that these views persist both as theories of market society and moral arguments about it. We then argue that a fourth view, which we call moralized markets, has become increasingly prominent in economic sociology. This line of research sees markets as cultural phenomena and moral projects in their own right, and seeks to study the mechanisms and techniques by which such projects are realized in practice.
Sociology
Keywords: capitalism; culture; governmentality; moral markets; moral order; performativity

Globalization, Welfare Reform and the Social Economy: Developing and Alternative Approach to Analyzing Social Welfare Systems in the Post-Industrial Era Special Issue on Globalization: Social Justice & Social Welfare - Gonzales, Vanna (Journal of Sociology and Social Welfare, 2007)
Our understanding of the relationship between globalization and contemporary social welfare systems is heavily influenced by three conventional approaches to studying welfare reform: the political economy, moral economy, and mixed economy approaches.In addition to analyzing the strengths and weaknesses of each of these approaches, a central aim of this article is to introduce the social economy approach as an emergent alternative. Drawing from a growing body of work on institutional innovation within the European third sector, I argue that the social economy approach makes a valuable contribution to understanding the role of welfare networks in recon-figuring globalizations 'impact on the character and quality of social provision so as to better reconcile social efficacy with social justice.
Sociology
Keywords: globalization; social enterprises; social inclusion; social justice; third sector; welfare networks; welfare reform

Karl Polanyi, Marshall Sahlins, and the Study of Ancient Social Relations - Kirk, Alan (Journal of Biblical Literature, 2007)
Questions arise whenever social-scientific models are used in analysis of ancient texts, particularly regarding the feasibility of their application to social and cultural milieux different from those from which they were derived. An essay I authored that assessed the command in Luke 6 to "love your enemies" from the perspective of ancient reciprocity ethics, and that invoked Marshall Sahlins's taxonomy of reciprocity relations (general, balanced, and negative reciprocity), was queried by Zeba Crook on precisely this point, namely, whether it applied Sahlins's taxonomy to Greco-Roman reciprocity relations without adequate attention to the distinctions between kinship organized tribal societies (the focus of Sahlins's analysis) and the socially stratified agrarian societies characteristic of the ancient Mediterranean world.1 Crook's piece was more than just a critique on that point; it raised questions about the extent to which Sahlins's model has applicability to the Roman world. This essay will focus on this key point and, it is hoped, will also contribute to the discussion on the use of social-scientific research in biblical studies.
Religion Studies; Philosophy
Keywords: SAHLINS; Marshall; biblical studies; clientelism; cognitive models; economic models; kinship; reciprocity; slave trade; social interaction; stone age

Embeddedness and the intellectual projects of economic sociology (English) - Krippner, Greta R. [b1] (analytic); Alvarez, Anthony S. [b2] (analytic) (Annu. rev. sociology, 2007)
In this review, we explore how the concept of embeddedness has shaped-and been shaped by-the evolution of the subfield of economic sociology. Although embeddedness is often taken as a conceptual umbrella for a single, if eclectic, approach to the sociological study of the economy, we argue that in fact the concept references two distinct intellectual projects. One project, following from Granovetter's (1985) well-known programmatic statement, attempts to discern the relational bases of social action in economic contexts. Another project, drawing from Polanyi's [1944 (2001), 1957 1977] social theory, concerns the integration of the economy into broader social systems. Critically, these two formulations of embeddedness involve different views of the relationship between the economic and the social. The implication is that the obstacles to theoretical integration in economic sociology, while not insurmountable, are greater than is typically acknowledged. (English)
Sociology
Keywords: GRANOVETTER; Mark; Réseau; action sociale; economic sociology; economic system; economy & society; economy/society; embeddedness; firms; marché; market; markets; network; networks; social action; système économique

India's Double-Movement: Polanyi and the National Alliance of People's Movements - Levien, Michael (Berkeley Journal of Sociology, 2007)
Through an examination of India's National Alliance of People's Movements (NAPM), the largest social movement alliance resisting neoliberal globalization in India, this paper attempts to theoretically reconstruct Polanyi's theory of (t the double movement" for the neoliberal age. Polanyi famously observed that early twentieth century liberal attempts to "dis-embed" the market from social controls created unprecedented social dislocations, leading to widespread protective (< countermovements "to "re-embed" the market within social constraints. I analyze the usefulness and shortcomings of Polanyi's formulation for understanding the current politics of neoliberal globalization. Specifically, I argue that Polanyi failed to explain how a "countermovement" is politically organized and did not develop an adequate theory for the anti-market countermovement he described. Using ethnographic observation ofNAPM's efforts to organize a national alliance against neoliberal globalization, I show how the nature of a "Polanyian" constituency creates previously untheorized obstacles for the effective political organization of a countermovement. These obstacles derive from inherent characteristics of a Polanyian constituency: 1) the economic and social diversity of—and therefore potential antagonism between—its prospective agents, who do not share similar relationships to the means of production, but only the common fact of being negatively affected by the market, and 2) the vastly different ways in which such diverse groups experience market displacements, leadings to a proliferation of single-issue movements whose commonality is hard to perceive and unity difficult to build.
Sociology
Keywords: India; constituents; double movement; globalization; international alliances; neoliberalism; protest movements; resistance movements; social movements

On the need for a heterodox health economics - McMaster, Robert (post-autistic economics review, 2007)
INTRO: This paper is a plea for greater cognizance of the errors of omission and commission committed by mainstream health economics, and the potential orientation in treating health and health care as (metaphorical) commodities that the unfettered influence of health economics may be prompting. Economic criticisms of mainstream health economics are evident, especially in the collection edited by John Davis (2001), but tend to be rather fragmented and lacking in credibility with our mainstream brethren. Contentiously, seeking the approval or otherwise of the mainstream is perhaps not as important as in other areas of economics, if indeed it is the case at all, but gaining the attention of other social scientists, medics, and policy makers may be of considerable consequence. The paper does not seek to speculate on strategies for addressing these bodies; instead it concentrates on the nature of the message.
Economics
Keywords: commodity fiction; fictitious commodities; health; health economics; political economy

Linking Political Economic Projects and Pension Systems in Europe: A Comparison of the Role of Occupational Pension Funds as Investment Actors in Three European Countries - Roumpakis, Antonios (Conference Papers – International Studies Association, 2007)
The paper explores the relation of different political economic projects and the development of pensions as a social right in three countries: Sweden, Germany and United Kingdom. It comprises three parts. The first part provides the conceptual framework, which combines a Polanyian perspective for the social embeddedness of markets with a three dimensional power theoretical approach in order to analyse modes of governance as practices of socio-economic regulation. The second part identifies the link between the macro-level of analysis i.e. different political economy logics and modes of governance and the meso-level of analysis i.e. the institutional paths that these countries have followed in developing their pensions systems and what used to be and currently is the role of occupational pension funds in them. This type of funds offers a prime example of how institutions that originally developed within a logic of social rights have now become actors in the economy. The decision-making of this new actor is however depended on the power relations between labour and capital in each country. The third part of the paper continues to show how the institutional paths have departed from their national spatio-temporal fix and have been re-embedded in the market-economy rationale of the neo-liberal project. The paper identifies a trend towards the ?equitisation? of pension funds as part of a broader process of marketisation of pensions as social right. The significance of the investment decision for pension occupational funds becomes crucial since funds are becoming major actors in the economic field. Their investment decision depends much on power relations between labour and capital ranging for example from social development (public houses, creation of jobs in the national environment) to the creation of profits through domestic and foreign financial markets. The paper concludes that pension occupational funds are re-embedded in a framework of choices, dominated increasingly more from the market economy rationale and the neo-liberal political project. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Germany; Great Britain; Sweden; capital; decision making; pensions; political economic analysis

Redistribution and Markets in the Economy of Ancient Mesopotamia: Updating Polanyi - Silver, Morris (Antiguo Oriente, 2007)
Economics
Keywords: capital formation; damkar/tamkaru; demand/supply curve; equivalence; redistribution

Society Must Be Protected - Turner, Mandy (Journal of Corporate Citizenship, 2007)
The multiple ways in which multinational corporations, financial and commodity markets and global trade feed into today's civil wars have recently become a key policy concern of the international community. Over the past five years, a number of initiatives have been launched, aimed at controlling the trade in conflict goods, ensuring good resource governance, advocating corporate social responsibility and promoting conflict-sensitive business practices. This article assesses these initiatives through the lens of Karl Polanyi's conception of the 'double movement', i.e. that capitalism automatically provokes protectionist impulses. It assesses the spaces created by neoliberal globalisation for illicit economic activity and conflict entrepreneurs, the relationship between the economy and conflict, and initiatives aimed at reducing conflict 'triggers'. It concludes that, in addition to the tension between commodification and social protection, there is another tension at work: between those who call for tough mandatory policies and those who promote best-practice guidelines.
Peace Studies; Business Studies
Keywords: Polanyi; business and conflict; capital market; commodification; corporate social responsibility; corruption; international business enterprises; international trade; protectionism; sanctions; social protection; social responsibility of business

Time–space intensification: Karl Polanyi, the double movement, and global informational capitalism - Ó Riain, Seán (Theory and Society, 2006)
This article advances the concept of “time–space intensification” as an alternative to existing notions of time–space distanciation, compression and embedding that attempt to capture the restructuring of time and space in contemporary advanced capitalism. This concept suggests time and space are intensified in the contemporary period – the social experience of time and space becomes more explicit and more crucial to socio-economic actors’ lives, time and space are mobilized more explicitly in individual and corporate action, and the institutionalization of time and space becomes more politicized. Drawing on Polanyi’s concepts of fictitious commodities and the double movement, and developing them through an analysis of work organization and economic development in the Irish software industry, the article argues that the concept of time–space intensification can add significantly to our understanding of key features of the restructuring of the temporal and spatial basis of economic development and work organization.
Sociology
Keywords: capitalism; double movement; fictitious commodities; social theory; time-space intensification

Understanding Global Capitalism: Passive Revolution and Double Movement in the Era of Globalization - Xing, Li; Hersh, Jacques (American Review of Political Economy, 2006)
This paper attempts to provide a framework for understanding the way globalization has reshaped the terrain and parameters of social, economic and political relations both at the national and global levels, and exerted pressure on the resiliency capacities of capitalism. It proposes to examine the ways social relations of domination and subordination are produced, reproduced and maintained while continuously undergoing transformations. Through conceptualizing the evolution of the capitalist world order in a historical perspective and by exploring the changes of relations brought about by the intensification of globalization since the 1990s, the objective is to generate a perspective for understanding such a process based on the application of Gramscian and Polanyian theoretical and analytical categories. The conclusion aims to convey that the process is contingent on both structures and agencies and it also produces the opposite result: i.e. reducing the legitimacy of capitalism's hegemony and especially limiting its resilient capacities.
Political Science
Keywords: capitalism; capitalist systems: political economy; colonialism; double movement; globalization; imperialism; international economic order; postcolonialism

Theorising globalisation's social impact: proposing the concept of vulnerability - Kirby, Peadar (Review of International Political Economy, 2006)
The concept of vulnerability was introduced into IR theorising by Keohane and Nye who saw it as one of the consequences of complex interdependence and it is being increasingly employed by IGOs to capture the impact of globalisation on society. However, the concept has been little used in the academic literature on globalisation, except in a descriptive sense. This article argues that the concept has the potential to fill a gap in the toolkit of the ‘new’ IPE, offering an analytical category that can capture the distinctive impact of globalisation on society more adequately than other concepts that are more widely used. The article begins by surveying how the concept has been used by Keohane and Nye and by IGOs. It then offers a definition and illustrates the application of the concept by describing some of the principal ways in which globalisation is increasing risk and eroding coping mechanisms. It goes on to argue that the concept of vulnerability captures in a fuller way the distinctive social impact of globalisation than do other concepts widely used in the IPE literature, examining in turn the limitations of the concepts of poverty/inequality, risk and insecurity. Finally, the article situates the concept of vulnerability within the social theory of Karl Polanyi, arguing that it expresses in the conditions of today's globalisation the threats to human livelihood from the inroads of the market that are widely referred to by scholars within the ‘new’ IPE, capturing better than do other concepts the key features of these threats as seen by Polanyi. The article concludes by proposing the concept of vulnerability as a core conceptual category for IPE scholars that offers the potential for the disciplinary field to generate more original insights into the social impacts of the political economy processes to the understanding of which it has made such a major contribution.
Political Science
Keywords: economics; globalisation; globalization; human security; industrial revolution; inequality; interdependence; international political economy; international relations; poverty; social impact; social problems; vulnerability

Towards a Polanyian Perspective on Fair Trade: Market-based Relationships and the Act of Ethical Consumption - Watson, Matthew (Global Society: Journal of Interdisciplinary International Relations, 2006)
Fair trade requires that developed country consumers engage in market-based transactions with developing country producers. Yet this is not market trade in any straightforward sense, because the purchase of fairly traded products brings consumers into two market relationships at the same time. One is the market relationship through which consumers buy the product itself, which enables them to act altruistically by consciously paying the price premium that the producer receives. The other is the market relationship through which consumers buy the socially reputable knowledge of having helped a distant stranger, which enables them to harness their ostensibly ethical consumption to a knowingly self-interested action. This latter relationship adds a new dimension to orthodox commodity fetishism. A Polanyian perspective is developed to investigate the way in which fair trade reworks the commodity fetish. This serves as a prelude to an extended discussion of the moral status of the behavioural motivations that underpin fair trade consumption.
Political Science; International Relations
Keywords: commodity fetishism; comparative studies; economic consumption & ethics; globalization; international trade; relationship marketing; unfair competition

On markets and morality: Revisiting Fred Hirsch - Carvalho, Luís Francisco; Rodrigues, João (Review of Social Economy, 2006)
This article argues for the continuing relevance of Fred Hirsch's The Social Limits to Growth (1976), valued as a critical analysis of the consequences of markets on the moral fabric of society. Two concepts that are fundamental to Hirsch—the commercialization bias and the depleting moral legacy—will be scrutinised. We further claim that this book, by emphasizing the tendency to market expansion and the corresponding commodification of increasing spheres of social life, while simultaneously acknowledging its adverse consequences on the motivational appeal of social and moral norms, offers insights that justify revisiting it.
Economics
Keywords: HIRSCH; Fred; double movement; markets; morality; neoliberalism; second great transformation; social economy

Globalization and contestation: A Polanyian problematic - Munck, Ronaldo (Globalizations, 2006)
The Polanyian problematic presents us with a unified, complex, and dialectical means to interpret globalization and its social contestation by diverse social and political forces. For Karl Polanyi (1886–1964), globalization as we know it would probably be conceived of as an extension of the ‘one big self-regulating market’ he discerned in his day, while his belief that ‘simultaneously a counter-movement was afoot’ provides an interpretative lens to examine the various facets of the counter-globalization movement. The Polanyian problematic of modern history as a ‘double movement’, whereby market expansion and social protection respectively lead phases, provides a useful antidote to all forms of economic reductionism when dealing with globalization on the one hand and political voluntarism with regard to contestation on the other. Basically, globalization is a human construct, and it can thus be deconstructed by society.
Sociology; Political Science
Keywords: Polanyi problem; countermovement; globalization

The Dialectics of Design - Jenkins, Barbara (Space & Culture, 2006)
The popularity of deconstructivist architecture around the world has invited controversy over the sensationalist design of these buildings. New urbanists, in particular, have criticized decon architecture as alienating and disorienting. From a historical perspective, this opposition between deconstructivists and new urbanists is the latest in a long line of debates over what constitutes "good design." Using a political-economy approach based on the work of Karl Polanyi, this article examines a centuries-long dialectic in design ideology between those who seek to embed design in social mores and those who attempt to "disembed" it from oppressive discourses. This analysis shows that the dialectic of design movements is intintately connected to the development of capitalist markets.
Architecture; Political Science
Keywords: capitalism; cities & towns; cultural studies; deconstructivism; deconstructivism (architecture); dialectic; disembeddedness; embeddedness; good design; modern architecture - 20th century; new urbanism; political economy

Between Aristotle and the Welfare State: The Establishment, Enforcement, and Transformation of the Moral Economy in Karl Polanyi's The Great Transformation - Akturk, Sener (Theoria: A Journal of Social & Political Theory, 2006)
The article examines the transformation of the moral economy in the book "The Great Transformation," by Karl Polyani. Polyani's work has been criticized for having an anti-democratic, Aristotelian, and aristocratic undertones. However, the author claimed that it has been misinterpreted and a communitarian-liberal debate has been brought to clarify the nature of moral economy.
Political Science
Keywords: Great Transformation; The (Book); criticism; democracy; economic policy

The Relationship between Economics and Sociology: The Contribution of Economic Sociology, Setting out from the Problem of Embeddedness - Rizza, Roberto (International Review of Sociology, 2006)
s essay aims to analyse the most recent acquisitions in economic sociology, setting out from the problem of embeddedness. Firstly, the contribution offered by Mark Granovetter shall be illustrated, demonstrating how the interpretation proposed by this scholar is concentrated on a structural-relational perspective that tends to trace the explanation of economic phenomena to a theory of social networks. In order to enrich and integrate this approach, the contribution offered by the new-institutionalist perspective in contemporary economic sociology will be emphasised, which has focused on the social construction of economic institutions. This current has underlined, on the one hand, the cognitive dimension of embeddedness, related to the way in which the uniformities structured by mental processes limit economic reasoning, and, on the other, the cultural dimension of embeddedness, concerning the role of collectively shared representations in the formation of economic goals. It will be concluded by illustrating the acquisitions of some theoretical perspectives linked to the polanyian tradition that have developed a 'plural' conception of economy, founded on the emphasis of socio-regulative principles, such as those of exchange, redistribution and reciprocity, which, in becoming hybrid, give shape to variable and historically anchored economic worlds. The concept of embeddedness roots historically and transmits a vision of economic processes as inseparable from noneconomic institutions
Sociology
Keywords: GRANOVETTER; Mark; economic research; economic sociology; embeddedness; industrial management; social sciences; socioeconomic factors; socioeconomics

Keynes and Polanyi: the 1920s and the 1990s - Polanyi Levitt, Kari (Review of International Political Economy, 2006)
Political Science
Keywords: KEYNES; John Maynard; 1883-1946; international political economy

The state we are in: insights from autopoiesis and complexity theory - Gregory, Amanda (Management Decision, 2006)
Purpose - Following Polanyi, this paper aims to suggest that the Industrial Revolution marked a break-point between pre-industrial society (characterised by integration) and industrial society (characterised by differentiation). Design/methodology/approach - As a conceptual paper, the focus is on drawing out the implications of Luhmann's application of the theory of autopoiesis to industrial society. This discussion leads to critical reflection on the state we are in and the active role we can each play in bringing about change. Findings - Differentiation, without an overall co-ordination and control function within society, has led to the sub-systems (and organisations) becoming self-serving or pathologically autopoietic. Society has a capacity for self-observation, through such mediums as the mass media. Alarm at the apparent increasing rate of change in both social and ecological systems reported by the mass media appears to be drawing us towards a second break-point. The outcome of this revolution, should it come about, is impossible to predict but descent into a new "dark age" is an option as is the re-integration of economic activity with social, religious and political functions. Luhmann's autopoiesis provides a convincing explanation for how society is structured and observing the implications of this. The role of the mass media as an observing system and in bringing information about change to society's attention is emphasised. Practical implications - The paper seeks to provide an explanation for how society is structured and demonstrate how society appears to be passively observing the implications of this. Proposals for both restructuring and the actions we, as active citizens and organisational members, can take to redress our current state are advanced. Originality/value - The paper brings together ideas from a diverse range of fields (including autopoiesis, complexity theory, and systems) and applies them to a highly significant topic.
Business; Systems Studies
Keywords: autopoiesis; complexity theory; economic history; industrial revolution; mass media; social history; social systems

Editor's Letter - Lomnitz, Claudio (Public Culture, 2006)
This article previews this edition of "Public Culture" and focuses on Karl Polanyi's theories on capitalism. Polanyi believed in trade liberalization and felt that market regulation is the principal obstacle to collective prosperity. He thought that unregulated markets could bring an end to poverty, and would resolve the chronic dislocation, inequality, and vulnerability that have marked capitalism from its inception. Polanyi demonstrated that market liberalization was only achieved through concerted state intervention.
Anthropology
Keywords: capitalism; free trade; intervention (federal government); poverty; public culture (periodical)

Is There an Opportunity to Establish the Social-Capitalism in the Post Socialist Transition? - Losonc, Alpar (Panoeconomicus, 2006)
Recently Claus Offe has put the question that concerns the fate of the European model of social capitalism: can the model of social capitalism survive the European integration in the context of certain contemporary tendencies? Offe has presupposed that the mentioned model is challenged by the processes of globalisation and the integration of the post socialist countries into the European Union. The working hypothesis of the article is that there is an opportunity to provide a coherent answer to this question. The article consists of two parts. In the first part the author starts with the Polanyi's socio-economic theory and emphasises the importance of this approach for the analysing of the tendencies of capitalism in Western Europe and in the post socialist countries. The author argues that with the Polanyi's theory we are able to explicate the forms of the embedded liberalism in Western Europe after 1945 and the orientation of non-embedded neo-liberalism and the functioning of the workfare state after the crisis of the Keynesian welfare state. Despite the tendencies of the globalisation projected by neo-liberalism, the central element of the social capitalism, namely, the welfare state, remains with the dimensions of the continuity. In the next part the author points out that there is an asymmetrical structure between the Western-Europe and non-Western part of Europe concerning the socialisation of capitalism. The neoliberalisation in accordance with the model of the transfer of ideal-type of capitalism is more strongly implemented in the countries of transition. In addition, the mentioned theoretical approach provides opportunities to explain the failures of implementing of neo-liberalism in the post socialist countries. On the basis of the endorsing of the socio-economic aspects we can address the issue pointed out by Offe.
Economics
Keywords: consumer economics; education and training; health; poverty; property rights; provision and effects of welfare programs; social security and public pensions; socialist institutions and their transitions; socialist systems and transitional economies: political economy; welfare; well-being; and poverty: government programs

Commercialisation, inequality and the limits to transition in health care: a Polanyian framework for policy analysis - Mackintosh, Maureen (Journal of International Development, 2006)
The effects of commercialised health care in embedding, exacerbating and legitimating social and economic inequality are at the root of widespread and recurrent resistance to commercialisation in health. In low income developing countries suffering generalised poverty, and notably in Sub-Saharan Africa, liberalisation of largely unregulated clinical provision has created a substantially informalised, fee-for-service primary health sector which is exclusionary, low quality and under stress. This article argues against a policy assumption that health systems constitute a sector that can benefit like other commodities from liberalisation. Health care is better understood as a ‘fictional commodity’ in the Polanyian sense: inappropriate for full commodification, producing intensely perverse effects when provided on competitive markets, and therefore requiring planning and social constraint. If managed effectively, integrated health systems—like redistributive land reform and effective labour protection—can support a broader economic transition that avoids extremes of inequality; conversely if treated simply as a transitional sector, health systems can make exclusion and inequality much worse. Copyright © 2006 John Wiley & Sons, Ltd.
Economics; Political Science
Keywords: Africa; Sub-Saharan; economic structure; equality; health care reform; liberalism; medical care; medical policy

Governing the Market: The "Political" and the "Economic" in the Restructuring of the "Third World" - Makki, Fouad (Conference Papers – International Studies Association, 2006)
My intention in this paper is to rethink the central contentions of "Globalization Theory" with respect to the relationship of the "state" to the "economy." I will do so via a consideration of recent discussions of the formation of the modern states system within the discipline of International Relations, and Karl Polanyi?s suggestive notion of the "double movement" presently enjoying a revival in sociological studies of the conjuncture of the 1990s. The paper concludes with reflections on how these critical reflections might make it possible to gain a betterappreciation of the current neoliberal restructuring of the erstwhile "Third World." PAT.-Conference Proceeding
Political Science; Sociology
Keywords: economic structure; economics; globalization; international markets; international trade

Food Sovereignty vs. the Corporate Food Regime - McMichael, Philip (Conference Papers – International Studies Association, 2006)
In the twenty-first century, the Polanyian trinity of fictitiouscommodities (land, labor and money) cannot be realised through thetwentieth-century double movement. The regulation of money is no longervested in the state per se, but in instrumentalities such as the IMF, whosetask has become a generalized imperative to reproduce (corporate) moneythrough expending labor and land across the world with decreasing regardfor their sustainability. The construction of a 'world agriculture,'deepening the instrumental use, misuse, and abandonment of natural andsocial resources, unfolds within this general imperative. This paper arguesthat the world-wide food sovereignty movement is the most direct symptom ofthis socio-ecological crisis, embodying a diversity of responsescorresponding to the re-spatialization of social and economic relations inthe corporate food regime. As an expression of the corporate food regime,it reveals both the immanent, and the historical, conditions governing thepolitics of capitalist development under the neo-liberal project. ..PAT.-Conference Proceeding
Political Science
Keywords: commercial products; economic policy; international economic assistance; international economic relations; international studies; sovereignty

The Poverty of the Global Order: Limits of the North/South Division - Mohan, Dia; McMichael, Philip (Conference Papers – International Studies Association, 2006)
Development in the global order is represented in economically reductionist, and in impoverished, terms. The latter refers to the global reproduction of material inequality through the progressive appropriation of alternative visions of development. We argue that the legitimacy of the global order, while represented in terms of 'economic progress,' depends on the progressive naturalization of its epistemological foundations. Here, solutions to the crisis of development become methods of social control through which the dominant visions of what count as viable futures are reproduced and regulated. We critique efforts to humanise development (eg, World Bank, Amartya Sen) as evidence of developmentalism's epistemological crisis. Karl Polanyi's distinction between 'formal' and 'substantive' economy allows us to transcend the reductionism of the scarcity paradigm and revalue difference as the foundation of equality. We consider examples of substantive economy, which realise equality through strategic sovereignty and representational power, in collective and individual terms. Among other such initiatives these represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects both development studies and international studies. Present divisions of the world must be understood as the impoverished outcomes of a market epistemology's construction and development of inequality. ..PAT.-Conference Proceeding
Political Science; International Studies
Keywords: economic development; international organization; international relations; reductionism; social control

An institutionalist perspective on the future of the capitalist world-economy - Özçelik, Emre; Özveren, Eyüp (Journal of Economic Issues, 2006)
The term world-economy in our title must have already given a hint to the careful reader of our purpose in writing this paper: We intend to bridge institutional economics with world-systems analysis in order to enhance the global applicability of the former. World-economy is a term used by Fernand Braudel and Immanuel Wallerstein and means a space defined by the existence of a single division of labor (coexistent with multiple States) whereas world economy would indicate the arithmetic summation of national economies each of which ... In this paper, we elaborate Polanyi's concept of embeddedness so as to construct an institutionalist framework to understand the contemporary world-economy. We contend that embeddedness can be deployed to analyze the so-called "global governance model" (GGM) as the most recent liberal recipe.
Economics
Keywords: embeddedness; global governance model; world-economy

The Market, Mind and Rationality. From Vienna to Paris and Back - Rotstein, Abraham (Revue européenne des sciences sociales, 2006)
The mention of the great city of Vienna conjures up the many legacies of music, art and philosophy which it nurtured. But as important as any of these is the more prosaic legacy of the Austrian economists ranging from C. Menger to F. von Hayek. And for some, Vienna may conjure up as well, the debate that K. Polanyi had with these economists in the 1920s. However paradoxical it may seem, it was by virtue of this debate, carried on directly and indirectly over a lifetime, that Polanyi was first and foremost an Austrian, or rather an Austrian «in mirror image ». This was true not only by virtue of the years of his life and his work in Vienna, but more so because he was drawn into and remained a protagonist in the debate around the fundamental issues first raised by the Austrian economists. Menger and his followers E. von Bohm-Bawerk, and L. von Mises had established and diligently pursued much of the agenda of the debate. F. von Hayek was the important representative of this school in recent decades. The particular topic launched by von Mises in 1920 was whether a socialist economy was at all viable without the direction provided by market prices. Regulated or administered prices were bound to lead to economic confusion and the misallocation of resources he maintained.
Economics
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; MISES; Ludwig von; history of economic thought; regulation; socialist economy

Globalization and Declining Welfare State: The Case of Social Insurance in Turkey - Yasar, Yavuz (Conference Papers – International Studies Association, 2006)
The norm has been rapidly moving from the managed markets under the welfare state back to self-regulating market with the rise of contemporary version of globalization. Today?s globalization is characterized by neoliberal economic policies such as privatization, deregulation, and limited government intervention–despite the growth of government–in open economies. In such an environment, social insurance, one of the defining characteristics of the welfare state, has become a great fiscal burden and not surprisingly on the neoliberal agenda of the institutions of global order such as IMF and the World Bank lately. Solutions required by the neoliberal agenda involve privatization and deregulation of social insurance systems especially in developing countries such as Turkey. Despite the fact that the welfare state played a significant role between 1960 and 1980, social insurance has become one of the few safety nets left for many since the beginning of neoliberal policies in Turkey. Now with the increasing pressure from IMF, Turkish government has been actively working on market oriented solutions for financing health insurance, social security and pensions. However, this trend undermining social insurance jeopardizes at least two, if not more, important issues: sovereignty of the state and future of welfare state as an insurance against the unwanted consequences of self-regulating markets. These two issues are investigated and alternative social policy measures are evaluated in the context of Karl Polanyi?s theory of ?double movement.? ..PAT.-Conference Proceeding
Political Science
Keywords: deregulation; economic policy; economics; globalization; privatization; welfare state

Human Freedom and the 'Reality of Society': Origins and Development of Karl Polanyi's Ideas during the Interwar Period - Thomasberger, Claus (History of Economic Thought, 2005)
Karl Polanyi's most famous book, The Great Transformation, contains several ideas and theoretical notions which are at the heart of long-lasting controversies throughout the social sciences. Categories such as "double movement," "embeddedness," "disembedding," "market society," or "social freedom" have proved to be fruitful notions not only in anthropology, but also in sociology, political sciences, and economic history. The recent three volume publication of Karl Polanyi's writings during the interwar period–including published articles and unpublished manuscripts–opens for the first time the possibility to have a closer look at the origins and the development of some of Polanyi's concepts during the interwar period. In the paper titled "Human Freedom and the Reality of Society–Origins and Development of Karl Polanyi's Ideas during the Interwar Period," Claus Thomasberger addresses Polanyi's idea of a polar relationship between human freedom and the "reality of society." The paper offers new insights, discussing central questions which are crucial to the understanding of Polanyi's reasoning: Where are the roots of his central categories? What influence did Marx have on Polanyi's thinking? What is the relationship between Polanyi's approach and the Austrian School of Economics? Is it appropriate to read his work in terms of an institutional approach? In order to give an answer to these questions, the paper goes back not only to the 1930s, but to the 1920s as well. As it demonstrates, Polanyi had already developed the core ideas of his thinking in Vienna, participating actively in the discussions between the Austrian School of Economics and Austro-Marxism about the possibilities of a socialist society.
Economics; Philosophy
Keywords: history of economic thought: individuals; reality of society

Massacre of the Doves?: Interpreting Israel's 2003 Elections - McMahon, Sean F. (British Journal of Middle Eastern Studies, 2005)
This article argues that Israel's 2003 elections are best understood as a deeper embedding of neoliberalism in the Israeli polity. It is argued that the most accurate characterization of the elections is as an articulation of Polanyi's Phase I of the double-movement. The argument is developed in four stages. First, the Israeli elections are understood as a local reaction to the multilayered processes of globalization. The Israeli state and its elections are located in the neoliberal ideology which underwrites the phenomenon broadly defined as globalization. Second, the election results are reviewed. Third, the dominant interpretations of the elections are critically examined. Specifically, representations of the elections as a defeat of the parties of peace and as a rebuke of Sephardim/ultra-Orthodox influence in Israeli government are interrogated. Fourth, the coalition negotiations of February 2003, the constitution of Israel's 30 th government and some of the initiatives undertaken by Finance Minister Benjamin Netanyahu are explicated through deployment of Polanyi's double-movement framework.
Political Science; Area Studies
Keywords: Israel - politics and government; double movement; elections; globalization; neoliberalism

Fighting standards with standards: harmonization, rents, and social accountability in certified agrofood networks - Mutersbaugh, Tad (Environment & Planning A, 2005)
In this paper I explore the remaking of globalized standards through harmonization, and its impact upon certified-organic and fair-trade agrofood networks. I focus on certification standards and discuss four shifts associated with globalized standards (an increased importance of multilateral institutions, changes to standards language, displacement of network-specific standards, and a shift away from relational standards). It is then argued, with reference to value-chain rent theory, that the shift to globalized standards has transformed rent relations in ways that benefit certain actors (that is, retailers) and imperil the earnings of others. In brief, globalized standards increase the costs of standards compliance, the full burden of which falls upon immiserated producers, to the point at which farmers see little economic advantage to certified-organic and fair-trade production. I then examine social-accountability standards that seek to `fight standards with standards' by championing the consolidation of strong labor and environmental protections under a single label. The study suggests that a single-label strategy can be successful, yet must struggle to overcome a Polanyian double bind, for, in order to build broad coalitions necessary to extend the reach of protective standards, the coalitions must include corporate interests that prefer weaker, contract-based standards.
Geography
Keywords: agricultural accounting; agricultural industries; applied ecology; environmental policy; retail industry; retail stores

Polanyi, Chayanov, and Lessons for the Study of the Informal Sector - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2005)
This article offers an alternative institutional economic approach to the informal sector by interpreting the works of economists Karl Polanyi and Alexander Vasil'evich Chayanov. Far from withering away, the informal sector continues to occupy an important place within economies in general and within the so-called developing economies in particular. Relatively speaking, the informal sector is inferior and more spontaneous, if not actually incomplete. Within the informal sector there are numerous small competitive firms, free entry, market-determined factor and product prices, together with a concentration of petty retail and services, labor-intensive production processes, and low productivity. According to Polanyi, one major drawback of mainstream economics is the insistence that the market mode is synonymous with the economy, and, under the weight of this assumption, formalistic economic analysis is assumed to be universally applicable to the study of all times and places. As a consequence, mainstream economists see markets where there are none.
Economics
Keywords: CHAYANOV; Alexander V.; POLANYI; Karl; 1886-1964; economic sectors; economics; informal sector (economics); labor productivity; labour productivity; small business

The role of the UN Millennium Declaration and of the World Economic and World Social Forum for Structural Change - Abrahamson, Hans (Conference Papers – International Studies Association, 2005)
Globalisation can in a polanyian sense be understood as a double movement. Societal reaction to the shortcomings of the corporate driven process of globalisation from above (the first movement) creates a counter movement from below (the second movement). The relations between different actors within the political landscape and the area of tensions between the two movements are characterised by the gramscian war of position and its power struggle over the hegemonic discourse. At times the constellation of political forces permits an institutionalised state of equilibrium built on converging interests between different social forces. During the Westphalia era with its nation-state project the social contract constituted the base for such an historic compromise. The end of the cold war and strengthened process of corporate globalisation has eroded the base for this social contract on a national level increasing development gaps not only between countries but also within countries. This paper addresses the question of room for manoeuvre for structural change in order to deal with present challenges within the Global Political Economy. It discusses how possibly the UN Millennium Declaration could be used in the ongoing discursive war of position between actors at the World Economic Forum in Davos (representing the first movement) and actors at the World Social Forum in Porto Alegre (representing the second movement) in order create a social base for a new social contract albeit on the global level. Such a discussion also illustrates present potential of these arenas in contributing to a future global political economy of peace and development.
Peace Studies; Development Studies
Keywords: United Nations; World Economic Forum; economics; forums (discussion & debate); globalization; hegemony; political science

Bridging boundaries and Mending Fences? Finding "community" in transboundary conservation approaches - Hoon, Parakh (Conference Papers – International Studies Association, 2005)
The article presents the conference paper titled "Bridging boundaries and Mending Fences? Finding community in transboundary conservation approaches" prepared for the "Annual Convention of the International Studies Association" held in Honolulu, Hawaii. It discusses the implementation of the Community Based Natural Resource Management in Botswana in early 1990s. It examines the contemporary applications of the idea of embeddedness which was coined by intellectual Karl Polanyi as an analytical and ideological foil to the notion of self-regulating markets.
Political Science
Keywords: Botswana; conservation of natural resources; conservation projects; international relations; self-regulating market

Gramsci, Polanyi and Impressions from Africa on the Social Forum Phenomenon - Bond, Patrick (International Journal of Urban and Regional Research, 2005)
The rise of the Social Forum phenomenon has been heartily welcomed, partly so as to unite diverse discourses of anti-neoliberal and anti-imperialist resistance under a common banner. There are debates worth flagging, however, that draw our attention to political philosophies (typically binary statist versus anti-statist disputes), visions of agency (typically networked movements versus parties), and potentials for revolutionary processes to emerge within ‘civil society’. In the spirit of Polanyi, many South Africans and other Africans are working on ‘decommodification’ strategies that range from particular sites of project-level struggles to national, regional and international advocacy. But we must be conscious, as well, of warnings by Gramsci about the long march through a civil society often co-opted to support state and neoliberal projects. The merits of African intellectual engagements with radical social movements have been shown in sites such as South African cities, but the African Social Forum awaits further opportunities to welcome allied researchers and academics. As the World Social Forum comes to Africa in 2007, Marcuse’s hope that the constituent movements begin to coalesce around a program is timely. However, this is likely to emanate more from intra-sectoral networks rather than from multidisciplinary moments such as the WSF itself. La montée du phénomène des Forums sociaux a été accueillie chaleureusement, en partie comme manière d’unifier sous un même drapeau les multiples discours de la résistance anti-néolibérale et anti-impérialiste. Certains débats éminents attirent pourtant l’attention sur des philosophies politiques (généralement des oppositions binaires étatistes/anti-étatistes), des visions de l’intermédiation (en général, mouvements interconnectés/partis) et des processus révolutionnaires susceptibles de naître au sein de ‘la société civile’. Dans l’esprit de Polanyi, nombre d’Africains, du Sud et d’ailleurs, s’emploient à des stratégies de ‘démarchandisation’ couvrant à la fois sites de conflit particuliers liés à un projet et plaidoyers aux niveaux national, régional et international. Toutefois, il ne faut pas oublier les avertissements de Gramsci pour qui la longue marche passant par la société civile risquait d’être cooptée afin de soutenir des projets gouvernementaux ou néolibéraux. Si les engagements d’intellectuels africains aux côtés de mouvement sociaux radiaux se sont révélés bénéfiques dans des cas tels que les villes d’Afrique du Sud, le Forum social africain espère d’autres occasions de rallier chercheurs et universitaires. Comme le Forum social mondial se tiendra en Afrique en 2007, l’espoir de Marcuse — de voir les mouvements constitutifs s’unir progressivement autour d’un programme — est d’actualité. Cependant, cette évolution viendra plus probablement de réseaux intra-sectoriels que d’élans multidisciplinaires comme le FSM.
Geography; Political Economy
Keywords: GRAMSCI; Antonio; 1891-1937; South Africa; decommodification; development studies; geography; social forum phenomenon

From flows to violence - Kalb, Don (Anthropological Theory, 2005)
Recent globalization theory reflected a chain of world historical events since the end of the Cold War. Globalization theories were tools for the making of political alliances between market liberals and political, liberals. From the mid-1990s a broad range of institutionalist social science programs showed that globalization outcomes were often better explained by institutional logics (including cultural ones) than by global flows per se. This is, among others, illustrated by the debate on global inequality data. The emerging debate on empire and imperalism is discussed as a logical offshoot of the globalization discussion just as the phenomenon itself is seen as a likely outcome of an epoch of market-driven globalization. Globalization was predicated on the emergence of a US-led transnational western state structure on behalf of the transnational capitalist class based in finance and the large corporations. Territory and space have become more important rather than less, but the explanation of regional trajectories must now be located more firmly in the interaction between local and global structures. This leads to a new agenda in the social sciences: one oriented toward common interdisciplinary programs with a limited range of core questions - about state formations, class formations, mobilizations, claim making, and associated cultural processes. Programs should be more theory driven, comparative, and in search of explanations of divergent spatial and temporal outcomes of universal process.
Anthropology
Keywords: alliances (international relations); civilization; cultural policy; dual polarization; empire; globalisation; globalization; imperialism; international relations; social sciences & state; transnational capitalist class

Beyond Boganism - Brown, Beth; Brown, Doug (Journal of Popular Culture, 2005)
The article analyzes the global economy by subjecting it to an interpretive scheme derived from popular culture Boganism, an Australian colloquialism or street slang used by teenagers. Boganism, the social phenomenon of being both unaware and irresponsible, is the result of a particular type of human abandonment. This abandonment is linked to the new hypercapitalism of globalization. The article will establish the structural roots of boganism, examine the case of the abandonment of U.S. youth, and conclude with reform recommendations necessary to shift us beyond boganism to a culture of sustainability. Karl Polanyi, a Hungarian economist, argued a half century ago that the birth of capitalism meant the emergence of what he called the disembedded economy. Polanyi's essential problem with capitalism, when it emerged in the sixteenth century, was that it creates a society in which everyone is dependent on markets to meet their basic needs. The pace of life has clearly increased with the maturation of capitalism and industrialism. But with the high-technology revolution, accompanied as it has been by the globalization of capitalism, what is happening is acceleration of everyday life, the economy, market transactions, and much more. Stratification: relationships of supra- and subordination, relations of domination and injustice. These are the social dimensions and institutional, structural relations between people and groups that have played defining roles in social, political, and economic analysis over the last three centuries of industrialism. Categories of stratification include classism, racism, statism, and sexism, and others. Along with these, we can add boganism.
Political Science; Economics
Keywords: capitalism; disembedded economy; disembeddedness; globalization; popular culture; socioeconomics

Labour and Globalization: Towards a New Internationalism? - Ramasamy, P. (Travail et Mondialisation: Vers un nouvel internationalisme?, 2005)
A one-dimensional view of capitalism inevitably leads to the conclusion that labour is in a state of deep crisis. However, if we examine globalization as a contradictory process, then it is possible to regard its relationship with labour as a transformative one. In this context, the decline of trade union density in developed countries and the rise of new forms of trade unionism in selected countries of the South, illustrate the contradictory relationship between labour and capital. In accordance with Marx, capitalist expansion not only does away with old forms of labour organizations, but has the tendency to create new forms of labour resistance. Similarly, Polanyi argues that attempts to disembed the economy (return to free market enterprise) from the rest of society will be resisted by societal forces. (English)
Political Science
Keywords: capitalism; developed countries; embeddedness; free enterprise; globalization; international trade; labor; labor unions; labour; labour unions; political doctrines

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Anthropology; Cultural Studies
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world

The fruits of intellectual production: economic and scientific specialisation among OECD countries - Laursen, Keld; Salter, Ammon (Cambridge Journal of Economics, 2005)
This paper brings together data from 17 OECD countries on scientific publications, patents and production, to explore the relationship between scientific and economic specialisation for 17 manufacturing industries. Since Marx, there has been a fundamental debate in economics about the link between science and the economic system. Marx argued that the needs of production shape scientific developments and that science has become a factor of production, whereas Polanyi argued that developments in science are largely independent of the economic sphere. Using a panel data model and econometric estimations at the industry level, the paper derives some hypotheses from the two positions and finds that, while the overall evidence on the link between national production and scientific specialisation is mixed, it is important to have high levels of relevant to-the-industry scientific strength per capita in order to be specialised in science-based industries.
Economics
Keywords: bibliometric data; econometrics; industries; international economic specialisation; manufactures; manufacturing industries; patent laws & legislation; patent suits; science & industry; scientific specialisation

Engendering Charismatic Economies: Pentecostalism, Global Political Economy, and the Crisis of Social Reproduction - Barker, Isabelle V. (Conference Papers – American Political Science Association, 2005)
Pentecostalism is the fastest growing religion in the world today. A number of explanatory theories exist, but in this paper, I hone in on the nexus between economic restructuring and Pentecostalism to explore this extraordinary expansion. Bringing together the work of feminist political economists and of Karl Polanyi, I argue that neo-liberal globalization threatens mechanisms for meeting social reproductive needs. Neo-liberalism cannot meet these needs on its own, and I suggest that Pentecostalism addresses these gaps, effectively embedding neo-liberal economic policies. It does so by facilitating norms and practices on the part of individual adherents to provide for the care work required for human reproduction; to adopt norms required of a neo-liberal labor force; and, to embrace the kind of transnational social identity that is compatible with labor migration and global markets. ..PAT.-Conference Proceeding
Political Science
Keywords: CHRISTIANITY; GLOBALIZATION; Globalization; PENTECOSTALISM; Pentecostalism; Polanyi; Karl; 1886-1964; RELIGION & sociology; feminism; feminist political economy; neo-liberalism; social reproduction

José Bové and the Globalisation Countermovement in France and Beyond: A Polanyian Interpretation - Birchfield, Vicki (Review of International Studies, 2005)
This article illustrates the continuing salience of Karl Polanyi's The Great Transformation (1944) by employing two of its central concepts, fictitious commodities and the double movement to interpret the globalisation countermovement and one of its most important figures, José Bové. I explain the transformation of José Bové from rural sheep farmer to French folk hero and global activist and analyse the extent to which his rhetoric and political actions are congruent with Polanyi's key insights. Arguing against the media characterisation of Bové as protectionist, I show that this misrepresentation conceals the larger ideological threat his movement poses to institutionalised politics and neoliberal hegemony. The political vision underlying Bové's symbolic media tactics and articulated in his book, Le Monde n'est pas une Marchandise, reveals significant manifestations of Polanyi's chief intellectual legacy - an unparalleled critique of economism and market society. An often neglected question in Polanyian scholarship is whether or not it is possible to have a market economy without becoming a market society. A more careful analysis of Polanyi's thought sheds light on this key issue while the empirical analysis of Bové's movement reveals its implications for French society and the broader globalisation countermovement.
Political Science
Keywords: capitalism; commodities; countermovement; economic globalization; economic liberalism; free market economies; globalization; international economics; political movements; social movements

Two heterodox economists: Neurath and Karl Polanyi - Giandomenica, Becchio (MyScienceWork Working paper No. 11/2005 Università di Torino 1, 2005)
This paper is based on the idea that between the 1920s and the mid-1930s in Vienna there were two forms of heterodox economic theory: the Austrian economic school headed by Ludwig von Mises and another interesting form of heterodox economics opposed to the Austrian school (above all politically) and pursued by various social thinkers (Otto Neurath, Karl Polanyi, Otto Bauer, Felix Schaffer, Felix Weil, Jacob Marschak). They were engaged in the debate on the possibilities of a planned economy: Austrian socialist economists proposed a sort of ‘third’ way between pure capitalism (whose Viennese stronghold was the Austrian economic school) and orthodox communism à la Kautzsky (deeply rooted in Germany). This paper focuses on the affinities between Neurath and Polanyi’s economic thought: despite some major differences between them, they shared a common philosophical background on which they founded their heterodox economic theory. After a brief historical premise, there is a first part, which deals with the debate on a planned economy and a second part, which deals with the influence of Neurath on the Polanyi’s vision of the faults of the neoclassical economic theory: the concepts of “disembedded economy” and of the so-called “economicistic fallacy”. NEURATH AND POLANYI IN VIENNA Neurath described himself as a ‘social engin
Economics; Philosophy
Keywords: Austrian economic school; NEURATH; Otto; economics; heterodox economics; philosophy; political science

A New Middle East? Globalization, Peace and the Double Movement - Guy Ben-Porat (International Relations, 2005)
The rise and fall of the New Middle East (NME) cannot be separated from wider global developments and must therefore be studied in relation to them, in both their ideational and material aspects. The ideological background of the NME has drawn upon the ideology of globalization and shares its underlying tenets of rationality, professionalism and virtues of market economy. In the early 1990s a discourse of globalization was set in motion, highlighting economic and technological development that supposedly rendered territory and territorial disputes marginal or irrelevant. The NME, supported by Israel's business, political and academic elites, advocated liberal economics and peace as a solution to the region's problems. But Israeli elites have failed to turn the idea of the NME into a hegemonic concept, as this attempted liberal hegemony invoked a Polanyian double movement that undermined the peace process. The scenario of the NME and the trade-off between territorial integrity and promised regional prosperity not only met fierce ideological rejection, but, perhaps more importantly, failed to persuade the many more skeptics. Limited in its appeal and lacking sufficient legitimacy, the peace process was exposed to derailment by extremists, locking the region into cycles of violence.
Political Science; International Relations
Keywords: Middle East; capitalism; double movement; economic development; globalization; ideology; international relations

The Transition between the Old and New Traditional Economies in India - Rosser, J. Barkley; Rosser, Marina V. (Comparative Economic Studies (Palgrave), 2005)
We extend Karl Polanyi's traditional economy concept to modern economies with advanced technology that are embedded in a traditional socio-cultural framework. This is the New Traditional economy, seen in parts of the Islamic world and with the Hindu nationalist movement in India. However, rural India is also the largest repository of the Old Traditional economy with its Hindu caste and jajmani system of reciprocal labour relations. The changes in India's complexly mixed economy, with its increasing market and strong planned elements, constitute a transition from the Old to the New Traditional economy. We shall consider this transition both ideologically and systemically.
Economics
Keywords: Hinduism; India; caste; economics; labor; labour; markets; nationalism; new traditional economy; old traditional economy; transition

Constructing opposition in the age of globalization: the potential of ATTAC - Birchfield, Vicki; Freyberg-Inan, Annette (Globalizations, 2004)
This article examines the movement ATTAC and assesses its potential to function as a vital part of the emerging global opposition to neoliberal globalization. We analyze the agenda of the movement and assess its coherence, both in terms of policy evaluations and prescriptions and in terms of the fit of the movement's organizational structure with its substantive mission and official aims. To this end, we explain the emergence and stellar rise of the movement, compare the particularly successful nation-wide organizations of ATTAC in France and Germany, and examine the movement's transnational activities. We find ATTAC to be coherent in terms of agenda as well as organizational practices and to make a laudable effort to reflect its agenda of democratic empowerment in its political praxis. Acknowledging the enormous challenges faced by transnational civic opposition, we nonetheless conclude optimistically that ATTAC has the potential of serving as a core movement around which such opposition might usefully rally. As a subordinate contribution, our investigation poses the question of how to most usefully conceptualize the nature and role of the movement. We invite scholarly dialogue by locating ATTAC in the context of the study of social movements and transnational civil society and by enriching the theoretical debate on the nature of the emerging global opposition with our empirical observations on one of its main protagonists. Annette Freyberg-Inan is assistant professor at the Political Science Department of the University of Amsterdam. She specializes in the areas of International Relations Theory; International Political Economy and Globalization; European Integration, Democratization and Enlargement; Romanian Politics; Political Psychology; and Methodology. Her most recent publications includeWhat Moves Man: The Realist Theory of International Relations and Its Judgment of Human Nature(New York: SUNY Press, 2004); ‘Organic intellectuals and counter-hegemonic politics in the age of globalisation: the case of ATTAC’, with Vicki Birchfield, in Catherine Eschle and Bice Maiguashca (eds), Critical Theories, World Politics and the ‘Anti-Globalization Movement’(London: Routledge, forthcoming 2005); ‘Transition economies’, in Richard Stubbs and Geoffrey Underhill (eds), Political Economy and the Changing Global Order(Oxford University Press, 3rd ed., forthcoming 2005); Transition, Civil Society, and the Social Sciences in Romania(Stuttgart/Hannover: Ibidem Verlag, forthcoming 2005); ‘World system theory: how the fate of Kosovo reflects the logic and the grip of the world capitalist order’ in Jennifer Sterling-Folker (ed.), Making Sense of IR Theory(Boulder, CO: Lynn Rienner, forthcoming 2005); ‘Which way to progress? The impact of international organizations in Romania’, in Ronald Linden (ed.), Norms and Nannies: The Impact of International Organizations on the Central and East European States(Lanham, MD: Rowman & Littlefield, 2002). Vicki Birchfield is an assistant professor in the School of International Affairs at the Georgia Institute of Technology. Her research interests include comparative and international political economy and European politics. She is currently completing a book manuscript entitledInstitutions, Values and Income Inequality in Capitalist Democraciesand has published articles in theReview of International Political Economy, European Journal of Political Researchand theReview of International Studies.
Political Science
Keywords: ATTAC; globalization; international studies; neoliberalism; social movements

The Continuing 'Wind of Change' in the Balkans: Sources of Housing Inequality in Bulgaria - Vesselinov, Elena (Urban Studies (Routledge), 2004)
The research in this paper explores the institutional changes in the housing system during the period of market transition in Bulgaria, which follow suit with the greater societal transformations. The societal changes are linked theoretically with Polanyi's understanding of the transition from a non-market to a market society. His argument helps in establishing the institutional context of the macroeconomic changes in the past decade. The article then focuses on the changing sources of housing inequality. It is argued that there are two urban regimes of housing inequality: the regime of controlled uniformity during the period of socialism and the regime of primitive diversity during the period of market transition. The two regimes are produced mainly through the changing role of the state.
Sociology; Urban Studies
Keywords: Bulgaria; cities & towns; equality; housing; macroeconomics; socialism; urban studies

Meat for the Multitudes: Market Culture in Paris, New York City, and Mexico City over the Long Nineteenth Century - Horowitz, Roger; Pilcher, Jeffrey M.; Watts, Sydney (American Historical Review, 2004)
Examines an earlier period of oscillation between state intervention and market liberalization in the meat trades of Paris, France New York City, and Mexico City, Mexico. Explanation on market culture; Argument of economic historian Karl Polanyi on the modern capitalist system and market rationality; Discussion on the rules governing the relationship between civil society and state power in the meat trade.
History
Keywords: Mexico; Mexico City; New York; Paris (France); civil society; intervention (federal government); liberalism; market liberalization; meat industry; state intervention

Rules of Privatization: Contradictions in Neoliberal Regulation of North Pacific Fisheries - Mansfield, Becky (Annals of the Association of American Geographers, 2004)
Recent changes in fisheries regulation in the U.S. North Pacific reveal how neoliberalism is constituted in practice, and the forms that neoliberalism takes when it engages with environmental management and ecological processes. Whereas neoliberalism can be taken as a political economic philosophy that posits that markets, without state involvement, can best allocate resources, the history and practice of neoliberalism show that it is not as unified as it often appears. Analysis of contemporary fisheries policy reveals not only contradictions in neoliberal approaches, but also how those contradictions are shaped by the environmental context of the industry. This article discusses the rationale for neoliberalism in fisheries and the governance changes enacted in the 1998 American Fisheries Act, which privatized the fishery for Alaska pollock by closing the fishery to all new entrants, providing a set percentage of the yearly catch to “cooperatives” of participants, and allowing individuals to lease their shares. Karl Polanyi's notion of the “double movement” provides a framework to argue that even though regulators tout these reforms because they rely on market mechanisms to resolve recalcitrant ecological and economic problems in these fisheries, writing and implementing the act simultaneously involved complex rule making designed to protect the market. This form of neoliberalism results from the history of fisheries regulation, including recent emphasis on cooperative management, and the ecological characteristics of marine fish. Moves to privatize the oceans entail developing distinctive forms of neoliberal practice that uniquely combine private industry and government regulation. Because fish are one of the last great resource commons, neoliberal approaches to fisheries mark a profound geographical transformation in the political economy of the oceans.
Geography
Keywords: Pacific Ocean; double movement; fishery policy; neoliberalism; privatization

Globalization, Labor and the 'Polanyi Problem' - Munck, Ronaldo (Labor History, 2004)
This article outlines what the Polanyi problem consists of and provides information on some of the implications that arise in developing a Gramscian/Polanyian strategy of counter-hegemony for the labor and the modern social movements, as of August 2004. Labor and new social movements are allegedly an integral element for a progressive solution of the so-called Polanyi problem, which is how the tendency towards the creation of a global free-market economy can be reconciled with a degree of stability and cohesion in society. Taking a Polanyian perspective allows the development of a historical perspective on the dual transformations of globalization and labor. Towards the end of the Second World War, Karl Polanyi wrote of how a self-regulating market that allegedly could not exist for any length of time without annihilating the human and natural substance of society. Such a utopia would allegedly destroy humanity and transform the world into a wilderness, an opinion mirrored by modern eco-socialists. The strategy and ideology of globalization as transformative revolution seems to echo and confirm Polanyi's account of the 19th century industrial revolution, an attempt to set up a self-regulating market.
Sociology; Political Science
Keywords: GRAMSCI; Antonio; 1891-1937; Polanyi and Gramsci; Polanyi problem; counter-hegemony; economic policy; free enterprise; globalization; international relations; labor movement; labour movement; social movements

Dynamics of Conflict and System Change: The Great Transformation Revisited - Halperin, Sandra (European Journal of International Relations, 2004)
Karl Polanyi's analysis in The Great Transformation has played a prominent role in shaping our understanding of the nature and outcome of both globalization and the movements that have emerged to resist it. However, this article argues that Polanyi's account of the rise and demise of Europe's 19th-century market system is, in important respects, incomplete and misleading. Its central concern is Polanyi's neglect of class structures and processes and how this leads him to mischaracterize both the international and domestic institutions of Europe's 19th-century market system, and the central dynamic driving its development and ultimate collapse. The article critically reviews key features of Polanyi's analysis. Based on this review, it then presents a re-reading of the history of Europe's unregulated market system. Finally, it considers the implications of this alternative account for how we view the context and conditions for globalization and the ways it can best be resisted or shaped in less destructive ways.
Political Science; International Relations
Keywords: Europe; class conflict; globalization; international relations; international trade; markets; organizations and policy; social conflict; transformation; transnational capital

And if there was no state?: critical reflections on Bates, Polanyi and Evans on the role of the state in promoting development - Menocal, Alina Rocha (Third World Quarterly, 2004)
The article review three books about the role of the state in promoting development. It includes "Markets and States in Tropical Africa: The Political Basis of Agricultural Policies," by Robert Bates, "Embedded Autonomy: States and Industrial Transformation," by Peter Evans and "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
Political Science; Development Studies
Keywords: BATES; Robert H.; 1942-; EVANS; Peter; 1944-; Embedded Autonomy: States and Industrial Transformation; Great Transformation; The (Book); Markets & States in Tropical Africa: The Political Basis of Agricultural Policies (Book); nonfiction; state development

Agenda 2010: German social democracy and the market state - Thompson, Peter (Debatte, 2004)
Ideology is always for something. Who thought neoliberalism was any different? The post-Cold War provides an excellent laboratory in which to observe 20th c. civilization crumbling, even as it marches towards world markets unbounded by law or social principles. Through repetition and rhetorical sleight-of-hand, the market has robbed the state and thus the polis of its agency. Thus, Schroeder’s SPD is contemplating yet another retreat from the social democratic model, in favor of the post-welfare-state model already well established in the UK and America. And yet within the SPD ranks are breaking as members watch the party abdicate Germany’s basic social contract. These events are reminiscent of M. Polanyi’s The Great Transformation [1744], and they demonstrate once again Marx’s prescience.
Political Science; Germanic Studies
Keywords: Germany; Great Transformation; The (Book); Social Democratic party; markets; social democracy

The third way and the third world: poverty reduction and social inclusion in the rise of 'inclusive' liberalism - Porter, Doug; Craig, David (Review of International Political Economy, 2004)
In the wake of frank neo-liberalism, and in the context of rising security fears, ways are being found to provide market liberalism with a more inclusive face. The Poverty Reduction Strategies currently prominent in international development, and Thirdway OECD 'Social Inclusion' policy frames claim common purpose to promote 'opportunity, empowerment and security' for people and places on the peripheries of global economies and societies. They share commitments to global economic integration and openness, market led growth, 'good' and 'joined up' governance, local and social partnerships, and wide-ranging activation of 'capacities'. But the high rhetorical aspirations of liberalism to social 'inclusivity' have so far overreached empirical gains for the poor. Drawing on developing country examples of Poverty Reduction Strategy and public policy in New Zealand's current Labour government, this paper sketches salient features of 'inclusive' liberalism. It critically examines its status as a Polanyian turn within a wider liberal project, which seeks to re-embed and legitimate a liberal social and economic order.
Sociology; Political Science
Keywords: New Zealand; developing countries; international competition; international political economy; liberalism; political planning; poverty; poverty reduction; self-efficacy; social inclusion; third way

'Spatial' relationships? Towards a reconceptualization of embeddedness - Hess, Martin (Progress in Human Geography, 2004)
The concept of embeddedness has gained much prominence in economic geography over the last decade, as much work has been done on the social and organizational foundations of economic activities and regional development. Unlike the original conceptualizations, however, embeddedness is mostly conceived of as a 'spatial' concept related to the local and regional levels of analysis. By revisiting the early literature on embeddedness - in particular the seminal work of Karl Polanyi and Mark Granovetter - and critically engaging with what I will call an 'overterritorialized' concept, a different view on the fundamental categories of embeddedness is proposed. This reconceptualization then is illustrated using the poststructuralist metaphor of a rhizome to interpret the notion of embeddedness and its applicability to different geographical scales.
Geography
Keywords: GRANOVETTER; Mark; associations; cosmography; economic geography; embeddedness; geography; global production networks; institutions; new regionalism; organization; rhizome; social networks; socioeconomics

Student Labor and Evolution of Education - Sidorkin, Alexander M. (World Futures: The Journal of General Evolution, 2004)
The evolution of teaching is examined in three stages: apprenticeship, classical schooling, and mass schooling. All three stages use different social technologies to operate. The mass schooling is analyzed from the point of view of economic anthropology developed by Karl Polanyi, as a non-market economic system. Mass schooling uses the forms of motivation found in archaic, tribal economies: students do their homework and attend school out of considerations of reciprocity. Schools must be treated differently with respect to their improvement. School improvement should be based on perfecting existing non-market economic mechanisms, not on plunging schools into market economy.
Anthropology
Keywords: POLANYI; Karl; 1886-1964; apprenticeship programs; economic anthropology; education; educational anthropology; evolution of education; motivation in education

Endogenous Preferences and Embeddedness: A Reappraisal of Karl Polanyi - Rodrigues, João (Journal of Economic Issues (Association for Evolutionary Economics), 2004)
This article examines the relevance of the Karl Polanyi's contributions to economics in general and to the issue of endogeneity of human preferences in particular. Although Polanyi never spoke of endogenous preferences, one can capture in his work a vision of the historical specificity and institutional dependence of human purposes and reasons for behavior. It is undeniable that in Polanyi there is a certain tendency to overlook human volition and to fall into a kind of institutional determinism. Nevertheless Polanyi recognizes the scope for deliberate human action when he defines institutions as the embodiments of human meaning and purposes. Furthermore, in Polanyi's work, there is a very clear awareness of the complexity of the motives for human action and a defense, which is continuously reaffirmed, of the plurality of reasons to act in economic interactions and their relation to the patterns of interaction that are dominant. Nevertheless, there is a lack of a clear and well-systematized account of the possible causal links by which institutions influence human preferences. His substantive economy takes morality into account, in the sense that its foundations lie on the recognition that man is a moral being with duties toward himself and others, with an understanding of what is good and what is bad and that these moral codes exert a powerful influence upon economic affairs.
Economics
Keywords: economic anthropology; embeddedness; endogenous preferences; ethics; human behavior; institutional economics; social sciences

Third Worldism and the lineages of global fascism: the regrouping of the global South in the neoliberal era - Patel, Rajeev; McMichael, Philip (Third World Quarterly, 2004)
We come to an analysis of Third Worldism through an historical understanding of the development project, one that locates Third Worldism as a moment in a broader series of resistances both to capital and colonialism, and to the techniques used by the state to maintain hegemony. Viewing Third Worldism in this wider context, we argue, enables us to not only explain the failure of Third Worldism to deliver on its vision of emancipation from colonialism, but to also explain the shape of contemporary resistance to the world capitalist order. We argue that the theory and practice of development depends on a certain biopolitics, rooted in a regime of sovereign state control, and designed to mobilise citizens in ways favourable to capital. We hold that Third Worldism embraced this form of sovereignty and its biopolitics. Further, by blending cultural studies analysis with a Polanyian interpretation of the rise of fascism, we argue that Third Worldism can be situated as a moment in the maturation of 'global fascism'. Finally, we argue that contemporary resistances to neoliberalism have recognised the complicity of the state with capital. These 'new internationalisms' arise from the ashes of Third Worldism, with an altered understanding of 'sovereignty' that challenges the trajectory of the Third World sovereign state.
Sociology; Development Studies
Keywords: biopolitics (sociobiology); capitalism; colonies; fascism; global capital; global fascism; hegemony; liberty; sovereignty (political science)

Social Exclusion in a Comparative Context - Reimer, Bill (Sociologia Ruralis, 2004)
This paper outlines a framework for understanding social exclusion that is multidimensional, dynamic, multi-leveled, and relational. Inspired by Polanyi's classification of the modes of economic inclusion, we propose that social inclusion and exclusion processes are rooted in four types of social relations: market (exchange and barter), bureaucratic (rational-legal), associative (common interest), and communal (complex reciprocity and shared identity). Each type reflects different, but integrated processes of social exclusion and inclusion. These four types are outlined conceptually, then operationalized using data from a Canadian survey conducted in 1995 rural households. The results show the extent to which the four types of relations are used for social support, their interdependence, and their relationship to selected household characteristics and outcomes. The policy implications discussed emphasize the ways in which building capacity in all four types of relations can increase the level of social inclusion.
Sociology
Keywords: Canada; economic inclusion; rural sociology; social exclusion

Debt Abides: A Prolegomena for Any Future Chapter 11 - Ayer, John D. (American Bankruptcy Law Journal, 2004)
This article presents information related to market transactions. As a mode of organization, markets are so pervasive in our own lives that it may be hard to think just how novel and contingent (in geologic time) they may be. It was economist Karl Polanyi who sought to isolate a juncture in this process of "becoming a market", the point at which the idea of the market transaction becomes not just a tool or an instrument, but a central organizing principle of social life. But it is not clear that even Polanyi would have been able to conceive a later stage, a stage in which the market becomes not merely a tool of the firm or an expression of sovereignty, but a substitute for the firm and for sovereignty itself.
Law; Political Science
Keywords: autonomy (Political science); international law; markets; organization; political science; social interaction

The Great Transformation in Understanding Polanyi: Reply to Hejeebu and McCloskey - Blyth, Mark (Critical Review, 2004)
Santhi Hejeebu and Deirdre McCloskey's rebuttal to Karl Polanyi's Great Transformation begs several important questions. Yes, commerce can be found throughout human history–but is that the same as saying that people have been equally capitalistic at all times? If not, then how did modern capitalism come into being? Hejeebu and McCloskey portray capitalism as having evolved gradually, indeed quite naturally, rather than being a contingent product of politics. Not inconsistently, Hejeebu and McCloskey radically distinguish between what people "think" and what they "do"–that is, between their ideas and their actions. This distinction, too, suggests that human action is ahistorically capitalistic–whatever human agents at different times and places might think.
Political Science
Keywords: Hejeebu; McCloskey; economic thought; history; modern capitalism

Pinochet meets Polanyi? The Curious Case of the Chilean Embrace of "Free" Market Economics - Cypher, Jame M. (Journal of Economic Issues, 2004)
This article argues, within the context of Karl Polanyi's work, that the common view of Chile is doubly miscontrued, in terms of free market economics. Events since the end of the dictatorship (1989) tend to confirm Polanyi's hypothesis in 'The Great Transformation' (1957; discussed in the following section) while at the same time negating the Chicago School's view that a free market society could be built–even under a dictatorship. In Chile from September 1973 onward through 1989, the Chicago School–inspired economists known as the Chicago Boys, engaged in what would appear to be the most determined utopian endeavor of economic liberalism to set up a self-regulating market system. It is the hypothesis of this paper that the Chicago School failed spectacularly in this effort and that the credit they have widely received for successfully remaking the Chilean economy properly belongs to the antithesis of the Chicago School–successful state-led efforts to restructure the economy and foster development. Far from the fictitious utopia of the free market, under the dictatorship the state was also heavily involved in projects designed to massively transfer economic rents to the private sector. Consistent with Polanyi's thesis, the Chicago School was able to drastically reduce Chile's social legislation, labor legislation, and social controls over the exploitation of the natural resources of Chile only within the context of a military dictatorship. While Chile's elected governments have embraced the Chicago School's faith in unlimited and unregulated free international trade, in the area of social legislation and labor legislation there are very strong indications that civil society is systematically and effectively striving to overcome the retrograde steps imposed by the dictatorship.
Economics
Keywords: Chicago school of economics; Chile; economic conditions; economics; free enterprise; politics and government

Heilbroner and Polanyi: A Shared Vision - Dimand, Robert W. (Social Research, 2004)
The article presents the shared vision of Polanyi and Heilbroner. This paper focuses on the parallel ideas of economists Karl Polanyi and Robert Heilbroner. Their concept on the role of market system in the emergence of economics as a field of study is explained. More issues included are the requirements for the transformation of a pre-market society into a true market, Polanyi's influence to several economists, and relevance of the Polanyi/Heilbroner vision of the market system to the postcommunist countries transition to the market.
Economics
Keywords: HEILBRONER; Robert; economics; economics - statistical methods; economists; markets; social sciences; societies; statistics

Re-Inventing Karl Polanyi: On the Contradictory Interpretations of Social Protectionism - Drahokoupil, Jan (Sociologický Časopis / Czech Sociological Review, 2004)
The ideas of Karl Polanyi's The Great Transformation have often been referred to in the recent debates that have emerged as a reaction to the rise of neoliberal policies. This paper deals with contradictory interpretations of the notion of social protectionism in the work of Karl Polanyi. There are two opposing interpretations distinguished here. The first interprets social protectionism as a balancing principle of economic liberalism. The second understands social protectionism as a part of market pathology. In order to assess the validity of competing interpretations, the author puts forth an account of social protectionism in the context of Polanyi's theory of the economy and society. The author concludes that the popular notion of social protectionism as a balancing principle of economic liberalism does not correspond to Polanyi's theory. In addition, the author offers a skeptical commentary on the utility of Polanyi for understanding social protectionism in social analysis.
Sociology; Economics
Keywords: critique; social protectionism

Polanyi and the History of Capitalism: Rejoinder to Blyth - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2004)
Mark Blyth's rebuttal to our constructive critique of Polanyi "blithely" takes for granted the accuracy of Polanyi's now-outdated historiography of capitalism–by means of a loose, overly expansive definition of capitalism that question-beggingly equates it with modernity. Blyth emphasizes the need to view markets as "socially embedded," with which we agree–but he appears not to take account of the individual self-interest that is thus embedded. Similarly, he asserts a priori the role of ideas in history, in parallel to the economists he condemns (unfairly) for reading ideas out of history a priori. All of this poorly serves the cause of extracting Polanyi's welcome emphasis on social embeddedness and on the empirical from the ideological and methodological certitudes and errors in which The Great Transformation placed them.
Economics
Keywords: BLYTH; Mark; history of economic thought: individuals

Polanyi Symposium: a conversation on embeddedness - Krippner, Greta; Granovetter, Mark; Block, Fred; Biggart, Nicole; Beamish, Tom; Hsing, Youtien; Hart, Gillian; Arrighi, Giovanni; Mendell, Margie; Hall, John; Burawoy, Michael; Vogel, Steve; et al. (Socio-Economic Review (2004), 2004)
This conversation, transcribed from a conference in April 2002, is intended to illuminate current debates about the use and abuse of the embeddedness concept in economic sociology.
Sociology
Keywords: economic sociology; embeddedness; markets; symposium

Introduction: Open Markets versus Welfare Citizenship: Conflicting Approaches to Policy Convergence in Europe - Taylor-Gooby, Peter (Social Policy & Administration, 2003)
Few would have predicted the rapid progress of the EU in developing common economic institutions 20 or 30 years ago, although many commentators might have foreseen the relatively slow development of convergent social policies. This paper sets the European debate in the context of the path-breaking work of Polanyi and Schumpeter at the end of the Second World War. It argues that the economic institutions of the EU are at least as important as the social policy institutions in understanding current developments, and suggests that a commitment to a broadly liberal market agenda at the economic level constrains and moulds social policies.
Sociology
Keywords: European Union; SCHUMPETER; Joseph Alois; 1883-1950; economic institutions; market; social policy; welfare state

The future of planning at the 'end of history' - Goonewardena, Kanishka (Planning Theory, 2003)
The hegemony of neoliberalism now poses a fundamental challenge to planners worldwide. Most influential in this regard has been Francis Fukuyama's 'end of history' ideology and its progenies - or mutations - such as the Third Way. A close reading of their proponents (especially Anthony Giddens) and critics (Perry Anderson, Pierre Bourdieu, Alex Callinicos, John Gray and others) with reference to the contrasting political-economic theories of Friedrich von Hayek and Karl Polanyi, however, reveals the fundamental contradictions of neoliberalism - especially between capitalism and democracy - and identifies for progressive planning the role of extending radical democracy to the realms of the state and the economy.
Geography
Keywords: BOURDIEU; Pierre; 1930-2002; FUKUYAMA; Francis; GIDDENS; Anthony; HABERMAS; Jurgen; neoliberalism; planning; social democracy

Beyond Social Democracy? Takis Fotopoulos' Vision of an Inclusive Democracy as a New Liberatory Project - Gare, Arran (Democracy & Nature: The International Journal of Inclusive Democracy, 2003)
Towards an Inclusive Democracy, it is argued, offers a powerful new interpretation of the history and destructive dynamics of the market and provides an inspiring new vision of the future in place of both neo-liberalism and existing forms of socialism. It is shown how this work synthesizes and develops Karl Polanyi's characterization of the relationship between society and the market and Cornelius Castoriadis' philosophy of autonomy. A central component of Fotopoulos' argument is that social democracy can provide no answer to neo-liberalism, so the only viable alternative to neo-liberalism is the form of inclusive democracy he elaborates. Reviewing Castoriadis' concept of autonomy, it is argued that while Fotopoulos is certainly correct given the present deformed nature of social democracy, there is no reason to exclude social democracy as such from what Fotopoulos calls the tradition of autonomy. It is suggested that if the working class movement could free itself from the capitalist imaginary and return to its quest for autonomy, a synthesis or a radically reformed social democracy and inclusive democracy could greatly improve the prospects of each to successfully challenge not only neo-liberalism, but also the emerging liberal fascism of USA, Britain and Australia.
Philosophy
Keywords: FOTOPOULOS; Takis; autonomy (political science); democracy; liberalism; political science; socialism

Global Transformation and Local Countermovements: The Prospects for Democracy Under Neoliberalism - Udayagiri, Mridula; Walton, John (International Journal of Comparative Sociology (Sage Publications, Ltd.), 2003)
This article compares Mexico and India's experiences with neoliberalism to propose that the collapse of the development state generates countermovements. In both nations, neoliberalism is associated with the decline of the one-party deminant system, and a restructuring of civil society. Variations emerge in the timing of democratization in these countries. In India, democratization preceded neoliberal reforms, whereas in Mexico democratization followed neoliberal reforms, but in both cases democratization mitigates the effects of neoliberalism on civil society. Conclusions drawn from the comparative analysis of Mexico and India concur with Karl Polanyi's proposition that there is a double movement of marketization and protectionest countermovements. The case studies suggest a pattern to these countermovements. Actors are confronted abruptly with threats to their well-being; not only economic threats but also environmental, political , and symbolic threats. The threatened value in each case is a former entitlement, typically a form of protection ensured by the state. Thus, even in the presence of countermovements, neoliberalism mediates a divergence of state and civil society relationships creating uncertain futures for democratic possibilities.
Sociology
Keywords: India; International Monetary Fund; Mexico; democracy; democratization; liberalism

Debt Peonage in Granada, Nicaragua, 1870-1930: Labor in a Noncapitalist Transition - Dore, Elizabeth (Hispanic American Historical Review, 2003)
Revisits the debt peonage debate, central to understanding Latin American transitions to capitalism, particularly in Diormo, Granada, Nicaragua. Differences between capitalist and noncapitalist societies according to Karl Polanyi and Robert Brenner; Land peasantry in Diriomo; Legislation enacted to compel peasants to work in plantation agriculture.
History
Keywords: BRENNER; Robert; 1943-; Nicaragua; capitalism; debates and debating; history; labor laws & legislation; labour laws & legislation; peasants

Reinstituting the Economic Process: (Re)embedding the Economy in Society and Nature - Adaman, Fikret; Devine, Pat; Ozkaynak, Begum (International Review of Sociology, 2003)
Polanyi argued that the project of creating a fully self-regulating market was utopian, in the sense of impossible. However, movement towards this utopia, the ever greater but never completed process of disembedding the economy from both society and nature, creates growing dislocations and tensions which call forth a counter movement. This double movement may be thought of as successive changes in the way in which the economic process is instituted. The focus of the paper is on the meaning of embeddedness, the ways in which the economy was reinstituted during the Great Transformation and the subsequent counter movements, and alternative approaches to further reinstituting the economy in ways that disembed it further or (re)embed it more firmly in society and nature. It is argued that prior to the creation of the capitalist market the economy was organically embedded in society and nature. However, the creation of separate economic institutions, the institution of the economic process as a distinct system with its own laws of motion, severed these organic links and the economy came to dominate both society and nature. Here, however, the symmetry between society and nature ends. Society has the capacity for conscious, purposeful action; nature does not. For the economy to be reinstituted in ways that create a sustainable organic relationship with nature, it must first be reinstituted in ways that bring it under social control.
Sociology
Keywords: CAPITALISM; POLANYI; Karl; 1886-1964; SOCIAL control; UTOPIAS; capitalism; economic development; economic policy; embeddedness; nature; social control; utopias

The Forgotten Institution - Cangiani, Michele (International Review of Sociology, 2003)
Presents views of scholar Karl Polanyi on economic integration. Views of Polanyi on modern capitalist society; Distinction between external, local and internal markets by Polanyi. The three forms of economic integration include reciprocity, redistribution, and exchange. The article discusses Polyani's book "The Great Transformation," the development of market economies, the self-regulating market, some of the writings of Max Weber, big businesses, the efficiency of the market system, and social engineering.
History
Keywords: Great Transformation; The (Book); WEBER; Max; 1864-1920; big business; capitalism; international economic integration; social engineering

Institutions, Politics and Culture: a Polanyian Perspective on Economic Change - Harriss, John (International Review of Sociology, 2003)
Presents the perspective of philosopher Karl Polanyi on economic change. Works of Polanyi on the topic; Analysis of pre-modern economies by Polanyi. According to Jeffrey Nugent, institutions make social life fairly predictable by restricting some actions and providing incentives for other actions. The article discusses Polanyi's book "The Great Transformation," the self-regulating market economy, scarcity, individual choice, economic development in India, trust in India's corporate sector, new institutional economics, and distribution of private property rights.
Political Science; Sociology
Keywords: Great Transformation; The (Book); India; NUGENT; Jeffrey; economic development; institutional economics; personal property; philosophers; scarcity; social interaction

The Enforcement of Contracts and Property Rights: Constitutive versus Epiphenomenal Conceptions of Law - Hodgson, Geoffrey M. (International Review of Sociology, 2003)
Discusses various conceptions of law. Concept of law as an epiphenomenon of underlying structures; Views of economist Karl Marx on law. Discusses doctrine of individualism, constitutive role of law, property rights, contracts, the emergence of law, social ontology, the relations of individuals with social structures, self-organizing institutions, self-enforcement, Karl Polyani's view that self-regulating markets are unattainable, rule of law, social reality, and how the nature of legal relations affects socio-economic behavior.
Sociology
Keywords: MARX; Karl; 1818-1883; economists; individualism; law; personal property; rule of law; social reality; social structure; socioeconomics

Moral Philosophy and Economic Sociology: What MacIntyre Learnt from Polanyi - McMylor, Peter (International Review of Sociology, 2003)
Focuses on the issue of moral philosophy and economic sociology. Views of philosopher Alasdair MacIntyre on morality; Works on morality. Discusses morality in social science, Karl Polyani's writings on the social context of economic change, Marxist socialism, human cooperation, social relations, self-interest, moral responsibility, market order, public ownership, redistributive taxation, social welfare, Max Weber's ethic of responsibility, and the connections between MacIntyre's and Polyani's thoughts on morality.
Sociology
Keywords: MACINTYRE; Alasdair C.; Marxian economics; WEBER; Max; 1864-1920; ethics; moral and ethical aspects; philosophers; responsibility; social psychology; social sciences; socioeconomics; sociology

The Creation of the European Market for Mobile Telephony: Overview of an Instituted Process - Mina, Andrea (International Review of Sociology, 2003)
Focuses on the creation of the European market for mobile telephony. Merits of the global system for mobile communications; Reasons for the emergence for a market for mobile telephony. Discusses the socio-economic factors that influenced the development of the mobile telephony market, the writings of Karl Polyani, instituted process, the process of standardization, digital technology, European telecommunications during the 1980s, and the development of market structure in the global equipment industry.
Sociology
Keywords: Europe; global system for mobile communications; industrial organization (economic theory); instituted economic process; instituted process; mobile communication systems; standardization; telecommunication

Polanyian Perspectives on Instituted Economic Processes, Development and Transformation: Introduction - Ramlogan, Ronnie; Harvey, Mark (International Review of Sociology, 2003)
Focuses on the presentation 'Polanyian Perspectives on Instituted Economic Processes, Development and Transformation' at an international workshop held at Manchester, Connecticut. Organizer of the workshop; Theme of the workshop. The workshop was organized by the Centre for Research on Innovation and Competition. The article discusses varieties of capitalism, supply and demand, price formation, competition, economic motives, market economy, and the book "The Great Transformation," by Karl Polyani.
Sociology
Keywords: Connecticut; Great Transformation; The (Book); Manchester Conn.; POLANYI; Karl; 1886-1964; United States; capitalism; competition; supply and demand; workshops (adult education)

Issues for a Neo-Polanyian Research Agenda in Economic Sociology - Randles, Sally (International Review of Sociology, 2003)
Kari Polanyi Levitt has commented that her father's writing was met with a 'deafening silence' in England, a silence which she suggests is 'yet to be explained'. Given The Great Transformation was purposefully, situated in England Polanyi Levitt's point is an interesting one, and one which still deserves attention. But the last two decades have witnessed an intensification of interest in Karl Polanyi's methodological approach and theoretical insights, from England as well as elsewhere, and representing a range of disciplines. This raises a string of associated questions: interest from who? Why now? And how? Further we could ask: Does this new interest have the potential to redress the Polanyi Levitt charge without falling prey to an opposite one of misusing or abusing the Polanyi legacy? This paper contributes to the much larger agenda of examining in a serious way the usefulness and applicability of Polanyi's key ideas and methods, particularly as they apply to the burgeoning interest in markets and exchange within New Economic Sociology (NES). A sub-set of this agenda is to explore whether Polanyian insights provide a more nuanced and critical understanding of competitive processes and innovation than is currently available within Economics, Sociology or indeed Economic Sociology.
Sociology
Keywords: England; Great Transformation; The (Book); POLANYI LEVITT; Kari; POLANYI; Karl; 1886-1964; Polanyi's legacy; economic sociology; economics; socioeconomics; sociology

Karl Polanyi and the writing of The Great Transformation - Block, Fred (Theory & Society, 2003)
Karl Polanyi’s 1944 book, The Great Transformation , has been recognized as central for the field of economic sociology, but it has not been subject to the same theoretical scrutiny as other classic works in the field. This is a particular problem in that there are central tensions and complexities in Polanyi’s argument. This article suggests that these tensions can be understood as a consequence of Polanyi’s changing theoretical orientation. The basic outline of the book was developed in England in the late 1930s when Polanyi was working within a specific type of Marxist framework. However, as he was writing the book, he developed several new concepts, including fictitious commodities and the embedded economy, that led in new directions. Because circumstances did not give him the time to revise his manuscript, the book is marked by a tension between these different moments in his own theoretical development. The result is that Polanyi glimpses the concept of the always embedded market economy, but he does not name it or elaborate it.
Sociology
Keywords: Great Transformation; The (Book); capitalism; economics; sociology

For a Sociological Marxism: The Complementary Convergence of Antonio Gramsci and Karl Polanyi - Burawoy, Michael (Politics & Society, 2003)
Analyzes the Marxist concept of society to interpret the rise and fall of communist orders, the shift from politics of class to politics of recognition, the transition from colonialism to postcolonialism and the development of an emergent transnationalism. Relationship between sociology and Marxism; Genesis of a sociological Marxism; Theorists of society and socialism.
Sociology
Keywords: GRAMSCI; Antonio; 1891-1937; administration and politics; communism and society; postcolonialism; socialism; sociology; transnationalism

The Near-Death of Liberal Capitalism: Perceptions from the Weber to the Polanyi Brothers - Roth, Guenther (Politics & Society, 2003)
Provides an overview of some critical moments in the history of liberal capitalism as perceived by some historical witnesses. Views of brothers Max and Alfred Weber on the world economy before 1914; Historical parallels to the introduction of euro bills and coins in January 2002; Access of Germany to the world market for demographic and geographic reasons.
Sociology
Keywords: Euro; POLANYI; Michael; 1891-1976; WEBER; Alfred; WEBER; Max; 1864-1920; administration and politics; capitalism; economics; history of liberal capitalism

Polanyi's 'Double Movement': The Belle Époques of British and U.S. Hegemony Compared - Silver, Beverly J.; Arrighi, Giovanni (Politics & Society, 2003)
Presents a comparative analysis of the double movement of the belle époque and collapse of British hegemony with the double movement of the late 20th and early 21st century belle époque and current crisis of U.S. hegemony. Emphasis on the book 'The Great Transformation,' by Karl Polanyi; Liberal crusade for free markets in the 1830s and 1840s; Role of Great Britain as the central entrepôt of world commerce and finance.
Sociology
Keywords: Great Britain; Great Transformation; The (Book); United States; administration and politics; commerce; double movement; free enterprise

Addressing the Negative Consequences of the Information Age Lessons from Karl Polanyi and the industrial revolution: A note on the politics of theorizing technology - Rogerson, Kenneth (Information, Communication & Society, 2003)
One of the great dilemmas of the information age is the tension between two dynamics: (1) the tendency of information to be free-flowing and not to lose its value as it moves and (2) the tendency to want to control that flow of information in order to profit from its value. In 1944, Karl Polanyi identified similar contradictions in the industrial revolution, except the flowing material was capital instead of information. He spent a lifetime exposing what he felt to be the negative consequences of this increasingly free-flowing capital, the hallmark of a free market economy. He advocated for a welfare state in which government intervention is necessary to control these negative effects. Given issues of the information age such as the digital divide, the commoditization of information, and security and privacy, as well as the arguments of the proponents and critics of these issues, Polanyi's concepts can provide insight into the complexities of increasingly technical and information-based societies.
Information Science; Media Studies
Keywords: industrial revolution; information technology

Idiosyncrasy and integration: suggestions from comparative political economy - Jones, Erik (Journal of European Public Policy, 2003)
There is a growing consensus in comparative political economy that 'globalization' is not eliminating the distinctive character of specific nation-states. Even in Europe, where formal integration between countries is most profound, nation-states remain idiosyncratic. Starting from this consensus, the questions I ask are: (a) how can we explain the coincidence of national idiosyncrasy and international integration; (b) what does our explanation tell us about processes of European integration? The answers, I argue, lie in two theoretical traditions – one stemming from Karl Polanyi's (1957) insistence on the social embeddedness of market institutions and the other from Gunnar Myrdal's (1956) interpretation of the cumulative causality behind integration at the national and international levels. Although well received in other areas, neither tradition has played much of a role in the study of the European Union. The article concludes by suggesting a research program that could develop from the interface between idiosyncrasy and integration.
Political Science
Keywords: MYRDAL; Gunnar; 1898-1987; convergence (economics); embeddedness; globalization; international political economy

Social Capital, Karl Polanyi, and American Social and Institutional Economics - Carroll, Michael C.; Stanfield, James Ronald (Journal of Economic Issues, 2003)
Economics
Keywords: World Bank; communities; division of labor; evolutionary economics; institutional economics; market economies; market economy; social capital; social networks; socioeconomics; solidarity

The Life and Work of Karl Polanyi/Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation - Dimand, Robert (Review of Radical Political Economics, 2003)
This article reviews two books about the thoughts of economist Karl Polanyi including "The Life and Work of Karl Polanyi," edited by Kari Polanyi-Levitt, and "Karl Polanyi in Vienna: The Contemporary Significance of the Great Transformation," edited by Kenneth McRobbie and Polanyi-Levitt.
Economics
Keywords: Karl Polanyi in Vienna: The Contemporary Significance of The Great Transformation (Book); Life and Work of Karl Polanyi; The (Book); MCROBBIE; Kenneth; POLANYI LEVITT; Kari; book review; economics; nonfiction

Employment, flexible working and the family - Crompton, Rosemary (The British Journal of Sociology, 2002)
This paper assesses some of the implications of one of the major social changes to have taken place in the West during the second half of the twentieth century — that is, the increased employment of women, together with normative changes in gender relations and in women's expectations. These changes have been linked to an increase in individualism, which itself is associated with the transcendence of ‘first modernity’. Thus it is suggested that new approaches to social analysis are required (Beck). Here it is argued that, rather than develop completely new approaches in order to grasp the changes that are under way, the ‘economic’ and the ‘social’ (that is, employment and the family) should be seen as intertwined, rather than approached as separate phenomena. Past debates in feminism, changes in the family, and flexible employment are critically examined. The growing tensions between employment and family life are discussed. It is argued that these changes are associated with the intensification of capitalist development, rather than reflecting a fundamental transformation of society. Existing approaches to the analysis of social change, including Polanyi's analysis of the development of ‘counter-movements’ against the ‘self-regulating’ market, will, therefore, still be relevant to our enquiries. In the concluding section, a programme of research that would examine these changes is outlined.
Sociology
Keywords: capitalism; family; flexible employment; gender; modernity

Theorizing the 'Third Sphere': A Critique of the Persistence of the 'Economistic Fallacy.' - Adaman, Fikret; Madra, Yahya M. (Journal of Economic Issues, 2002)
The paper seeks to investigate, from a methodological and ontological perspective, different ways of theorizing the third sphere–the set of activities that can be captured by neither the price mechanism of the markets nor by governmental transactions. The first aim is to elucidate the constitutive elements of the third sphere by deploying Polanyi's forms of integration (reciprocity, redistribution, and exchange). The second is to survey the ontologically individualist and methodologically formalist literature on the third sphere. After elucidating the coexisting sets of behavioral essences in contemporary ontologically individualist and methodologically formalist models of third-sphere activities, the paper claims that this proliferation of behavioral essences can only lead to a methodological impasse. The paper concludes that only with a committed recognition of the heterogeneity of the economy and the endogeneity of the economic subject will it become possible to better grasp the richness of third sphere activities.
Economics
Keywords: current heterodox approaches: institutional; economic methodology; economistic fallacy

Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Sociology; Criminology
Keywords: DURKHEIM; Emile; MERTON; Robert; anomie; crime; criminology; disembeddedness

Market Liberalism and Social Protection: Hayek, Durkheim and Polanyi in Theoretical Perspective - Akturk, Sener (Journal of Academic Studies, 2002)
Examines the views of neoclassicist Friedrich A. Hayek, sociologist Emile Durkheim and Karl Polanyi on liberalism. Relationship between the individual, the market economy and society; Features of Hayekian neoclassical economics; Information on Polanyi's book 'The Great Transformation.'
Political Science
Keywords: DURKHEIM; Emile; Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; liberalism; social protection

The Contested Sovereignty of the Firm - Dietrich, Michael (Review of Political Economy, 2002)
This paper suggests that the firm can be analysed as a regulated system of contested sovereignty. The economic literature on the firm is categorised in terms of four different perspectives on sovereignty identified using the twin factors of power and authority. But rather than any single perspective being identified as analytically superior, it is argued that a system of contested sovereignty should be based on all four perspectives. Following this, a Polanyi-inspired analysis of firm regulation is presented in which the regulation of the firm emerges to control the costs of free markets. However, this regulation depicts firm sovereignty as complex and contested rather than simply an optimal response to market failures.
Economics
Keywords: business enterprises; economics and literature; firm regulation; firm sovereignty; political economy

The 'new contractualism', social protection and the Yeatman thesis - Gaby Ramia (Journal of Sociology, 2002)
An important characteristic of public policy formulation over the 1980s and 1990s, particularly in the English-speaking countries, has been the increasing use of contractual principles as regulatory tools. The 'new contractualism' represents the recent re-emergence and adaptation of the social contract of the 17th and 18th centuries and the classical legal contract that emerged in the 19th century. The work of Anna Yeatman provides the most cogent and influential, non-neo-liberal scholarly appraisal of the new contractualism. Yeatman argues that the current contractualist agenda is consistent with equality of opportunity, occasioning a redefinition of citizenship so as to improve on the discourse of social protection. This paper argues that any attempt to remove social protection flawed though it is from discussions of the new contractualism is artificial. The social justice implications of such a position are perilous, for policy formulation has not yet entered a phase in which social protection can be superseded in a way which does not violate the rights of the socio-economically disadvantaged.
Sociology
Keywords: English-speaking countries; YEATMAN; Anna; citizenship; commodity fiction; contractualism; double movement; equality; fictitious commodities; governance; human rights; political planning; social justice; social movements; social protection; sociology

Ecosocialisation and environmental planning: a Polanyian approach - Low, Nicholas (Environment & Planning A, 2002)
Discusses a Polanyian approach to environmental planning, foregrounding the concept of ecosocialization. Global problems of urban modernity; Ecological modernization and the transformation of capitalism; Discussion on ecological Marxism and the transition to socialism; Polanyian perspective for environmental planning.
Geography
Keywords: capitalism; environmental engineering; human ecology

Towards a Theory of Values-Based Labeling - Barham, Elizabeth (Agriculture and Human Values, 2002)
An outline of a theory of values-based labeling as a social movement argues that it is motivated by the need to re-embed the agro-food economy in the larger social economy. A review of some basic premises of embeddedness theories derived from the work of Karl Polanyi reveals their connection to particular values-based labeling efforts. From this perspective, values-based labeling presents itself as primarily an ethical and moral effort to counter unsustainable trends within presently existing capitalism. These labels distinguish themselves from ordinary commercial labels by a focus on process and on quality. Evaluating the transformative potential and progressive nature of values-based labeling poses a key challenge. One avenue for gauging this potential is conventions theory. This approach can be adapted to consider the decision making processes that go on within values-based labeling groups, as well as consumer decision making based on such labels, as instances of what is termed a politics of ethical judgment. The conclusion emphasizes the need for more research in this area and suggests how it could be furthered.
Sociology
Keywords: agricultural policy; agro-food economy; embeddedness; food policy; household production and intrahousehold allocation; marketing; relation of economics to social values; social economy

Transnational Pharmaceutical Corporations and Neo-Liberal Business Ethics in India - D'Mello, Bernard (Journal of Business Ethics, 2002)
The author critiques the expedient application of market valuation principles by the transnational corporations and other large firms in the Indian pharmaceutical industry on a number of issues like patents, pricing, irrational drugs, clinical trials, etc. He contends that ethics in business is chiseled and etched within the confines of particular social structures of accumulation. An ascendant neo-liberal social structure of accumulation has basically shaped these firms' sharp opposition to the Indian Patents Act, 1970, government administered pricing, etc. The author contends that the practice of neo-liberal economics is strongly associated with a "one dimensional" ethics that privileges market valuation principles over all others. This seems to inevitably generate a social counter-movement that struggles for social protections. He critiques neo-liberal business practices from a perspective that derives from the work of the economic anthropologist Karl Polanyi. Before the present phase of liberalization in India, markets were "managed", but without a "welfare state" in place. Moving toward deregulation of the markets without a welfare state in place is unethical. Keeping the debilities of the institutional framework of public policy in mind, the author adopts a Polanyian perspective that places its trust and hope in the growing social legitimacy of the counter-movement in opposition to both neo-liberal business practices and the degenerate behavior of state agencies.
Political Science; Economics
Keywords: India; business ethics; intellectual property; international business enterprises; pharmaceutical industry; socialism

The World Bank or Polanyi: Markets, Poverty and Social Well-being in Latin America - Kirby, Peadar (New Political Economy, 2002)
Explores the role of markets in achieving social well-being in Latin America, highlighting alternatives theories for this relationship based on the work of Karl Polanyi. Role of markets in reducing poverty; Relation between markets and social institutions; Ways in which market liberalization is damaging the livelihoods of the poor.
Political Science
Keywords: Latin America; markets; poverty; social institutions

Globalization and Democracy: A New 'Great Transformation'? - Munck, Ronaldo (Annals of the American Academy of Political & Social Science, 2002)
Examines the relationship between democracy and development to set the scene for the pressing contemporary issue of how globalization might affect democracy and vice versa. Reference to the work of Karl Polanyi who posited a dual movement of market expansion matched by increasing social control over it; Impact of globalization.
Sociology; Political Science
Keywords: POLANYI; Karl; 1886-1964; democracy; double movement; economic development; globalization

The Construction of Market Institutions in Russia: A View from the Institutionalism of Polanyi - Sánchez-Andrés, Antonio; March-Poquet, José M. (Journal of Economic Issues, 2002)
This article presents information on the construction of market institutions in Russia and includes the institutional conception provided by analyst Karl Polanyi. Polanyi's main ideas will be expounded in regard to his interest in analyzing the transition. These ideas will be adapted to the object of study and then specified so that they will be efficient criteria for analyzing the present economic transition. Second, the results obtained will be applied to the Russian case, and an attempt will be made to draw some conclusions about whether Russia is moving toward a market economy. Although several distinct parts of the work of Polanyi may be of great interest in analyzing the transition process that is occurring in countries that until the 1990s were organized by central planning.. This paper discusses only the aspects which are most closely related to the construction of market economies will be mentioned. According to Polanyi, the commercialization of productive factors and money are among the determining elements for the construction of an economic market.
Economics
Keywords: Russia (federation); analysts; central planning; economic reform; industrialization; markets; transition economies

Reply to Professor Levine on Rhetoric and Reality in American Welfare History - Kern, William S. (Journal of Economic Issues (Association for Evolutionary Economics), 2001)
The article replies to professor David Levine's rhetoric and reality in American welfare history. The author largely agrees with Professor Levine's conclusion that the impact of the application of the principles of 1834 on contemporary welfare reform is "far more potent rhetorically than it is in fact" (733) and that "the slowly expanding mild welfare state is here to stay" (741). Levine argues that this is the result of the emergence and persistence of a "New Deal consensus" regarding the responsibility of government to secure macroeconomic stability and individual security that survives from its origin in the 1930s till today. The questions that arise are why this consensus emerged when it did and why it persists. In his paper the author attempts to explain why the reemergence of the rhetoric and practice of welfare reform had occurred, and he argues that an answer could be found in ideas developed by Karl Polanyi in The Great Transformation (1944). It had been argued that the logic of the self-regulating market required the denial of a right to life outside the market. This was affirmed in the passage of the New Poor Law and in the rhetoric and practices of current welfare reform. However, Polanyi's Great Transformation also provided us with an explanation of the factors which underlie the emergence of the New Deal consensus in the 1930s, the persistence of the welfare state, and the largely rhetorical impact of the principles of 1834 on current welfare reforms.
Economics
Keywords: United States; economic conditions - United States; economic history; macroeconomics; public welfare; reforms; welfare economics

Planning and the Politics of Markets: Some Lessons from Financial Regulation in Nepal - Rankin, Katharine N. (International Planning Studies, 2001)
This paper calls for an explicit return to questions about the normative foundations of planning theory and practice. It argues that a simultaneous reading of Karl Polanyi with Friedrich von Hayek can contribute to developing an ethical basis for tempering market rationality with social rationality in the current global economic conjuncture. Empirically, the paper investigates recent initiatives in Nepal to provide social protections (à la Polanyi) through financial market rules. In the face of threats to the progressive legacy in planning practice posed by the prevailing neoliberal orthodoxy, Nepal's targeted lending policies and microcredit programmes offer some optimism about the potential to embed welfare provisions within market regulation, especially when compared to developments in other countries. At the same time, however, the perspectives of rural women explored here through critical ethnography raise key questions about the capacity of these regulations to generate social opportunity and highlight a role for locally situated social criticism in progressive planning practice.
Geography
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Nepal; financial regulation; international planning studies; markets; planning; social protection

Discourses on peace and development - Hettne, B. (Progress in Development Studies, 2001)
Assuming a close relationship between peace and development, this paper analyses a succession of schools of thought in development forming part of three distinct, historically contextualized development and security discourses: the industrialization imperative in the emerging state-system in nineteenth-century Europe, the international concern with global poverty in the bipolar post second world war world and the current meaning of development in a globalized and increasingly chaotic world. The third of these discourses contains major challenges for development theory. The discourses are related to great transformations in political economy, understood in Polanyian terms as tensions between market expansion and societal response.
Peace Studies; Development Studies
Keywords: conflict; development theory; discourse; economic development; market expansion; peace; peace - economic aspects; security

Institutional Investors and Polanyi's Double Movement: A Model of Contemporary Currency Crises - Harmes, Adam (Review of International Political Economy, 2001)
This article constructs a model of contemporary currency crises which incorporates the role played by institutional investors and the dynamics associated with Karl Polanyi's notion of the "double movement." Polanyi's double movement, and its recognition of the need to integrate politics with economics, is used to explain why so many governments are prone to pursue policies that lead to a speculative attack against fixed exchange rates and why virtually every modern fixed exchange rate regime has ended in crisis. Evidence on the short-term and herd behaviour of institutional investors is used to explain why contemporary currency crises do not appear to be justified by underlying economic fundamentals and why these crises do so much more damage than their earlier counterparts. The model is then applied to the 1992 European Exchange Rate Mechanism crisis, the 1994 Mexican peso crisis and the 1997 East Asian crisis. While recognizing that variations exist in the specific circumstances of each episode, the argument of this article is that the progression of events do seem to conform to the model presented.
Political Science
Keywords: corporate finance and governance; double movement; economic development; financial instruments; financial markets; foreign exchange; institutional investors; international linkages to development; international monetary arrangements and institutions; international political economy; non-bank financial institutions; pension funds; role of international organizations; saving and capital investment

Regulationist and Autopoieticist Reflections on Polanyi's Account of Market Economies and the Market Society - Jessop, Bob (New Political Economy, 2001)
This article re-interprets and develops Polanyi’s substantive institutionalist analysis of capitalist market economies and the market society in the light of two more recent approaches to the same issues. These are the Parisian ‘regulation school’ on contemporary capitalism and systems-theoretica l accounts of the modern economy. All three regard the capitalist economy (or, for autopoietic systems theory, the market economy) as an operationally autonomous system that is nonetheless socially embedded and needful of complex forms of social regulation. For each, an adequate account of economic activities should explore how they are related to the wider social environment; how they are embedded in a wider nexus of social institutions; how the latter assist in reproducing the capitalist (or market) economy; and how their development is coupled to that of these and other environing institutions. There are also some important differ- ences among these approaches, however, which enable an exploration of their respective limitations and also provide useful bases for further theoretical and empirical research. Thus, after presenting these three perspectives on the institutedness and embeddedness of economies. I consider some basic problems in analysing the improbable stability and reproducibility of the capitalist economy, paying particular attention to governance and meta-governance.
Sociology; Political Science
Keywords: capitalism; economics; market society; political economy; regulation school; substantive approach

Religion and the Market: Opposition, Absorption, or Ambiguity? - Haddorff, David W. (Review of Social Economy, 2000)
This article addressed the complex relationship between religion and the market by proposing three basic paradigms, and then applying them to contemporary Christian social thought (or social ethics). The first conflicting model, following Max Weber and Karl Marx, views religion and the market in opposition, which results in greater secularisation. The second, following Emile Durkheim, proposes a 'functionalist' model of society, in which the market itself becomes sacred. The third, following Karl Polanyi, claims the two are more dialectical, in that both are affected by the power of the other; they remain in an ambiguous relationship. The author argues that the third model is the most coherent description of this complex relationship as well as the one most consistent with the convictions of Chrstian social thought.
Religion Studies; Theology
Keywords: church & state; dialectical; double movement; dystopian; economics; functionalism; hom. economics; homo economicus; religious aspects; secularisation; secularization; social ethics

Rural Community Life and the Importance of Reciprocal Survival Strategies - Meert, Henk (Sociologia Ruralis, 2000)
Although Belgian poverty is mainly concentrated in urban regions, the profound restructuring of labour and food markets, the dismantling of the welfare state and the growth of new types of households are also producing poverty and social exclusion in rural areas. This paper stresses that not every deprived rural household should be regarded as excluded from society. By developing survival strategies, households attempt to escape from social marginalization. To understand these responses, a typology of survival strategies is constructed, based on Polanyi’s spheres of economic integration (market exchange, redistribution and reciprocity). These survival strategies, including agricultural and non-agricultural activities, are analysed in relation to the Hageland,a peripheral rural area in Flanders. Based upon Doreen Massey’s geological metaphor, the current potentials and obstacles embedded in the historical layers of the socio-spatial structure of the area, are assessed. By comparing the results of this research with similar research amongst urban households, some particularities of rural poverty are distinguished.
Sociology
Keywords: Belgium; economic integration; poverty; urban poverty

Interpreting the Consequences of Midwestern Agricultural Industrialization - King, Martin Burce (Journal of Economic Issues (Association for Evolutionary Economics), 2000)
The article focuses on the interpretation of consequences of Midwestern agricultural industrialization. The nature and consequences of the industrialization of agriculture are well documented in academic research and in the popular press. Interpretations of the process vary in reflection of the diverse perceptions of the nature and overall significance of industrialization. Suggested policies range from a "hands-off" to a "prohibit and prevent wherever possible" approach. Both approaches are unrealistic because they fail to recognize the historical context in which agricultural industrialization is taking place. In this paper, the author presents a historical context for the process, using nineteenth-century Illinois and the industrialization of swine production as examples of commercialization and industrialization of Midwestern agriculture, respectively. The author integrates the work of Karl Polanyi and K. William Kapp into the discussion to provide a foundation for realistic policy and to demonstrate the relevance of an institutionalist perspective to the formation of contemporary agricultural policy.
Economics
Keywords: KAPP; Karl William; agriculture; commercialization; crop insurance; economic theory; evolutionary economics; industrialization; production (economic theory); rural industries

A Tale of Three Karls: Marx, Popper, Polanyi and Post-Socialist Europe - Marquand, David (Royal Institute of Philosophy Supplement, 2000)
Focuses on the social and political changes brought about by capitalism in Europe. Advocacy of socialist Karl Marx, Karl Popper and Karl Polanyi for social democracy; Discussion on the relationship between society and economy; Notion of futurism regarding the inevitability of change.
Philosophy; Political Science
Keywords: Europe; European politics & government; capitalism; change; socialism

The Second Great Transformation: The Politics of Globalisation in the Global North - Zincone, Giovanna; Agnew, John (Space & Polity, 2000)
Dominant strands of thinking in contemporary social science consider economic globalisation, the increasing role of cross-border flows and transactions in economic organisation, in terms of some combination of either limited or considerable economic impact and either positive or negative consequences for the general welfare. Little attention has been given thus far to its political consequences within those parts of the world, the developed countries of the Global North, where its impact should be greatest. This paper argues that economic globalisation is in fact the geographical face of a new great transformation in the forces of production (reductions in transport and communication costs, dramatically increased capital and labour mobility, delocalisation of technological innovation, etc.) on a par in its potential impact with the transition to market society with fragmented states first identified by Karl Polanyi. Globalisation, it is claimed here, is the product of action by states as much as markets and, in the short-term, seems to accentuate social inequalities within states, to weaken the rights of current citizens, to lessen the weight of the democratic vote and to stimulate a profound restructuring of both work and the welfare state in the developed world or ‘Global North'. But more significantly, in the long term, when focus on globalisation shifts from its recent economic causes and short-term political impact to its more long term political consequences, recent trends towards a more global economy can be seen in a different light: as entailing a potential positive transformation in the geographical organisation of political rights and citizenship on a par with the first great transformation in economic life and citizenship signalled by the coming of market society.
Political Science; Geography
Keywords: globalization; international economic relations; market society; political science; production (economic theory)

Three Pillars of Welfare State Theory: T.H. Marshall, Karl Polanyi and Alva Myrdal in Defence of the National Welfare State - Holmwood, John (European Journal of Social Theory, 2000)
Current social and political theory is sceptical of the future of welfare states in the face of global markets. Their moral claims, too, have been challenged by the neo-liberal association of market capitalism and individual freedom and by an implicit acceptance of that critique - of the welfare state as bureaucratic - by left-wing commentators. This article offers a defence of the national welfare state as the guarantor of 'complex freedom'. This defence is derived from the theoretical contributions of Marshall, Polanyi and Myrdal and offers a reconsideration of the debate immediately after the second world war over the welfare state and its relevance today. Marshall's concept of social rights has become a familiar part of our own debate, but it is argued that Polanyi provides the rigorous critique of market relationships which is missing, and Myrdal locates gender issues as central to the understanding of welfare state development and women's rights as integral to social rights.
Sociology
Keywords: economic policy; gender; globalization; government policy; human rights; markets; public welfare; social & economic rights; social rights; welfare; welfare economics

The Great Transformation - Brand, Horst (Dissent (00123846), 2000)
The article reviews the book "The Great Transformation: The Political and Economic Origins of Our Time," by Karl Polanyi.
N/A
Keywords: Great Transformation; The (Book); book review; economics; nonfiction

The Reproving of Karl Polanyi - Hejeebu, Santhi; McCloskey, Deirdre (Critical Review, 2000)
Karl Polanyi's The Great Transformation has had enormous influence since its publication in 1944. In form, this influence has been salutary: Polanyi targets one of the main weaknesses of modern economics. But in substance, Polanyi's influence has been baneful. Mirroring the methodological blindness he criticizes, Polanyi insists on the all-or-nothing existence/nonexistence of laissez faire–and on its all-or-nothing goodness/badness.
Economics
Keywords: critique; history of economic thought: individuals

Freedom and the Market (An Analysis of the Anti-globalization Movement from the Perspective of the Theoretical Foundation of the Evaluation of the Dynamics of Capitalism by Polanyi, Hayek and Keynes.) - Nikitin, Pavel V.; Elliott, John E. (Forum for Social Economics, 2000)
Those who believe that the free market is positively related to both economic efficiency and individual freedom are prone to regard resistance to the establishment of the global market essentially free from any serious sociopolitical constraint as a politically insignificant expression of impatience, ignorance, and hypocrisy. This article attempts to endow the manifestation of discontent with the status quo evident in public protests in Seattle and Washington DC with political significance through explicating it as an expression of a fundamental conflict between economic efficiency and individual freedom inherent in the global implementation of the principle of self-regulating markets. This analysis of the anti-globalization movement is conducted from the perspective of the theoretical foundation of the evaluation of the dynamics of capitalism by Polanyi, Hayek, and Keynes, and its conclusions are brought to bear upon the validity of their contesting views of the relationship between economic efficiency and individual freedom.
Economics
Keywords: anti-globalization movement; capitalist systems; international economic order; political economy

Karl Polanyi's Forms of Integration as Ways of Mapping - Schaniel, William C.; Neale, Walter C. (Journal of Economic Issues, 2000)
Researcher Karl Polanyi's "forms of integration"–redistribution, reciprocity, and exchange–have been much used to describe and explain various economies. Such mapping presents information about the sources and destinations of the flows of material means in each society in ways that are easily correlated with the variables that most thoroughly and simply account for the flows of material means in different societies. Mapping may be looked upon as the selection of a "projection" for portraying the flows of material means. The diagrams below illustrate the discussions of each form of integration and are examples of mapping. As is the case for projections selected for geographical mapping, for each way of mapping a form of integration the criterion of the appropriateness of the choice of projection is analogous to a mathematical function. The independent variables would be information about the social system; the dependent variable would be the directions in which the material means flow. The merits of the choice of projection are simplicity and the accuracy with which the directions of flow are portrayed.
Economics
Keywords: commercial policy; economics; forms of integration; functions; mappings (mathematics); mathematics; social sciences

Competing economic ideologies in South Africa's economic debate - Lazar, David (British Journal of Sociology, 1996)
This paper develops an analytical framework for the sociological analysis of the clash of economic ideologies. The framework is then used to make sense of the economic debate in South Africa in the 1990s. The argument is that, following Karl Polanyi, we must treat economic life as 'embedded' in social life; that is, economic action is a form of social action. However, the notion of 'embeddedness' must not blind us to the tendency in all economies, especially contemporary market economies, for economic motivations to become differentiated from the rest of our lives. Accordingly, the framework developed through a critique of key assumptions of neoclassical economic theory attends to both the embeddedness and the differentiation of the economic element. Having established a framework of analysis, I apply it to the debate in South Africa about the most relevant frame- work for economic policy in the post-Apartheid economy. The article traces the gradual move of the African National Congress (ANC) away from statist economics to a much more market-oriented policy and shows how this reflects the ANC leaders need to balance the demands of their constituency's (embedded) conception of rationality against the potential investor's more mainstream conception of economic rationality, which is itself embedded in prosperous communities with property and skills. A similar analysis is applied to the development of the economic policy of the ANC's rival, the former ruling National Party (NP). The NP advocates an economic policy framework based on an individual self- reliance and 'free' markets, that is, on an individualistic calculative rationality similar to that of the neoclassical textbooks. However, the NP too has to pursue politics and they, although rather differently from the ANC, have sought to reconcile individual maximizing rationality with the collective rationalities of the oppressed black communities in order to win maximum support.
Sociology
Keywords: South Africa; South Africa - economic conditions; economic policy; social action; social classes; socioeconomics

Working Paper No. 63, On Karl Polanyi and His Conception of Fascism - Mistkawi, Serene (Working Papers in Economics, 2022)
This inquiry seeks to establish that the writings of author Karl Polanyi offered insights into key variables and historical conditions that gave rise to the system we know of as “fascism.” Integral to his insights, Polanyi describes economic conditions attendant for fascism to emerge, with one condition noted as widespread and persistent unemployment. Polanyi stresses that fascism needs to be understood as reactionary, a responding to features integral to classical liberalism. Considering a broad historical context Polanyi teaches us of the political conditions necessary for fascism to emerge and take form as political movements wielding power. He considers conflicts in aims between economic and political institutions. In addition, Polanyi analyzes some implications of a changing market, as well as some effects that a changing market might have over individual freedoms, as well as some of the complexities that can be associated with regulation.
Economics
Keywords: classical liberalism; currency; fascism; interventionism; regulation

Karl Polanyi and the Rise of Fascism - England, Christopher M. (New Political Science, 2022)
This article reconstructs Karl Polanyi’s account of fascism’s rise in his 1935 article, “The Essence of Fascism.” Following the elevation of Hitler to power in 1933, Polanyi embarked on a reassessment of Nietzsche, Othmar Spann, Spengler, Evola, and other figures of the interwar conservative revolution. He argues that the fascist quest for national unity emerges when 19th century liberalism fails to address the growing atomization and economic dislocation of modern society. On the one hand, fascism valorizes the mythopoetic, prehistorical vitalism that liberal rationalism and social democracy sought to purge from public life. On the other, fascism aspires to a higher form of elitist, technological mastery than egalitarian states can achieve. These tensions, he predicts, will result in the radicalization and collapse of fascist regimes in a European war. This article illuminates Polanyi’s deep understanding of political modernity and the contemporary implications of his philosophical critique of the far right.
Political Science
Keywords: Karl Polanyi; conservative revolution; fascism; modernity; radical right

Karl Polanyi’s ‘socialist accounting’ and ‘overview’ in the age of data analytics - Rief, Silvia (New Political Economy, 2022)
Digital capitalism’s information infrastructure is the subject of contentious debates concerning its transformative effects on the political economy and society. A frequent proposition, referring to older arguments of the ‘socialist calculation debate’, is that with big data analytics the pro-market arguments of neoliberal economists such as Hayek or Mises become obsolete. This article critically examines this proposition by drawing on Karl Polanyi’s notion of overview; a core theme in his outlines of a socialist economy and accounting written in the 1920s. In these contributions to the early Austrian socialist calculation debate, Polanyi discusses how to gain knowledge of the economic and social processes in such a way that the economy can be democratically governed according to its socialist aims and purposes. This article highlights the relevance of Polanyi’s work on socialist accounting, along with his later perspectives on technology and on social scientific method, for reflecting upon data- and algorithm-driven economic governance. Polanyi’s critical analysis of abstraction effected through methods of knowing suggests a sceptical stance vis-à-vis current versions of technological ‘solutionism’, which places its faith in data and algorithms as tools for economic and social, or socialist, planning.
Sociology; Economics
Keywords: Karl Polanyi; accounting; data analytics; digital socialism; economic theory; overview; socialist accounting; socialist calculation

Polanyi and the Peasant Question in China: State, Peasant, and Land Relations in China, 1949–Present - Chuang, Julia; Yasuda, John (Politics & Society, 2022)
This article applies Karl Polanyi’s concept of a double movement to the trajectory of rural state policies in China since 1949. It argues that Chinese socialism created a contradictory social contract that has fueled an ongoing struggle between state and peasantry over the surplus generated from rural land. This struggle has shaped a historical oscillation between state policies that facilitate extraction of agricultural surpluses and policies that introduce social protections in the form of household farming and revitalized collective ownership. Based on secondary sources, this article compares the arc of rural policies during the Mao era and in the transition to and during the current state capitalist period. Then, based on original interview-based and ethnographic fieldwork undertaken in rural Sichuan Province, it analyzes the current introduction of urban and agrarian capital into the rural economy, revealing dynamics of a current countermovement from state-led extraction to compromise.
Publisher: SAGE Publications Inc
Keywords: China; Polanyi; agrarian transition; land politics; peasant politics; state capitalism; urbanization

Planning laissez-faire: Supranational central banking and structural reforms - Braun, Benjamin; Carlo, Donato Di; Diessner, Sebastian (Zeitschrift für Politikwissenschaft, 2022)
The mandate of the European Central Bank (ECB) does not extend to labor market and social policies at the national level. Why, despite the reputational costs, did the ECB act as a staunch advocate of structural labor market reforms from 1999 through 2015? We discuss this question through the theoretical lens of Karl Polanyi’s The Great Transformation. Although Polanyi has been a key reference point for the debate on the social consequences of European economic and monetary integration, one of his key insights has received surprisingly little attention—that central banks have the power to mitigate the impact of international economic integration on domestic social protection. Polanyi regarded central banks—much like trade unions—as national-level institutions of non-market coordination, acting as a protective buffer against the functional pressures of the fixed-exchange-rate monetary regime that was the international gold standard. By contrast, the ECB, as a supranational central bank, embodies these functional pressures. This helps explain why, rather than protecting existing social structures against the logic of the fixed-exchange-rate monetary regime, the ECB has sought to protect the monetary regime by going out of its way to re-shape labor market institutions at the national level.
Sociology
Keywords: European Central Bank; Europäische Zentralbank; Karl Polanyi; monetary integration; social protection; sozialpolitik; structural reforms; strukturreformen; wirtschafts- und währungsunion

The Political Economy of Revolution: Karl Polanyi in Tahrir Square - Zayed, Hany (Theory, Culture & Society, 2022)
The causes and consequences of revolutionary change have long been the subject of scholarly debate. Through a systematic integration of political economic elements into an analysis of contemporary social transformations, this article joins this conversation by asking how Karl Polanyi’s double movement framework can clarify, and be extended by, the Egyptian Revolution of 2011. By embedding a nuanced account of neoliberalism in Egypt’s modern politics and by bringing those in dialogue with Polanyi’s theoretical apparatus, this article contends that there is a broad alignment between the first movement and the Egyptian neoliberal experience, a partial alignment between the second movement and the Egyptian Revolution, and a multilayered entanglement that implicates and encircles both movements. Not only does this research demonstrate that contemporary Egyptian history can find new currency in and be further illuminated by Polanyi’s political economy, it also critiques, complicates, reconceptualizes and extends Polanyi’s theoretical framework. In so doing, it redresses the underfocus of Polanyian political economy on the theory of revolution in general and the Egyptian Revolution in particular, problematizes extant accounts on neoliberalism and the double movement, and extends analyses between neoliberalism and revolution in political economy literatures. By clarifying our understanding of contemporary social change, this essay underscores how Polanyi’s work remains a pertinent, viable and valuable prism to examine momentous social transformations.
Publisher: SAGE Publications Ltd
Keywords: Egypt; Karl Polanyi; double movement; neoliberalism; revolution

The political trilemma of contemporary social-ecological transformation – lessons from Karl Polanyi’s The Great Transformation - Novy, Andreas (Globalizations, 2022)
This article advances Rodrik's political trilemma of the world economy by using insights from Polanyi’s The Great Transformation, which helps to grasp the interwoven dynamics of long-term transformations due to climate change and geopolitical reordering on one hand, and on the other short-term political ruptures due to countermovements. Rodrik's globalization trilemma shows the incompatibility of hyperglobalization with the need for an enlarged democratic policy space. Its nodes (globalization, nation state and democracy), however, have to be redefined to grasp contemporary dynamics of deglobalization. Based on a modified political trilemma of contemporary social-ecological transformation, I discuss and compare three visions and the resultant strategies: (1) Liberal globalism, focusing on hyperglobalization and individualism, (2) nationalistic capitalism, stressing national sovereignty and authoritarian governance, and (3) foundational economy based on planetary coexistence which combines selective economic deglobalization with a strengthening of a place-based foundational economy, and their respective social-ecological infrastructural configurations.
Political Science; Economics
Keywords: Great Transformation; The (Book); Polanyi; deglobalization; foundational economy; hyperglobalization; social-ecological transformation

The double movement in Africa: a Nkrumah-Polanyi analysis of free market fatigue in Ghana’s private sector - Langan, Mark (Review of International Political Economy, 2021)
Karl Polanyi’s double movement is a key tool for conceptualising free market fatigue in African business communities wrought by the insecurities of trade liberalisation. Synthesising Polanyi with Kwame Nkrumah’s work on neo-colonialism, the article argues that exhausted business communities in Africa can contest free market reforms and push for a return to developmentalist strategies, underscoring a double movement. In this discussion it highlights Ghana, a ‘donor darling’ in terms of historical implementation of free market reform. It builds upon the author’s engagement with 66 interviewees – business people and policy stakeholders – in relation to the condition of that country’s poultry and tomato industries. Unpacking interviewee narratives, the article points to a striking common theme, namely that business stakeholders call for the re-embedding of the economy via developmentalist strategies to move beyond neo-colonial trade systems. In this vein, the article provides an original contribution to studies of International Political Economy by demonstrating the efficacy of a Nkrumah-Polanyi ensemble for making sense of business communities’ potential role in countermovements for developmentalism in Africa.
Political Science
Keywords: Ghana; Nkrumah; Polanyi; double movement; free trade; neo-colonialism; private sector

Neoliberal Capitalism and Visegrád Countermovements - Hann, Chris; Scheiring, Gábor (Europe-Asia Studies, 2021)
Area Studies; Anthropology
Keywords: countermovement; populism; visegrad countries

Seeing like a Socialist: On Socialist Worldviews from Polanyi to Taylor to Now - Grant, John; Dunlop, Mallory (New Political Science, 2021)
In this article we argue that reinvigorating socialist politics requires championing a socialist worldview that goes beyond the critique of capitalism. Neglecting such an outlook leaves socialism tethered to the fortunes of capitalism and inhibits a broader account of its own virtues. We begin by explaining why worldview thinking is appropriate today. Then we examine two underappreciated works by Karl Polanyi (his 1927 lecture “On Freedom”) and Charles Taylor (his 1974 essay “Socialism and Weltanschauung”). Each treats worldview thinking as indispensable and we use them as catalysts for developing a socialist vision. Finally, we bring our insights to bear on the worldview potential of socialist republicanism. We contend that a promising worldview emerges by elaborating the following components: a political anthropology of human possibilities; anti-capitalism, social freedom, and non-domination; socialist civic virtues; and the promise and limits of pluralism.
Publisher: Routledge _eprint: https://doi.org/10.1080/07393148.2021.2002093
Keywords: TAYLOR; Charles; socialism

The Greater Transformation: Digitalization and the Transformative Power of Distributive Forces in Digital Capitalism - Pfeiffer, Sabine (International Critical Thought, 2021)
This article discusses digitalization and its connection with the political economy of transformation. Its point of departure is Karl Polanyi's historical analysis as presented in The Great Transformation. Polanyi analyzed the development of “self-regulating” markets—with transformative and destructive consequences for individuals, nature, and society—and government efforts to contain these consequences. Polanyi's perspective is compared to Marx's theorem of the development of productive forces. Their respective focal points are different but complementary. For Polanyi, the decisive historical and theoretical break (and the cause of the destructive effects) lies in the act of purchasing human labor, whereas for Marx it lies in the act of producing value and in the relations of production as well as the relations of distribution linked to it. Working from this theoretical basis, current developments in digitalization are analyzed not as a further development within productive forces but as a transforming development of distributive forces. Following the logic of The Great Transformation, current developments should thus not be interpreted as a second great transformation but as the augmentation of the first, leading to a “greater” transformation associated with even more destructive potential. This leaves little hope for a smooth transition into any form of post-growth society.
Sociology
Keywords: digital capitalism; digital transformation; distribution; political economy; productive forces

Karl Polanyi, the New Deal and the Green New Deal - Dale, Gareth (Environmental Values, 2021)
In this paper, I present an analysis of those aspects of Karl Polanyi's social and political thought that relate to environmentalism and 'green' politics today. I discuss whether or not he prefigured the degrowth movement, before focusing on his understanding of the New Deal (1933-1939). At the time of writing, the prospect appears likely of a return, at a global scale, of economic slump, mass unemployment and ecological crisis, the background conditions to which Franklin D. Roosevelt's New Deal was responding on the national scale. The paper concludes by drawing lessons from this comparison for possible Green New Deals.
Keywords: Green New Deal; Karl Polanyi; New Deal; degrowth; embeddedness

On Polanyi - Munck, Ronaldo (Area Development and Policy, 2021)
Karl Polanyi provides a rich repertoire of concepts to build a critical understanding of the world of globalization and alternatives to the status quo. In reviewing two recent collections around the work of Polanyi, we show some of the concepts that might be developed in terms of ‘using Polanyi’. This would include his inspired double-movement concept and the way he dealt with non-capitalist societies. Polanyi is as relevant for the so-called developing societies as he is for the advanced industrial societies where he has garnered most attention.
Publisher: Routledge _eprint: https://doi.org/10.1080/23792949.2020.1830708
Keywords: Polanyi; double movement; globalización; globalization; movimiento doble; no capitalista; non-capitalist; Поланьи; глобализация; двойное движение; некапиталистический.; 全球化; 双重运动; 波兰尼; 非资本主义

Karl Polanyi and the Reappraisal of Happiness Economics - Özveren, Eyüp; Gürpinar, Erkan; Karagöz, Ufuk (Journal of Economic Issues, 2021)
Happiness economics unearths the undesirable effects of economic growth and criticizes the economic model based on the belief in the supremacy of market relations over the relational bonds of society. Economic growth brings about substantial increases in material well-being; yet, it has the potential to destroy the social and environmental fabric of society. This is visible in the post-World War II cross-country variability of the subjective well-being measures, which shows the importance of relational goods and associational activities. These themes echo Karl Polanyi’s concerns over the destructive effects of the self-regulating market mechanism. In this paper, we demonstrate the relevance of the interdisciplinary work of Polanyi for happiness economics. We argue that Polanyi’s conception of the self-regulating market system comes together with the spread of unhappiness. The treatment of labor as a fictitious commodity is of utmost significance in this respect. No less important is the similar degrading of land, a proxy for environment. Furthermore, the distinction Polanyi maintained between “exploitation” and “cultural degeneration” in assessing the Industrial Revolution is useful for this critique. In essence, Polanyi’s approach is relevant to explain the deterioration of social relations, which is thought to be the ultimate reason behind the happiness paradox.
Economics
Keywords: Karl Polanyi; consumption; happiness; hedonism; self-regulating market system

CAPITALISM, DEMOCRACY, AND SOCIAL THEORY IN KARL POLANYI: AN INTERVIEW WITH GARETH DALE - Santos, Rodrigo Salles Pereira dos; Onto, Gustavo Gomes (Sociologia & Antropologia, 2021)
Resumo Uma introdução à entrevista realizada com Gareth Dale (Brunel University) − economista político e especialista na trajetória e na obra de Karl Polanyi − e a um conjunto de textos inspirados na abordagem polanyiana publicados neste número de S&A. Recupera questões-chave apresentadas na entrevista e na obra de Dale, dando relevo à literatura recente produzida sobre o autor, à contínua e difundida relevância das ideias de Polanyi para a compreensão do capitalismo e da democracia, e a uma leitura crítica e aberta de suas contribuições teóricas. Divulga as contribuições específicas, teóricas e empíricas, de quatro artigos originais que mobilizam ativamente conceitos polanyianos no entendimento da pluralidade dos processos de enraizamento e das dinâmicas do movimento duplo, de mercantilização da terra e do trabalho, e da centralidade da praça de mercado no capitalismo contemporâneo; além dos aportes de um registro de pesquisa e duas resenhas sobre agências e pedagogias econômicas e financeirização da vida cotidiana. An introduction to the interview with Gareth Dale (Brunel University) − a political economist and expert on Karl Polanyi’s life and work − and to a set of papers, inspired by the Polanyian approach, published in the current issue of S&A. The paper highlights key questions presented in the interview and in Dale’s work, with a focus on the recent literature produced about the author, the continuous and widespread relevance of Polanyi’s ideas for the understanding of capitalism and democracy, and a critical and open reading of his theoretical contributions. Next, the paper presents the specific contributions, both theoretical and empirical, of four original papers that actively dip into Polanyian concepts in understanding the plurality of the embeddedness processes and the dynamics of the double movement, the commodification of land and labor, and the centrality of the marketplace in contemporary capitalism; as well as the contributions of a research recording and of two book reviews on economic agencies and pedagogies and the financialization of everyday life.
Sociology; Anthropology
Keywords: DALE; Gareth; Karl Polanyi; capitalism; democracy; market

New Limits of the Neoliberalism: Society and Market - Vidal, Laura; Correa, Eugenia (Journal of Economic Issues, 2021)
Neoliberalism has been able to change the markets and the economy of societies around the world. These transformations are especially important with regards to fictitious commodities: land, labor, and money. However, the 2020 pandemic imposes new limits, when life itself is at risk globally. This work highlights the major neoliberal reforms relating to fictitious commodities, the difficulties of society to resist and create counterweights. The health crisis that has emerged with the COVID-19 pandemic is the result of decades of over-exploitation of nature and human beings. The reforms over fictitious commodities, especially labor, have led to a constant and systematic decline of society. This article is supported by the theoretical legacy of Karl Polanyi and Kari Polanyi Levitt that allows us to consider the most important trends of neoliberal reforms and their main objectives.
Economics
Keywords: fictitious commodities; health crisis; neoliberal counterrevolution; neoliberalism

Non-market institutions and crime in US counties: Hayek v. Polanyi - Zullo, Roland (Review of Social Economy, 2021)
Karl Polanyi’s The great transformation emphasized the importance of non-market institutions for social equity and stability. In that same era, Friedrich Hayek postulated in The road to serfdom that superior economies were market-based and featured minimal government. I compare these worldviews in relation to property and violent crime. Using US county data, change in crime is modeled as a function of economic structure, economic conditions, and demographics. Consistent with Polanyi, the size of the public sector in the economy negatively associates with crime. Within the public sector, education is a critical crime-reducing function, more so than law enforcement. Industry diversity is positively associated with crime, contrary to Hayek. Manufacturing equates with lower crime and the size of the private non-profit sector is unrelated to crime. Overall the results favor Polanyi’s assertion that non-market institutions are necessary to counter the harsh outcomes arising from market economic systems.
Publisher: Routledge _eprint: https://doi.org/10.1080/00346764.2019.1663909
Keywords: H41 (public goods); P17 (capitalism performance); Socialism; Z13 (economic sociology); crime; laissez-faire; non-market institutions; public goods

On the meaning and contemporary significance of fascism in the writings of Karl Polanyi - Millett, Kris (Theory and Society, 2021)
This paper assesses the contribution of Karl Polanyi, a theorist largely ignored in fascism scholarship, toward understanding fascism’s interwar rise and present-day implications. In exploring Polanyi’s work in The Great Transformation and lesser-known and unpublished writings, a sophisticated and largely original conception of fascism emerges, rooted in the idea of ‘anti-individualism’ as its foundational trait. Polanyi accounts for fascism’s philosophical content, ideological plasticity, political function and societal form, intervening in debates over how to define fascism, its ambiguity with the populist far-right, and on its both economically reactionary and socially revolutionary qualities. Polanyi’s analysis suggests an enduring vulnerability on the part of liberal capitalism to fascist currents as (1) a solution to the instability of the market economy (and broader incompatibility between capitalism and democracy) at the systemic level, and (2) to the crisis of the individual subject on a social and moral level. I end by considering how Polanyi’s theory might be applied to locate current neo-fascist movements and elucidate the sociological problems underpinning their existence.
Sociology
Keywords: Anti-individualism; Fascism; Neo-fascism; Polanyi; Totalitarianism; Vitalism

Karl Polanyi: a theorist of mixed economies - Szelényi, Iván; Mihályi, Péter (Theory and Society, 2021)
Karl Polanyi’s scholarship is interpreted in radically different ways. The “hard” reading of Polanyi sees him as a radical socialist; the “soft” reading presents him as a theorist of mixed economy. This article sides with the soft interpretation. It uses Polanyi’s biography to explain his theoretical “elusiveness,” presents a novel interpretation of his three types of economic integration, claiming all economies are “mixed.” While it acknowledges Polanyi as one of the major sources of world system theory, it claims that Polanyi saw not only the dangers, but also the necessity and positive consequences of globalization. Finally, it shows that, in spite of Polanyi’s life-long commitment to the political left, his scholarly work did not offer an apology of socialism. Instead this article uses Polanyi’s theory of economic integration to build a critical political economy of state socialism.
Keywords: capitalism; reciprocity; redistribution; rent-seeking; socialism; world system theory

Our Obsolete Marketing Mentality: George Fisk, Meet Karl Polanyi - Benton, Raymond (Journal of Macromarketing, 2021)
Marketing in general can have greater influence if a new, yet old, perspective on marketing is adopted—something akin to the original orientation of marketing. Adopting George Fisk’s definition of marketing and marrying it with notions derived from the institutional economist Karl Polanyi is proposed. The histories of marketing thought and of institutional economics are reviewed to demonstrate their affinity and similar origins. Fisk’s conceptualization of marketing as societies’ provisioning systems is shown to correspond with Polanyi’s conceptualization of economies as instituted processes, admitting more than the market and the state as ways economies have historically and cross-culturally integrated with society. The obsolete marketing mentality is that marketers, including macromarketers, are overly fixated on the market and ignore or overlook alternatives. The Fisk/Polanyi orientation will attract macromarketers interested in marketing and development, critical marketing, sustainability, alternative economies, and those interested in the long-term prospects of macromarketing. Adopting this old, but new, framework will connect the past with the future, permit macromarketers make a mark on a larger intellectual landscape and serve to invite scholars in this larger landscape to engage with macromarketing.
Publisher: SAGE Publications Inc
Keywords: Future of Macromarketing; George Fisk; German Historical School; History of Economic Thought; Institutional Economics; Karl Polanyi; Marketing and Economics; history of marketing thought; macromarketing

Fascism and the enduring problem of the liberal individual in Polanyi - Millett, Kris (Dewey Studies, 2021)
This application of Polanyi to the question of fascism’s resurgence provides an important corrective to mainstream liberal explanations (e.g., Albright 2018), inviting the reader to “look up rather than down” (Lim 2021) by tying fascism’s significance to the functioning of the capitalist system rather than to the personalities of fascist politicians or their degree of mass support. The merits of this notwithstanding, I argue that current Polanyian treatments have neglected to engage with a core aspect of Polanyi’s theory, which is that fascism, at its roots, is a fundamentally anti-individualist ideology that aims to address a moral and social crisis of the individual subject in liberal capitalism. Omitting this risks obfuscating what makes fascism distinctive as well as why its ideas have retained their appeal.
Sociology
Keywords: essence of fascism; fascism; individualism

Karl Polanyi on strategy: The effects of culture, morality and double-movements on embedded strategy - Faulconbridge, James R.; Muzio, Daniel (Critical Perspectives on Accounting, 2020)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market.
Management; Accounting
Keywords: Double movement; Globalization; Law firms; Polanyi; Strategy

A Polanyi-inspired perspective on social-ecological transformations of cities - Bärnthaler, Richard; Novy, Andreas; Stadelmann, Basil (Journal of Urban Affairs, 2020)
Based on a Polanyi-inspired research program, we analyze urban transformations as interrelations between infrastructural configurations, i.e. context-dependent material infrastructures and their multi-scalar political-economic regulations, and socio-cultural modes of living. Describing different modes of infrastructure provisioning in Vienna between 1890 and today, we illustrate how political-economic processes of commodification and decommodification have co-evolved with socio-culturally specific modes of living, grounded in different classes and milieus. We show how, today, two modes of living—“traditional,” established during postwar welfare capitalism, and “liberal,” formed during neoliberal capitalism—co-exist. In the current conjuncture of rising inequality, neoliberal urban regeneration, and accelerating climate crisis, these modes of living are not only increasingly polarized and antagonistic, but also increasingly unable to satisfy needs and self-defined aspirations. Therefore, we explore the potential of social-ecological infrastructural configurations as an alliance-building project for a systemic social-ecological transformation, potentially linking different classes, social segments and forces around a common eco-social endeavor.
Publisher: Routledge _eprint: https://doi.org/10.1080/07352166.2020.1834404

Polanyi meets Bolsonaro: Reactionary politics and the double movement in twenty-first-century Brazil - Evans, Peter (International Sociology, 2020)
Twenty-first-century Brazil’s political evolution is a window on the dynamics of contemporary political transitions. The inability of Brazil’s Workers’ Party to sustain its social democratic project and the subsequent rise of the reactionary regime of Jair Bolsonaro are, in turn, part of a global pattern of political change. Karl Polanyi’s vision of the ‘double movement,’ in which the dominance of the market vies with the countervailing movement for social protection, offers an analytical springboard for reflecting on these political transitions. Trying to understand the movement for social protection leads to examining ebbs and flows in the momentum of mobilization. Trying to understand how market dominance leads to reaction brings us back to Polanyi’s advocacy of ‘crass materialism’ as a lens for looking at reaction, and from there to consideration of how the structural power of capital undercuts efforts at social protection and opens the door to reaction.
Publisher: SAGE Publications Ltd
Keywords: Brasil; Brazil; Brésil; Polanyi; finance; finanzas; protección social; protection sociale; reacción; reaction; réaction; social protection

Re-grounding the city with Polanyi: From urban entrepreneurialism to entrepreneurial municipalism - Thompson, Matthew; Nowak, Vicky; Southern, Alan; Davies, Jackie; Furmedge, Peter (Environment and Planning A: Economy and Space, 2020)
Conventional approaches to local economic development are failing to address deepening polarisation both within and between city regions across advanced capitalist economies. At the same time, austerity urbanism, particularly in the UK, presents challenges for urban authorities facing reduced budgets to meet increased demands on public services. Municipalities are beginning to experiment with creative responses to these crises, such as taking more interventionist and entrepreneurial roles in developing local economies, generating alternative sources of revenue or financialising existing assets. Rooted in a Polanyian perspective and building on the concepts of the entrepreneurial state and grounded city, we identify an embryonic alternative approach – what we call ‘entrepreneurial municipalism’ – as a policy pathway towards resolving enduring socioeconomic problems where neoliberal urban-entrepreneurial strategies have failed. We situate entrepreneurial municipalism as one strand in an assemblage of new municipalist interventions, between radical urban social movements and more neoliberal strategies such as financialised municipal entrepreneurialism. Drawing on original research on the Liverpool City Region, we explore how local authorities are working with social enterprises to harness place-based assets in ways which de-commodify land, labour and capital and re-embed markets back into society. Finally, we draw upon Polanyi as our guide to disentangle differences in approach amongst divergent forms of municipalist statecraft and to critically evaluate entrepreneurial municipalism as a possible trajectory towards the grounded city.
Publisher: SAGE Publications Ltd
Keywords: Entrepreneurial state; Polanyian economic geography; local economic development; municipal statecraft; urban policy

BRIE Working Paper 2020-6 What Polanyi Teaches Us: The Platform Economy and Structural Change - Eldred, Christopher (The Berkeley Roundtable on the International Economy, 2020)
The welfare system was meant to reduce the 9 vulnerability of citizens to the market, thereby containing the consequences of the market economy and labor commodification. [...] As an adaptation to the consequences of the market, the welfare system is an effort to cushion the effects of the market, not a change its underlying logic of commodification. [...] From this perspective, the political debates about the rules to be applied to the operations of the platform economy are part of the “second movement,” i.e., a reaction to the platform economy. [...] In contrast, to the industrial revolution where the capitalist moved production into the factory to develop greater control than was possible with the putting-out system, the platform extrudes the work and obligations outside the boundaries of the firm. [...] In actuality the relationship between the members of the ecosystem and the platform is hierarchical and based upon an extreme power asymmetry within which the ecosystem members are at the mercy of the platform which controls the nexus of relationships (Cutolo and Kenney, 2020).
Economics
Keywords: platform economy; welfare

Commodification & countermovement: community-supported agriculture (CSA): a case study in Minas Gerais, Brazil - Matzembacher, Daniele Eckert; Meira, Fabio Bittencourt (Organizações & Sociedade, 2020)
The conventional way of producing and distributing food is based on the use of agrochemicals, fertilizers, industrial fertilizers and other techniques from the Green Revolution, with increasing dependence on financial-industrial capital, which implies the intensification of the agriculture commodification. The object of this study was the emergence of modes of organization resisting this trend. Based on the theoretical reference of Karl Polanyi (2012a, 2012b), a case study was developed in a Community-Supported Agriculture (CSA) initiative. It is a movement that resituates agricultural production through the principles of fair trade, agroecology and the use of short supply chains, which bring production and consumption closer together. The result is a better nutritious quality food at affordable and fair price. The analysis of the CSA Alfa case points to the coexistence of different principles of regulation, in a combination of mercantile exchange and reciprocity. According to the proposition by Karl Polanyi, the economic activity is shown to imbricate with the social aspect, of which friendship, tolerance, fidelity and commitment establish a community ethos around food. The CSA seems to manifest a countermovement to the commodification by enhancing the relative autonomy of individuals that elevates the social cohesion of the participating groups. Resumo A forma que se tornou convencional de produzir e distribuir alimentos baseia-se no uso de agroquímicos, adubos, fertilizantes industriais e de outras técnicas provenientes da Revolução Verde, com crescente dependência do capital financeiro-industrial. Isto significa a intensificação da mercantilização da agricultura. O problema que norteou esta pesquisa é a emergência de modos de organização resistentes a essa tendência. Com base no referencial teórico de Karl Polanyi (2012a, 2012b), construiu-se um estudo de caso cujo objeto é a agricultura sustentada pela comunidade, cujo acrônimo em inglês é CSA (community supported agriculture). Trata-se de um movimento que ressitua a produção agrícola pelos princípios do comércio justo e da agroecologia e uso de cadeias curtas que aproximam produção e consumo. O resultado é um alimento de qualidade nutritiva superior a preço acessível e justo. A análise do caso CSA Alfa aponta a coexistência de diferentes princípios de regulação numa combinação de troca mercantil e reciprocidade. Na esteira de Karl Polanyi, observa-se a atividade econômica imbricada ao social, daí que amizade, tolerância, fidelidade e comprometimento estabelecem um ethos comunitário em torno do alimento. A CSA parece manifestar um contramovimento à mercantilização ao potencializar a autonomia relativa dos indivíduos, o que eleva a coesão social dos grupos participantes.
Political Science; Management Studies
Keywords: Karl Polanyi; commodification; community-supported agriculture; reciprocity; social cohesion

The Euro as a Polity: Karl Polanyi in Frankfurt? - Thomasberger, Claus (Global Perspectives, 2020)
As factors of production, labor, money, and land play a role in economics that is rarely understood. The difficulty of deriving the contribution of the individual factor of production to the value of jointly produced final commodities (the famous “problem of imputation”) occupied generations of Austrian economists (Hayek 1984) and inspired Ludwig Mises to produce his 1920 article “Economic Calculation in the Socialist Commonwealth” (Mises 1935). Any attempt at rational socialist planning is utopian, Mises argued, because only price-making markets for the factors of production provide the information for economically rational decision-making. If the birthplace of neoliberalism was, as Slobodian (2018, p. 30) put it, Ludwig Mises’s office in the Vienna Chamber of Commerce, this article was its moment of birth.Karl Polanyi was one of the first to respond, doing so in the same journal in which Mises’s piece had been published, the Archiv für Sozialwissenschaften, long before Friedrich Hayek, Walter Lippmann, Lionel Robbins, and German ordoliberals such as Alexander Rüstow and Wilhelm Röpke intervened (Polanyi 2016, 2018b). In his contributions to what became the famous socialist accounting debate, Polanyi outlined his idea of a society’s “constitutional form … as a relationship of mutual recognition” (Polanyi 2018a, 54) based on direct cooperation between consumers and producers, as well as a functional democracy.Two decades later, Polanyi resumed this discourse with a more radical critique, making use of Mises’s argument for his own end (cf. Thomasberger 2020). Mises’s case for price making markets is no less utopian than the central planning model, he argued in The Great Transformation (TGT). The crucial point, Polanyi contended, is that the factors of production are fundamentally different from genuine commodities. Polanyi drew on a line of reasoning put forward by the sociologist Ferdinand Tönnies (2001, p. 81-82) and by Mises’s intimate enemy, the Austrian economist Friedrich Wieser (1927, p. 175-77), who was inclined toward Fabian socialist ideas. Given that the factors of production are not (and cannot be) produced for sale by private enterprises, the commodity form of labor, money, and land is fictitious.Polanyi’s category fictitious commodities is the pivot of Klein’s paper. This starting point allows him to go beyond the common interpretation of Polanyi’s work, which focuses on the dichotomy of market opening and social closure, and to address instead a more profound problem: the conflict between capitalism and democracy. Such a reading is indeed closer to the core of the Polanyi approach, which refers to a society that “transcends the self-regulating market by consciously subordinating it to a democratic society” (Polanyi 2001, 242). Not social protection, but democracy, is the alternative to the self-regulation of the market. Polanyi never believed that protection could achieve more than a temporary stabilization of market society. In fact, it is somewhat paradoxical that in the discussion about the contradictions of European integration, Polanyi is celebrated as a defender of societal closure, while he himself expressed the conviction that the protective measures “impaired the self-regulation of the market, disorganized industrial life … and finally disrupted the social organization based upon it” (Polanyi 2001, 4). From the point of view of the conflict between capitalism and democracy, the institutions that result from the attempt to commodify labor, money, and land are crucial because they are, as Klein puts it, the “point of entry of political power into the economic sphere” (Klein 2020, 11). Concerning the debate about the crisis of European integration, this is a rather unexplored terrain.In what follows, I will not discuss the question of whether the category fictitious commodities can be fruitfully linked to the idea of premodern modes of economic integration, a connection that Polanyi himself never established. Instead, I will concentrate on two issues that Klein’s paper raises without discussing them explicitly. The first question is: What if the creation of a self-regulating market system becomes the dominant political goal? What if, for example, the central bank is transformed into a market maker for money on political grounds? The second point seems to me even more important. Europe is not a nation. However, “in Polanyi’s schema, the self-regulating market was a national economic institution” (Polanyi-Levitt 2013, 89), which linked the “rest of the world” to England by a “golden straightjacket,” as Polanyi’s daughter, the development economist Kari Polanyi Levitt, remarked. In TGT even European colonialism plays only a marginal role. As a result, European integration after World War II raises issues that Polanyi did not discuss in depth. I will proceed in two steps: First, I will reconstruct some essential points of Polanyi’s analysis. Following this, I will pose the question of how to apply his analysis to Europe.From the point of view of a market system, the crux of the factors of production—or the fictitious commodities, as I shall hereinafter refer to them—is that, on the one hand, private enterprises must be enabled to buy labor, land, and money on a market. On the other hand, private companies are notcapable of producing and selling the fictitious commodities. The difficulty is obvious: In a market economy, enterprises depend on markets for the fictitious commodities, but such an economy is unable to produce them. This means that the market system depends on external forces. Certainly, this is also true for other institutions and social infrastructures that only the state can provide. However, the fictitious commodities are different in that they cannot be understood as part of the extra-economic framework. Labor, money, and land are economic factors; they are the condition sine qua non of the market system. No self-regulation is conceivable without including the fictitious commodities. What legal scholars with regard to the secular state call the Böckenförde dilemma in the case of fictitious commodities affects economic liberalism directly. The market system is unable to produce and reproduce itself spontaneously. The economic mechanism lives by prerequisites it cannot create. Social institutions are required to provide what for the functioning of a market system is indispensable. Only society can provide the commodities on which a market economy is based. Therefore, in a market society, the economy is not—and can never be—a functional machinery. “Laissez-faire economy was the product of deliberate State action,” as Polanyi (2001, p. 147) stated, summing up the nineteenth-century answer to the dilemma. The different institutions that coordinate economic activities are the outcome not of functional pressure but of a political struggle around the (de)commodification of the fictitious commodities. “Market economies are polities,” to paraphrase the felicitous title of a book edited by Christian Joerges, Bo Stråth, and Peter Wagner (2005).In other words, an ideal market society presupposes the political creation and regulation of particular social institutions whose purpose is to simulate market conditions. Unemployment insurance, health care, union legislation, central bank acts, land property rules, and environmental regulations are indispensable for transforming labor, money, and land into commodity-like entities. Here a conflict between the social nature of the task and its economic role arises. From the perspective of the market system, these institutions fulfill the function of market makers. However, from the viewpoint of society, they allow for various forms of political regulation and economic planning, taking into account the social needs of the different strata of society. It is this tension between their political roots and their economic function within the market system that puts these institutions at the center of the political struggle. Since law cannot ignore prevailing ideals, worldviews, and external expertise, it plays a contradictory role in this process, functioning as a vehicle for commodification and political regulation.In TGT Polanyi showed that from the beginning, law played a key role in the process of commodification. In England, three legal regulations were crucial:Even if a market society presupposes the commodification of all three fictitious commodities, for reasons of space I will concentrate on money. The crucial point is to understand that the nineteenth-century gold standard was primarily not an economic but a political system.In the first decades of the century, substantially inconvertible paper money circulated in England. The commercial banks—and their theoretical advocates, the so-called Currency School—pushed for the right to provide money according to the banks’ calculations. In contrast, the supporters of the Banking School argued that this would lead to the risk of an overissuance of notes. The essential feature of the banking system created by the abovementioned Peel’s Bank Act was to keep the supply of money artificially scarce by linking the amount of banknotes to the quantity of gold in the issuing department of the Bank of England (BoE). By law, political control and the discretionary influence of the government on money and banking were reduced to a minimum.Over the course of the century, the commodification of labor, money, and land in England set in motion a transformation on a global scale. Relying on bank money, the market system generated a previously unknown social and economic dynamic. In the last decades of the “long” nineteenth century, Polanyi (2001, p. 136) commented, “a new way of life spread over the planet with a claim to universality.” The international gold standard gave birth to a worldwide system, in which the constitutional regimes became almost the corollary of the gold standard.Here we can observe in outline two problems that we encounter again in Europe today: (1) Given the legislation that forced central banks to limit the supply of money, the international gold standard not only limited the British government’s room for maneuver, but it confined also, and often even more strictly, the policy space in the other countries. The open market for money and finance created international economic and political interdependencies, which reached deeply into society and undermined democratic aspirations. Social legislation, labor unions, and budgetary and monetary policy were forced to accept the priority of the external monetary stability even if this was in contradiction to national interests. (2) The variety of socioeconomic environments, institutional traditions, and sociopolitical objectives in different countries was negated. The gold standard forced the individual countries to adapt to the liberal economic model with its universal aspirations.The BoE functioned as the conductor of the global monetary orchestra. Polanyi introduced two categories to describe the international dependencies in this period: “anarchistic sovereignty and ‘justified’ intervention in the affairs of other countries” (Polanyi 2001, 261). On the one hand, sovereignty was “anarchistic” insofar as under the gold standard and the prevailing system of unregulated foreign trade, governments lacked any power with respect to international economic affairs. The treatment of trade as a relationship between private undertakings made effective international (political) economic cooperation between states impossible. On the other hand, interventions were “justified” whenever the budgets, finances, and currencies of debtor countries required control. Given the rigidities of the economic system, Polanyi underlined that “the peoples of the world were institutionally standardized to a degree unknown before” (Polanyi 2001, 261).At the same time, however, the inelasticity of the gold supply resulted in a deflationary bias that spread over the world. Even if central banks tried to introduce some doses of flexibility, the system required the adjustment of wages and prices to the current account balances, affecting both the opportunities for profit and the living conditions of large sections of the population. Such a rigid system could survive, Polanyi summarized, only as long as popular democracy was suppressed. Confronted withIn nineteenth-century England, the gold standard and popular democracy were irreconcilable. This explains why attempts to restore the former in the 1920s were bound to fail. Barry Eichengreen took up Polanyi’s point when he pointed out that after the First World War, “the spread of universal suffrage and … the consequent politicization of the policy environment … had destroyed the viability of the gold standard itself” (Polanyi 2001, 233–34). As long as prosperity prevailed, the conflict could be contained. Not so in crisis situations. The restored international gold standard collapsed in 1931.The European Monetary Union (EMU) is at the heart of current debates on the crisis of European integration. Whether Streeck (2014, p. 185) calls the EMU “a political mistake” or Habermas (2012, p. 3) criticizes the “construction flaw of a monetary union,” they share a focus on the Maastricht process. Obviously, this interpretation ignores the fact that the crisis also includes countries—among others the United Kingdom, Poland, and Hungary—that have never been part of the EMU.If we look at the crisis from Polanyi’s perspective, the focus shifts. Not the EMU but the Single European Act, signed in 1986, emerges as the turning point. The single market program was by no means the deregulatory exercise that the European Commission had presented it as being. It was about developing competition throughout the European Union, including markets for labor, land, and money. The novel feature of the program was that it aimed at creating cross-national markets for the fictitious commodities between democratically constituted countries. This is not to say that markets for genuine goods do not cause interdependencies; however, the political character of the process of commodification of the fictitious commodities produces interdependencies of a different quality. Economic, monetary, fiscal, income, and social policy decisions in one country affect directly all other countries participating in the single market. They create political interdependencies, which, if we take Habermas’s understanding that “democratic self-government means that the addressees of mandatory laws are at the same time their authors” (Habermas 2012, 14), is incompatible with national democracy.Why did Jacques Delors and the European Commission nevertheless argue for the creation of Europe-wide markets for the fictitious commodities? Did they underestimate the political costs? Or did they believe that the economic benefits outweighed the loss of political self-determination?It is important to keep in mind that the discussions within the economic discipline never led to the consensus that the European Commission assumed. David Ricardo (1817) had already argued that markets for production factors are by no means necessary in order to enjoy the advantages of the international division of labor. In the twentieth century, declared supporters of free trade such as Gottfried Haberler (1930) and Jagdish Bhagwati (1998) took the same line. Recently, an IMF Staff Paper evaluating empirical studies on the effects of financial globalization concluded that there is evidence not of direct economic gains but rather of political effects: “Our interpretation of the newer literature is that … financial openness can … impose discipline on macroeconomic policies” (Kose et al. 2009, 10). In Europe, the internal market program was met with strong approval by the neoliberal camp. It is reasonable to assume that with the single market, Europe made the political turnaround that the Anglo-Saxon world had already accomplished with Thatcher and Reagan.Be that as it may, the commodification of labor, land, and above all money changed the rules of the game.1 To remain within the context of monetary relations: Open financial markets transformed the European Monetary System (EMS) into an arrangement that came close to what McKinnon (1988) had defined as the “gold standard without gold.” Although the EMS was intended as a symmetrical arrangement, under the conditions of open financial markets the most hard-nosed national central bank, the Deutsche Bundesbank (DBB), assumed the role of a kind of European central bank. The monetary authorities of other European countries were forced to adapt. Recall that in autumn 1992, the conflicts that arose out of these political dependencies nearly put an end to European monetary integration. The different conditions—most European countries were in recession, while Germany was experiencing the unification boom—placed incompatible demands on monetary policy. In this conflict, the DBB acted not as a European but as a German central bank, raising interest rates to record levels. In September 1992, the system faltered. The Italian lira and the pound sterling were forced out of the exchange rate mechanism. Great Britain definitively turned its back on monetary integration, while in Italy a political earthquake shook the party-political landscape.Streeck (2014, p. 186) calls for “a new European monetary system” built on Keynes’s model of fixed but adjustable exchange rates. Now, Keynes was well aware of the fact that systems such as the Bretton Woods System (or the original EMS) are incompatible with transnational financial markets.2 They can function only as long as capital movements are politically controlled. The internal market program destroyed these conditions.Fatally, the Maastricht Treaty did not pursue the goal of reducing political interdependencies but was limited to replacing asymmetry with the all-encompassing dependence on a supranational, technocratic institution that is apparently separate from the political sphere. The German economist Horst Sievert (1993, p. 18) exposed the core idea of the EMU when he remarked, “What is decisive, is that in the monetary union the individual state must pay its debts with money that it cannot produce itself.”3 In the European type of monetary union, not the political authorities but technocrats and private financial institutions control the currency in which public debt is denominated. While in countries with their own currencies the government can turn to its central bank in a time of need, in the EMU, as we have seen in the case of Greece, state bankruptcy becomes a real threat.The financial and economic crisis has revealed the utopian character of the idea of imposing discipline through markets. To touch on just two aspects: (1) Since then, the socioeconomic heterogeneity between the countries has found new forms of expression. By creating long-term interest rate differentials, the crisis has spatially divided what was conceived as a single European capital market. Paradoxically, those countries most dependent on cheap credit are penalized by less favorable financing conditions. (2) If the demand for money and credit is insufficient, efforts to keep the money supply scarce lose their purpose. Neither the Public Sector Purchase Program (PSPP) adopted in 2015 nor the Pandemic Emergency Purchase Program (PEPP) can be derived from theoretical principles based on the commodity fiction of money. The coronavirus crisis is, as Peter Bofinger (2020) suggests, “the hour of Modern Monetary Theory”—an approach that until recently was marginalized by mainstream economics because it regards money not as a commodity but as a means of payment.To overcome the crisis of European integration, two alternatives are usually proposed: deepening integration, “an ever closer union,” or downscaling of integration, defending democracy on the nation-state level. More than seven decades ago, Polanyi already envisaged a third possibility: political cooperation between self-determining nations. Polanyi was in favor of (a) the international division of labor and (b) the liberty of the individual countries “to organize national life at will” (Polanyi 2001, 262). He was (c) aware that both could be achieved only if the commodification of labor, money, and land was restricted. His ideas were indeed aimed at politically controlled regional cooperation between countries that would maintain and develop their particular characteristics. In the final chapter of TGT, he highlighted:The link between the removal of the fictitious commodities from the market and the emergence of a variety of new societies is the crucial point. In another well-known essay published shortly after TGT, Polanyi outlined his idea of a global economic order by contrasting his concept of “regional planning” with that of “universal capitalism” (Polanyi 2018b). For Polanyi, a variety of human societies was not only a fact but also a normative value. It must suffice here to recall his last project, the magazine Co-Existence, which explicitly aimed at the strengthening of peaceful international cooperation.4From this perspective, the debate on the ECB cannot be limited to questions of Outright Monetary Transactions, negative interest rates, state financing, and price stability. The question of how the monetary authorities of a heterogeneous European Union can and should act has to go back to the root problem, the commodification of money. To bring Polanyi’s ideas to Frankfurt would mean at least:However, from the point of view of the commodity fiction, the erosion of the predominance of formal legal rules in the mid-1980s, the emergence of the “regulatory state,” the turn toward governance, and finally the spread of “executive managerialism” (Joerges and Weimer 2013) since the financial crisis appear as a series of functionally necessary adjustments to an originally incomplete regime. As long as this vision prevails, the tensions between increasingly technocratic rule and democratic control are likely to persist. In the light of Europe’s ever-growing diversity, a fundamental redesign of the project, including a reconceptualization of European law that overcomes the fiction of an apolitical integration process, is necessary and, indeed, overdue. Polanyi’s analysis can provide the economic and sociological premises for such an endeavor. However, his writings also show that, especially in the twentieth century, social transformations that would have been necessary proved impossible to implement. We should be prepared; the possibility of some kind of “fundamental shock” to the integration project cannot be ruled out.Claus Thomasberger is a sociologist and economist whose main fields of research are political philosophy, history of economic thought, international political economy, European integration and social ecological transformation. Until 2017, he was Professor of Economics and Foreign Economic Policy at the Berlin University of Applied Sciences. He has been a visiting Professor at the University of Knoxville, the Duke University, and the Vienna University of Economics and Business. He is a member of the Board of the Institute for Ecological Economy Research, Berlin, the International Karl Polanyi Society, Vienna, and of the Executive Committee of the Karl Polanyi Institute of Political Economy, Montreal. Among his publications are: Chronik der großen Transformation, Artikel und Aufsätze von Karl Polanyi 1920-1947 (3 vol.) (with M. Cangiani and K. Polanyi Levitt), 2002-2005; Der neoliberale Marktdiskurs (with W. Ötsch), 2009; Das neoliberale Credo, 2012; Auf der Suche nach dem Ökonomischen (with R. Lucas and R. Pfriem), 2018; Karl Polanyi’s Vision of a Socialist Transformation (with M. Brie), 2018; Karl Polanyi. Economy and Society. Selected Writings (with M. Cangiani), 2018.
Publisher: University of California Press

The Contemporary Relevance of Karl Polanyi to Critical Social Enterprise Scholarship - Roy, Michael J.; Grant, Suzanne (Journal of Social Entrepreneurship, 2020)
The importance of the work of Karl Polanyi to social enterprise scholarship is often maintained. However, explanations as to how and why his ideas are so relevant to the field are still relatively scarce. In this essay, we argue that engaging with Polanyi’s work directly, and Polanyian scholarship more widely, can provide a deep understanding of the underlying assumptions within current social enterprise conceptualizations, and provide insights into how the relative positioning of market and society may be manipulated to maintain hegemonic positions. Three of Polanyi’s key concepts are considered and discussed in turn: the ‘substantive economy’, the notion of ‘embeddedness’, and his ‘double movement’ thesis. The contemporary relevance of each concept, and the implications for future research, are presented and discussed, with a view to providing a platform from which to pursue a reinvigorated, emancipatory critical research agenda.
Publisher: Routledge _eprint: https://doi.org/10.1080/19420676.2019.1621363
Keywords: Polanyi; Social enterprise; critical research; critical social enterprise scholarship; double movement; economic sociology; embeddedness; social business; social enterprise; social innovation; substantive economy

Embedding the atom: Pro-neoliberal activism, Polanyi, and sites of acceptance in American uranium communities - Malin, Stephanie A.; Alexis-Martin, Becky (The Extractive Industries and Society, 2020)
In North America, uranium workers are fighting for their right to participate in a free-market system that provides them with small personal benefits. These workers experience powerlessness, instability, and unpredictability – or social dislocation – by living amidst capitalism’s polluted ecosystems, unstable economies, and disintegrating communities. However, they feel reliant on uranium for their livelihoods and strongly support the industry’s renewal and form sites of acceptance to support industry renewal. Here, we explore the phenomenon of pro-neoliberal activism emerging in communities that identify with uranium markets and that trust in corporate self-regulation, private transparency, and the perceived benefits of potential economic development. Polanyian theory helps us analyze these curious socio-environmental outcomes. While social movements might be ‘progressive,’ ‘regressive,’ or otherwise diverge, Polanyi consistently characterized double movement activists as protecting communities and ecosystems from unstable, self-regulating market systems. But here we see something different and ask: First, how does pro-neoliberal activism contribute to the embedding and institutionalization of neoliberal regimes in uranium mining communities? Second, what structural mechanisms precede and help to facilitate socio-cultural support for free markets and corporate self-regulation, as opposed to support for re-embedding markets in local, public social protections for the US uranium industry?
Keywords: double movement; environmental justice; pro-neoliberal activism; uranium

Karl Polanyi and substantivism in economic development - Rodrigues, Waldecy; Santos, Nayara Silva Dos (Brazilian Journal of Political Economy, 2020)
ABSTRACT A reading of Karl Polanyi’s work gives us a broader and more plural view of the development process beyond the exclusively economic dimension. This scientific text aims to recover the theoretical contribution of Karl Polanyi and its contribution to the understanding of the development process from a plural and substantive conception of economy. The key lesson learned in this research is that regardless of a country’s economic system, one should pay attention to the existing institutional variety and complexity of its cultural and social mosaic. True development will only be achieved if it is structured with effective public policies in order to promote this heterogeneity to the maximum possible social welfare.
Publisher: Centro de Economia Política
Keywords: Economic development; Karl Polanyi; plural economy

On the Nature of the Countermovement: A Response to Stuart et al.’s ‘Climate Change and the Polanyian Countermovement: Carbon Markets or Degrowth?’ - Carton, Wim (New Political Economy, 2020)
In a recent article for this journal, Stuart, D., Gunderson, R., and Petersen, B. [(2017). Climate change and the Polanyian counter-movement: carbon markets or degrowth? New political economy, 1–14. doi:10.1080/13563467.2017.1417364] discuss solutions to climate change in terms of Karl Polanyi’s concept of the double movement. They set up their argument as a critique of my own article on the topic to make the point that carbon markets do not constitute a genuine form of such countermovement. I’m sympathetic to the critique of carbon markets that the authors present, as well as their discussion of degrowth, which mirrors a by now extensive literature demonstrating the pitfalls respectively the necessity of these diametrically opposed approaches to the current socioecological crisis. However, in setting up their case the authors provide an overly optimistic reading of Polanyi that I believe misses a crucial part of his argument, a reading that at least partly explains our differences in opinion. This commentary offers a friendly critique of Stuart et al.’s use of Polanyi and clarifies the argument in my previous text that the authors take issue with.
Political Science; Environmental Studies
Keywords: Polanyi; carbon markets; climate change; commodification; countermovement

Polanyi, Callon, and Amazon: Institutionalist, ANT, and DRAN Approaches to Platform Economies - Caliskan, Koray (Sociologica, 2020)
Drawing on a detailed analysis of Grabher and König’s study of platformization (Grabher & König, 2020), this essay develops a revision of Actor-Network Theory by proposing how a Device, Representation, Actor and Network or a DRAN Approach can be more helpful in making sense of platform economic processes. First, it locates the ways in which Grabher & König’s article approach platforms from an updated Polanyian perspective. Second, it elaborates on how the aforementioned article critiques static Polanyian perspectives while at the same time building a double tension by a) not being clear whether we observe "the platform economy" as an object or platform economization as a process, and b) not paying sufficient attention to how platforms that draw on intangible materialities move beyond being mere marketization relations. Third, it presents how to address these tensions by drawing on novel theoretical advances of DRAN Approaches and fresh empirical research concerning platform economies, located at the intersection between computer science and social sciences. Proposing a possibility to integrate historical and contemporary studies of economic processes, the essay ends by elaborating on how Grabher & König’s article has a potential to enable a multi-perspective dynamic research strategy in making sense of not only the contemporary working of platforms, but their historical and socio-technical condition of possibility.
Sociology
Keywords: CALLON; Michel; Platform economy; Polanyi; actor-network theory; platform

State Formation, Habitus, and National Character: Elias, Bourdieu, Polanyi, and Gellner and the Case of Asylum Seekers in Ireland - Loyal, Steven; Quilley, Stephen (Historical Social Research, 2020)
Synthesizing material derived from Norbert Elias, Pierre Bourdieu, Karl Polanyi, Max Weber, Benedict Anderson and Ernest Gellner, in Part I the concept of “national character” is delineated as a special case of “habitus” relating to the socio-spatial scale of the nation state. In relation to problems of state-formation, national character is shown to be a figurational and co-developmental function of the system of nation-states in which patterns of mutual identification and “imagined community” involve both the coercive codification and internalization of particular national narratives and origin myths which define “people like us” in terms of a symbolic family; and also, in relation to competing nation-states, the projection and internalization of national group charisma and shame. In Part II, these ideas are applied to the pattern of state formation in Ireland and the recent history of the reception, cultural accommodation, and treatment of asylum seekers.
Keywords: BOURDIEU; Pierre; 1930-2002; ELIAS; Norbert; Ireland; Irishman; Kultur; Sozialpsychologie; Staatenbildung; culture; figuration; habits; habitus; nation; national identity; national stereotype; nationale Identität; nationales Stereotyp; social psychology; state formation

The Moral Economy of the Capitalist Crowd: Utopianism, the Reality of Society, and the Market as a Morally Instituted Process in Karl Polanyi’s The Great Transformation - Somers, Margaret R. (Humanity: An International Journal of Human Rights, Humanitarianism, and Development, 2020)
In an age of egregious inequality and rising authoritarian, many call for a new “moral economy” and turn to Karl Polanyi’s The Great Transformation for inspiration. Yet Polanyi’s great insight is that those who cannot reckon with the moral economy of “market justice”—the claim that market outcomes, however unequal, are morally just—fail to understand the power of capitalism. Justified by its original claim to rest on natural science, market justice laid the predicate for democracy as mortal threat. Polanyi reveals market justice as based not on natural law but on predistributive political power, and builds his democratic socialist vision on the “reality of society.”
Political Science
Keywords: market justice; moral economy

Economy–society tensions in the Eurozone: the "anti-democratic virus" revived - Markantonatou, Maria (Capitalism in Transformation, 2019)
This chapter draws on Polanyi’s analysis of the economy-democracy tension to discuss today’s crisis in Greece and the Eurozone. First, some of the economic and social effects of the Greek austerity programme are discussed with reference to his observations on liberal international interventionism in the interwar period. Secondly, the chapter looks at the ways in which democratic outcomes (elections, referenda, parliamentarian decisions, etc.) in Greece and elsewhere were, during different crisis episodes following 2010, put aside in favour of market discipline and austerity doctrines. It is argued that Polanyi’s thesis on the “mutual incompatibility” between capitalism and democracy (the core of what he termed the “anti-democratic virus”) is crucial for understanding today’s crisis and crisis management in the framework of Eurozone’s liberalism.
Political Science
Keywords: Eurozone crisis; Greece; fascist virus

Karl Polanyi and the Global Network Inspired by His Work - Mendell, Marguerite; Aulenbacher, Brigitte; Novy, Andreas (Österreichische Zeitschrift für Soziologie, 2019)
Sociology

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare

Embeddedness, Redistribution and Double Dependence: Polányi-reception Reconsidered - Lengyel, György (Intersections. East European Journal of Society and Politics, 2016)
This article – a modified version of a lecture – is a contribution to the reception of Polányi in the West and the East, more precisely, to the inquiry about what impact Polányi’s views have had on American and Hungarian economic sociology, which are the contact points between the two, and what research perspectives they offer. It concentrates on the perception of embeddedness and redistribution, not touching on other views unless they are conducive to the comprehension of certain connections. Polányi’s oeuvre is so rich and it has inspired such a wide range of debates that a conclusive review is impossible within a single article. It is hoped however that the polemic on the concept of embeddedness may be illuminating and also the aftermath of the forms of integration, particularly redistribution, important. The concept of double dependence is touched upon as well, for it grasps an essential feature of the post-socialist Eastern European economies. It is worth mentioning it in this context, for Polányi’s influence left its mark upon it and it is also related to the conceptual apparatus of the substantive view.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: Polányi; dependent market economy; double dependenc; embeddedness; fictitious commodities; forms of integration; post-socialist transformation; redistribution; state socialism; varieties of capitalism

Sustaining Democracy in an Era of Free Markets: Karl Polanyi’s Perspectives on the Politics of Finance - Scheiring, Gábor (Intersections. East European Journal of Society and Politics, 2016)
With the contemporary crisis of liberal democracy and the rise of illiberalism in the aftermath of the global financial crisis we need a theoretical framework that links modernization, crises and the fate of democracy. In my paper I attempt to show that Polanyi’s thinking represents such a framework. I focus on Polanyi’s historically informed political economic analysis of the tensions between liberal finance and liberal democracy. In the first section I reconstruct Polanyi’s political stance regarding democracy, socialism and the market. Based on this I will bring to the fore his often neglected views regarding the commodification of money and the tensions between international finance and democracy. Polanyi shows that monetary policy is not a technical but a deeply political question with major social implications. In the final section of my paper I conclude that Polanyi’s theory of the double movement and fictitious commodification can only be understood once we strip it of its excessive functionalism and bring it into dialogue with his political views. Polanyi urges to preserve the market by protecting the economy and society from the damages of excessive commodification: markets need to be protected from themselves.
Sociology; Economics
Keywords: Polanyi; democracy; double movement; fictitious commodities; finance

An Evaluation of Institutional Matrices Theory Which Was Designed to Illustrate Differences Between Russian and Western Political Economies - Hayden, F. Gregory (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
This article is devoted to the evaluation of the institutional matrices theory (IMT), which was designed to illustrate the differences between Russian and Western political economic systems. IMT has no matrix, and it is an ideological declaration rather than a theory. It is a set of assertions and assumptions that are adopted without evidence, and then hypostatized to be Russian and Western socioeconomic systems. IMT literature claims to utilize the reciprocity, redistribution, and exchange model of Karl Polanyi (1944, 1957). However, IMT suffers from a number of assumptive and methodological problems in its application, the first of which consists of the complete exclusion of reciprocity from consideration. The first section of the article is an explanation of problems with IMT, and the second section demonstrates some particulars of the IMT problems with a real-world social fabric matrix from a Western nation.
Economics
Keywords: Russia; economic policy; economics; institutional economics; institutional matrices theory; social fabric matrix; socioeconomics

Risk Markets and the Landscape of Social Change - Breger Bush, Sasha (International Journal of Political Economy, 2016)
With the critical derivatives and financialization literatures as background, I argue in this essay that risk markets (i.e., derivatives and insurance markets) play an integral role in insulating global neoliberalism from popular and elite demands for reform, as well as from the related imposition of new forms of government intervention. Inspired by Polanyi’s “double movement” and Bryan and Rafferty’s (2006) notion of “blending” in derivatives markets, the argument rests upon the insight that risk markets transform social risk into individual cost, resulting in potentially large but subtle implications for global prospects for social change. After providing a taxonomy of risk instruments that emphasizes their growing role in managing important social risks, I describe and provide brief case studies of two pathways through which risk markets help to protect the neoliberal order from political threats. The first involves the political positioning of insurance and derivatives instruments and markets as “solutions” to global social problems. The second involves the manner in which insurance and derivatives products generate “political moral hazards” that discourage support for new kinds of global policies and structures. As such, this essay contributes to the growing body of critical political economy literature on financialization, financial innovation, and derivatives and insurance markets.
Political Science
Keywords: Polanyi; derivative securities; derivatives; finance; financialization; innovation; insurance; insurance exchanges; neoliberalism; social change

'Freedom in a Complex Society': The Relevance of Karl Polanyi's Political Philosophy in the Neoliberal Age - Cangiani, Michele (International Journal of Political Economy, 2012)
Karl Polanyi's demanding vision of freedom and democracy seems far from the reality of our times and current ideologies. However, a deeper analysis reveals the ability of his political philosophy not only to find a solution of the paradox of liberty in spite of social constraints, indeed through social institutions, but also to answer the most important practical question with which we are confronted: that of improving, as Polanyi says, "our chances of survival." The conception synthetically expounded in the last pages of The Great Transformation can be better clarified through some of Polanyi's recently published manuscripts of the interwar period. A reference is also to be made to Karl Marx in the first place but also to other more recent authors.
History; Political Science
Keywords: capitalist systems; elections; freedom in a complex society; history of economic thought; legislatures; lobbying; political philosophy; political processes; rent-seeking; voting behavior

The Belief in Economic Determinism, Neoliberalism, and the Significance of Polanyi's Contribution in the Twenty-First Century - Thomasberger, Claus (International Journal of Political Economy, 2012)
How can we explain why Karl Polanyi's book The Great Transformation is more relevant today than ever before? The central thesis of the paper is that Polanyi's analysis is groundbreaking because it goes far beyond the interpretation of the civilization of the nineteenth century. By focusing on the "belief of economic determinism," Polanyi challenges the juxtaposition of being and thinking, of material life-process and consciousness. He rejects the assumption that society encompasses a world of objective facts independent of theoretical beliefs and visions. Polanyi's work is of utmost importance today because by anticipating a change in approach such as the liberal authors made, from the opposite point of view, during the interwar period, he offers the key not only to the analysis of the market mechanism, but also to a critical understanding of neoliberalism.
Economics; Philosophy
Keywords: Austrian school; Austrian school of economics; Great Transformation; The (Book); Keynesian economics; Marxist philosophy; POLANYI; Karl; 1886-1964; belief & doubt - social aspects; central economic planning - social aspects; double movement; economic determinism; economic history - 19th century; economic planning; economic theory; fictitious commodities; free enterprise - social aspects; history of economics - 20th century; human behavior - economic aspects; laissez-faire; neoliberalism; neoliberalism - social aspects; self-fulfilling prophecy; socioeconomics; utopias - economic aspects

'Planning for Freedom': Hayekian and Polanyian Policies in Latin America - Valderrama, Paula (International Journal of Political Economy, 2012)
In the first part of the paper, the concepts of "planning for freedom" by Friedrich Hayek and Karl Polanyi are compared. Hayek rejects "central planning" and also all kinds of "planning for specific aims," but he defends the principle of "planning for competition" as the main condition of a free society. This principle includes the provision of a pertinent institutional framework and state intervention to create markets in spheres of society previously ruled by nonmarket principles. Polanyi agrees that "planning" is necessary in order to achieve freedom in a complex society, but he criticizes the liberal understanding of freedom as a vain "illusion" and considers the principle of "planning for competition" a political ideal that endangers the cohesion of societies. The starting point of Polanyi's argumentation is Karl Marx's theory of reification, but he goes beyond this, complementing it with the concept of "social freedom" based on knowledge and responsibility. Considering the Latin American experience in recent decades, the paper compares Hayekian and Polanyian concepts of "planning for freedom" in their real political and social dimensions.
Philosophy; Political Science
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Latin America; capitalist systems: planning; coordination; and reform; formal and informal sectors; freedom; history of economic thought: individuals; institutional arrangements; planning models; planning policy; political processes: rent-seeking; lobbying; elections; legislatures; and voting behavior; shadow economy